Anonim şirketin haklı sebeple feshinde haklı sebep teşkil edebilecek durumlar - Sunay Ece, Defne (Dokuz Eylül Üniversitesi, 2025)
6102 sayılı Türk Ticaret Kanunu m. 531'de anonim şirketin özel sona erme hallerinden biri olarak haklı sebeplerle fesih düzenlenmiştir. Bu düzenleme ile 6762 sayılı Türk Ticaret Kanunu döneminde anonim şirketin haklı sebeple feshinin mümkün olup olmadığı yönündeki tartışmalar sona ermiş ve anonim şirketin haklı sebeple feshi kurumu hukukumuza kazandırılmıştır. Anonim şirketin haklı sebeple feshi, haklı sebeplerin varlığı durumunda, sermayenin en az onda birini ve halka açık şirketlerde yirmide birini temsil eden pay sahipleri tarafından istenebilir. Anonim şirketin haklı sebeple feshi davası şirket merkezinin bulunduğu yer asliye ticaret mahkemesinde açılır. Kanunda anonim şirketin haklı sebeple feshinde haklı sebep kavramı tanımlanmamış ve haklı sebep teşkil edebilecek durumlara örnek gösterilmemiştir. Kanun gerekçesinde bu kavramın niteliklerinin gösterilmesinin ve tanımlanmasının yargı kararları ve doktrine bırakıldığı belirtilmiştir. İleri sürülen sebeplerin haklı sebep olarak kabul edilip edilmemesi mahkemenin takdirindedir. Yargılama sonucunda mahkemenin şirketin feshine, davacı pay sahiplerinin paylarının değerinin ödenerek şirketten çıkarılmasına veya uygun düşen ve kabul edilebilir diğer bir çözüme karar verme yetkisi bulunmaktadır. Çalışmamız kapsamında anonim şirketin haklı sebeple feshinde haklı sebep teşkil edebilecek durumlar incelenmiştir. Bu inceleme yapılırken kanun metni ve gerekçesi, doktrinde ileri sürülen görüşler ve yargı kararları ile çalışmamız desteklenmiştir. Article 531 of the Turkish Commercial Code No. 6102 regulates the dissolution of a joint stock company for just cause as one of its special grounds for termination. With the introduction of this provision, the debates regarding whether the dissolution of a joint stock company for just cause was possible under the period of the Turkish Commercial Code No. 6762 have been resolved, and the institution of dissolution of a joint stock company for just cause has been incorporated into our legal system. The dissolution of a joint stock company for just cause may be requested by shareholders representing at least one-tenth of the capital, or one-twentieth in publicly traded companies, in the presence of just causes. The lawsuit for the dissolution of a joint stock company for just cause is filed in the commercial court where the company's head office is located. The law does not define the concept of "just cause" in the context of the dissolution of a joint stock company, nor does it provide examples of situations that might constitute just cause. According to the legislative intent, the determination and definition of the characteristics of this concept are left to judicial decisions and legal doctrine. Whether the reasons presented are accepted as just cause is at the discretion of the court. Following the trial, the court has the authority to decide on the dissolution of the company, the payment of the value of the shares to the plaintiff shareholders in exchange for their exit from the company, or another suitable and acceptable solution. This study examines situations that may constitute just cause for the dissolution of a joint stock company for just cause. In this analysis, the text and rationale of the law, views expressed in legal doctrine and judicial decisions have been taken into account.
914518
Keywords: Commercial Law; Corporate law; Dissolution; Joint Stock Company; Just Cause

Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimatın e-memnuniyet, e-sadakat ve ödeme isteği üzerine etkisi: Tüketicilere yönelik karma yöntem uygulaması - Teki̇n, Makber (Akdeniz Üniversitesi, 2025)
Dijitalleşmenin hız kazandığı ve tüketici davranışlarının dönüşüme uğradığı günümüz e-ticaret ortamında, özellikle Covid-19 pandemisi sonrası çevrimiçi alışverişin yaygınlaşması sürdürülebilir lojistik uygulamalarının önemini artırmıştır. Artan sipariş hacmi, çevresel etkiler, karbon salımı ve teslimat sürelerine ilişkin beklentiler; daha verimli, esnek ve çevre dostu teslimat çözümlerine olan ihtiyacı gündeme getirmiştir. Bu bağlamda ev dışında teslimat gibi alternatif lojistik hizmetler ile sosyal, çevresel ve ekonomik sürdürülebilirlik yaklaşımları, tüketici davranışlarını etkileme potansiyeli taşıyan önemli değişkenler olarak öne çıkmaktadır. Bu doğrultuda tezin amacı, sürdürülebilir tedarik zinciri uygulamaları ile ev dışında teslimat modellerinin, e-memnuniyet, e-sadakat ve ödeme isteği üzerindeki etkilerini tüketiciler üzerinden incelemektir. Araştırma, açıklayıcı sıralı karma yöntem stratejisi ile yürütülmüştür. İlk aşamada 300'ü aşkın tüketiciden anket yoluyla nicel veriler toplanmış, ardından ikinci aşamada 27 katılımcı ile yapılan yarı yapılandırılmış görüşmeler aracılığıyla nitel veriler elde edilmiştir. Nicel veriler yapısal eşitlik modellemesiyle, nitel veriler ise tematik analiz yöntemiyle değerlendirilmiştir. Bulgular, özellikle sosyal ve çevresel sürdürülebilirlik boyutlarının e-memnuniyet üzerinde ve ekonomik ve çevresel sürdürülebilirlik boyutlarının ise e-sadakat üzerinde anlamlı etkiler yarattığı yönündedir. Sürdürülebilirliğin üç boyutu da ödeme istekliliği üzerinde anlamlı ve pozitif bir etki yaratmamıştır. Ekonomik sürdürülebilirlik boyutu ise tüketiciler tarafından doğrudan algılanamadığı için memnuniyet üzerinde anlamlı bir etki göstermemiştir. Ev dışında teslimat uygulamalarının esneklik, zaman tasarrufu ve erişilebilirlik gibi avantajlar sunarak e-memnuniyeti ve ödeme isteğini artırdığını göstermektedir. Son olarak e-memnuniyetin, e-sadakati ve e-sadakatin, ödeme isteğini pozitif yönde anlamlı etkilediği sonucuna ulaşılmıştır. Bu tez, sürdürülebilir tedarik zinciri yönetimi, ev dışında teslimat ve e-ticarette tüketici memnuniyeti, tüketici sadakati ve ödeme isteğini bütüncül biçimde ele alan özgün bir model sunmaktadır. Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimat hizmetlerinin tüketici davranışları üzerindeki etkilerini açıklamak amacıyla Sosyal Kimlik Teorisi (SIT), Yeşil Tüketici Davranışı Yaklaşımı ve destekleyici olarak Yeniliğin Yayılımı Teorisi (YYT) çerçevesinde şekillenen kuramsal yapı, sürdürülebilir uygulamaların tüketicilerdeki karşılığını açıklamaya yardımcı olmuştur. Ayrıca bu çalışma, Türkiye örneğinde sürdürülebilir teslimat hizmetlerine yönelik farkındalık düzeyini ve bu hizmetlerin e-memnuniyet, e-sadakat ve ödeme davranışları üzerindeki etkilerini analiz ederek hem akademik literatüre hem de pratik lojistik ve pazarlama stratejilerine katkı sunması beklenmektedir. In today's rapidly evolving e-commerce landscape, shaped by accelerated digitalization and shifting consumer behaviors, the widespread adoption of online shopping - particularly in the aftermath of the Covid-19 pandemic - has amplified the significance of sustainable logistics practices. Increasing order volumes, environmental impacts, carbon emissions, and heightened expectations regarding delivery times have underscored the need for more efficient, flexible, and eco-friendly delivery solutions. In this context, out-of-home delivery services and the dimensions of social, environmental, and economic sustainability have emerged as key variables with the potential to influence consumer behavior. Accordingly, the purpose of this dissertation is to examine the effects of sustainable supply chain practices and out-of-home delivery models on e-satisfaction, e-loyalty, and willingness to pay, through the lens of consumer perceptions. The research adopts an explanatory sequential mixed-methods design. In the first phase, quantitative data were collected via a survey administered to over 300 consumers; in the second phase, qualitative data were obtained through semi-structured interviews conducted with 27 participants. The quantitative data were analyzed using structural equation modeling, while the qualitative data were evaluated through thematic analysis. The findings indicate that the social and environmental dimensions of sustainability have a significant impact on e-satisfaction, while the economic and environmental dimensions significantly influence e-loyalty. None of the three dimensions of sustainability were found to have a significant and positive effect on willingness to pay. The economic dimension of sustainability did not show a significant effect on satisfaction, likely because it is not directly perceived by consumers. Out-of-home delivery practices were found to enhance e-satisfaction and willingness to pay by offering advantages such as flexibility, time savings, and accessibility. Finally, the results revealed that e-satisfaction has a positive and significant effect on e-loyalty, and e-loyalty, in turn, significantly and positively affects willingness to pay. This study aims to develop an original and integrative model that examines sustainable supply chain management, out-of-home delivery, and key consumer outcomes in e-commerce, namely e-satisfaction, e-loyalty, and willingness to pay. Grounded in the Social Identity Theory (SIT), the Green Consumer Behavior Approach, and supported by the Diffusion of Innovations Theory (DOI), the proposed theoretical framework explains how sustainable supply chain practices and out-of-home delivery services shape consumer behavior. Moreover, by investigating the level of awareness of sustainable delivery services in the Turkish context and analyzing their effects on e-satisfaction, e-loyalty, and payment behavior, this research is expected to provide significant contributions to both academic literature and practical implications for logistics and marketing strategies.
Keywords: E-commerce; E-ticaret; Ev Dışı Teslimat; Green Consumer Behavior; Karma Yöntem; Mixed Methods; Out-of-Home Delivery; Sustainable Supply Chain Practices; Sürdürülebilir Tedarik Zinciri Uygulamaları; Yeşil Tüketici Davranışı

Anonim şirketlerde imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu - Tuğçe Altintaş, Fatma (Ufuk Üniversitesi, 2025)
Serbest piyasada önemli bir işleve sahip anonim şirketlerde, şirkete yeni sermaye sağlamak veya şirketteki mevcut pay sahiplerinin kontrolü elinde tutmak amacıyla imtiyazlı paylar oluşturulur. İmtiyazlı paylar (TTK m.478) ve imtiyazlı pay sahipleri özel kurulu (TTK m.454) ile şirketteki bazı paylara, diğer paylardan farklı ve üstün haklar, koruma mekanizmaları tanınmıştır. Bu çalışma kapsamında imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu; 6102 sayılı Türk Ticaret Kanunu'ndaki (TTK) hükümler, mukayeseli hukuktaki düzenlemeler, öğreti görüşleri, Yargıtay kararları ve uygulamadaki sorunlar ele alınarak incelenmiştir. Konumuz ile ilgili tartışmalı hususlar, kanun ve yargı kararlarıyla netlik kazanması beklenen durumlar irdelenerek yeni bir bakış açısı kazandırmak amaçlanmıştır. Bu doğrultuda ''Anonim Şirketlerde İmtiyazlı Paylar ve İmtiyazlı Pay Sahipleri Özel Kurulu'' başlıklı tezimiz dört bölüm olarak hazırlanmıştır. ''İmtiyazlı Paylar'' başlıklı birinci bölümde, imtiyazlı pay kavramı, benzer kavramlar ve anonim şirketlere hakim olan ilkeler ile mukayese edilerek imtiyazlı pay ilkeleri çerçevesinde incelenmiştir. ''İmtiyazlı Pay Çeşitleri'' başlıklı ikinci bölümde, imtiyazlı pay çeşitleri incelenerek, bölümün ana omurgasını oluşturacak şekilde uygulamada en çok tartışılan hususlar olan, oy hakkında imtiyazlı paylar ve yönetim kurulunda temsil edilme hakkında imtiyazlı paylar irdelenmiştir. ''İmtiyazlı Pay Sahipleri Özel Kurulu'' başlıklı üçüncü bölümde imtiyazlı pay sahipleri özel kurulu kavramı, oluşturulma amacı, hukuki niteliği, mukayeseli hukukta imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu, imtiyazlı pay sahipleri özel kurulunun toplanma şartları, toplanma süreci, toplanmasını gerektiren kararlar ve toplanmasına gerek olmayan durumlar ele alınarak incelenmiştir. ''İmtiyazlı Pay Sahipleri Özel Kurul Kararlarının Hukuki Etkisi, İptali ve Hükümsüzlüğü'' başlıklı dördüncü bölümde ise imtiyazlı pay sahipleri özel kurulu kararlarına karşı hukuki koruma mekanizmaları incelenmiştir. In joint-stock companies, which have an important function in the free market, privileged shares are created to provide new capital to the company or to maintain the control of the existing shareholders. In the Turkish Commercial Code No. 6102, privileged shares (TTK m. 478) and the special assembly of privileged shareholders (TTK m. 454) are regulated, granting certain shares in the company different and superior rights and protection mechanisms compared to other shares. With in the scope of this study, privileged shares and the special assembly of privileged shareholders have been examined by addressing the provisions of the Turkish Commercial Code No. 6102, comparative law regulations, doctrinal views, Supreme Court decisions, and practical issues. By examining the controversial issues related to our topic and the situations expected to gain clarity through laws and judicial decisions, it is aimed to provide a new perspective. In this context, our thesis titled "Special Shares and Special Shareholders in Joint-Stock Companies" has been prepared in four sections. In the first chapter titled "Preferred Shares," the concept of preferred shares was examined within the framework of preferred share principles by comparing it with similar concepts and the principles governing joint-stock companies. In the second section titled "Types of Preferred Shares," the various types of preferred shares are examined, focusing on the most debated issues in practice, namely, preferred shares with voting rights and preferred shares with representation on the board of directors, which form the main backbone of the section. In the third section titled "Special Assembly of Preferred Shareholders," the concept of the special assembly of preferred shareholders, its purpose of establishment, legal nature, preferred shares in comparative law, and the special assembly of preferred shareholders, the conditions for convening the special assembly of preferred shareholders, the process of convening, decisions requiring a meeting , and situations where a meeting is not necessary have been examined. In the fourth section titled "Legal Effect, Annulment, and Nullity of Preferred Shareholders Special Assembly Decisions," the legal protection mechanisms against the decisions of the preferred shareholders' special assembly are examined.

Sermaye piyasası hukuku bakımından Mortgage - Aktaş, Mehmet Murat (Ankara Üniversitesi, 2024)
Türk mortgage sistemi veya mortgage menkul kıymetleştirmesi ve İpoteğe Dayalı Menkul Kıymetler-İDMK ihracı, sistemsel bütün olarak ilk kez uygulamada "Mortgage Kanunu" olarak da anılan 5582 sayılı "Konut Finansmanı Sistemine İlişkin Çeşitli Kanunlarda Değişiklik Yapılması Hakkındaki Kanun" (Konut Finansmanı Kanunu) ile 2007 yılında düzenlenmiştir. Meri'i düzenlemeler bakımından İDMK ihracı 6362 sayılı Sermaye Piyasası Kanunu (SerPK) madde 58 ve III-58.1 sayılı Varlığa ve İpoteğe Dayalı Menkul Kıymetler Tebliği (VİDMK Tebliği) ile düzenlenmiştir. Çalışmamızın amacı ve kapsamı, bünyesinde tek bir çalışmada ele alınması olanaksız sayıda hukuki düzenleme, kavram, kurum ve ilişki barındıran mortgage sistemini sermaye piyasası bakış açısıyla mevzuat tekrarlarından arındırılmış özlü tespit ve değerlendirmeleri esas alacak şekilde ele almaktır. Çalışmamızda mortgage sistemi kavramsal olarak gerçek anlamı ile ortaya konulacak ve ayrıca sistemin varlık nedeni ve özünü oluşturan sermaye piyasası unsuru olarak İDMK'ya ilişkin tespit, değerlendirme ve öneriler yer almaktadır. Mortgage ifadesi dar anlamda, Anglo-Sakson hukukunda kullanılan mortgage rehni ve mortgage teminatlı finansman alacaklarını ifade etmektedir. Mortgage terimi, sermaye ve finans piyasaları bakımından ise mortgage teminatlı alacakların İpoteğe Dayalı Menkul Kıymetler (İDMK/mortgage-backed securities-MBS) ihraç edilerek menkul kıymetleştirildiği (securitization) sistemi anlatmaktadır. Mortgage sistemi veya menkul kıymetleştirmesi ve İDMK ihracı ilk olarak Amerika Birleşik Devletleri (ABD) hukukunda uygulanmıştır. Mortgage sisteminin varlık nedeni, sermaye piyasalarından İDMK ihracı yoluyla en az maliyetle ve güvenilir bir şekilde finansman sağlanmasıdır. İDMK ihracı, mortgage (ipotek) teminatlı finansman alacaklarının, mortgage sistemi içerisinde gerçek satışa (true sale) dayalı olarak bilânço dışına çıkarılması ve menkul kıymetleştirilmesi ile gerçekleştirilmektedir. Bu nedenle İDMK, gerçek satışa dayalı bilânço dışı olarak gerçekleştirilen gerçek (geleneksel) menkul kıymetleştirme ürünü bir menkul kıymet niteliğindedir. Toplam beş bölümden oluşan Tez çalışmamızın ilk bölümünde, mortgage sistemi kavramı teknik anlamıyla değerlendirilecek, sistemin tarihi gelişim süreci ve ilişkili düzenlemeler ve niteliği olarak menkul kıymetleştirme ele alınacaktır. Çalışmamızın ikinci bölümünde, mortgage sisteminin işleyişi, sistemde kullanılan varlıklar ve safhaları, sistemin özgün terminolojisi berberinde değerlendirilecektir. Çalışmamızın üçüncü bölümünde ise mortgage sisteminde yer alan kuruluşlar gene sistemin kendine özgü kavram ve gereklilikleri dahilinde değerlendirilecektir. Çalışmamızın dördüncü bölümünde sistemin hedefi ve varlık sebebi olan İDMK tanımı türleri ve benzeri menkul kıymetler beraberinde ele alınacaktır. Çalışmamızın beşinci ve son bölümünde ise İDMK ihracı ile sağlanan sebepler ve ihracını güçleştiren sebeplere dair tespit ve önerilerimiz topluca yer alacaktır. Tezimizin sonuç kısmında ise gerçek anlamıyla uygulanması halinde ülkemizin hızlı ve sürdürülebilir bir biçimde kalkınmasını sağlayabilecek niteliği haiz bir sistem olan mortgage sistemi ve onun ürünü menkul kıymet olan İDMK'nın ihracı bakımından tespit ve çıkarımlarımız yer alacaktır. Tezimiz genel olarak Türkiye'nin finansal kurumlara, İDMK'yı, iç pazardaki ekonomik kalkınmayı hızlandırmak için sermaye piyasalarından fon sağlamak için kullanma önerisi de getirmektedir. Bu tez ile Türkiye'de finans kurumlarının MBS ihraçları için alternatif bir finansman kaynağı olarak dikkat çekilmesi de amaçlanmaktadır. Burada kamusal bir gelişme olarak ifade edilecek olursak, "Yeni Ekonomi Program", finansal derinliğin ve istikrarın sağlanması için Türkiye'deki menkul kıymetleştirmelerin (İDMK ihraçları dahildir) desteklenmesi tedbirini de içermektedir. The Turkish mortgage system, mortgage securitization, and the issuance of Mortgage-Backed Securities (MBS), collectively referred to as the "Mortgage Law," were initially regulated in 2007 by Law No. 5582, also known as the "Law on Various Amendments Regarding the Housing Finance System" (Housing Finance Law), commonly referred to as the "Mortgage Law" in practical application. In terms of secondary regulations, the issuance of MBS is governed by Article 58 of the Capital Markets Law No. 6362 (CML) and the Communiqué on Asset-Backed Securities and Mortgage-Backed Securities (ABS-MBS Communiqué). The aim and scope of this study involve a comprehensive examination of the mortgage system, which encompasses numerous legal regulations, concepts, institutions, and relationships. The focus is on providing concise assessments and evaluations, free from legal redundancies, based on the perspective of capital markets. The study conceptually presents the mortgage system in its true sense, addressing the essence and purpose of the system, particularly focusing on Mortgage-Backed Securities (MBS) as a capital market element, along with relevant findings, evaluations, and recommendations. In a narrow sense, the term "mortgage" refers to the mortgage lien and financing receivables secured by mortgages in Anglo-Saxon law. In the context of capital and financial markets, the mortgage system refers to the securitization of mortgage-backed receivables by issuing Mortgage-Backed Securities (MBS). The mortgage system, its securitization, and MBS issuance were initially implemented in the United States (US) legal framework. The raison d'être of the mortgage system lies in obtaining financing from capital markets through the issuance of MBS at minimal cost and in a reliable manner. MBS issuance involves transferring mortgage-backed financing receivables out of the balance sheet through a true sale mechanism within the mortgage system, facilitating their securitization. Therefore, MBS represents a security of a true sale-based, off-balance-sheet, and traditional nature. The thesis comprises five sections. The first section evaluates the concept of the mortgage system in technical terms, discussing its historical development, related regulations, and its nature as securitization. The second section delves into the operation of the mortgage system, the assets used, stages involved, and the system's unique terminology. The third section examines the institutions within the mortgage system, considering their specific concepts and requirements. The fourth section covers the objective of the system and the definition of MBS, its types, and similar securities. The fifth and final section consolidates our findings and recommendations regarding the reasons for MBS issuance and the challenges hindering it. In the conclusion, we highlight the potential of the mortgage system and its product, MBS, as a system capable of fostering rapid and sustainable development in Turkey when implemented in its true sense. The thesis suggests that financial institutions in Turkey consider MBS issuances as an alternative source of funding, aiming to accelerate economic development in the domestic market. Additionally, the study aligns with the "New Economic Program," which includes measures to support securitizations in Turkey, including MBS issuances, to ensure financial depth and stability.
Tez N°865004
Keywords: Capital market; Hypothèque; Menkul kıymetleştirme; Mortgage; Mortgage Backed Securities; Securtization; Sermaye Piyasası Hukuku; Sûretés; İpoteğe Dayalı Menkul Kıymetler

Milletlerarası özel hukukta iflâs - Dorken, Oğuz (Galatasaray Üniversitesi, 2024)
This study aims to provide a detailed and comprehensive legal analysis of international bankruptcy and related issues by drawing on comparative law and private international law. In this context, this thesis aims to determine the legal qualifications of the transactions that fall within the framework of international insolvency and to address the problems related to these issues in detail. This study consists of five chapters. The first chapter examines the specific aspects of insolvency in the fields of debt enforcement, procedural law, and substantive law. The main argument in this chapter is that bankruptcy law has its own normative scope. In this framework, bankruptcy law and enforcement law regulate areas that can be analytically distinguished from each other. The law of debt enforcement regulates all actions and procedures based on the state's sovereignty and power to use force. On the other hand, bankruptcy law can be characterized as a multi-layered and unique branch of substantive law that has features related to the law of obligations or commercial law, depending on the context. The first chapter begins with an etymology of the concept of insolvency across various languages. The Turkish word "iflâs" is highlighted, which comes from the Arabic word "fls" (fels), indicating a state of destitution and insolvency. In English, the term "bankruptcy" has historical origins that trace back to medieval Italy, where merchants who couldn't pay their debts had their trading benches physically broken, a practice referred to as "banca rotta." The main goal of this analysis is to emphasize that historically, insolvency has been perceived as a condition of incapacity and deficiency resulting in disgrace, even in the mildest scenarios. In terms of the severity of Roman law, penalties such as enslavement or death for bankrupt individuals illustrate how grave the offense of bankruptcy was considered. Furthermore, during the Middle Ages, those in financial distress were scorned by society. Meanwhile, with the modernization of legal systems, efforts have been made to alleviate the negative social perception of individuals who become insolvent. These efforts have led to changes in the law and the emergence of new terminologies. Over time, legal terminology across different countries has evolved. For example, in the US, the terms "debtor" and "insolvency" are now more commonly used in place of "bankrupt" and "bankruptcy" respectively, in the context of insolvency law. In line with these changes in terminology, reform efforts at both the comparative and international law levels aim to diminish the stigma attached to insolvent individuals and companies, striving to provide them with the opportunity for a fresh start within the economic order. Moving on, the first section distinguishes between the narrow and broad meanings of the concept of insolvency in comparative law and international instruments. Throughout this study, bankruptcy in its narrow sense refers specifically to procedures that involve the liquidation and distribution of a debtor's assets and/or the dissolution of their legal personality to satisfy creditors in accordance with applicable laws. In contrast, the broad sense of insolvency encompasses the debtor's objective inability to pay, the formal declaration of this predicament by a competent authority, body, or the debtor themselves, as well as all subsequent actions taken to settle claims and manage the debtor's assets. Within this expansive interpretation of insolvency, the study underscores the principle of collectivity, which is critical in administering bankruptcy procedures. Additionally, it conceptualizes bankruptcy as a wide-ranging framework, starting from liquidation in the narrowest scope and extending to include debt restructuring and non-judicial workout solutions. Furthermore, this study primarily considers insolvency law as substantive law. It supports the notion that while insolvency contains procedural elements, these are not its defining features. The focus here is on the processes associated with the initiation, execution, management, and conclusion of bankruptcy proceedings. The second chapter of the study is dedicated to the conceptual framework and theoretical perspectives of international insolvency. The term "international insolvency" refers to various situations in which a debtor may have a cross-border element—such as operating in more than one country, being domestic with creditors located abroad, being a foreign entity with domestic creditors, or having assets dispersed over multiple countries. In this section, the chapter elaborates on various theoretical approaches to the legal framework governing international insolvency. These approaches include territorialism, which is based on the principle of territoriality or locality; universalism, which advocates for consistent practices and standards in cross-border insolvencies; and the hybrid approach. Due to the practical difficulties encountered with universalism, mixed approaches have been developed, offering alternatives such as cooperative territoriality, multilateralism, contract theory, universal proceduralism, and modified universalism. The examination of these approaches, each presenting distinctive advantages and challenges, provides significant insights into the ongoing and potential resolutions for issues in international insolvency. Chapter Three outlines a general framework that defines the relationship between international insolvency and the law. In this chapter, the legal nature of international insolvency law is first explained, and a reminder is provided of the modern insolvency law approach introduced in the first chapter. Within this framework, the aim of insolvency law is to develop a collective procedural structure founded on the principles of justice that considers the interests of all parties involved. It seeks to maximize the value of the debtor's assets, minimize waste, ensure the rescue of viable businesses, and develop appropriate techniques for these purposes. The transnational aspect of bankruptcy introduces an additional layer of complexity to the existing definition and framework. Consequently, international insolvency law is evolving into a distinct system within private international law, specifically catering to transnational insolvency cases. This system often described as "sui generis" strives to fulfill the objectives of insolvency in scenarios that transcend national borders. The growing field of transnational insolvency anticipates the effective centralization of proceedings that are acknowledged and aided by foreign authorities. The goal is to maximize asset values and ensure business recovery while carefully considering the interests of all affected parties, regardless of their location. In international insolvency cases, it's important to balance the interests of creditors and debtors. Factors like nationality or foreign status, as well as the role of the state as an entity under international law, should be considered in this balance. In order to establish this balance, it is of great importance to explore harmonious and effective solutions by evaluating these interests in a holistic framework. Practices in international insolvency and comparative law have tended towards a perspective that aims to harmonize and coordinate different interests. In fact, this is the main concern of the modified universalism approach. From this perspective, the final section of the third chapter examines various legal frameworks or regimes for international insolvency. This includes a study of the ecosystem of Model Laws related to insolvency, with particular emphasis on the 1997 UNCITRAL Model Law, as well as the regulations in force within the European Union, the United States, and Latin American countries. The fourth chapter delves into international insolvency by addressing traditional concepts of international procedural law. It evaluates the criteria for international jurisdiction in insolvency proceedings, the recognition of foreign insolvency judgments, and the determination of applicable law. These topics are scrutinized using a comparative legal framework, drawing from the UNCITRAL Model Law, regulations in the U.S. and the EU, and various national laws, which the third chapter discusses. Techniques from comparative and private international law are employed to analyze these issues, which can be summarized as follows: Firstly, in the realm of international insolvency and private international law, a common challenge involves identifying the competent court for the proceedings. This issue is often resolved using the principle of the Center of Main Interests (COMI). COMI refers to the primary location of a company's or legal entity's operational activities in the context of insolvency or debt restructuring. It is typically associated with the site of the debtor's main administrative office, the place where significant operations are conducted, or the location where crucial commercial decisions are made. Additionally, the issue of forum shopping often arises in discussions of international jurisdiction and represents the second significant concern. In the context of international insolvency, 'forum shopping' is the practice where an internationally active company selects a jurisdiction that is perceived to offer the most favorable legal environment for its restructuring or insolvency processes. The company then takes steps to establish its case in the chosen jurisdiction in hopes of benefiting from its laws in the event of insolvency. The modified universalism approach argues for a legal framework where the primary insolvency proceedings are initiated in the debtor's Center of Main Interests (COMI), while ancillary proceedings may occur in other jurisdictions. Such a framework aims to curb the practice of forum shopping. Both the UNCITRAL Model Law and the EU Insolvency Regulation embrace this approach, thus promoting a more orderly and predictable system for handling cross-border insolvencies. The second issue addressed in Chapter Four is the recognition of the effect of foreign insolvency procedures. This section scrutinizes how foreign insolvency procedures interrelate with existing cross-border insolvency frameworks and evaluates the limitations imposed by such frameworks on the ability of these procedures to be recognized and enforced. Initially, the discussion focuses on how international frameworks handle the concept of a foreign procedure, beginning with standards set by the Model Law and then proceeding to the foreign insolvency procedures outlined in the EU Insolvency Regulation. The characteristics of the procedures in these two contexts are compared, and the techniques foreign courts apply to recognize, enforce, or reject them are examined. The third issue explored in the fourth chapter is the rules concerning the applicable law, with a focus on the principle of Lex fori concursus. This concept is rooted in the broader lex fori principle, a cornerstone of private international law. Under the Lex fori principle, a court typically applies its own domestic law—the law of the forum—to decide both procedural matters and, in the context of insolvency, the substantive rules governing the proceedings. This application of domestic law aligns with the state's sovereignty, as procedural law is deemed an extension of a nation's public law framework. According to the principle of Lex fori concursus, the law of the country where the insolvency proceedings are initiated typically governs the insolvency process and any related legal actions. This principle is formalized as a general rule in Article 7 of the EU Insolvency Regulation. Nevertheless, the regulation also delineates specific exceptions to this principle in subsequent provisions. These exceptions, as articulated in the EU Insolvency Regulation, include the following: (1) Third parties' rights in rem; (2) set-off; (3) reservation of title; (4) contracts relating to immoveable property; (5) payment systems and financial markets; (6) contracts of employment; (7) rights subject to registration; (8) detrimental acts of the debtor; (9) effects of insolvency proceedings on pending lawsuits or arbitral proceedings and 10) Protection of third-party purchasers. Furthermore, public policy is also recognized as an exception. It is a general principle that when foreign court proceedings are concerned, the Lex fori concursus - the law of the place where the insolvency proceedings are occurring -should be applied by the local court. The public policy exception, however, might place restrictions on this principle. This safeguard, which bars the application of foreign laws that are in conflict with the fundamental principles of the local law, enables the local court to give preference to its own laws over those of another country under specific, limited circumstances in bankruptcy cases. Nevertheless, it is important to underline that the concept of public policy does not grant countries unfettered discretion. UNCITRAL emphasizes that for the exception to the lex fori concursus to be invoked on public policy grounds, the contravention must be "manifestly" evident, leaving no room for doubt. Chapter 5 explores the specific challenges associated with international insolvency, such as the identification of the debtor's assets, the imposition of insolvency seizures, the prioritization of claims, and the annulment of detrimental transactions intended to disadvantage creditors. Furthermore, the chapter examines the procedures governing insolvency and the complexities surrounding the insolvency of multinational corporations. Among these problems, under the section titled 'Determination of the Debtor's Assets and Insolvency Seizure,' the text mentions the difficult task of monitoring and recovering assets internationally in the digital age, where goods can rapidly move across borders. Variations in practices among different countries contribute to inconsistencies in this area and exacerbate challenges in insolvency cases. International commercial activities and cross-border bankruptcies further complicate the process of tracing and recouping assets and can result in conflicts between laws. The absence of a universal legal framework, applicable across all countries, poses a significant impediment to protecting assets and maximizing their recovery in the course of insolvency proceedings. In this context, there is a pressing need to cultivate global cooperation and establish mechanisms that address critical issues such as the identification of assets, the temporary seizure of assets, and the prevention of unauthorized transfers. For instance, the use of 'freezing orders'—the authority to impose temporary restrictions on the transfer, sale, or disposal of assets under foreign jurisdictions—has proven effective in safeguarding assets. Within the European Union, Articles 19(1) and 20(1) of the EU Insolvency Regulation mandate that an EU-wide suspension of transactions automatically takes effect upon the initiation of substantive insolvency proceedings in any Member State. Another issue discussed in the fifth chapter concerns the annulment of transactions made with the intent to harm creditors, an issue commonly referred to as 'avoidance.' This term describes any actions that undermine the debtor's ability to fulfill its obligations, thus impairing the rights of creditors by devaluing the debtor's assets or rendering them unreachable for creditor claims. The UNCITRAL Model Law on Cross-Border Insolvency and the EU Insolvency Regulation both seek to offer various solutions to this problem. Nevertheless, avoidance laws can differ significantly from one country to another, where legal systems have disparate criteria for assessing the validity of such transactions. A transaction that is deemed fraudulent in one jurisdiction could be considered valid in another. The chapter also addresses "conflicts of priorities" which present analogous challenges. The matter of creditor priority in international insolvency law underscores the absence of standardized regulations and systems, consequently impeding cooperation among courts and complicating the adjudication process. Considerable variations exist in the interpretation of equitable treatment for domestic and foreign creditors during insolvency proceedings, as well as in how such equity should be guaranteed. These complexities span from determining the sequence of repayment to more granular concerns regarding the handling of various types of creditors and their respective claims. These difficulties obstruct efforts to establish a consistent and harmonized framework for international insolvency law. In international insolvency cases, the varying legal traditions, economic levels of different countries, and cultural norms that shape business and economic practices necessitate a flexible framework capable of accommodating all alternatives—judicial and extrajudicial—to manage insolvency effectively. The prevailing trend in cross border insolvency law, as reflected in internationally recognized instruments, aligns with the general evolution of insolvency and restructuring law. This trend entails examining the compatibility of evolved insolvency procedures, which offer solutions for early-stage financial distress, with the mechanisms for recognition, cooperation, and legal assistance provided by international frameworks. Moreover, the impact of these procedures' implementation within the context of such frameworks is thoroughly considered. Chapter 5 concludes with a discussion on the insolvencies of multinational corporations, which have significantly grown in complexity due to the global economic downturns experienced over the past three decades. These insolvencies have carved out a distinct and intricate niche within international insolvency law, necessitating detailed scrutiny. The collapse of such large, cross-border enterprises highlights some of the most challenging facets of insolvency cases and has a profound influence on the global economic landscape. As this area intersects with the broader issues explored earlier in the study, it stands out as a fertile ground for legal innovation and swift progression, drawing upon advancements in legal theory, comparative law practices, and international regulations. The ongoing efforts and developments in this sector are proving essential in tackling these multifaceted challenges day by day. In conclusion, this study provides a thorough examination of the foundations, distinguishing traits, and practical applications of international insolvency law, framed within comparative and private international law. Its principal aim is to enrich the legal and theoretical discourse on cross-border insolvency by meticulously investigating the multifaceted procedures of insolvency in their global context. The historical development of insolvency and its integration into modern legal systems are explored, recognizing the profound influence of international insolvency's complexities on various legal frameworks. With a particular focus on two salient issues, the study confronts challenging topics such as the recognition and interrelationship of insolvency proceedings, their alignment with collaborative mechanisms and judicial support, the expansive definition and scope of insolvency across jurisdictions, and the intricate insolvencies faced by multinational corporations.
Tez N°863799
Keywords: Insolvency; International bankruptcy; International law

Genişletilmiş toplu lisanslama - Erçal, Hi̇lal (Ankara Yıldırım Beyazıt Üniversitesi, 2024)
Teknolojik ilerlemenin bir sonucu olarak internet, telif hakkına konu fikri ürünlerin dağıtımının yapıldığı ana mecra haline gelmiştir. Dijital teknolojinin birçok yerde ve çok yönlü birçok kişi ya da kurum tarafından kullanılması, özellikle telif haklarına konu fikri ürünleri etkilemiştir. Avrupa Birliği (AB) ise Dijital Tek Pazar oluşturma stratejisi kapsamında düzenlemelerine 2019/790 sayılı Dijital Tek Pazarda Telif Hakları ve Bağlantılı Haklar Yönergesini eklemiştir. Söz konusu direktifin 8 ve 12. maddelerinde ise genişletilmiş toplu lisanslama (GTL) düzenlenmiştir. GTL özellikle kitlesel olarak dijital mecrada kullanımın yoğun olduğu müzik, işitsel-görsel, sinema vb. eserlerin teliften arındırılmış şekilde kullanılmasına olanak sağlayan bir sistemdir. Özellikle televizyon yayınlarında olduğu gibi bazı kullanımların çok miktarda eser veya telif unsuru içermesi nedeniyle, tüm hak sahipleri ile görüşülerek kullanım izinlerinin alınması dijitalleşen dünyada hem çok maliyetli hem de oldukça zahmetli ve hatta çoğu zaman imkânsız bir hal almaktadır. Fikri ürünler üzerinde hak sahibi olanların, telif haklarını kullanma yetkisini herhangi bir meslek birliğine ya da toplu hak takibi yapan bir organizasyona vermemesi, başka bir deyişle oranın bir üyesi olmaması halinde söz konusu kullanımlar için izin alınması hem kullanıcılar açısından oldukça külfetli, hem de hak sahiplerinin menfaatlerini koruma noktasında daha da büyük bir sorun teşkil etmektedir. Bunun yanında kültürel mirasın korunmasıyla yükümlü olan kurumlar açısından en önemli zorluklardan biri, telif hakkı sahiplerinin kimliklerinin belirlenmesi ve telif hakkı içeren eserlerin kullanılması için yetki ya da lisans alınması gibi telif hakkı temizliğine ilişkin süreçlerdir. Özellikle sınır ötesi online kullanımlar açısından düşünüldüğünde bu çok daha karmaşıktır. GTL düzenlemesi ile dijital çağda herhangi bir toplu hak yönetimi organizasyonuna üye olmayan eser ve bağlantılı hak sahipleri açısından da meslek birlikleri ile kullanıcılar arasında yapılan lisans sözleşmelerinin geçerli olmasını sağlayacak bir sistem öngörülmüştür. As a conclusion of technological progress, the Internet has named as the main channel where the intellectual products subject to copyright are distributed. The use of digital technology by many people or institutions in many places and in many ways has especially affected the products that are subject to copyright. On the other hand The European Union (EU), within the scope of the Digital Single Market creation strategy, has added the Digital Signal Market Directive EC 2019/790 to its regulations. Extended Collective Licensing (ECL) is regulated in 8th and 12th articles of the mentioned directive. ECL is a system that enables the copyright permisson obtained use of works such as music, audio-visual, cinema, etc., which are massively used in digital media. As some uses especially like television broadcasts include a large amount of copyright items or works, in the digitalized world, it becomes costly as well as tough and even imposibble obtaining authorisations from right-holders by negotiating with all of them. If the rightholders of the intellectual products don't give authorisation of the exercise of their rights to a collecting society in another words, ıf they are not member of this organisation, obtaining permission for such uses would be very hard and transaction costs would be very high for the users and creates a greater issue as for the protection of benefits of the right-holders. Besides that the largest copyright challenge for Cultural Heritage Instutitions is the process of identification of right holders of copyright and clearence of rights, i.e obtaining authorization of licences for use of in-copyright works. When it's considered for cross-border online uses, it is more complex. In the digital age with the regulation of ECL, a system has been predicted to ensure that the licence agreements made between collecting societies and users are valid for authors and related-right holders who are not members of any collective rights management organisations.
Tez N°892117
Keywords: Copyright; Extended Collective Licensing; Extended Effect; Genişletilmiş Etki; Genişletilmiş Toplu Lisanslama; Intellectual property; Telif Hakkı

Girişim şirketlerinin finansmanının hukuki çerçevesi - Günay, Yavuz Selim (Ankara Hacı Bayram Veli Üniversitesi, 2024)
Girişimcilik hem ülkemiz hem de dünya ekonomisi için, ekonomik gelişme sağlaması, istihdamı artırması gibi bir çok sebeple, son derece önemlidir. Girişimcilik ekosisteminde uygulanan finansman yöntemleri, sözleşmeler, hukuk kuralları gibi unsurlar dinamik ve esnek yapısı dolayısıyla geleneksel yöntem ve kurallardan ayrışmaktadır. Girişimcilerin banka kredisi gibi geleneksel finansman yöntemlerine erişememesi dolayısıyla kitle fonlaması, gölge pay, aile ve arkadaşlar, girişim sermayesi ve melek yatırımcı gibi yenilikçi finansman yöntemleri ortaya çıkmıştır. Bu finansman yöntemlerinden en yaygın ve yapısal olarak kullanılanı girişim sermayesidir. Girişim sermayesi, çeşitli fonlar ve şirketlerden toplanan kaynakların, büyüme potansiyeli gösteren ve gelecek vadeden girişim şirketlerine, pay karşılığı yatırım yapılmasını ifade etmektedir. Girişim şirketleri bakımından finansman haricinde de bir çok faydası bulunan girişim sermayesi, Türk hukukunda SPK tarafından GSYO ve GSYF yapıları altında düzenlenmiştir. Girişim sermayesi uygulamasında en çok sorun teşkil eden hususlardan biri ise girişimci ile yatırımcı ilişkileridir. Girişimci ile yatırımcı arasında hem yatırım öncesinde hem de yatırım sonrasında bilgi asimetrisinin ve menfaat farklılaşmasının söz konusu olması, girişimci ile yatırımcı arasında yönetilmesi zorunlu hale gelen bir menfaat çatışması yaratmaktadır. Bu menfaat çatışmasının olumsuz etkilerinin en aza indirilememesi ve yönetilememesi sadece girişim şirketi için değil ülke ekonomisi için de olumsuz sonuçlar doğuracaktır. Girişimci ile yatırımcı arasındaki bu menfaat çatışmasının pay devir sözleşmesi, pay sahipleri sözleşmesi, paya dönüştürülebilir borçlanma araçları gibi çeşitli sözleşmesel düzenlemelerle yönetilmesi mümkündür. Ayrıca, girişimci ile yatırımcının kendi aralarında gerçekleştirecekleri sözleşmesel kurumsal yönetim düzenlemeleri de girişimci ile yatırımcı arasındaki menfaat çatışmasının yönetilmesinde etkili olacaktır. Entrepreneurship is important for both our country and the world economy for many reasons such as providing economic development and increasing employment. Elements such as financing methods, contracts and legal rules applied in the entrepreneurship ecosystem differ from traditional methods and rules due to their dynamic and flexible structure. Since entrepreneurs cannot access traditional financing methods such as bank loans, innovative financing methods such as crowdfunding, phantom share, venture capital and angel investors have emerged. The most widely and structurally used of these financing methods is venture capital. Venture capital refers to the investment of resources collected from various funds and companies in return for shares in promising venture companies with growth potential. Venture capital, which has many benefits other than financing for venture companies, is regulated by the CMB under the structures of GSYO and GSYF in Turkish law. One of the most problematic issues in venture capital implementation is the relationship between the entrepreneur and the investor. The fact that there is information asymmetry and interest differentiation between the entrepreneur and the investor both before and after the investment creates a conflict of interest between the entrepreneur and the investor that must be managed. Failure to minimize and manage the negative effects of this conflict of interest will have negative consequences not only for the venture firm but also for the national economy. It is possible to manage this conflict of interest between the entrepreneur and the investor through various contractual arrangements such as share transfer agreements, shareholders' agreements, convertible debt instruments. In addition, contractual corporate governance arrangements between the entrepreneur and the investor will also be effective in managing the conflict of interest between the entrepreneur and the investor.

Bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta taraflar - Güngör, Tuba (Kırıkkale Üniversitesi, 2024)
Türk hukukunda, özellikle iş uyuşmazlıkları bakımından arabuluculuğun dava şartı olarak kabul edildiği tarihten bu yana, arabuluculuk kurumundan beklenen faydanın elde edilip edilmediği bir yana bırakılırsa öğreti ve uygulamada halen tartışıla gelen birçok konu bulunmaktadır. Bunlardan biri, çalışma konumuzu oluşturan bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta işçi ve işveren tarafların doğru ve tam olarak teşkilinin sağlanmasıdır. Alternatif çözüm yollarından biri olan arabuluculuğun dava şartı olarak düzenlenmesi, arabuluculuk faaliyetini yargılamanın ön şartı ve ayrılmaz bir parçası haline getirmiştir. Bu bakımdan arabuluculuk sürecinin doğru işçi veya işveren tarafla yürütülmemesi yargılamayı doğrudan etkileyecektir. İş uyuşmazlıkları bakımından işçi sıfatının belirlenmesi özellikle işçi olup olmadığı konusunda tereddüt yaşanan çalışanlar açısından önemlidir. İşveren tarafının doğru belirlenmesi ise, arabuluculuk faaliyetinin yanlış veya eksik işverenle yürütülmesinin ardından, yargılama sürecinde bu durumun tespit edilmesi halinde işveren tarafında değişiklik yapılamaması bakımından önem arz etmektedir. Arabuluculuk dava şartı olarak düzenlendiğinden, yargılama sırasında tamamlanabilmesi olanaklı değildir. Sürecin bu şekilde işlemesi ise mahkemeye erişim hakkının önünde engel teşkil edebileceği gibi, gerek iş güvencesi gerekse işçinin alacağına kavuşma noktasında hak kaybına ve mağduriyetine yol açabilecektir. In Turkish law, especially since the adoption of mediation as a condition for litigation in terms of labour disputes, there are still many issues that are still debated in the doctrine and practice, let alone whether the expected benefit of the mediation institution has been achieved. One of these issues is to ensure that the employee and employer parties are accurately and fully constituted in the mediation as a condition for litigation in terms of individual labour disputes, which is the subject of our study. The regulation of mediation as a condition of litigation, which is one of the alternative remedies, has made the mediation activity a prerequisite and an integral part of the proceedings. In this respect, failure to conduct the mediation process with the right employee or employer party will directly affect the proceedings. In terms of labour disputes, the determination of the employee party is especially important for employees who are in doubt as to whether they are employees or not. The correct determination of the employer party is important in terms of not being able to make changes on the employer side if this situation is detected during the proceedings after the mediation is carried out with the wrong or incomplete employer. Since mediation is regulated as a condition of litigation, it is not possible to complete it during the proceedings. This process may constitute an obstacle to the right of access to the court, and may lead to loss of rights and victimisation in terms of both job security and the employee's receivables.
920954
Keywords: Dava şartı arabuluculuk; Employee; Employer; Iş uyuşmazlığı; Işveren; Labour dispute; Mediation; İşçi

Anonim şirketlerde yönetim kurulu iç yönergesi - İlgün Çamli, Zehra (Kırıkkale Üniversitesi, 2024)
Anonim şirket organları, özel hukuktaki sözleşme özgürlüğünün bir sonucu olarak kendi yetki alanlarına giren konuları iç yönerge ile düzenleyebilirler. Anonim şirket yönetim kurulu da yetki alanına giren konularda iç yönerge çıkarmak suretiyle düzenleme yapabilir. Türk Ticaret Kanunu'nda yönetim kurulunun yönetim yetkisini devrettiği ve sınırlı yetkili ticari vekil ve diğer tacir yardımcıları atadığı durumlarda bu işlemleri bir iç yönerge çıkararak gerçekleştirmesi zorunlu tutulmuştur. Bununla birlikte anonim şirket yönetim kurulu iç yönergesinde iç yönerge çıkarma zorunluluğu doğuran bu iki durum dışında yetki alanına giren diğer birçok konuyu düzenleyebilir. Bu kapsamda belirli durumlarda çıkarılması zorunlu olan bu iç yönergelerin zorunlu içeriğinin dışında, iç yönergede, yönetim kurulunun görevleri, çalışma usulü, yönetim kurulu üyelerinin ve yönetim yetkisinin devredildiği kişilerin hak ve yükümlülükleri gibi birçok husus yer alabilir. Bu düzenlemelerin sınırını da ilk başta Türk Ticaret Kanunu ve diğer kanunların emredici hükümleri oluşturur. Yönetim kurulunun Türk Ticaret Kanunu'nda çizilen yetki sınırları da bu çerçevede yönetim kurulu iç yönergesinin azami içeriğini belirler. Çalışmamızın ilk bölümünde anonim şirketlerde iç yönerge terimi açıklanmaya çalışılmış, ardından yönetim kurulu iç yönergesi terimi yetki devrinden ve sınırlı yetkili ticari vekil ve diğer tacir yardımcısı atanmasından bağımsız şekilde yönetim kurulunun çıkardığı düzenleyici bir metin olarak ele alınmıştır. Çalışmamızın ikinci bölümünde anonim şirket yönetim kurulu iç yönergesinin içerebileceği düzenlemeler ve bunların iç yönergede ne şekilde düzenlenebileceği incelenmiştir. Çalışmamızın son bölümünde ise yönetim kurulunun kendi çıkardığı iç yönergeyi ihlal etmesinin sonuçları gibi iç yönergeye ilişkin diğer meseleler ele alınmıştır. The organs of a joint stock company, as a result of the freedom of contract in private law, can regulate matters within their jurisdiction through internal directives. The board of directors of a joint stock company can also regulate matters within its jurisdiction by issuing internal directives. According to the Turkish Commercial Code, it is mandatory for the board of directors to execute transactions, such as delegating management authority and appointing limited authority commercial representatives and other merchant assistants, through the issuance of an internal directive. However, beyond these two instances where issuing an internal directive is mandatory, the board of directors can regulate many other matters within its jurisdiction through an internal directive. In this context, aside from the mandatory content in specific situations, an internal directive can include many issues such as the duties of the board of directors, working procedures, and the rights and obligations of board members and those to whom management authority has been delegated. The boundaries of these regulations are primarily determined by the mandatory provisions of the Turkish Commercial Code and other laws. The authority limits outlined in the Turkish Commercial Code also define the maximum content of the board's internal directive. In the first part of our study, the term "internal directive" in joint stock companies is explained. Subsequently, the term "internal directive of the board of directors" is examined as a regulatory document issued by the board, independent of authority delegation and the appointment of limited authority commercial representatives and other merchant assistants. In the second part of our study, the potential regulations that could be included in the internal directive of the board of directors of a joint stock company and how these can be arranged within the internal directive are analyzed. In the final part of our study, other issues related to internal directives, such as the consequences of the board of directors violating its own internal directive, are discussed.
Keywords: Authority of the Board of Directors; Board of directors; Delegation of Management; Droit des sociétés commerciales; Internal Directive; Limited Authority Commercial Representative; Sınırlı Yetkili Ticari Vekil; Working Procedures of the Board of Directors; Yönetim Kurulu; Yönetim Kurulunun Yetki Alanı; Yönetim Kurulunun Çalışma Usulü; Yönetimin Devri; İç Yönerge

Pazarlamacılık sözleşmesi - Kaya, Servecan (Üniversitesi Ankara, 2024)
Ticari hayatta duyulan ihtiyaç sonucu ortaya çıkmış sözleşmelerden birisi olan pazarlamacılık sözleşmesi, sıklıkla uygulanan sözleşmelerden olması ve hizmet sözleşmesinin özel bir türü olmasına karşın farklılaştığı hususların önemi sebebiyle kanun koyucu tarafından Türk Borçlar Kanunu içerisinde hizmet sözleşmesinden ayrı olarak düzenlenmiştir. Kanuni bir tanımının da bulunmasının etkisiyle tarafları ve unsurları rahatlıkla belirlenebilir mahiyettedir. Pazarlamacılık sözleşmesi unsurları; bağımlılık, süreklilik, iş yeri dışı faaliyet alanı ve ücret olan, rızai ve tam iki tarafa borç yükleyen bir isimli sözleşmedir. Pazarlamacılık sözleşmesinin taraflarından sözleşmeye de ismini vermiş olan pazarlamacı aynı zamanda bağımlı bir tacir yardımcısıdır. Bu bağlamda pazarlamacılık sözleşmesinin benzer olduğu birçok sözleşme bulunduğu gibi pazarlamacının da benzer olduğu birçok tacir yardımcısı bulunmaktadır, ancak her ikisinin de özüne inildiğinde benzer noktalardan ziyade diğerlerinden farklı karakteristik özellikleri bulunduğu rahatlıkla anlaşılacaktır. Tarafların hakları ve yükümlülükleri genel itibariyle pazarlamacılık sözleşmesinde birbirlerine karşılık gelmektedir, sözleşme böylece taraflar arasında kurulur, sürer ve sona erer. Pazarlamacılık sözleşmesinin sona ermesinde hizmet sözleşmesine ilişkin sona erme hallerinin söz konusu olduğu gibi kendine has sona erme halleri de söz konusudur. Her sözleşmede olduğu gibi sona erme halinde bunun da meydana getireceği sonuçlar taraflar özelinde kendisini gösterir. Ticaret hukuku ve borçlar hukuku özellikleri gösteren bir sözleşme olan pazarlamacılık sözleşmesi, özellikle belirli sektörlerde sıklıkla uygulanması, uyuşmazlıklara konu olması haricinde pazarlamacının sözleşmenin diğer tarafı olan işverene bağlı olarak faaliyet göstermesi sebebiyle de iş hukuku özelliği de gösteren bir sözleşmedir. Traveling salesman, which is one of the contracts that emerged as a result of a need in commercial life, has been arranged separately from the contract of service in the Turkish Code of Obligations, due to the importance of the matters that differentiate it, although it is one of the most frequently applied contracts and it is a special type of contract of service. With the effect of having a legal definition, its parties and facts can be easily identified. Traveling salesman is a consensual and bilateral contract with its elements which are dependency, continuity, non-operational field of business and fee. Traveling salesman as one of the parties of traveling salesman contract, who has given its name to the contract, is also a dependent tradesman assistant. In this context, as there are several contracts that traveling salesman is similar to, there are several tradesman assistants that traveling salesman is similar to, but when the essence of both is examined, it will be easily understood that they have various characteristics from the others. The rights and obligations of the parties generally correspond to each other in traveling salesman, so the contract is concluded, continued and terminated between the parties. In the termination of traveling salesman, there are specific termination cases as well as the termination cases related to contract of service. As with every contract, the consequences of termination in the event of termination will manifest themselves in particular to the parties. Traveling salesman is a contract that has the characteristics of commercial law and law of obligations, and also is a contract that has labor law characteristics, especially since it is frequently applied in certain sectors, is the subject of disputes, and because the traveling salesman operates under the employer, the other party of the contract.
Tez N°871625
Keywords: Code of Obligations; Commercial traveller; Contract; Traveling salesman

Hava Kargo Taşımacılığının Ülke Refahına Etkisi: OECD Ülke Analizi - Kelek, Bura Sabiha (İstanbul Ticaret Üniversitesi, 2024)
Bu çalışmanın amacı, ülkelerin rekabet güçleri açısından oldukça önemli olan lojistik performansları ile insani gelişmişlik düzeylerinin hava kargo ve küresel rekabet faktörlerinin nasıl ilişkili olduğunu ortaya koymaktır. Bunu ifade etmek için, 29 OECD (Ekonomik İş birliği ve Gelişme Teşkilatı) ülkesinin lojistik performanslarını hava taşımacılığının kargo göstergeleri ile ilişkilendirip ve sonuçları bahsi geçen ülkelerin insani gelişmişlik düzeyine etkisi açısından yorumlamaktır. Verilerin tüm ülkeler için eşit olmasına dikkat edilmiştir. Kullanılan puanlamaların zaman serisi 2010, 2012, 2014, 2016, 2018 yıllarını kapsamaktadır. Sonuçların analizi, kullanılan verilerin SPSS ile ortaya çıkarılarak oluşan yapısal eşitlik modellemesinin (YEM) üzerinden, çalışan ve çalışmayan regresyonların belirlenip ortaya hava taşımacılığı açısından etki eden verilerin bulgusuna erişmek ve yapılan analiz ile bu verilerin göstergesi ışığında hava lojistiği performansıyla ilişkili olup olmadığını göstermeye çalışılmaktadır. Çalışmada özellikle elde edilmek istenen bulgular bahsi geçen ülkelerin gayri safi milli hasıla ile kişi başına düşen milli gelirin hava taşımacılığının doğrudan veya dolaylı yoldan hem küresel rekabete olan etkisi hem de GSYİH’ye olan katkısıdır. Çalışma da lojistik kavramı ile birlikte ülkelerin ticaretleri ele alınarak dünya üzerindeki ticari üstünlüklerine değinilmiştir. Literatür araştırması, insani açıdan yetkin ülkelerin lojistik endüstrisine bakış açıları değerlendirilmiş ve lojistik alanındaki yükselişleri ile bağlantılı kalkınmasına işaret edilmiştir. Kullanılan veriler güvenilirlik açısından Dünya Bankası’ndan alınmış ve kullanılan endeksler çalışmanın kapsamında bulunan bütün parametreler ile analiz edilmiştir. Bunun sonucunda kurulan model de hava kargo taşımacılığının dolaylı olarak küresel rekabete etkisi ile Gayri Safi Yurtiçi Hasıla’ya ve aynı zamanda insani rekabet performanslarının lojistik performans endeksi ile anlamlı bir ilişki kurduğu ortaya çıkmıştır.
Keywords: Hava Kargo; Küresel Rekabet; Lojistik Performans; Lojistik Yönetimi; Milli Gelir

Vergi ceza hukukunda muhasebe hileleri ve hukuki sonuçları - Parlak, Mehmet Ali (İstanbul Üniversitesi, 2024)
Bu çalışma, Vergi Usul Kanunu'nun 359. maddesinin (a) fıkrasının birinci bendinde düzenlenen "hesap ve muhasebe hileleri yapmak" hükmünün, suç ve cezada kanunilik ilkesini karşılayıp karşılamadığı temelinde suçun kapsamı, özellikleri, unsurları ve sonuçlarının doktrin, içtihat ve mevzuat hükümleri ışığında incelenmesini konu edinmektedir. Muhasebe hilesi geniş anlamda, işletmelerde meydana gelen değer hareketlerinin belgelendirilmesinden faaliyet sonuçlarının raporlanmasına kadar olan süreçte, işlemlerin gerçeği yansıtmayacak şekilde değiştirilmesidir. Bu itibarla muhasebe hilesi muhasebe, denetim, ticaret hukuku gibi farklı disiplinlerin inceleme alanlarına giren genel bir kavramdır. Bunun yanında vergi kaçakçılık fiili olarak vergi hukuku doktrininde de önemli bir yer tutan tartışma konusudur. Vergi hukukundaki tartışmalar, hükümdeki muhasebe hilesi kavramının tanımsız, torba suç, kaçakçılık suçlarının en geneli ve işlevsiz bir suç olup olmadığına yöneliktir. Bu tartışmaların kaynağı kanun koyucunun maddede suçun kurucu unsurlarına yer vermemesi ve herhangi bir soyut tipe dair belirleme yapmamasıdır. Bu bakımdan çalışmada farklı disiplinler bakımından muhasebe hilesinin kapsamı, yöntemleri, sebep ve sonuçları karşılaştırmalı olarak ele alınmış; tümden gelim yöntemiyle vergi hukukundaki muhasebe hilesi suçunun içeriği tespit edilmeye çalışılmıştır. Çalışmada ulaşılan sonuç; "hesap ve muhasebe hileleri yapmak" hükmünün suçu tanımlamak bakımından "belirlilik" ilkesini karşılamadığıdır. Dolayısıyla adli ve idari mercilerin subjektif değerlendirmelerinin önüne geçilmesi, hukuki kesinlik ve eşitliğin temini, hukuki güvencenin sağlanabilmesi ve normun işlerlik kazanabilmesi için bir düzenlemeye ihtiyaç duyulmaktadır. This study examines the scope, characteristics, elements and consequences of the crime in the light of doctrine, jurisprudence and legislation on the basis of whether the provision of "committing accounting and accounting fraud" regulated in the first paragraph of paragraph (a) of Article 359 of the Tax Procedure Law meets the principle of legality in crime and punishment. It is about to be examined. Accounting fraud, in broad terms, is changing transactions in a way that does not reflect reality, from the documentation of value movements in businesses to the reporting of activity results. In this respect, accounting fraud is a general concept that falls into the fields of investigation of different disciplines such as accounting, auditing and commercial law. Discussions in tax law are about whether the concept of accounting fraud in the provision is undefined, an omnibus crime, the most general of smuggling crimes, and whether it is a dysfunctional crime. The source of these discussions is that the legislator does not include the constitutive elements of the crime in the article and does not specify any abstract type. In this regard, the scope, methods, causes and consequences of accounting fraud in terms of different disciplines were discussed comparatively in the study; The content of the crime of accounting fraud in tax law has been tried to be determined by deductive method. The result reached in the study; The provision of "committing account and accounting fraud" does not meet the principle of "specificity" in terms of defining the crime. Therefore, a regulation is needed to prevent subjective evaluations of judicial and administrative authorities, to ensure legal certainty and equality, to provide legal assurance and to make the norm functional.
Tez N°857786
Keywords: Accounting; Finance; Fraud; Fraude fiscale; Maliye; Tax fraud

Arabuluculuk faaliyetinin anlaşma ile sona ermesi - Terzi̇ Kahraman, Si̇bel (Kadir Has Üniversitesi, 2024)
Arabuluculuk kurumundan beklenen avantajların ortaya çıkabilmesi arabuluculuk faaliyeti sonunda anlaşmaya varılması ile mümkündür. Mevzuatta sürekli değişiklikler meydana gelmekte ve kurumun kapsamına aldığı uyuşmazlıklar hızla genişletmektedir. Uygulamanın yerleşmesi ve zaman zaman doktrinde görüş ayrılıkları yaşanması kaçınılmazdır. Mevzuatta daha detaylı ya da değiştirilerek düzenlenmesine ihtiyaç duyulan alanlar bulunmaktadır. Tez, mevzuatta yapılan son düzenlemeleri de kapsayarak anlaşmayı tüm yönleriyle ele almayı ve kurumun daha iyi anlaşılmasına hizmet etmeyi amaçlamaktadır. Yapılan bu çalışmanın ilk bölümde arabuluculuğun kurumsal çerçevesi ortaya konulmuştur. Bu bölümde amaç arabuluculuk kurumunu ve arabuluculuk faaliyetinin işleyişini anlatabilmektir. Bu amaçla arabuluculuğun kapsamı, türleri, arabuluculuğun karşılaştırmalı hukukta ve Türk hukukunda gelişimi, yargı ve tahkimden farkı, med-arb uygulaması anlatılmıştır. İkinci bölümde sona erme halleri tek tek ele alınmış, sona erme hallerinin mevzuatta dağınık halde düzenlendiği hususuna dikkat çekilmiş ve başkaca sona erme halleri de dikkate alınarak tek bir madde halinde düzenlenebilmesi hususu önerilmiştir. Arabulucunun, faaliyeti sona erdirme yönünde inisiyatif almasının sona erme hali olarak düzenlenmesi yönünde de öneri getirilmiştir. Üçüncü bölümde anlaşmanın terminoloji sorununa ve benzer kavramlardan farkına değinilmiştir. Arabuluculuk faaliyeti sonunda varılan anlaşmanın esaslı unsurları tespit edilmiştir. Bu kapsamda, sözleşme serbestisi, şarta bağlı edim düzenlenip düzenlenemeyeceği gibi önemli hususlara yer verilmiştir. Anlaşmanın nasıl düzenleneceğine ilişkin öneride bulunulmuştur. Anlaşmanın hukuki niteliği, anlaşılan hususlara karşı dava açılamayacağı, anlaşmanın hukuka uygun düzenlenmediği takdirde karşılaşılabilecek sonuçlar anlatılmış ve anlaşmanın arabuluculuğa elverişli olmamasına rağmen düzenlenmesi, dava şartı kapsamına girmeyen bir hususta faaliyetin yürütülmesi ve anlaşmaya varılması, yanlış dava türünden yapılan başvuru sonucu anlaşmaya varılması, arabulucunun uzmanlık alanına girmeyen bir konuyla ilgili anlaşma sürecini tamamlaması, hukuka uygun arabuluculuk faaliyeti yürütülmemesi sonucunda anlaşmaya varılması, arabulucunun arabuluculuktan çekilmesi gerekirken yine de anlaşma yapması gibi anlaşmadan kaynaklı sorunlara yer verilmiştir. Dördüncü bölümde anlaşmanın yerine getirilmemesi durumunda icra edilebilirlik şerhi alınması hususu, mahkemeye başvuru, yargılama usulü, mahkemenin incelemesi, şarta bağlı olarak yapılan anlaşmaya şerh verilmesi, icra edilebilirlik şerhi alınan anlaşmanın icrası, anlaşmayla ilamlı ve ilamsız takip yapılması gibi önemli hususlar ele alınmıştır. Son olarak, arabuluculuk sonucunda elde edilen uluslararası ticari anlaşmaların icra edilmesini kolaylaştırması amacıyla hukukumuzda da kabul edilen Singapur Konvansiyonu incelenmiştir. The expected advantages of the mediation institution can be realized through reaching an agreement at the end of the mediation process. There are continuous changes in the legislation, rapidly expanding the scope of disputes covered by the institution. The thesis aims to comprehensively examine the agreement reached at the end of the mediation process, including recent legislative amendments, to better understand the institution and its operations. The first part of this study outlines the institutional framework of mediation, explaining its scope, types, development in comparative law and Turkish law, differences from judiciary and arbitration, and the practice of med-arb. The second part discusses the various termination conditions, highlighting the scattered nature of these conditions in legislation and proposing their consolidation into a single provision. It also suggests granting mediators the initiative to terminate the process as a termination condition. In the third part, attention is given to the terminology issues and distinctions from similar concepts regarding the agreement reached through mediation. The essential elements of such agreements are identified, covering issues like contractual freedom and the regulation of conditional obligations. Recommendations are made on how agreements should be drafted. The legal nature of the agreement, restrictions on litigation concerning agreed-upon matters, consequences of improperly drafted agreements, and issues arising from inappropriate mediation activities are discussed. The fourth part addresses the issue of obtaining enforceability endorsements for agreements not fulfilled, court applications, trial procedures, court reviews, endorsement of conditional agreements, enforcement of endorsed agreements, and procedures for enforcement with and without judgments. Finally, the study explores the Singapore Convention, adopted in our legal system to facilitate the enforcement of international commercial agreements resulting from mediation.
884007
Keywords: ADR; Agreement termination; Alternative dispute resolution; Anlaşmazlık; Arabuluculuk; Executability Annotation; Kanunlar 6325 sayılı; Laws 6325 numbered; Mandatory mediation; Mediation; Mediator; Médiation; Singapore Convention; Zorunlu arabuluculuk

Sermaye şirketlerinde zorunlu arabuluculuk - Ulusan, Banu (Galatasaray Üniversitesi, 2024)
Çalışma 06.12.2018 tarihinde 7155 sayılı Kanun ile Türk Ticaret Kanunu'na eklenen TTK m. 5A hükmüyle getirilmiş zorunlu arabuluculuğun, sermaye şirketleri çerçevesinde incelenmesini konu almaktadır. TTK m. 5A hükmüyle önce, ticari davalardan, konusu bir miktar paranın ödenmesi olan, alacak ve tazminat davalarının zorunlu arabuluculuğa tabi olduğu düzenlenmiştir. Daha sonra, 28.02.2023 tarihli ve 7445 sayılı Kanun ile yine ticari dava olmaları kaydıyla, menfi tespit, itirazın iptâlî ve istirdat davalarını da zorunlu arabuluculuk kapsamına almıştır. TTK lafzıyla dava şartı arabuluculuk olarak da nitelendirilen zorunlu arabuluculuk kavramı, Türk hukuku bakımından yeni bir kavram sayılabilir. İlk olarak 2017 yılında 7036 sayılı Kanun ile iş uyuşmazlıkları için düzenlenen zorunlu arabuluculuk kavramı, daha sonra ticari uyuşmazlıklar ve tüketici uyuşmazlıkları için de düzenlenmiştir ve Türk hukukunda zorunlu arabuluculuğun uygulama alanı git gide genişleme eğilimi göstermektedir. Bu sebeple, doktrinde pek çok eleştiriye de uğrayan zorunlu arabuluculuk kavramının, özellikle sermaye şirketleri bağlamında incelenmesi amaçlanmıştır. Her ne kadar Türk hukukunda yeni bir kavram olsa da, karşılaştırmalı hukukta zorunlu arabuluculuk uzun zamandan beri uygulanan ve tartışilânbir konu olagelmiştir. Karşılaştırmalı hukuk bağlamında bir inceleme yapıldığında öncelikle, özellikle zorunlu arabuluculuğun menşei sayılabilecek Amerikan hukukunda, konu özellikle doktrinde farklı açılardan ele alınmıştır. Çalışmanın birinci bölümünde bu çerçevede bir inceleme yapılmış, zorunlu arabuluculuğun tabi olması gereken kıstaslar ortaya konulmaya çalışılmıştır. Bu kıstaslar, çalışmanın ilerleyen bölümlerinde yapılacak değerlendirmeler için de önem taşımaktadır. Bunun yanı sıra zorunlu arabuluculuğun türleri ve zorunlu arabuluculuğa aykırı davranışlara bağlanan yaptırımlar üzerinde de durulmuştur. Zorunlu arabuluculuğun ve benzeri uygulamaların farklı hukuk sistemlerinde ne şekilde yer aldığı değerlendirilmiştir. Bu değerlendirmeler kapsamında Alman hukuku bakımından ZPO §278 ile EGZPO §15a incelenmiştir. İsviçre hukuku bakımından ise ZPO §197 vd. hükümleri incelenmiştir. Her iki hukuk sistemi de zorunlu arabuluculuğu düzenlememiş, bunun yerine medeni usûl kanunlarında davanın görüleceği mahkemeler nezdinde uyuşmazlık çözüm sürecini düzenlemiştir. İtalya ve Fransa'da ise zorunlu arabuluculuk uygulamaları mevcut ise de bu, Türk hukukunun aksine, son derece sınırlı bir şekilde gerçekleşmiştir. Zorunlu arabuluculuğun kaynağı olan Amerikan hukukunda ise arabuluculuk, zorunlu tutulan tek uyuşmazlık çözüm yöntemi olmamıştır. Ayrıca zorunluluk hususu kanunla değil, genellikle her bir dava için mahkemenin yönlendirmesiyle sağlanmaktadır. Tüm bu ülkelerin ortak özelliği ise ticari uyuşmazlıkları zorunlu arabuluculuğa ya hiç tabi tutmamaları ya da çok dar bir kapsamda tabi tutmalarıdır. Arabuluculuk her ne kadar bir yargılama faaliyeti olmasa da zorunlu arabuluculuk dava öncesinde yer alan bir aşama olduğundan, kanaatimizce medeni usûl hukukuna hâkim olan ilkeler bakımından da incelenmelidir. Bu kapsamda zorunlu arabuluculuğun öncelikle adil yargılanma ilkesi ve mahkemeye erişim hakkı kapsamında tartışmalara sebep olduğu görülmektedir. Bunun yanı sıra usûl ekonomisi ilkesi, aleniyet ilkesi, tasarruf ilkesi ve dürüst davranma yükümlülüğü bakımından da değerlendirmelere yer verilmiştir. Aleniyet ilkesi bağlamında arabuluculuğa hâkim olan ilkelerden gizlilik ilkesinin ticari uyuşmazlıklar bakımından bir avantaj oluşturduğu söylenebilir. Tasarruf ilkesinde yapılandeğerlendirme maddî hukuk ve usûl hukuku çerçevelerinde yapılmıştır. Ayrıca zorunlu arabuluculuğun menşei Amerikan hukukunda hâkimin ve avukatların rolleri de dikkate alınarak, zorunlu arabuluculuğun Türk hukukundaki hâkimin yargılamayı sevk ve idaresi ilkesiyle tamamen bağdaşmadığı sonucuna varılmıştır. Dürüstlük ilkesi bakımından yine maddî hukukla da bağlantı kurularak bir değerlendirme yapılmış, zorunlu arabuluculuk süreci sonunda varılacak anlaşmanın dürüstlük kuralına uygun yapılması için yeterli mekanizmaların bulunmadığı kanaatine varılmıştır. Bunun dışında HUAK m. 18A/11 hükmü uyarınca zorunlu arabuluculuk sürecinin ilk toplantısına mazeretsiz katılmayan tarafın her durumda yargılama giderlerinin tümünden sorumlu olması ve lehine vekalet ücretine hükmedilememesinin orantısız bir yaptırım olduğu, ayrıca bu sebeple hiçbir durumda yargılama giderlerinden sorumlu olmayacağını bilen tarafın, açılacak dava sürecinde davayı uzatacak veya yanlış yönlendirecek ve dürüstlük kuralına uymayacak her tür davranışı yapabileceği kanaatine varılmıştır. Çalışmanın ikinci bölümü TTK m. 5A hükmünün uygulama koşullarına yoğunlaşmaktadır. Bu kapsamda, ticari davalar bakımından karşılaştırmalı bir değerlendirme yapılmak istenmiştir. Türk hukukunda TTK m. 4 hükmüyle ayrıca düzenlenen ticari davalar, diğer hukuk sistemlerinde ticaret mahkemeleriyle ilişkili olarak düzenlenmiştir. Bu değerlendirmede dikkat çeken husus, davaların ucuz, hızlı ve etkin bir şekilde sonuçlandırılmasının amaçlandığı diğer hukuk sistemlerinde hukukçu olmayan hâkimlerin de görev yaptığıdır. Türk doktrininde ise böyle bir uygulamanın uygun olmayacağı haklı olarak belirtilmiş, bu bağlamda zorunlu arabuluculuk uygulamasının daha uygun olduğu kanaatine varılmıştır. Ticari davalarda dava şartını düzenleyen TTK m. 5A hem medeni usûl hukuku hem de ticaret hukuku bakımından incelenmiştir. Medeni usûl hukukun bakımından yapılanincelemede dava şartı kavramı ve hükmün dava türlerine göre gösterdiği özellikler incelenmiştir. Ticaret hukuku bakımından ise, arabuluculuk süreci sonucunda varılacak anlaşmanın bir maddî hukuk sözleşmesi oluşundan da yola çıkarak basiretli tacir kavramı incelenmiştir. Ayrıca zorunlu arabuluculuğun HUAK m. 5 hükmü ve gizlilik ilkesi nedeniyle göstereceği özellikler nedeniyle, ticari sırların korunması bağlamında da bir değerlendirme yapılmıştır. Çalışmanın üçüncü ve son kısmı sermaye şirketlerinde zorunlu arabuluculuğun incelenmesine ayrılmıştır. Bunun için öncelikle Alman hukukunda pay sahipleri davaları olarak adlandırilândavalar hakkında değerlendirme yapılmaya çalışılmıştır. Bu değerlendirmeyle adi şirketlerden farklı olarak pay sahipleri davalarının genel olarak ortağa değil şirket tüzel kişiliğine yöneltilmesi gerektiği, bunun yanı sıra pay sahiplerinin şirketin menfaatleri için dava haklarını kullanabildiği görülmüştür. Bu değerlendirmenin, sermaye şirketleri uyuşmazlıklarında zorunlu arabuluculuk sürecinde başvuru yapacak taraflar ve anlaşmanın etkileyeceği kişilerin tespitinde yararlı olduğu kanaatindeyiz. Bu değerlendirmenin ardından TTK m. 5A kapsamına girebilecek sermaye şirketi uyuşmazlıkları tespit edilerek, her biri için zorunlu arabuluculuğun göstereceği özelliklerin belirlenmesine çalışılmıştır. Bu belirleme yapılırken her bir uyuşmazlık konusu hakkında genel bir çerçeve sunulmuş, açılabilecek davalar hakkında bilgi verilmiş ve bu bilgiler ışığında zorunlu arabuluculuğun uygulama koşulları ile doğurabileceği sakıncalar üzerinde durulmuştur. Son olarak, yapılantüm değerlendirmeler ışığında sermaye şirketlerinde zorunlu arabuluculukla ilgili de lege ferenda görüşümüze yer verilmiştir. Bu kapsamda sermaye şirketleri uyuşmazlıklarının, dava konularının şirketler hukuku kısıtlarına ve emredici kurallara tabi olması sebebiyle, zorunlu arabuluculuğa her zaman uyumlu olmayabileceği sonucuna varılmıştır. Üstelik, bazı arabuluculuk türlerinde yapılması elzem hukuki denetimin ve arabulucunun bu denetimi yapamayacak olmasının yaratacağı sakıncalara da değinilmiştir. Bunun sonucunda İsviçre ve Almanya örneklerinde olduğu gibi mahkeme bağlantılı uyuşmazlık çözümlerinin düzenlenmesinin daha uygun olduğu kanaatine varılmıştır. İflas bakımından bir değerlendirme yapıldığında ise, İİK m. 226 hükmü nedeniyle doğabilecek sorunlara dikkat çekilmiş, bu bağlamda zorunlu arabuluculuğa başvuru kapsamında düzenleme yapılması önerilmiştir. Son olarak zorunlu arabuluculuk ile varılmak istenen amaçlar da dikkate alındığında, bu amaçlara ulaşmak için taraflara arabuluculuk dışında uyuşmazlık çözüm yollarına başvurabilmelerine imkân verilmesi gerektiği kanaatine varılmıştır. Bu şekilde hem çabuk ve ucuz bir şekilde uyuşmazlıkların çözümü amacına ulaşabilecek, hem de tarafların ihtiyaçlarına daha uygun bir yöntem seçmelerine imkân tanınacaktır. […] This study focuses on application of Turkish Commercial Code Art. 5A, which is amended with Code Nr. 7155 in 2018, to equity companies. TCC Art. 5A regulated mandatory mediation for commercial cases with monetary claims at the beginning. However, through amendment with Code Nr. 7445 in 2023, negative declaratory actions, actions for annulment of objections and actions for restitution were taken into scope of this regulation. Mandatory mediation, which can also be named mediation as cause of action according to TCC m. 5A, can be deemed as a new context in Turkish law. Regulated for the first time for some labour law conflicts with Code Nr. 7036 in 2017, mandatory mediation is regulated also for commercial conflicts as well as consumer law conflicts. Thus, it can be observed that scope of mandatory mediation in Turkish law has a tendency to spread within time. Therefore, as a concept subject to various critics, mandatory mediation is to be evaluated in context of equity companies within this study. Although mandatory mediation is considered to be a relatively new concept in Turkish law, in frame of comparative law, it has a long history of application and has been subject to critics for a long time. It is observed that in comparative law, especially in American law, which can be considered as the source, mandatory mediation has been taken into consideration with many aspects. The first chapter of this study conducts an evaluation within this frame and aims to set the criterias for a better application of mandatory mediation. These criterias are important for evaluation in following chapters of this study. In addition, the variations of mandatory mediations and sanctions applied to the acts contrary to mandatory mediations are observed. Mandatory mediation and similar applications in different law systems are also examined. Within light of this examination, ZPO §278 and EGZPO §15a in German law is taken into consideration, as well as ZPO §197 ff. in Swiss law. Both systems do not regulate mandatory mediation and instead, regulated dispute resolution process within their Civil Procedure Codes. Although mandatory mediation is regulated in Itâlîan and French law systems, these regulations have strictly limited scope. American law, the origin of mandatory mediation, applies other means of dispute resolution as well. Moreover, mandatory mediation in American law is not regulated by a code; it is court oriented in general. The common point of these countries is that none of them applies mandatory mediation within a wide scope on commercial disputes. Although mediation cannot be considered as an act of judication, since mandatory mediation is a step before courts, it should be evaluated with regard of principals of civil procedure law. In this context, it is observed that mandatory mediation gave reason to many arguments related to fair trial and access to court. In addition, evaluations on principals pf procedural economy, publicity, power of disposition and honesty are conducted. With regard of principal of publicity, it can be considered that principal of confidentiality of mediation is an advantage. The evaluations on principal of power of disposition are made in frame of substantial and procedural law. Furthermore, taking the features of American civil procedure law, it is concluded that mandatory mediation is not compatible with the role of judge in Turkish law. With regard of principal of honesty, an evaluation in the light of substantial law is also made and it is concluded that rules to maintain honesty in mandatory mediation are not sufficient in Turkish law. As an addition, it is also stated that sanction in Code of Mediation Art. 18A/11 is unproportionate in context of principal of honesty before courts. The second chapter of this study focuses on conditions of TCC Art. 5A. With this regard, a comparative evaluation on commercial actions is made. Commercial actions, regulated with TCC Art. 4 in Turkish law, are regulated in relation with commercial courts in other law systems. With this evaluation, it is noted that in commercial courts, which aims to solve disputes in a cheap, quick and effective manner, gives place to judges who have not a judicial notion in other law systems. In Turkish literature, it is rightly emphasized that such an application is not appropriate for Turkish law. TCC Art. 5A is also examined within frame of civil procedure and commercial law. Within civil procedure law frame, the concept of cause of action is examined, as well as features of TCC Art 5A in relation to claim in actions. Within commercial law frame, since the agreement concluded within mediation is a contract in context of substantial law, the notion of prudent merchant is evaluated. Furtermore, for mandatory mediation demonstrates features within light of Code of Mediation Art. 5 and principal of confidentiality, an evaluation of trade secrets are also conducted. The third and last chapter concentrates on examination of mediation as a cause of action in equity company disputes. Thus, an action named shareholders' action in German law, which is clarified using notion of actio pro socio, is evaluated. According to this evaluation it is concluded that, unlike simple partnerships, shareholders shall submit their claims against legal entity of equity companies and not against other shareholders. Neverthless, it is also observed that in some cases shareholders are entitled to submit the tools of defence of equity companies for interests of company. This evaluation is essential in order to determine the parties of dispute and the persons effected from the agreement reached at the end of mandatory mediation process. Following this evaluation, the kinds of disputes in equity companies, which fall into scope of TCC Art. 5A, are determined and the features demonstrated by them in context of mediation as a cause of action are defined. In order to comply with this evaluation, information on each subject of action is given, features of the relevant actions are explained and in the light of all evaluations, conditions of application of mediation as a cause of action are explained. Finally, in light of evaluations made within this study, our de lege ferenda opinions on mandatory mediation in equity companies are set. Within this frame, since dispute in equity companies are subject to limitations on equity company law and compulsory legal rules, it is stated that they might not always compatible with mediation as a cause of action. In addition, possible problems arisen from lack of legal supervision in mediation process are also mentioned. As a result, it is concluded that, it would be more convenient to regulate court annexed dispute resolution tools, similar with examples of Germany and Switzerland. With regard to bankruptcy proceedings, it is concluded that possible problems in relation to Turkish Code of Bankruptcy and Enforcement Art. 226 are highlighted and it is suggested that, in order to eliminate such problems, necesarry regulations by legislator should be made. Lastly, taking the goals of mediation into consideration, in order to reach these goals effectively, the importance of giving parties the opportunity to be able to choose other means of dispute resolution apart from mandatory mediation, is found to be essential. Thus, dispute resolution process will take place in a quick and cheap manner and parties will have the chance to be able to choose a dispute resolution method that suits their needs and interests.
Keywords: MARD; Mediación; Mediation; Mediação; Médiation

Arabulucu mesleki sorumluluk sigortası bir uygulama - Yildirim, Ferhat (Marmara Üniversitesi, 2024)
Riskleri bertaraf etmenin çeşitli yolları olmakla birlikte sigorta bu yöntemler içerisinde en bilinen ve tercih edilenidir. Risklerin çeşitliliği, farklı sigorta türlerinin oluşumuna neden olmaktadır. Duyulan ihtiyaçlara, mevcut risklere göre sigortanın şekillenmesi, öznelleştirilmesi mümkündür. İfa edilen meslek nedeniyle üçüncü kişilere verilecek zarardan ötürü oluşan sorumluluğun sigortacıya devrini esas alan mesleki sorumluluk sigortası da farklı sigorta türlerinden sadece bir tanesidir. Alternatif uyuşmazlık çözüm yöntemlerinden olan arabuluculuk, 2012 yılında 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu ile Türk hukuk sistemine dahil olmuştur. Kanunun yürürlüğe girdiği tarihten bu yana arabuluculuk yönteminin kullanımı hızla yaygınlaşmış ve uyuşmazlığın taraflarınca tercih görmesi, arabuluculuğu en popüler alternatif uyuşmazlık çözüm yöntemlerinden biri haline getirmiştir. Buna bağlı olarak da Türkiye'de arabulucu sayısı gün geçtikçe artış göstermeye devam etmektedir. Arabulucular siciline kayıtlı arabulucuların, arabuluculuk uygulamalarında karşı karşıya kaldıkları risklerin varlığı, yasal düzenleme dışında da bir takım koruyucu mekanizmaların devreye girmesini zaruri kılmaktadır. Özellikle mesleğin ifası esnasında meslek nedeniyle üçüncü kişilere karşı sorumluluğun doğumuna yol açan hallerin varlığında sigorta önemli bir enstrüman olarak görülmektedir. Çalışma ile İstanbul ilinde (Avrupa-Anadolu yakasında) aktif olarak faaliyet gösteren ve Arabuluculuk Daire Başkanlığı tarafından tutulan arabulucular siciline kayıtlı olan 30 arabulucu ile yapılan derinlemesine görüşme neticesinde, arabuluculuğun katılımcıların çoğunluğu tarafından meslek olarak görülmesi, mehaz olarak kabul edilen Avusturya Hukuk Uyuşmazlıklarında Arabuluculuk Federal Kanunu uygulamasında yer alan ve mesleğin ifası için ön koşul olarak sunulan arabulucu mesleki sorumluluk sigortasının Türkiye açısından ne denli uygulanabileceği ve tercih göreceği sorusunu ortaya çıkarmış ve böyle bir sigortanın tesis edilmesi durumunda arabulucuların bu sigortaya duydukları ihtiyaç ve yaklaşımları ele alınmış ve irdelenmiştir. While there are various ways to eliminate risks, insurance is the most well-known and preferred one among such methods. The diversity of risks leads to the occurrence of different types of insurance. It is possible to shape and subjectivize insurance depending on the needs and existing risks. Professional liability insurance, which is based on the transfer of liability to the insurer for damage to third parties due to the profession being performed, is just one of the different types of insurance. Mediation, one of the alternative dispute resolution methods, was introduced to the Turkish legal system in 2012 with the Law No. 6325 on Mediation in Civil Disputes. Since the date the law came into force, the use of the mediation method has become widespread rapidly and its preference by the parties to the disputes has rendered mediation one of the most popular alternative dispute resolution methods. Accordingly, the number of mediators in Türkiye continues to increase day by day. The existence of risks faced by the mediators registered with the registry of mediators in mediation practices necessitates the introduction of certain protective mechanisms in addition to the statutory provisions. Insurance is considered as an important instrument, particularly in the existence of cases that lead to the emergence of liability against third parties due to the profession while the profession is being performed. With the study, as a result of the in-depth interviews conducted with 30 mediators who are active in the province of Istanbul (European and Anatolian sides) and registered with the registry of mediators maintained by the Department of Mediation, the fact that mediation is considered as a profession by the majority of the participants reveals the question of to what extent the mediator professional liability insurance, which is included in the practice of the model law i.e., the Austrian Federal Law on Mediation in Civil Disputes and presented as a prerequisite to perform the profession, is applicable and preferable for Türkiye; and the mediators' needs and approaches to this insurance in case of creation of such insurance are discussed and analyzed in the study.
868641
Keywords: Assurance; Geçmişe etkili sigorta; Liability insurance; Mandatory mediation; Mesleki sorumluluk sigortası; Mesuliyet sigortası; Médiateur; Private insurance; Private insurances; Professional liability insurance; Recroactive insurance; Responsabilité professionnelle; Sorumluluk sigortası; Zorunlu arabuluculuk; Özel sigortacılık; Özel sigortalar

Anonim şirkette imtiyazlı pay sahipleri özel kurulu - Yilmaz, Hümeyra (İstanbul Üniversitesi, 2024)
Bu doktora tezi, 6102 sayılı Türk Ticaret Kanunu'nun 454. maddesinde düzenlenen imtiyazlı pay sahipleri özel kurulunu konu almaktadır. Çalışmanın ilk bölümünde imtiyaza ilişkin genel bilgiler verildikten sonra ikinci bölümünde imtiyazlı pay sahipleri özel kurulunun yapısı, yetkisi, hukuki niteliği üzerinde durulmuştur. Çalışmanın üçüncü ve dördüncü bölümlerinde, imtiyazlı pay sahipleri özel kurulunun toplanma şartları ile toplantı süreci kapsamlı bir şekilde ele alınmıştır. Çalışmanın son bölümünde ise imtiyazlı pay sahipleri özel kurul kararlarının hukuki niteliği, etkisi ve hükümsüzlüğü irdelenmiştir. Çalışmanın hazırlanmasında, Türk hukukundaki ilgili mevzuat hükümleri başta olmak üzere karşılaştırmalı hukuktaki dikkate değer yasal düzenlemeler, öğretideki görüşler ve yargı kararlarından faydalanılmıştır. Anahtar kelimeler: Anonim şirketler, imtiyaz, TTK m. 454, imtiyazlı pay, imtiyazlı pay sahipleri özel kurulu. This doctoral thesis deals with the special committee of privileged shareholders regulated under Article 454 of the Turkish Commercial Code No. 6102. After giving general information about privilege in the first part of the study, the structure, authority, and legal nature of the special committee of privileged shareholders are mentioned in the second part. In the third and fourth parts of the study, the conditions for the meeting and the meeting process of the special committee of privileged shareholders are extensively discussed. In the last part of the study, the legal effect, nature, and invalidity of the special committee decisions of privileged shareholders are examined. In the preparation of the study, notable legal regulations in comparative law, doctrines and judicial decisions, especially related legislation in Turkish law have been benefited from. Key Words: Joint Stock Companies, privilege, the article 454 of the Turkish Commercial Code No. 6102, privileged share, the special committee of privileged shareholders.
Tez n°867760
Keywords: Anonim şirketler; Joint stock company; Special meeting; Turkish commercial law; Türk ticaret hukuku; Özel kurul

Ticari İşlemlerde Taşınır Rehni Kanunu uyarınca ticari işletme rehninin kuruluşu - Balkan, Nurdan (İstanbul Üniversitesi, 2023)
6750 sayılı Ticari İşlemlerde Taşınır Rehni Kanunu (TİTRK) 01.01.2017 tarihi itibariyle yürürlüğe girmiştir. TİTRK'de de ticari işletme, üzerinde rehin kurulabilecek taşınır varlıklardan biri olarak düzenlenmiştir. Hukuki niteliği itibariyle taşınır olarak kabul edilmeyen ticari işletmenin, taşınır varlıkların rehninin düzenlendiği bir Kanun'da kapsamlıca düzenlenemediği ilk bakışta görülmektedir. Bu nedenle ticari işletme rehninin kuruluşu tez konusu olarak seçilmiştir. Çalışmamızda TİTRK ile yapılan değişiklikler ve yenilikler ticari işletme rehninin kuruluşu özelinde incelenmiştir. Bu kapsamda ticari işletme rehninin kuruluşu konusu, TİTRK ve ikincil mevzuat, yeri geldikçe mülga TİRK ve TİTRK'nin mehazı olduğunu düşündüğümüz Uncitral Secured Transactions Model Law ile karşılaştırmalı olarak değerlendirilmiştir. Ticari işletme rehninin kuruluşu, ticaret hukuku, medeni hukuk ve borçlar hukukunun ilgili düzenlemelerinin bir bütün olarak incelenmesini gerekli kıldığından yeri geldikçe, TTK, TMK ve TBK'nın ilgili düzenlemeleri, tez konumuz özelinde incelenmiştir. The Law Numbered 6750 "The Law On Pledge Over Movable Assets In Commercial Transactions (TITRK)", which is a regulation that allows not only commercial enterprises but also many movable assets to be pledged without delivery entered into force as of 01.01.2017. In TITRK, a commercial enterprise is regulated as one of the movable assets that can be pledged too. However, it can be seen at first glance that the commercial enterprise, which is not considered as movable due to its legal nature, cannot be comprehensively regulated in the Law that regulates the pledge of movable assets. For this reason, the establishment of the commercial enterprise pledge has been chosen as the thesis topic. In our study, the changes and innovations made with TITRK were examined in terms of the establishment of the commercial enterprise pledge. In this context, the establishment of the commercial enterprise pledge have been examined in comparison with TITRK, its secondary legislation, mulga TIRK and Uncitral Secured Transactions Model Law, which we think is the basis of TITRK. Since the establishment of the commercial enterprise pledge requires the examination of the relevant regulations of the commercial law, civil law and law of obligations as a whole, the relevant regulations of the Turkish Commercial Code, Turkish Civil Code and Turkish Code of Obligations have been examined specifically for our thesis topic. In this section the secured transactions arrangements in comparative law will be discussed too.
Tez N°778878
Keywords: Commercial Transactions; Commercial institutes; Hypotheca; Movable Assets; Pledge of assets agreement; Rehin hakkı; Taşınır mal; Ticari işlemler; Ticari işletme rehni sözleşmesi; Ticari işletmeler; Ticari İşlemlerde Taşınır Rehni Kanunu; Trading operations

Kurumsal yönetim bakış açısıyla mali durumu bozulan anonim şirketlerde alacaklıların menfaatinin korunması - Demi̇rel Özdemi̇r, Duygu (Kocaeli Üniversitesi, 2023)
Anonim şirketler hukukunda alacaklılar, şirketlerin dış finansman kaynaklarının merkezini oluşturmakta ve bu nedenle de son derece önemli bir menfaat grubunu teşkil etmektedirler. Bu durum şirket alacaklılarının çıkarlarının etkin bir biçimde gözetilmesi ve korunmasını gerekli kılmaktadır. Zira alacaklıların alacaklarına kavuşabilmeleri için müracaat edebilecekleri tek kaynak şirketin malvarlığıdır. Dolayısıyla anonim şirketin mali durumunun bozulması sonucu malvarlığının kayba uğraması veya uğrama tehlikesi altında olması, alacaklıların menfaatlerini zedeleyici niteliktedir. Bu durum mali durumu bozulan anonim şirketlerde, alacaklıların menfaatlerinin gözetilmesini ve özellikle de öncül (ex-ante) koruma imkânlarıyla bu risk gerçekleşmeden önce bu konuda tedbirler alınmasını gerektirmektedir. Kurumsal yönetim anlayışı, anonim şirketlerde menfaat grupları arasındaki çıkar çatışmalarının en iyi, en adil şekilde dengelenmesini hedeflemektedir. Bu itibarla bu tez çalışmasında söz konusu menfaat çatışmaları özelinde kurumsal yönetimin şeffaflık, adillik, hesap verilebilirlik ve sorumluluk ilkeleri çerçevesinde bir menfaat grubu olarak şirket alacaklılarının menfaatlerinin, mali durumu bozulan veya bozulma tehlikesi altında olan anonim şirketlerde nasıl gözetilmesi ve korunması gerektiği hususunda bir bakış açısı sunulması hedeflenmektedir. Bu bakış açısından hareketle sermaye kaybı yaşayan, borca batık hale gelen anonim şirketlerin mali durumlarının iyileştirilmesi maksadıyla sermayenin korunması esası benimsenerek öngörülen TTK m.376 hükmü ile bu hükmün uygulanmasına ilişkin Tebliğ kapsamında öngörülen düzenlemelerin, alacaklıların menfaatlerinin korunması bakımından etkileri tartışılmaktadır. Ayrıca ilgili hükümlerin, şirketlerin mali yapılarının güçlendirilmesi bakımından yeterlilikleri ve yerindelikleri, karşılaştırmalı hukuk düzenlemeleri de göz önünde bulundurularak eleştirel bir bakış açıyla ayrıntılı şekilde incelenmektedir. Creditors are the key to external financing sources for companies under the statute of joint stock companies, and hence represent an important figure interest group. This situation needs the effective supervision and protection of the company's creditors' interests. This is because the company's assets are the only source to which creditors can turn to acquire receivables. Hence, the loss or threatened loss of the joint stock company's assets because of its worsening financial situation is detrimental to the creditors' interests. This circumstance necessitates that the interests of the creditors of companies with a worsening financial situation be considered and that steps be taken in this respect prior to the realization of this danger, particularly with ex-ante protection opportunities. The corporate governance method strives to achieve the most equitable resolution of conflicts of interest between interest groups in joint stock companies. This thesis aims to provide a perspective on how the interests of company creditors, as an interest group, should be observed and protected in joint stock companies whose financial situation deteriorates or is at risk of deterioration, within the framework of the principles of transparency, fairness, accountability, and responsibility of corporate governance. From this perspective, to improve the financial situation of companies that have capital loss and become over-indebted, the effects of the provisions of TCC art.376 and the Communiqué, which are envisioned based on the principle of capital maintenance, are discussed in terms of protecting the interests of creditors. In addition, the adequacy and suitability of the relevant rules in terms of strengthening the financial structures of corporations are analysed in depth from a critical standpoint, considering the norms of comparative law.
Tez N°789500
Keywords: Corporate governance; Creditors; Financial distress; Joint stock company

Milletlerarası ticari tahkimde hakem kararlarının iptali - Ersari̇, Danyal (Marmara Üniversitesi, 2023)
Günümüzde ticaretin globalleşmesi ile birlikte tahkim, uluslararası uyuşmazlıkların çözümünde devlet mahkemelerine nazaran kişiler, şirketler ve devletler tarafından daha çok tercih edilir hale gelmiştir. Bu tercihin en önemli sebeplerinden biri tahkim yargılaması sonucunda verilen hakem kararlarının tıpkı mahkeme kararlarında olduğu gibi kesin ve bağlayıcı olmasıdır. Ancak aleyhine karar verilen taraf, ilgili hakem kararının adalete uygun olmadığını düşünebilir. Bu bağlamda hakem kararlarının devlet mahkemeleri tarafından denetlenebilmesi için neredeyse tüm milli hukuk sistemlerinde hakem kararlarına karşı denetim yolu olarak "iptal davası" öngörülmüştür. İptal talebinde bulunan taraf belirli sebeplerin olması halinde tahkim yeri mahkemesinde iptal davası açabilecektir. Hakem kararına karşı iptal talebinde bulunan tarafın amacı, kararın bir kısmını ya da tamamını geçersiz hale getirmek ve icrasını engellemektir. UNCITRAL Model Kanun ve ulusal hukuk sistemlerinde iptal sebepleri sınırlı şekilde sayılmıştır. Ancak bazen bu iptal sebeplerinin faklı şekillerde yorumlandığı görülmüştür. İptal sebeplerinin geniş yorumlanması hakem kararlarının iptal olasılığını orantısız şekilde arttıracaktır. Bu durum alternatif uyuşmazlık çözüm yolu olan tahkimin güvenirliğine zarar verdiği gibi uzun, meşakkatli ve masraflı tahkim yargılama sürecini de boşa çıkaracaktır. Ancak, iptal sebeplerin adaletsizliğe yol açacak şekilde çok dar yorumlanması da keyfiliğe, tutarsızlığa ve tarafların istemediği sonuçlara yol açacaktır. Bu çerçevede Türk kanunları dahil çeşitli ülkelerdeki kanunları ve mahkeme uygulamalarını dikkate alarak kanımızca iptal sebepleri bakımından doğru yaklaşımları ortaya koymaya çalışacağız. Çalışmamız üç bölümden oluşmaktadır. İlk bölümde milletlerarası tahkime ilişkin genel bilgiler, yabancı hakem kararlarının tabiiyetinin belirlenmesi ve iptal davasına konu olabilecek yabancı hakem kararlarının türleri yer almaktadır. Bunun devamında, ikinci bölümde, çeşitli ülkelerin tahkime ilişkin kanunları, tahkime ilişkin milletlerarası literatürde kabul gören hukuki metinleri de dikkate alınarak iptal sebepleri ortaya konulacaktır. Aynı zamanda, konu ile ilgili doktrindeki görüşlere yer verilerek çeşitli ülkelerde verilen mahkeme kararları çerçevesinde iptal sebeplerine ilişkin yaklaşımlara ver verilecektir. Çalışmamızın üçüncü ve son bölümünde ise iptal davasının tarafları, iptal davasında görevli ve yetkili mahkeme ve iptal davasından feragat konuları Türk hukuku ve karşılaştırmalı hukuk bakımından incelenmeye çalışılmaktadır. Along with the globalization of trade, arbitration has become more preferred by individuals, companies and states than state courts in resolving international disputes. One of the most important reasons for this preference is that the arbitral awards given after the arbitration proceedings are final and binding, just as the court decisions. However, the party rendered against the award may consider it unjust. In this context, in order for the arbitral awards to be audited by the state courts, "annulment case" is designed as a legal remedy in almost all national legal systems. The party requesting annulment may file an action for annulment in the court of the place of arbitration if there are certain reasons. The purpose of the party requesting annulment against the arbitral award is to invalidate some or all of the decision and to prevent its execution. Although the reasons for annulment are limited and similar in many legal systems, the interpretation of these reasons is of great importance. A broad interpretation of the grounds for annulment will disproportionately increase the possibility of annulment of arbitral awards. This situation will not only harm the reliability of arbitration, which is an alternative dispute resolution method, but will also nullify the long, laboursome and costly arbitration proceedings. On the other hand, much narrower interpretation of the grounds for annulment in a way that leads to injustice may lead to arbitrariness and inconsistency, as well as result in undesirable results by the parties. Considering these, we will try to put forward approaches that can be consistent in terms of the grounds for annulment, taking into account the laws and court practices in various countries, including Turkish laws. This study consists of three parts. In the first part, general information about international arbitration, determination of the nationality of foreign arbitral awards and types of foreign arbitral awards that may be subject to annulment proceedings are included. Following this, in the second part, the reasons for annulment will be presented considering the arbitration laws of various countries and the internationally accepted legal texts on arbitration. At the same time, we try to put forward the approaches regarding the reasons for annulment within the framework of the court decisions given in various countries by giving place to the opinions in the doctrine on the subject. In the third and final part of our study, the parties of the annulment case, the competent court in charge of the annulment case and the waiver of the annulment case are to be examined in terms of Turkish law and comparative law.
826515
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; International commercial arbitration

Anonim şirketlerde imtiyazlı paylar - Erten, Cengiz (Kocaeli Üniversitesi, 2023)
6102 sayılı Türk Ticaret Kanunu (TTK) ile Türk Ticaret Hukuku'nda özellikle anonim şirketler hukukunda yapılan değişiklikler arasında imtiyazlı paylarla ilgili düzenlemeler de bulunmaktadır. Mülga 6762 sayılı Türk Ticaret Kanunundaki (eTK) hükümlere benzerlik gösteren yönleri olsa da imtiyazlı paylarla ilgili daha ayrıntılı, yenilikler getiren ve önceki Kanun döneminde karşılaşılan sorunları gidermeye çalışan düzenlemelerin yapıldığı görülmektedir. TTK'daki imtiyazlı paylarla ilgili düzenlemelerin eTK döneminde ortaya çıkan sorunları giderip gidermediğinin ya da yeni sorunlara, belirsizliklere ve tartışmalara yol açıp açmadığının tespit edilerek değerlendirilmesi amacı bu tezin yazılmasına sebep oluşturmaktadır. Birinci bölümde önce genel olarak pay kavramı, imtiyazlı payın tanınması koşulları, imtiyaz kavramının terminolojik yönü ve mevzuatımızda konuyla ilgili düzenlemelerle hukuk sistemimize esin kaynağı olan yabancı hukuk sistemlerindeki düzenlemeler incelenmiştir. Ardından, imtiyaz tanınan hakların, eşitlik ilkesi, müktesep hak ve vazgeçilmez hak ile olan ilişkilerine değinilmiş ve imtiyazlı pay kavramının nasıl tanımlanması gerektiği üzerinde durulmuştur. Tezin asıl omurgasını oluşturan ikinci bölümde, imtiyaza konu haklar, malvarlığı hakları ve yönetim hakları olarak iki asıl eksen üzerinde incelenmiştir. İkinci bölüm için en fazla tartışılmış bulunan konu, yönetim haklarında imtiyaza ilişkindir. Yönetim haklarında imtiyazı oluşturan iki alt başlık, oy hakkında imtiyaz ve yönetim kurulunda temsilde imtiyaz ayrıntılı bir şekilde incelenmeye çalışılmış, imtiyazın kanundan kaynaklanan nedenlerle engellenmesinden bahsedilmiş ve diğer haklarda imtiyaza değinilmiştir. Tezin üçüncü bölümü imtiyazların korunması konusuna ayrılmıştır. Bu bölümde imtiyazlı pay sahipleri özel kurulunun (İPSÖK) yapısı, niteliği ve toplanması ile özel kurulun onayına bağlı kararlar halka açık olan ve olmayan şirketler dikkate alınarak açıklanmıştır. Üçüncü bölümde ayrıca İPSÖK kararlarına karşı açılacak iptal davalarıyla ilgili değerlendirmeler yapılmıştır. It is observed that although there are some similarities with the previous one, the new Turkish Commercial Code, Law No: 6102, introduces more detailed and innovative arrangements which is intended to provide an answer to the problems experienced during the abrogated code was in force in relation to preference shares. It is easily can be said that, by and large, the topic "preference shares" is the one of the most radically altered topic in the new code. The main purpose of this thesis is to shed light whether these innovative arrangements in the new code actually solving the problems that is intended to solve or, rather opposite, causing new problems and ambiguities. For this purpose, the first section of this thesis is allocated to analyse the concept of "share" in general and under which conditions the preference shares are granted first and then the meaning of the concept of "preference" is investigated. It is followed by subsections devised to identify the current domestic law, and comprative law that inspried the law makers in this area. In the following subsections it is attempted to explain where preference shares stand with respect to principle of equality, vested interests and inalienable rights, and how the concept of preference shares should be defined. In the second section, which constitutes the backbone of this thesis, the rights that are being subject of the preference shares are examined on the axis of the assest rights and the administrative rights. The topic of the administrative rights attached to preference shares is the most debated topic in this section. In this context under the head of the administrative rights, the issues related to priveleges in votes and the representation on the executive board are examined seperately in two separate subsections. Also in this subsection the issues of statutory basis of the prevention of preferences and the preferences in relation to other rights are grappled. The third section of the thesis is completely devised to the issues related to the protection of the preference shares. In this section the structure, qualifications, gathering of the board of preference shares owners and the decisions subject to approval of this board are explained in the context of private and public companies. In this section the suits that could be brought for the annulment of this board decision is evaluated briefly.
Tez N°818042
Keywords: Joint stock company; Preference Shares

İcra ve iflâs hukukunda ticarî işletmenin bir bütün hâlinde paraya çevrilmesi - Erzeybek, Hakan (Ankara Hacı Bayram Veli Üniversitesi, 2023)
Ticarî işletme, kendisine özgülenen malvarlığı unsurlarının tamamı ile kapsamlı bir organizasyon niteliğini haiz olup, ticarî ve ekonomik bir bütünlük arz etmektedir. Ticarî işletme, ticarî bir amaca özgülenen ve bütünlük arz eden yapısı gereği, tacire ait malvarlığı unsurlarından belki de en değerlisidir. Bu yapısı gereği ticarî işletme, cebri icra hukukunda alacaklıların ilk müracaat edeceği malvarlığı unsurudur. Alacaklıların borçluya ait mal veya hakların paraya çevrilmesi sonucu tatmin edilmesi, cebri icra hukukuna hâkim olan genel bir ilkedir. Ticarî işletmenin cebri icra hukukunda paraya çevrilmesi, kapsamında bulunan mal veya hakların niteliği ve çeşitliliği gözetildiğinde ayrı bir önem taşımaktadır. Ticarî işletmeye özgülenen mal veya hakların ayrı ayrı paraya çevrilmesi, bu mal veya hakların parçalanmasına sebep olacağından, işletme faaliyetinin sona ermesine yol açar. Ticarî işletme faaliyetinin devamlılığının zedelenmesi, alacaklı ve borçlu menfaatlerini doğrudan etkilediği gibi ekonomik, sosyal ve toplumsal bir kısım olumsuz etkileri de beraberinde getirir. Bu nedenle, cebri icra prosedürleri içerisinde ticarî işletme bütünlüğünün bozulmaması büyük önem arz eder. Ticarî işletmenin cebri icra yoluyla bir bütün hâlinde paraya çevrilmesi, işletmeye özgülenen mal veya hakların bütünlüğünün bozulmasının önüne geçerek, faaliyetin devamlılığını sağlayan bir paraya çevirme şekli olarak karşımıza çıkmaktadır. Bunun yanında, ticarî işletmenin bir bütün hâlinde paraya çevrilmesi ile ayrı ayrı paraya çevirmeye nazaran daha yüksek gelir elde edilir. Çalışmamızda, öncelikle, ticarî işletmenin bir bütün hâlinde paraya çevrilmesi açısından karşılaştırmalı hukuk sistemlerinde yer alan bazı düzenlemeler incelenmiştir. Daha sonra, ticarî işletmenin bir bütün hâlinde paraya çevrilmesinin İcra ve İflâs Kanunu'nda yer alan her bir paraya çevirme türü açısından durumu ve ticarî işletmenin bir bütün hâlinde paraya çevrilmesinin yerine getirilme usulü ile paraya çevirmenin etki ve sonuçları ortaya konulmaya çalışılmıştır. A commercial enterprise has the character of a comprehensive organization with all the elements of assets specific to it, and it offers a commercial and economic integrity. A commercial enterprise, due to its structure that is specific to a commercial purpose and offers integrity, is perhaps the most valuable of the elements of the merchant's assets. Due to this structure, a commercial enterprise is the first asset element that creditors will apply for in forced execution law. The satisfaction of creditors as a result of the conversion of the debtor's goods or rights into money is a general principle that dominates the enforcement law. The conversion of a commercial enterprise into money in compulsory enforcement law is of particular importance when the nature and diversity of the goods or rights covered by it are taken into account. The conversion of goods or rights specific to the commercial enterprise into money separately leads to the termination of the business activity, as this will lead to the fragmentation of these goods or rights. Damage to the continuity of commercial business activity directly affects the interests of creditors and debtors, as well as brings with it some negative economic, social and social effects. For this reason, it is of great importance that the integrity of the commercial enterprise is not disrupted within the forced execution procedures. The conversion of a commercial enterprise into money as a whole through forced execution appears as a form of conversion into money that ensures the continuity of activity by preventing the deterioration of the integrity of the goods or rights specific to the enterprise. In addition, a higher income is obtained by converting the commercial enterprise into money as a whole than by converting it into money separately. In our study, first of all, some regulations in comparative legal systems have been examined in terms of the conversion of commercial enterprise into money as a whole. Subsequently, the situation of the conversion of the commercial enterprise into money as a whole in terms of each type of conversion contained in the Execution and Bankruptcy Code, as well as the procedure for performing the conversion of the commercial enterprise into money as a whole, as well as the effects and consequences of the conversion into money have been tried to be revealed.
Tez N°812486
Keywords: Cebri icra hukuku; Commercial institutes; Compulsory enforcement law; Ticari işletmeler; Turkish commercial law; Türk ticaret hukuku

Bireysel iş hukukunda arabuluculuk - Gül Küçükkaya, Hande (Marmara Üniversitesi, 2023)
Arabuluculuk tarafların tarafsız bir üçüncü bir kişinin yardımı ile ihtilaflarını çözmeye yardımcı olması olarak tanımlanabilir. Türkiye'de özel hukuktan doğan ve tarafların üzerinde serbestçe tasarruf edebilecekleri uyuşmazlıkların arabuluculuk ile çözümüne ilişkin 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu'nun 2013 yılında kabulü ile arabuluculuk uygulamasına geçilmiştir. 7036 sayılı İş Mahkemeleri Kanunu ile 2018 yılı itibariyle dava şartı arabuluculuk kavramı Türk hukuk literatürüne girmiştir. 7036 sayılı İş Mahkemeleri Kanunu md.3 uyarınca kanuna, bireysel iş sözleşmesine, toplu iş sözleşmesine dayanan alacak, tazminat veya işe iade talebi ile açılan davalarda arabuluculuğa başvurulması dava şartıdır. İtalya, Almanya ve ABD'nin bazı eyaletlerinde iş hukukunda dava şartı arabuluculuk uygulaması yoktur. İngiltere'de iş mahkemelerine başvurmak için önce ACAS isimli kuruma başvurmak gerekir. ABD 'de ise iş ilişkilerindeki ayrımcılık iddiaları öncelikle EEOC'de görülmektedir. Bireysel İş Hukukunda Arabuluculuk başlıklı doktora tezi çalışmamız dört bölümden oluşmaktadır. Çalışmanın birinci bölümünde alternatif uyuşmazlık çözüm yöntemleri kavramı ve belli başlı alternatif uyuşmazlık yöntemleri irdelenerek incelenmiş, ikinci bölümde arabuluculuk kurumu, amacı, prensipleri, türleri, arabulucunun hak ve yükümlülükleri, arabulucu ve arabuluculuk sözleşmelerinin hukuki mahiyeti ve arabuluculuk etiği gibi konular çalışılmıştır. Mukayeseli İş Hukukunda Arabuluculuk başlıklı üçüncü bölümde, arabuluculuğun anavatanı olan Amerika Birleşik Devletleri, Birleşik Krallık gibi Anglo Sakson sistemindeki devletlerde, İtalya, Almanya, Fransa gibi Roma Cermen sistemindeki devletlerde ve Avrupa Birliği müktesabatında arabuluculuğun nasıl düzenlendiği ve son olarak dördüncü bölüm olan Türk İş Hukukunda Arabuluculuk başlığı altında, dava şartı arabuluculuk kavramına ilişkin konular yargı kararları da işlenerek ayrıntılı olarak irdelenmiştir. Mediation can be defined as helping parties resolve their disputes with the help of a third party. With the adoption of the Law No. 6325 on Mediation in Civil Disputes in 2013, mediation has been implemented regarding the resolution of disputes arising from private law and on which the parties can freely dispose of. As of 2018, with the adoption of the Labor Courts Law numbered 7036 the concept of mediation as a cause of action in employment disputes litigation introduced in our legal literature. Pursuant to Article 3 of Labor Courts Law numbered 7036, lawsuits filed with the demand for receivables, compensation or reemployment based on the law, individual employment contract, collective bargaining agreement are subject to mediation as a cause of action. In Italy and Germany mediation in employment disputes does not exist. In England, in order to apply to the labor courts, firstly it must be applied to ACAS. In the United States of America, for discriminatory allegations in the employment relation firstly EEOC must be addressed. The doctoral thesis titled Mediation in Individual Employment Law consists of four parts. In the first part of the study, the concept of the alternative dispute resolution methods is investigated by examining the main alternative dispute methods, in the second part, the mediation institution, its purpose, principles, types, rights and responsibilities of the mediator, the legal nature of the mediator and mediation agreemets and mediation ethics are studied. In the third part titled Mediation in Comparative Employment Law, the Anglo-Saxon countries such as the United States of America and the United Kingdom, which are the homeland of mediation, in the Roman Germanic system states such as Italy, Germany France and in European Union legal system are explained and lastly under the title of Mediation in Turkish Employment Law, which is the fourth part, the issues related to the concept of mediation as a cause of action are also discussed in detail adding judicial decisions.
805181
Keywords: ACAS; Arabuluculuk; Cause of action; Comparative law; Danışma; Dava şartı; Karşılaştırmalı hukuk; Labour disagrement; Labour dispute; Labour law; Mediation; Uzlaşma ve Tahkim Servisi; İş hukuku; İş uyuşmazlıkları

Anonim ortaklıkta yönetim ve temsil yetkisinin devrinde yönetim kurulu üyelerinin hukuki sorumluluğu - Kalender, Süleyman (Çukurova Üniversitesi, 2023)
Anonim şirketlerde yönetim veya temsil yetkisi kural olarak yönetim kurulu tarafından kullanılmakla birlikte, özellikle halka açık veya büyük ölçekli ortaklıklarda söz konusu yetkilerin tamamının yönetim kurulu tarafından bizzat yerine getirilmesi uygulamada sık rastlanan bir durum değildir. Bu nedenle kanunda, yönetim kuruluna, yönetim veya temsil yetkisinin 6102 sayılı Türk Ticaret Kanunu' nun 367/I ve 370/II hükümlerinde yer alan şartlara uygun olarak, mevcut yönetim kurulu üyelerinden bir veya birkaçına yahut üçüncü kişilere devretmek suretiyle, şirketin yönetim teşkilatını belirleme yetkisi tanınmıştır. Şirket yönetimi konusunda uzmanlaşmış ve yeterli mesleki tecrübeye sahip olan kişilere yetkilerin devredilmesi, bir yandan şirkette profesyonelleşmeyi sağlamakta, diğer yandan kural olarak, devredilen yetkilerle birlikte bu kapsamda ortaya çıkabilecek hukuki sorumluluk da devredilmiş sayılacağından, yönetim kurulu üyelerinin hukuki sorumluluğunu sınırlandırmaktadır. Yönetim veya temsil yetkilerinin geçerli bir şekilde devredilmesi halinde, devredilen yetkilerle ilgili olarak yönetim kurulu üyelerinin hukuki sorumluluğu; murahhasların seçiminde, onlara verilecek talimatlarda ve murahhasların üst gözetiminde göstermeleri gereken makul derecede özen yükümlülüğü ile sınırlı olarak devam eder. Çalışmamızda, geçerli ve geçersiz yetki devri hallerinde, yönetim kurulu üyelerinin hukuki sorumluluğunun ne şekilde ortaya çıkacağı meselesi, mehaz İsviçre hukukundaki görüş ve yargı kararlarına yer verilmek suretiyle, detaylı bir şekilde incelenmiştir. Although the management or representation authority in joint stock companies is used by the board of directors as a rule, it is not common in practice that all of the said authorities are personally exercised by the board of directors, especially in publicly held or large-scale partnerships. For this reason, in the law, the board of directors is authorized to determine the management organization of the company by delegating the management or representation authority to one or more of the existing board members or to third parties in accordance with the provisions of the Turkish Commercial Code numbered 6102, 367/I and 370/II has been recognized. Delegation of powers to people who are specialized in company management and have sufficient professional experience, on the one hand, ensures professionalization in the company, and on the other hand, as a rule, legal responsibility that may arise in this context together with the delegated powers will be deemed to have been transferred, thus limiting the legal liability of the members of the board of directors. In case of a valid transfer of management or representation powers, the legal responsibility of the members of the board of directors regarding the delegated powers; limited to the reasonable care obligation that they must show in the selection of the executive directors, in the instructions to be given to them and under the supervision of the executive directors. In our study, the issue of how the legal responsibility of the members of the board of directors will arise in cases of valid and invalid delegation of authority has been examined in detail by including the opinions and judicial decisions in the Swiss law.
Tez N°832769
Keywords: Board of directors; Joint stock company

Milletlerarası ticari tahkimde delillerin değerlendirilmesi - Kesi̇kli̇, Ömer (Galatasaray Üniversitesi, 2023)
It is nowadays generally accepted that international commercial arbitration is the most popular method of resolving international disputes between commercial parties. This popularity is the cumulative result of many advantages that international commercial arbitration offers to the parties. It is suggested in the literature that one of these advantages is the freedom of parties and the resulting procedural flexibility. In virtue of this principle, the parties have the opportunity to establish a specific method of adjudication adapted to the nature of their dispute. This opportunity is provided by the fact that the arbitration regulations do not include detailed rules on the collection of evidence, thus leaving the parties and the arbitrators' range of motion. Therefore, we consider that this procedural flexibility has emerged as a possibility obtained at the expense of certainty in international commercial arbitration proceedings. This uncertainty is to such an extent that it also warrants the question as to whether there is an applicable law to take evidence in international commercial arbitration proceedings. Such procedural flexibility afforded to the parties, however, comes at a price of uncertainty with respect to arbitral procedure. International commercial arbitration developed as a reaction to the failings of proceedings in domestic courts, which were subject to detailed rules of evidence. Thus, the consensus in the arbitration community is that party freedom and the procedural flexibility that comes with it are fundamental attributes of arbitration. Although this presumption is theoretically correct; in other words, the parties are indeed able to craft such a procedure that would perfectly fit for adjudication of their disputes, mostly it does not reflect the practical reality. In practice, when parties are negotiating the terms of an agreement to govern their business relationship, they generally tend to avoid discussions as to what will happen if things go wrong. As a matter of fact, according to our practice experiences, when one of the parties' legal counsel tries to address such hypothetical scenarios, the parties generally prefer to suppress such "negative thoughts" and refuse to make in-depth discussions as to how a possible dispute is to be handled. Hereby, this leaves open the question of the procedure to be followed in arbitration proceedings in case of potential disputes. As a result, the provisions on how to resolve disputes that may arise between the parties, in other words, the "dispute resolution" provisions, are left to the very end of the negotiations and passed over in a few sentences. When the relationship between the parties becomes truly strained and a dispute comes to an unavoidable stage, it becomes even less likely that the parties will agree on how to gather evidence on the dispute in question. In a such situation, any suggestions made by one party regarding the procedure for the taking of evidence will be viewed with suspicion by the other party. In an environment of suspicion and animosity, it is often unrealistic to expect productive negotiations to take place on procedural matters. As a result, although the parties have a wide range of motions to make agreements regarding the method of collecting evidence in arbitration proceedings, they are often unable to exercise this authority in practice. As the parties are not exercising their rule-making powers, this important task, which is decisive for the resolution of the dispute, shifts to the arbitrators. Therefore, in our opinion, it would not be a wrong assessment to say that the freedom of the parties has turned into the freedom of the arbitrator in practice. Once appointed, arbitrators have to decide on many issues with respect to the taking of evidence as rules applicable to arbitration are generally silent as to these matters. Although arbitrators have the opportunity to be guided by some non-binding rules, such as the IBA Rules and the Prague Rules, which are considered to be effective and instructive in the arbitration community, they are ultimately left to make their assessments and reach an award based on their judgment. The above-mentioned non-binding rules can undoubtedly assist arbitral tribunals to a certain extent with regard to the taking of evidence. However, it is not possible to say that these rules are enforceable guidelines that can be blindly followed by arbitral tribunals. A closer look at these rules reveals that they leave many issues to the discretion of the arbitral tribunals. Of course, any decision regarding the taking of evidence in international commercial arbitration is already within the discretion of the arbitral tribunals, even in the absence of these rules. Therefore, these provisions, which have been drafted to allow the arbitral tribunals to decide as they see fit, are no more than general guidance on how to exercise their discretion. For these reasons, even if the parties have agreed on the application of these non-binding rules, the fact remains that the collection and evaluation of evidence are still left to the discretion of the arbitral tribunals. This study takes an inductive approach by analyzing the normative and non-binding rules of law applicable to evidence in international commercial arbitration. Firstly, this study examines whether there is a body of rules that can be characterized as the law of evidence in international commercial arbitration. It is determined that there is a law of evidence in international commercial arbitration; however, its content is rather composed of general principles. After determining that these rules have normative value, it is examined how and to what extent these general principles are concretized in terms of the types of evidence used in international commercial arbitration. Although the degree of concretization of these principles varies according to the types of evidence, as a general characteristic, it is determined that arbitral tribunals are left with a very wide discretionary power. It is concluded that arbitral tribunals have a wide latitude of action with respect to the submission of documents, the presentation of witness testimony, the use of expert testimony, the use of discovery and the extent of the res judicata effect of a prior award. Subsequently, the rules on the admissibility and evaluation of evidence are analyzed and it is concluded that the arbitral tribunals have wide discretion in international commercial arbitration, as in other matters relating to evidence and even the discretion regarding the evaluation of evidence is relatively wider. Since it is difficult to review the discretionary power exercised in these matters, it is observed that the arbitral tribunals' decisions on evidentiary issues fall outside the scope of judicial review. This leads to a further blurring of the already grey evidentiary issues in international commercial arbitration proceedings. This is because it is not possible to determine the extent to which the arbitral tribunal has relied on evidence that ostensibly played a role during the proceedings. In the last instance, although the arbitrators' discretionary powers are limited by general principles such as due process and opportunity to be heard, the limits of such discretionary powers are, generally speaking, somewhat blurred as these are general principles. Another issue is that arbitral tribunals are often subject to pressure from the parties when making their decisions on the taking of evidence during the arbitral proceedings. The parties are more interested in being the winner of the concrete proceedings than in the proper conduct of the proceedings in accordance with the law, procedure and rules. In this sense, a party whose request for evidence is likely to be rejected will often argue that the arbitral tribunal's decision violates the principle of a fair trial, even if this is not the case. It is in these circumstances that arbitral tribunals must strike a balance between a fair trial and an efficient trial and make appropriate decisions on evidentiary issues. If arbitral tribunals emphasize procedural efficiency and defer to the parties' presentation of their claims and defences, this may not in itself constitute an obstacle to legally correct decisions. However, this would violate the fundamental procedural safeguards of the participants in the proceedings and may even lead to arbitration proceedings becoming a mechanism for arbitrary and haphazard decision-making. If the opposite approach is taken, in other words, if the priority is to uncover the material truth at all costs and the procedural economy is put on the back burner, this will result in costly and protracted proceedings that will far exceed the limits of reasonableness. Given the limited scope of the guidelines available to arbitrators on the collection and evaluation of evidence, striking this balance is not an easy task. Therefore, it is quite understandable that arbitral tribunals, when deciding on evidentiary issues, may prefer the safer route and give precedence to claims of breach of the principle of a fair trial, even at the expense of the efficiency of the proceedings. Additionally, the confidential nature of the international commercial arbitral proceedings also amplifies the problem. As a result of this principle, the available knowledge as to the practice of arbitration becomes limited to anecdotal stories as to what has happened in certain individual international commercial arbitration proceedings. The arbitrators do not have sufficient opportunity to know about how their colleagues have dealt with certain issues that may have similarities with the issues that they have been trying to solve. In conclusion, in light of the foregoing, since the arbitral tribunals are the rule-makers of arbitration proceedings, the extent to which arbitration proceedings will function correctly and efficiently depends on the experience of the arbitral tribunals and their knowledge of the law, procedure and rules. Basing a correct and efficient arbitration procedure solely on the initiative of experienced arbitrators reduces the 'certainty' of the arbitral procedure. In the face of this situation, it may be tempting to argue that it is inappropriate for arbitrators to have so much freedom and that the rules applicable to arbitral proceedings should be revised to be more detailed. Indeed, there are those who argue that such a change should take place. In the final analysis, a good system should be able to function well regardless of how qualified (or unqualified) its participants are. It is obvious that an argument that sees detailed procedural rules as a remedy for this would contradict the historical development of arbitration and therefore would not be accepted by the international arbitration community. Likewise, from the other side of the coin, it could be argued that detailed procedural rules that are not appropriate to the nature of the individual dispute would prevent qualified and experienced arbitral tribunals from formulating rules that are appropriate to the resolution of the dispute in question, and that the hands of arbitral tribunals may be tied in this way. Although it may be argued that these counter-arguments are equally justified, they do not negate the fact that certainty should be ensured in international commercial arbitration proceedings. Therefore, this suggests that it may be appropriate to resort to alternative methods to ensure certainty. Indeed, it would be a mistake to assume that the only way to achieve certainty is through a detailed set of rules, as we, as legal practitioners in the Continental European legal system, are accustomed to. In the countries subject to the Common Law system, many branches of law do not have such a detailed set of rules and therefore it is not possible to claim that these legal systems lack certainty. Especially in the common law, certainty is provided by case law. If the same logic were to be applied to international commercial arbitration proceedings, it would mean that making information on arbitration proceedings more accessible could help to achieve the goal of certainty. In recent years, there have been some initiatives recognizing the benefits of this approach. While arbitral tribunals are under no obligation to follow the decisions of other arbitral tribunals, having the opportunity to see that there is a consistent pattern of decisions on a particular issue would undoubtedly provide valuable guidance for arbitral tribunals. As the pool of information available to arbitral tribunals and the parties expands, it is obvious that the grey areas regarding evidence in international commercial arbitration will diminish over time. In this way, it will be possible to achieve greater certainty without undermining the fundamental values of the arbitral procedure. Reducing the uncertainty caused by procedural flexibility on procedural certainty in this way will contribute significantly to the development of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Delil; Evidence; International Arbitiation Law; Milletlerarası Tahkim Kanunu; Proof (presentation); Tahkim; İbraz (İspat)

Ticari davalarda arabuluculuk - Yildirimoğlu, Hakan (İstanbul Ticaret Üniversitesi, 2023)
Dünya genelinde, uyuşmazlıkların mahkeme dışında alternatif uyuşmazlık çözüm yolları ile çözülmesi konusunda artan bir eğilim bulunmaktadır. Alternatif uyuşmazlık çözüm yollarından biri de arabuluculuktur. Arabuluculuk gönüllülük esasına dayanan bir uyuşmazlık çözme biçimidir. Arabuluculuk sistemi, AB'ye üye bazı ülkeler başta olmak üzere birçok ülkede özellikle ticari uyuşmazlıklarda uygulanmakta ve sonuçları itibariyle tarafları memnun etmekte, yargının yükünün de ciddi şekilde azaltılmasına destek olmaktadır. Yargının iş yükünün hızla arttığı, yargılamadaki gecikmeler nedeniyle adalete duyulan güvenin azaldığı bir ortamda arabuluculuk uygulamaları birçok ülkeye örnek olmaktadır. Ülkemizde de arabuluculuk uygulanmaya başlanmış; hatta en sık karşılaşılan uyuşmazlıklardan iş uyuşmazlıkları, ticari uyuşmazlıklar ve tüketici uyuşmazlıkları dava şartı arabuluculuk kapsamına alınmıştır. Ticari davaların zorunlu arabuluculuk yoluyla çözülmesi uygulamada bazı sorunlara ve çelişkili yargı kararlarının ortaya çıkmasına neden olmuştur. Arabuluculuk, Ticari Davalar, Ticari Davalarda Arabuluculuk, Avrupa Birliği, Zorunlu Arabuluculuk, Alternatif Uyuşmazlık Çözüm Yolları, Dava Şartı Arabuluculuk, Uzlaşma. There is an increasing trend around the world related with the resolution of disputes through alternative dispute resolution methods out of court. One of the alternative dispute resolution methods' is mediation. Mediation is a form of dispute resolution on a voluntary basis. The mediation system is applied especially in commercial disputes in many countries, also in some member countries of European Union. The mediation not only satisfies the parties in terms of its results but also helps to reduce the burden of the judiciary. In a world where the workload of the judiciary increases rapidly and trust in justice decreases due to delays in the trial, commercial mediation practices in European countries set an example for many other countries. Mediation is not also practised in Turkiye but also mandatory in labor disputes, commercial disputes and consumer disputes. Contradiction and discrepancy between the court decisions and other judicial problems arised arised as a result of mandatory mediation. Mediation, Commercial Disputes, Mediation in Commercial Disputes, European Union, Mandatory Mediation, Alternative Dispute Resolution, Condition of Litigation, Commercial Mediation. Reconciliation, Voluntary Mediation
784490
Keywords: Alternate dispute; Alternatif uyuşmazlık; Arabuluculuk; Avrupa Birliği; Commercial cases; Commercial disputes; European Union; Hukuk düzeni; Incompatibility; Judicial decisions; Law order; Mandatory mediation; Mediation; Ticari davalar; Ticari uyuşmazlıklar; Uyuşmazlık; Yargı kararları; Zorunlu arabuluculuk

Multimodal taşıma operatörünün sorumluluğu - Alhan, Yunus (Akdeniz Üniversitesi, 2022)
Multimodal taşıma; multimodal taşıma sözleşmesine binaen multimodal taşıma operatörünün eşyaların bir yerden farklı yerdeki teslimat için belirlenmiş bir noktaya taşınmasını en az iki farklı taşıma türü ile gerçekleştirmeyi taahhüt ettiği bir taşımadır. Konteyner kullanımının yaygınlaşması, günümüzde uluslararası eşya taşımalarının birden fazla taşıma türü kullanılarak kapıdan kapıya şeklinde yapılmasına olanak sağlamıştır. Bu sayede multimodal taşıma tüm dünyada yaygın hale gelmiştir. Taşıma sektöründe sıklıkla kullanılan bu taşıma türünün hukuki açıdan izahı önem arz etmektedir. Bu sebeple, multimodal taşımanın tanımı ve unsurları ele alınmıştır. Bu taşımanın diğer taşıma türleri ile benzerlik ve farklıkları değerlendirilmiştir. Her bir taşıma türüne ilişkin konvansiyonlar, ülkelerin ulusal hukuk düzenlemeleri ve multimodal taşımaya ilişkin yeknesak kurallar oluşturma amacıyla getirilen düzenleme çalışmaları ve düzenlemeler göz önüne alındığında multimodal taşımaya hangi hukuk düzenlemelerinin uygulanacağını öngörmek zordur. Multimodal taşımalarda sorumluluğu yeknesaklaştırmak adına en önemli düzenlemeler 1975 ve 1992 tarihli Milletlerarası Ticaret Odası (ICC) Kuralları ve halen yürürlüğe girmemiş olan 1980 Tarihli Multimodal Taşıma Konvansiyonu (MTC), 2009 tarihinde imzaya açılan Eşyaların Tamamen veya Kısmen Deniz Yoluyla Uluslararası Taşınmasına İlişkin Konvansiyondur (Rotterdam Kuralları-RK). Bu düzenlemelerden esinlenilerek ortaya çıkmış çeşitli bölgesel düzenlemeler söz konusudur. Bunun yanı sıra multimodal taşımanın ülke sınırları içerisinde gerçekleşebilmesi sebebiyle bazı ülkeler bu konuyu düzenleyen kanunlar yapmışlardır. Türk Hukunda ise multimodal taşımaya ilk kez 6102 sayılı Türk Ticaret Kanunu'nda (TTK), 'Değişik Tür Araçlar İle Taşıma' başlığı altında yer verilmiştir. MTO'nun zıya, hasar ve geç teslime dayalı sözleşme kaynaklı sorumluluğu zarar yerinin belirlenebilir olup olmamasına göre farklı kurallara tabidir. Zarar yerinin belirlenmesi ve multimodal taşıma sözleşmesinin taraflarından birinin zararın hangi taşıma türünde oluştuğunu ispatlaması durumunda, multimodal taşıma birden fazla taşıma türünü içerdiğinden denizyolu, havayolu, karayolu, demiryolu ve ülke iç suyolu gibi her bir taşıma türünü ayrı ayrı düzenleyen ve her biri kendi sorumluluk rejimini içeren uluslararası unimodal (tekil) taşıma konvansiyonlarından usulüne göre yürürlüğe girmiş olanları öncelikli olmak üzere, ilgili taşıma türünü özel olarak düzenleyen kurallar uygulanacaktır. Zararın gerçekleştiği taşıma türünün tespit edilememesi durumunda genel hüküm olarak adlandırabileceğimiz TTK hükümleri uygulama alanı bulacaktır. Çalışmada, Türk Hukukunda MTO'nun sorumluluğu ilgili konvansiyonlar ve TTK ışığında ele alınmış, uygulanacak hükümler ortaya konmaya çalışılmıştır. Anahtar Kelimeler: Multimodal Taşıma, Multimodal Taşıma Sözleşmesi, Multimodal Taşıma Operatörü, Multimodal Taşıma Operatörünün Sorumluluğu. Multimodal transport is a carriage in which multimodal transport operator, who assumes the responsibility of performing the carriage under the multimodal transport contract, undertakes to perform the carriage of goods by at least two modes of transport from one place to another place designated for delivery. Widespread use of containers today allows international transport of goods to be in the form of door-to-door transport using more than one mode of transport. Thus, multimodal transport becomes more widespread all over the world. Explaining this mode of transport, which is frequently used in the transport industry, from the legal perspective is of high importance. Hence, in this study, the definition and elements of multimodal transport are studied. The similarities and differences of this mode of transport with other modes of transport are evaluated. Considering different conventions regulating each mode of transport, national transport legislations and regulations aimed at setting forth uniform provisions, it is clearly difficult to determine rules that are applicable for the multimodal transport contract. Major regulations to uniform the liability in multimodal carriages are the 1975 and 1992 International Chamber of Commerce Rules, the 1980 Multimodal Transport Convention (MTC) and the United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (Rotterdam Rules-RT), which was open for signature in 2009. There are also regional regulations inspired by these instruments. In addition, a number of countries enact laws regulating multimodal transport, as multimodal transport may be performed within national boundaries, and there are no uniform rules regulating it. In Turkish law, certain rules on multimodal transport in the Turkish Commercial Law (TTK) No.6102 under the heading of 'Carriage by Various Modes of Transport (Multimodal Transport)' were introduced. The MTO's contractual liability for loss of or damage to goods or delay in delivery is subject to different rules depending on whether the place of loss can be located. If the place of loss is located, and the leg of transport in which the loss occurs is proved by any party of the multimodal transport contract, as the transport involves more than one mode of transport, rules specifically regulating that mode of transport, in particular unimodal conventions, which duly entered into effect, individually governing each mode of transport such as sea, air, road, rail and inland waterway transports and having its own liability regime, will be applicable. If the mode of transport in which the loss occurs cannot be ascertained, TTK provisions, which we may call general rules, will be applicable. In the present study, we analyse the liability of MTO within the framework of relevant conventions and TTK and seek to reveal applicable provisions. Keywords: Multimodal Transport, Multimodal Transport Contract Multimodal Transport Operator, Liability of Multimodal Transport Operator
Keywords: Carrier's responsibility; Contract of carriage; Multimodal taşımacılık; Multimodal transport; Taşıma sorumluluğu; Taşıma sözleşmesi; Taşımacılık; Transportation; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

İslam borçlar hukuku açısından ticari ihtilafların çözümünde 'Arabuluculuk' - Almasri, Raed (Ankara Üniversitesi, 2022)
Bu tez, anlaşmazlıkları çözmede arabuluculuk konusunu ele almaktadır. Arabuluculuk konusu ticari mali muamelelerdeki anlaşmazlıklar ile sınırlıdır. Dolayısıyla tez ailevi anlaşmazlıklardaki nafaka gibi diğer mali anlaşmazlıklara değinmemektedir. Tez konusu fıkhi açıdan ele alındığı için, dört fıkhi mezhebin konuyla ilgili görüşleri, mukayeseli olarak işlenmiş, mezhepler arasında ihtilaf ve ittifak edilen noktalar ele alınmış ve görüşler arasında tercih yapılarak ortaya konulmuştur. Tez; bir mukaddime, üç bölüm, bir sonuç ve kaynakçadan meydana gelmektedir. Mukaddime de tezin planı, fihrist ve içerik ele alınmıştır. Tezin birinci bölümünde; arabuluculuk kavramının tanımı ve meşruiyeti, ikinci bölümde; arabuluculuğun rükünleri ve arabuluculukla ilgili hükümler ve şartlar, üçüncü bölümde ise; arabuluculuğun sonuçları ve etkisi ele alınmıştır. The dissertation aims to cover the subject of mediation in dispute resolutions exclusively in commercial disputes. Therefore, the research does not cover mediation in other disputes such as domestic disputes even when it's related to financial matters such as alimony. The research also studies mediation in commercial disputes from a jurisprudential perspective. Hence the jurists' opinions are presented and analyzed in a comparative approach to show its similarities, differences and present a jurisprudential preference. The dissertation is presented in an introduction, three chapters, a conclusion followed by the list of references and resources. The introduction provides an insight into the research contents and methodology. The first chapter discuss the definition of mediations and its legitimacy. The second chapter tackle the main pillars of mediations and clarify its ruling and conditions. Finally, the third chapter view the results of mediations and its expected impacts.
753533
Keywords: Arabuluculuk; Borçlar hukuku; Commercial disputes; Incompatibility; Islamic law; Law of obligations; Mediation; Ticari uyuşmazlıklar; Uyuşmazlık; İslam hukuku

Navlun sözleşmesinde gönderilenin sorumluluğu - Arslan, Zeynep (Kocaeli Üniversitesi, 2022)
Deniz ticaret hukukunda, varma limanında yükün teslimini talep eden kişi, gönderilen olarak tanımlanmaktadır. Gönderilen, navlun sözleşmesinin tarafı olan taşıtan olabileceği gibi sözleşme ilişkisi dışında üçüncü bir kişi de olabilir. Gönderilenin üçüncü kişi olması hâlinde navlun sözleşmesi üçüncü kişi yararına sözleşme olarak nitelendirilmektedir. Kanun koyucu, sözleşme ilişkisine taraf olmayan bu üçüncü kişi için de bir takım hak ve sorumluluklar getirmiştir. İşte bu çalışmanın konusunu üçüncü kişi sıfatını haiz gönderilenin navlun sözleşmesinden kaynaklanan sorumluluğu oluşturmaktadır. Sözleşmelerin nispiliği prensibi gereği kural olarak tarafların anlaşarak üçüncü kişiyi borç altına sokmaları mümkün değildir. Bununla birlikte üçüncü kişi gönderilenin hangi hallerde sorumlu olacağı TTK m. 1203'te düzenlenmiştir. Buna göre gönderilenin navlun sözleşmesi kapsamında sorumlu olması için ilk olarak eşyanın teslimini talep etmesi gerekmektedir. Eşyanın teslimini talep, üçüncü kişi lehine sözleşme teorisi açısından edimin kabulü olarak değerlendirilmekte ve haliyle gönderilenin borç altına girmesi tarafların kararlaştırması ile değil öncelikle kendi iradesi ile olmaktadır. Gönderilenin sorumlu tutulmasının diğer şartını, teslim talebinin dayandığı taşıma sözleşmesinde ya da deniz taşıma senetlerinde bu borçların gönderilen üzerine bırakılması oluşturmaktadır. Dolayısıyla gönderilenin yükün teslimi sözleşmeden ya da deniz taşıma senetlerinden kaynaklanan bu alacakların ödenmesi şartına bağlanmaktadır. Gönderilenin hangi alacaklardan sorumlu olduğu sözleşme şartlarına göre tespit edilmektedir. Bu kapsamda sözleşme kayıtlarının incelenmesi gerekir. Navlun sözleşmesinde gönderilen uygulamada genellikle denizaşırı alıcı olarak karşımıza çıkmaktadır. Dolayısıyla Incoterms uyarınca tarafların kararlaştırdığı teslim şekillerinin ve FIO/FIOST/FILO/LIFO gibi gönderilenin sorumluluğunu genişleten kayıtların incelenmesi önemlidir. Bu kapsamda gönderilenin navlun sözleşmesinden kaynaklanan hangi borç kalemlerinden sorumlu olduğu sözleşme hükümleri ve mevzuat ile ayrıntılı bir şekilde açıklanmıştır. The consignee is defined as a person who requesting the delivery of the cargo at the discharge port by the maritime commercial law. The consignee might be the shipper, as a party of contract of affreightment, or might be a third party of the contract. In the case of the consignee is a third party, the contract of affreightment is characterized as a third-party beneficiary contract in which determined rights and responsibilities are given to this third party by the law makers. This thesis aims to determine the responsibilities of the third-party consignee that arising from the contract of affreightment. With regard to privity of the contract principle, as a rule, parties of a contract do not have right to bind a third party with obligations. On the other hand, the conditions of responsibilities of the third party consignee is regulated in the article 1203 of TCC. With regard to the article, in order for the consignee to be liable under the freight contract, the consignee must first request the delivery of the goods. The demand for the delivery of the goods is considered as the acceptance of the performance in terms of the theory of third party beneficiary contract and as a matter of fact, the consignee do not incur a debt with the parties' decision, but primarily with his own will. The other condition of holding the consignee responsible is the transfer of these debts to the consignee in the contract of affreightment or other transport documents on which the delivery request is based. Therefore, the delivery of the cargo is subject to the payment of these debts arising from the contract or transport documents. The debts of the consignee are determined according to the terms of the contract. In this context, it is necessary to review of the terms of the contract. In practice, the consignee in the contract of affreightment usually appears as a overseas receiver of the sale contract. Therefore, it is important to examine both the delivery methods agreed by the parties with regard to INCOTERMS and clauses that expand the responsibility of the sender, such as FIO/FIOST/FILO/LIFO. In this framework, this study explains in detail the responsibilities of consignee with regard to freight contract provisions and legislations.
Tez N°740401
Keywords: Commercial law; Contracts of affreightments; Deniz hukuku; Droit maritime; Freight; Gönderenin sorumluluğu; Law of the sea; Navlun; Navlun sözleşmeleri; Responsibility; Responsibility attiribution; Senders responsibility; Sorumluluk; Sorumluluk yükleme; Sözleşmeler; Ticaret hukuku

Şirketler hukukunun geleceği üzerine bir inceleme: Şirket yönetiminde yapay zekâ - Bora Çinar, Sevda (Akdeniz Üniversitesi, 2022)
Yapay zekâ teknolojileri, insan unsurunun egemen olduğu pek çok alanı etkisi altına almaya hazırlanmaktadır. Bu alanlar arasında tıp, hukuk, eğitim, mühendislik olduğu gibi ticaret de bulunmaktadır. Yapay zekâ teknolojileri, özellikle şirketler hukukunun geleneksel yapısını kökünden sarsacak yeni bir ticari düzen ve anlayış yaratma yolundadır. Karar alma süreçlerini otomatikleştiren yapay zekâ teknolojilerinin verimliliği ve hızı, şirketlerin bu sistemleri geliştirerek pazarlamalarının yanı sıra bizzat şirket bünyelerine katarak kullanma eğilimi göstermelerine de yol açmaktadır. Bu şekilde kendi kendini besleyen bu döngü, yapay zekâ alanına sermaye yapısı güçlü şirketlerin yönelmesini ve araştırma kapsamının gittikçe genişletilmesini sağlamaktadır. Şirketlerdeki bu yönelim neticesinde, hızla gelişen yapay zekâ teknolojilerinin geleneksel şirket yapılarını etkileyebilme potansiyelinin yükselmesi olgusu, şirketler hukukunun geleceği üzerine bir inceleme yapılması gerekliliğini ortaya çıkarmaktadır. Çalışmamızda şirket yönetiminde yapay zekâ teknolojilerinin kullanımına ve bunun hukuki sonuçlarına odaklanılmakta ve konu dört temel bölüme ayrılarak incelenmektedir. Giriş bölümünde kısaca çalışmanın konusu, önemi, amacı, kapsamı ve sistematiği açıklanmakta, yapay zekâ ve şirket yönetiminin kavramsal çerçevesine yer verilmektedir. Birinci bölümde şirketler hukuku ve yapay zekâ teknolojilerinin etkileşimi incelenmektedir. Bu bölümde yapay zekâ teknolojilerinin ticaret hukuku ve şirketler hukuku ile etkileşimi incelenmekte, dijitalleşmenin şirketler hukukuna etkileri, özellikle şirket yapılarındaki ve menfaat çatışmalarındaki dönüşüm çerçevesinde ele alınmaktadır. İkinci bölümde, şirket yönetiminde yapay zekâ teknolojilerinin kullanılması bir süreç olarak incelenmektedir. Kullanım kararı alınmasından başlamak üzere, şirkete uygun yapay zekâ teknolojilerinin edinimi ve bu teknolojilerinin şirket yönetiminde kullanılma yöntemlerinin araştırıldığı bu bölümde, teknik, hukuki ve ticari başta olmak üzere ilgili beklenti ve belirsizlikler araştırılmaktadır. Üçüncü bölümde şirket yönetiminde yapay zekâ teknolojilerinin kullanılmasının hukuki sonuçları ve hukukun bu dönüşümden nasıl etkileneceği üzerinde durulmaktadır. Son bölümde ise yönetimin geleceği üzerine düşüncelerin yer altığı bir karar ağacı tasarımı içeren interaktif bir bölüme yer verilmektedir. Artificial intelligence technologies are preparing to influence many human-dominated and human-related fields. These fields include medicine, law, education, engineering as well as commerce. Artificial intelligence technologies are on the way to create a new commercial order and understanding that will shake up the traditional structure of corporate law. In particular, the efficiency and speed of artificial intelligence technologies that automate decision-making processes have led companies to tend to use these systems both by developing and marketing them and by incorporating them. In this way, this self-sustaining cycle has led companies with strong capital structures to move towards the field of artificial intelligence, and the scope of research has been gradually expanded. This orientation in companies and the high potential of rapidly developing artificial intelligence technologies to affect traditional company structures have revealed the necessity of conducting an examination on the future of company law. Our study focuses on the use of artificial intelligence technologies in company management and its legal consequences, and the subject is examined under four main sections. In the introduction, the subject, importance, purpose, scope and systematics of the study are briefly explained, and the conceptual framework of artificial intelligence and company management is given. In the first part, the interaction of corporate law and artificial intelligence technologies is examined. In this section, the interaction of artificial intelligence technologies with commercial law and company law is examined, the effects of digitalization on corporate law are discussed, especially within the framework of the transformation in company structures and conflicts of interest. In the second part, the use of artificial intelligence technologies in company management is examined as a process. In this section, where the acquisition of artificial intelligence technologies suitable for the company and the methods of using these technologies in company management are investigated, starting from the decision to use, all technical, legal and commercial expectations and uncertainties are investigated. The third chapter focuses on the legal consequences of the use of artificial intelligence technologies in company management and how the law will be affected by this transformation. In the last part, there is an interactive section that includes a decision tree design with thoughts on the future of management.
Keywords: AI; Anonim şirketler; Artificial Intelligence; Bilgi ve belge yönetimi; Bilgi yönetim sistemi; Bilgi yönetimi; Capital companies; Commercial companies; Financial data management system; Finansal veri yönetim sistemi; Hukuki sorumluluk; Information and records management; Information management; Information management system; Institutional responsibility; Inteligência artificial; Intelligence Artificielle; Joint stock company; Kurumsal sorumluluk; Legal responsibility; Sermaye şirketleri; Ticari şirketler; Yapay zeka

Ticari işletmenin devri - Cerenoğluak, Ceren (Yeditepe Üniversitesi, 2022)
Ticari hayatın gerekleri, ticari işletmelerin faaliyetlerini devam ettiren bir organizasyon bütünü olarak devredilebilmesi ihtiyacını doğurmaktadır. Tüzel kişilik tanınmamış ve hukuk süjesi sayılmamış olan ticari işletmeyi ilgilendiren malvarlığının, hukuki işlemlere konu olması ve özellikle devri bakımından özel bir hukuki rejim öngörülmüştür. Bunun için, Türk Ticaret Kanunu'nun 11/3 fıkrasında düzenlenen şekil ve koşullara uyularak, ticari işletmenin devri gerçekleştirilebilir. 1 Temmuz 2012 tarihinde yürürlüğe giren 6102 sayılı Türk Ticaret Kanunu 11. maddesi ile ticari işletmenin devri sözleşmesinin ve de ticari işletmeyi bir tütün halinde konu alan diğer sözleşmelerin yazılı olarak yapılacağı belirtilerek yazılı şekil şartı ilk kez hukukumuza getirilmiştir. Bununla birlikte, yeni Ticaret Kanunumuz, ticari işletmenin devri prosedürünü kolaylaştırmak adına tescilsiz kazanım öngörmekte ve de aktif unsurların devri için genel hükümlerin gerektirdiği kurucu işlemlerin yapılmasına gerek olmadan devrin gerçekleşeceğini düzenlemektedir. Bu düzenlemenin sicile güven ilkesi açısından neticeleri ve doğura bileceği hukuki sakıncalar tezimizde incelenmiştir. The requirements of commercial life may create the need to transfer the commercial enterprises as a whole organization that continues its activities. A special legal regime has been foreseen for assets of business, which is not recognised as a legal entity, to be subject to transactions, particularly to assignment. For this purpose, the transfer of a commercial enterprise is to be carried out in compliance with the forms and conditions set out in article 11/3 of the Turkish Commercial Code. The written form condition for the transfer of the commercial enterprise agreements and the other agreements in relation to the commercial enterprise has firstly regulated under the Article 11 of the Turkish Commercial Code numbered 6102, has entered in to ferce on July 1, 2012. In addition to this, in order to facilitate the transfer of the commercial enterprise procedure, New Commercial Code stipulates the acquisition without registration officially and transfers of the assets without performing the transaction required by the general provision. The results and legal inconveniency of the said regulation with respect to the believe in registration principle will be discussed in our thesis.
709946
Keywords: Commercial institutes; Contracts; Devir; Kanunlar 6102 sayılı; Laws 6102 numbered; Sözleşmeler; Ticari işletmeler; Transfer of enterprise; Turkish Commercial Code; Turkish commercial law; Turnover; Türk Ticaret Kanunu; Türk ticaret hukuku; İşletmenin devri

Yönetim kurulu üyelerinin şahsî sorumluluğuna ilişkin davalarda maddî hukukun usûl hukukuyla etkileşimi - Eski̇ocak, Ali (Galatasaray Üniversitesi, 2022)
Les membres du conseil d'administration, qui sont l'organe représentatif et exécutif de la société anonyme, sont investis de pouvoirs et d'attributions étendus à tous les stades de leur activité (Code de Commerce turc art. 365, art. 374). En cas de perte résultant de la violation de ces obligations, il est inévitable que la responsabilité soit mise en avant. Ceci est principalement une conséquence naturelle de la règle générale de "l'équilibre autorité-responsabilité". Dans ce contexte, l'existence et l'effectivité des actions en responsabilité ont un rôle dissuasif pour que les administrateurs ne manquent pas à leurs obligations. D'autre part, en raison du principe de la responsabilité limitée avec les actifs contre les créanciers de la société anonyme (Code de Commerce turc art. 329/1), la protection des actifs est importante pour empêcher les créanciers de subir des pertes. De plus, la question de la responsabilité revêt une importance particulière au regard des principes de gouvernance d'entreprise. Parce que la comptabilité et la responsabilité sont les éléments clés du principe de gouvernance d'entreprise dans les sociétés anonymes qui sont les acteurs les plus importants de la vie économique d'aujourd'hui. Par conséquent, des réglementations détaillées prises en vertu du Code de Commerce turc concernant les obligations et les responsabilités des membres du conseil d'administration; en outre, les dispositions relatives aux poursuites en responsabilité ont été réglementées de manière plus détaillée et systématique et des changements importants ont également été introduits à cet égard. Dans ce cadre, un régime de responsabilité spéciale a été institué pour les administrateurs en dehors des dispositions de responsabilité générale, tandis que les articles 549 à 552 du Code de Commerce turc réglementent la responsabilité spéciale, l'article 553 et les articles suivants du Code de Commerce turc réglementent les dispositions relatives à la responsabilité générale. Ces articles sont relativement larges et complets par rapport à l'ancien code. Diverses études monographiques ont été réalisées en matière de responsabilité juridique des membres du conseil d'administration et ce sujet a été largement examiné dans les travaux sur le droit des sociétés anonymes. Cependant, l'aspect droit matériel de la responsabilité juridique a été principalement examiné dans la doctrine mais les questions liées aux actions en responsabilité et l'aspect procédurale de l'action ont trouvé une place limitée dans la doctrine. Les expressions similaires sont souvent utilisées concernant la nature du droit d'action des actionnaires et créanciers, mais l'aspect procédurale n'est généralement pas examiné avec une explication détaillée, des analyses et une caractérisation. Cependant, cette question est étroitement liée à des questions importantes telles que la relation entre les demandeurs, la litispendance, le jugement définitif, l'exécution du jugement et les caractéristiques des défenses. Dans notre étude, en raison de l'importance des actions en responsabilité et de l'augmentation du nombre des actions en pratique, nous essayons d'expliquer les caractéristiques de l'action en responsabilité (l'aspect procédural) ainsi que l'aspect du droit matériel. Cependant, notre étude n'est pas une thèse de procédure civile, c'est une thèse de droit matériel et il vise à examiner les questions liées au droit procédural en commençant par la nature de la responsabilité, l'engagement de l'action jusqu'à l'exécution du jugement définitif rendu. En conséquence, le sujet de notre étude est de décrire l'aspect de droit substantiel de l'action en responsabilité et d'examiner les domaines où la responsabilité des membres du conseil d'administration intersecter avec le droit procédural. Donc l'objectif de cette étude est l'aspect de droit substantiel de la responsabilité. Les problèmes procéduraux sont examinés dans cette perspective. La responsabilité civile des membres du conseil d'administration a été examiné conformément à l'article 553 et les dispositions suivantes. L'analyse a été faite pour les personnes qui ont le droit d'action avant la déclaration de faillite, mais pas pour les autres qui ont le droit d'action après la déclaration de faillite (administration de la faillite, créanciers). La responsabilité des membres du conseil d'administration et des dirigeants a été prise en considération. Par ailleurs, la responsabilité résultant de la fondation, les cas particuliers de responsabilité régis par l'article 549 et suivants du Code de Commerce turc, la responsabilité de contrôleur qui est régie par l'article 554 du Code de Commerce turc, l'action particulière en responsabilité régie par l'article 193 du Code de Commerce turc, l'action en responsabilité à l'égard d'un groupe de sociétés régi par l'article 202 et les dispositions suivantes du Code de Commerce turc et la révocation des personnes responsables entre elles selon leurs relations internes (action en révocation) sont exclues du champ de cette étude. Notre étude, préparée dans ce contexte, se compose de cinq grandes parties, dans la première partie, les principes de l'aspect droit matériel de l'action en responsabilité ont été examinés. Dans ce cadre, les réglementations légales antérieures et nouvelles en matière de responsabilité, les innovations apportées par la Code de Commerce turc, la base juridique (la source), le but, l'objet, l'intérêt qu'elle protège, ses éléments, sa relation avec divers actions et institutions et ses caractéristiques sont important. La source de responsabilité est basée sur la relation contractuelle entre les membres du conseil d'administration et la société, et les éléments de responsabilité sont l'illégalité, le dommage, le lien de causalité et la faute. La responsabilité des membres du conseil d'administration appartient à l'organe de gestion, est personnelle et fondée sur la faute. Sur cette note, la présomption de responsabilité a été révoquée et le fardeau de la preuve repose sur le demandeur. Alors que le principe de solidarité différenciée a été inclus dans l'article 557 du Code de Commerce turc, il a été mis l'accent sur l'application des dispositions de relation de causalité ainsi que les articles 51-52 du Code des Obligations turc. En ce qui concerne le devoir de diligence, la méthode de référence indirecte au devoir de diligence de l'employé qui était régie par l'article 320 du précédent Code de Commerce a été abandonnée par l'article 369 du Code de Commerce turc, et le devoir de diligence a acquis l'objectivité par l'adoption de « business judgement rule (agir avec diligence, bonne foi et loyauté en decision de gestion)». En outre, dans l'exposé des motifs de l'article, il a été clairement indiqué que le critère de prudence sont pertinents avec la « business judgement rule» Le devoir de diligence est lié à des éléments d'« illégalité » et de « faute ». Par conséquent, cet article signifie l'objectivation de la faute. De ce fait, la frontière entre les éléments d'illégalité et de faute est devenue encore plus incertaine. La délégation de gestion (art.367 du Code de Commerce turc) est une situation qui a un impact sur la responsabilité, avec une délégation valable il y aurait partage responsabilité primaire - responsabilité de surveillance (art. 553/2 du Code de Commerce turc). La nouvelle règle, régie par l'article 557/2 du Code de Commerce turc qui prévoit qu'une action en justice peut être intentée pour l'ensemble du dommage et qu'il peut être demandé au juge de déterminer l'indemnisation de chaque défendeur dans une même action en justice, est importante pour fixer qu'il n'est pas nécessaire que le demandeur tienne compte du principe de solidarité différenciée, et que ce principe est une règle qui ne s'adresse qu'au juge et à la décision qu'il établira. Dans la deuxième partie, les caractéristiques du droit d'intenter une action en responsabilité, les parties de l'action et les modalités d'exercice du droit d'action sont discutées. La caractéristique du droit d'action qui pourrait être exercé par d'autres personnes que la société est importante. Le résultat est étroitement liée aux questions critiques telles que les défenses qui pourraient être invoquées par les défendeurs, et avec quelles défenses pourraient être invoquées contre quel demandeur, la relation entre les demandeurs, la litispendance, le jugement définitif, l'exécution du jugement. Après une évaluation détaillée, notre opinion est que les actionnaires et les créanciers ont chacun individuellement un droit substantiel d'engager une action en responsabilité. En outre, la manière d'exercer le droit de la demande réglementé par la loi est également importante. Étant donné qu'il n'y a pas de disposition ou de déclaration restrictive dans la loi concernant la manière de demande du dommage de l'entreprise, il est également possible d'appliquer tous les recours disponibles en vertu du droit de la procédure civile, de l'exécution et de la faillite. Il est possible de demander des mesures provisoires. Bien qu'il existe une réglementation générale quant aux parties à l'action en responsabilité dans la loi, il est important d'examiner ce sujet. A cet égard, l'action intentée par l'actionnaire avant la faillite n'est soumise à aucune condition. Le montant (ratio) de l'action (la part) n'est pas important. En ce qui concerne le défendeur, les défendeurs sont comptés dans la loi. A ce propos, il est important de déterminer qui entrera dans le champ d'application du concept de « dirigeants», qui est réglementé pour être responsable aux côtés des membres du conseil d'administration. La position des personnes qui ont le droit d'action peut varier selon les avis sur la caractéristique du droit d'action. A notre avis, il n'y a pas d'obstacle légal au dépôt d'actions en responsabilité distinctes par des personnes ayant droit d'action, et cette situation ne constitue pas une litispendance. Dans la troisième partie de notre étude, les instruments de défense relatifs aux actions en responsabilité et à la question de la preuve sont abordés. Les moyens de défense sont importants en ce qui concerne l'instance pendante, la détermination de l'existence des éléments de responsabilité et le calcul du montant de l'indemnité. Parmi les conditions d'action, en tant que moyens de défense en matière de droit procédural, la décision de l'assemblée générale et l'intérêt à agir revêtent une importance particulière. À notre avis la décision de l'assemblée générale devait être recherchée comme condition d'action. En outre, bien que l'intérêt à agir soit une condition générale d'action, il prend plus d'importance pour le cette étude, car dans les actions en responsabilité l'événement qui constitue une violation de l'interdiction de l'abus de droit (art. 2 Code Civil turc). En outre, l'adoption du principe de solidarité différenciée a accru l'importance des motifs de défense individuels. Les motifs matériels de la défense peuvent être très divers, tels que le fait de ne pas être investi d'un organe de gestion, la libération, la prescription, la forclusion, l'exécution du devoir de diligence et la délégation de pouvoir. De plus, comme dans tous les procès, la question de la preuve est également très importante dans les actions en responsabilité. Cependant, un système de preuve spécial et une méthode de preuve n'ont pas été prévus en termes des actions en responsabilité. Par conséquent, des questions telles que la charge de la preuve, l'objet de la preuve, l'échelle de la preuve et les preuves propres doivent être déterminées en tenant compte des caractéristiques spécifiques de l'action en responsabilité, et cela a été examiné dans ce cadre dans notre étude. Dans le quatrième chapitre, le déroulement du procès, le jugement et l'exécution du jugement sont expliqués. En particulier, l'accent mis sur le lien de causalité et l'acceptation du principe de solidarité différenciée avec de nouvelles dispositions obligent le juge à procéder à un examen précis. Dans ce contexte, des questions telles que l'impossibilité du contrôle d'opportunité, la mise en œuvre du principe de solidarité différenciée et la prise en compte de la situation des responsables, qui ne sont pas parties au procès, sont les aspects originaux de la procédure. L'effet du jugement à la fin de l'action est également un sujet discuté dans la doctrine. À notre avis, le jugement ne constituera pas res iudicata (l'autorité de la chose jugée) pour les autres actions en responsabilité et les actions en révocation. Cependant, il convient de noter que l'effet de l'intervention en cas de dénonciation d'instance et d'intervention accessoire, pourrait être important en termes d'action en révocation, et de fait, il peut avoir un effet plus important que res iudicata. Une autre question importante est celle de savoir qui a le pouvoir d'exécuter le jugement et les possibilités dans cette question. Le point le plus prénant ici est que le droit de réclamation de l'actionnaire (le demandeur) comprend le pouvoir d'exécuter le jugement, mais le paiement perçu au stade de l'exécution doit être versée à la société. Dans le cinquième chapitre, quelques situations particulières liées aux actions en responsabilité sont examinées. Dans ce contexte, il a été analysé que l'effet du recouvrement partiel ou total du dommage sur les autres parties responsables dans le cadre de diverses possibilités, la transaction et le désistement d'action (la validité et caractère obligatoire), l'examen de la libération d'une ou plusieurs des personnes responsables au sens de l'article 166/3 du Code des obligations turc, la pertinence de la révocation dans le cadre de l'action en responsabilité et les opérations collusoires de l'entreprise dans le cadre de l'action en responsabilité. Notre avis a été indiqué en conjonction avec l'analyse des arguments de la doctrine et de la pratique sur ces questions.
728363
Keywords: Borçlar hukuku; Cases; Davalar; Faulty liability; Hukuki sorumluluk; Kusurlu sorumluluk; Law of obligations; Legal responsibility; Maddi hukuk; Members of the board directors; Procedural law; Responsibility; Sorumluluk; Substantive law; Turkish Commercial Code; Türk Ticaret Kanunu; Usul hukuku; Yönetim kurulu üyeleri

Anonim ortaklıkta yönetim kurulu üyesinin rekabet yasağı - Günaydin Gülteki̇n, Burcu (Galatasaray Üniversitesi, 2022)
This subject matter of this work is the prohibition of competition with the company of members of board of directors in joint stock companies under art. 396 of the Turkish Commercial Code. The prohibition of competition is a limitation on the commercial activities and the freedom of competition of a restricted party who has access to information, means or resources due to the legal relationship between parties which grant the restricted party a leverage in competition with the other. The core idea underlying the prohibition of competition is the necessity to protect the party benefiting from this prohibition against competitive activities of the restricted party. The prohibition of competition bans the restricted party from establishing competition with the party benefiting from the prohibition through competitive actions, ultimately from becoming the competitor of the beneficiary. The said competition relationship will occur in the event the services or products serving the same or similar needs are provided to the entirety or part of the same customers or customer group. Board members in joint stock company, having the prevailing right of access to all information and resources of the company leads to the risk that it may use this power for its own or other parties' benefit instead of that of the company. Hence, the prohibition of competition on board members regulated under article 396 of the Turkish Commercial Code is one of the concrete examples of the duty of loyalty of a board member towards the company aiming to prevent such usages prioritizing the benefit of the member or of a third person over that of the company. The focal point of this work is the determination of the scope of application and conditions of this prohibition as a whole. The first chapter of this thesis aims to convey the conceptual basis of the prohibition of competition. In this scope, we first assessed the economic and legal basis of competition. Economic competition is the race/competition of two or more market actors in a specific market in order to engage in a transaction with its counterparty in the market through offering better prices, conditions, goods or services in order to be superior from its competitors. However, the intention to supersede its competitors and the efforts for this purpose may result in the misuse of the right to compete or in an act limiting or eliminating the competitive environment. The Republic of Turkey provides for a constitutional protection over a person's right to engage in commercial activities and, although not expressly regulated, right to compete. However, as is the case for all rights and liberties, the right and liberty to compete cannot be exercised without any limitation. Second, the scope of the prohibition of competition is assessed. In this regard, we tried to determine the elements of the prohibition of competition, its definition, and its legal categorization. Moreover, a comparison of the prohibition of competition with the provisions governing unjust competition aiming to establish honest and undisrupted competition as well as with the rules of Competition Law aiming to prevent disruption of competition through restrictive actions is provided in order to specify the prominent characteristics of the prohibition of competition. Third, the attributes of the provisions governing the prohibition of competition are assessed. Provisions governing prohibition of competition which do not relate to the public order but to the internal relations of parties, and which serve the personal benefit of the beneficiary, are not of a peremptory nature. The prohibition of competition, which materially limits the liberty of engaging in commercial activities protected under the constitutional law, is of an exceptional nature and hence the provisions governing the prohibition of competition need to be construed in a limited manner. Fourth, the prohibition of competition can be regulated in the letter of a contract through mutual agreement thereon by its parties, or the legislator occasionally provides for a legal provision governing the prohibition of competition by attributing a special importance to this prohibition with respect to a specific relationship between the parties. Last, in this first chapter, we identify the reflections of this prohibition of competition within the scope of the Law of Obligations, and the Law of Corporations. The second chapter of this work takes into consideration the reasons of regulating a prohibition of competition on board members, and its scope of application regarding the persons concerned. In this context we first broadly assessed the position of the board of directors, board members and affiliated commercial auxiliaries in a company. Then, the legislative provisions respectively of German Law, Swiss Law and Turkish Law governing the board members' prohibition of competition are specified. While in German Law, just as is the case in Turkish law, the prohibition of competition of board members is stipulated in § 88 of the German Stock Corporation Act, the Swiss Law does not regulate this prohibition of competition of board members with a statutory provision, nonetheless, this prohibition is accepted by the scholars. Thereafter, the reason for regulating the prohibition of competition of board members is assessed. In this scope, the duty of loyalty of a board member arises from the legal relationship between the member and the corporation being based on the principle of trust. The member must refrain from conflicting its interests with the interests of the corporation, in other words, from conflict of interests, due to its duty of loyalty. When the member engages in competition with the company, the interests of the company and the board member conflict with each other. The member is in a considerably advantageous position in this conflict compared to the company, due to the information and resources to which it has access thanks to its position within the company. For this reason, the duty of loyalty aiming to prevent the conflict of interest between the company and the member lies at the basis of the board member's prohibition of competition. Lastly, in this chapter, the persons subject to the prohibition of competition pursuant to article 396 of the Turkish Commercial Code are identified. In this respect, the members of the board of directors as well as persons to whom management authorities are delegated fall within the scope of the ratione personae of article 396 of the Turkish Commercial Code. The commercial representatives and commercial proxies of a company are prohibited from competition pursuant to the prohibition of competition regarding commercial auxiliaries pursuant to article 553 of the Turkish Code of Obligations. Whereas a shareholder is not subject to the prohibition of competition with the company; this prohibition may only be regulated by a contract subject to the Law of Obligations. Furthermore, when evaluating the prohibition of competition of shareholders, whether the shareholder has a duty of loyalty to the company has been assessed under German Law, Swiss Law and Turkish Law. The third chapter of this work sets forth the scope of application of the prohibition of competition of board members with respect to its subject matter, place, and time. In order for a board member to violate the prohibition of competition with the company, the member must engage in an activity competing with the company. Pursuant to the first paragraph of article 396 of the Turkish Commercial Code, two types of competitive actions of board members are banned. The first type is the member engaging in an action which is a commercial transaction that falls within the scope of the field of activity of the company, on behalf of itself or a third party. Accordingly, all kinds of acts and actions of the member realized on behalf of itself or third parties which fall within the scope of activity of the corporation would constitute the breach of the prohibition. The scope of this prohibition also encompasses joining the managing body of another corporation. Furthermore, depending on the specifics of a concrete case, the same member being an employee of a competitor corporation under a service contract, or providing consultancy services or extending facilities to a competitor, or benefiting from a job opportunity which belonged to the company may also be construed to be within the scope of the prohibition of competition. The second type is the member being engaged as a partner with unlimited liability in a corporation engaging in the same types of commercial activities. In this regard, if a member becomes a partner of an ordinary partnership or a collective corporation, or a partner with unlimited liability of a commandite corporation, which engages in activities that fall within the scope of activities of the joint stock company, the prohibition will be breached. The prohibition of competition of the board member with the company may be lifted by an authorization granted by the general assembly pursuant to article 396 of the Turkish Commercial Code. This permission to compete to be granted to a board member may be in the form of a prior approval or a later acknowledgement (ratification), in an expressed or implied manner. As a result of the member being permitted to compete, article 396 of the Turkish Commercial Code will no longer apply even if the member engages in activities in competition with the company. The prohibition to compete of the board member lasts for the duration of the board membership. Once the membership ends, the parties must conclude an agreement in order to continue the prohibition of competition. The said agreement regarding the prohibition of competition will be subject to form requirements to be valid. Pursuant to the liberty of contract inherent in the Law of Obligations, the parties may freely execute an agreement regarding the prohibition of competition, provided they comply with the provisions in paragraph 2 of article 23 of the Civil Code or article 26 and first paragraph of article 27 of the Turkish Commercial Code. The prohibition to compete of board members is valid as long as they execute the activities of the company, and within the geography where the clientele of the corporation is located. The fourth and last chapter of this work is devoted to the consequences of breach of the prohibition to compete by a board member. If a member of the board of directors violates this prohibition, the consequence of this breach is regulated in the first paragraph of art. 396 of the Turkish Commercial Code. Accordingly, the joint stock company is granted with certain elective rights. Such that, primarily the company may request compensation from the member in breach of the prohibition of competition. Second, it may be requested that the transaction is deemed concluded on behalf of the joint stock company, third, that the benefits arising from the agreement the member concludes on behalf of third parties belong to the joint stock company. In its request for compensation, the joint stock company must prove the action of the board member violating the prohibition of competition, that the corporation suffered losses from this activity, and the causal link between this activity and the loss of the company. In its request for the transaction to be deemed concluded on its behalf, the company requests for the economic consequences of the transactions the member concluded in violation of the prohibition of competition on its behalf. In its request for the benefits arising from the agreement, the company requests that benefits arising from the agreement the member concluded on behalf of third parties are left to itself. At this point, we materially benefited from the German doctrine and jurisprudence in explaining the claims requesting that a transaction is deemed concluded on behalf of the company and that the benefits from the transactions are left to the company. These rights granted in the first paragraph of article 396 of the Turkish Commercial Code are not cumulative but elective. Pursuant to the second paragraph of article 396 of the Turkish Commercial Code, the authority to chose one of the elective rights granted to the company belongs to the members of the board of directors, excluding the member having violated the prohibition of competition. The third paragraph of article 396 of the Turkish Commercial Code regulates a dual prescription period of three months and one year. These periods are with respect to the exercise by the company of its elective right to make a claim. The first is the period of three months whose commencement will be determined based on the knowledge by other members that an action subject to the prohibition of competition is realized or that a board member joined another corporation. The second period is the period of one year commencing from the realization of the action violating the prohibition to compete. This one-year period is independent from other members' knowledge that the prohibition to compete has been breached. The corporation may raise other claims against the member violating the prohibition of competition which are not stipulated under article 396 of the Turkish Commercial Code. Accordingly, the corporation may request that the member violating the prohibition of competition through joining a competing corporation as a partner with unlimited liability or joining the managing body of a competitive corporation resigns from this corporation or managing body. Further, the company may dismiss the member violating the prohibition of competition from board membership. Again, the company may initiate a lawsuit to cease the ongoing violation of the prohibition of competition by a board member, or a lawsuit of preclusion prior to probable breaches which have not yet occurred. In this chapter, lastly, the fourth paragraph of article 396 of the Turkish Commercial Code is assessed. This paragraph regulates that provisions governing liability of the members of the board of directors are reserved. This is a new provision which was not present in the abrogated Turkish Commercial Code no. 6762, newly introduced under the Turkish Commercial Code. In this context, we tried to determine the purpose and characteristics of this provision and concluded this work.
Keywords: Administrateurs; Anonim şirketler; Board of directors; Competition prohibition; Concurrence (interdiction); Joint stock company; Members of the board directors; Rekabet yasağı; Société par actions; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yönetim kurulu; Yönetim kurulu üyeleri

Hâkim pay sahibinin azınlığı şirketten çıkarma hakkı (Squeeze-out) - Keski̇n, Harun (Ankara Üniversitesi, 2022)
Klasik anlamdaki şirketten çıkarma düzenlemeleri, "haklı sebep" temeline dayanmaktadır. Bu düzenlemelerin en tipik özelliği, düzenlemiş oldukları çıkarma hakkı ile şirketin feshi kurumu arasında bir bağlantıya yer vermiş olmalarıdır. Bu bağlantı, haklı sebebe dayalı çıkarma düzenlemelerinin hizmet ettiği birincil amacı da ortaya koymaktadır: Şirketin devamlılığını sağlamak suretiyle ortaklar arasındaki menfaatler dengesi korumak. Türk hukukuna 6102 sayılı Türk Ticaret Kanunu ve 6362 sayılı Sermaye Piyasası Kanunu ile kazandırılan "squeeze-out" müessesesi ise daha farklı bir kuramsal temele dayanmaktadır. Bu müessese ile, şirkette genellikle %90-95 arasında nitelikli bir pay ve/veya oy oranına ulaşmış olan hâkim pay sahibine, azınlığın paylarını herhangi bir sebep göstermeden iktisap edip, onu şirketten çıkarma hakkı tanınmıştır. Böylece çıkarmanın ekseni, "haklı sebep" olgusundan "hâkimiyet" olgusuna kaymıştır. Kanun koyucuların bu şekilde bir çıkarma hakkını öngörmelerindeki temel sebep ise kurumsal nitelikte bazı amaçları gerçekleştirmek isteyen hâkim konumdaki pay sahiplerine bir imkân sunmaktır. Tezimizde, klasik anlamdaki çıkarma müesseselerinin dayanmış olduğu kuramsal temelden ayrılan "squeeze-out" kurumunun kuramsal temeli, düzenlemenin hangi amaçlarla öngörüldüğü meseleleri ele alınmakta; bu bağlamda, kurumun karşılaştırmalı hukuktaki ne şekilde düzenlendiği, kurumun ortaya çıkardığı sorunlar ve bu sorunların çözümüne yönelik önerilere yer verilmektedir. The classic rules designed for exclusion of a partner has a simple theoretical basis: A/an justified/objective reason (or in other words "good cause"). The most typical feature of these rules is they build a bridge between the exclusion right and the dissolution of the company. This bridge also shows the the primary purpose served by these rules which is to maintain the balance of interests among the partners by ensuring the continuity of the company. In comparison with the classical rules, the "squeeze-out" rules which have been introduced into Turkish law with the Turkish Commercial Code No. 6102 and the Capital Markets Law No. 6362, have a different theoretical basis. The controlling shareholder who has reached a qualified percentage of capital and/or voting rights (usually %90-95), has been granted the right to acquire the minority's shares without asserting any justified reason and exclude him from the company. Thus the idea behind the exclusion has been changed from "good cause" to the "dominance/control". The main reason for designing such an exclusion right is to provide an opportunity to the controlling shareholders trying to achieve institutional objectives in the company. In our thesis, the theoretical basis of the "squeeze-out" rules and the reasons for designing such a new exclusion right will be examined within the framework of other squeeze-out rules in comparative law. Within this context, the most common problems in squeeze-outs and suggestions for solving these problems are analyzed.
737725
Keywords: Actionnaire majoritaire; Actionnaire minoritaire; Anonim şirketler; Azınlık hakları; Capital companies; Dismissal from the partnership; Dominant position; Exclusion; Hakim durum; Joint stock company; Kanunlar 6362 sayılı; Laws 6362 numbered; Limited company; Limited şirketler; Minority rights; Ortaklıktan çıkarılma; Satın alma hakkı; Sermaye şirketleri; Société commerciale; Squeeze-out right; Turkish commercial law; Türk ticaret hukuku

Kripto varlıkların dış ticaret kapsamında değerlendirilmesi ve kripto varlıklar üzerine nicel bir araştırma - Koç, Tayfur Süleyman (Alanya Alaaddin Keykubat Üniversitesi, 2022)
Tez çalışmasının amacı, kripto varlıkların ödeme aracı olarak kullanımını dış ticaretin bileşenleri kapsamında değerlendirmek ve kripto varlıkların yurtdışı ödemelerde ve bireysel yatırımlarda kullanılmaları bağlamında, bireylerin tutumlarını etkileyen faktörleri incelemektir. Bu amaç doğrultusunda öncelikli olarak, kripto varlıkların para işlev ve özelliklerine ne ölçüde uyum sağladıkları hususunda tespitlerde bulunulmuştur. Ulusal paralara eşdeğer kılınan stabil fiyatlı kripto varlıkların geleneksel ve modern para işlevlerine uyumlu oldukları yönünde görüş bildirilmiştir. Para özellikleri açısından ele alındığında da "kabul edilebilirlik" ve "sıradanlık" dışındaki para özelliklerine, tüm kripto varlıkların uyum sağladıkları değerlendirilmiştir. Ayrıca kripto varlık birimleri parasal niteliklerine göre tasnif edilerek, değişken fiyatlı, stabil fiyatlı ve finansal ürünlere bağlanan kripto varlıklar olmak üzere, üç kategoriden oluşan bir sınıflandırma geliştirilmiştir. Para işlev ve özellikleri kapsamındaki tespitlerin ardından, önceden belirlenen dış ticaret bileşenlerinin özelinde kripto varlıkların mevcut ve muhtemel kullanım alanları incelenmiştir. Belirlenmiş olan dış ticaret bileşenleri, uluslararası para birimleri, uluslararası bankacılık, uluslararası lojistik, dış ticaret hukuku ve gümrük işlemleridir. Dış ticaret bileşenlerine yönelik değerlendirmelerde kripto varlıkların ödeme aracı olarak kullanımları esas alınmıştır ve değerlendirme sürecinde çalışma kapsamında oluşturulmuş olan kripto varlık sınıflandırmasının kategorileri için de görüşler oluşturulmuştur. Çalışma kapsamında kripto varlıklara yönelik bireysel tutumları irdelemek amacıyla ampirik bir araştırma gerçekleştirilmiştir. Araştırma kapsamında UTAUT-2 modelini temel alan bir araştırma modeli oluşturulmuş ve yurtdışı ödemelerde kullanım niyeti ile yatırımda bulunma niyeti olmak üzere, iki farklı bağımlı yapıyı etkileyen unsurlar irdelenmiştir. Yol katsayısı değerine (β) göre yurtdışı ödemelerde kullanım niyetini anlamlı ölçüde etkileyen yapıların önem sırasına göre, "performans beklentisi", "sosyal etki" ve "algılanan risk" adlı boyutlar olduğu bulgusuna ulaşılmıştır. Yatırımda bulunma niyetini anlamlı düzeyde etkileyen bileşenler ise sırasıyla; "performans beklentisi", "sosyal etki", "farkındalık" ve "algılanan risktir". Araştırma kapsamında bağımlı ve bağımsız yapılar arasındaki etkileşimi incelemek amacıyla etki büyüklüğü (f²) ve tahmin gücü (q²) değerleri de hesaplanmıştır. Yol katsayısı değerlerine göre modelin bağımlı yapılarını anlamlı düzeyde ve negatif yönde etkileyen "algılanan risk" boyutunun, f² değeri açısından anlamlı bir katkısının olmadığı görülmüştür. Ayrıca yol katsayılarına göre "performans beklentisi" bağımlı yapılar üzerinde en çok etkiye sahipken, etki büyüklüğüne göre en önemli yapı "sosyal etkidir". Bağımsız yapıların tahmin gücü (q²) değerleri de etki büyüklüğü (f²) değerleri ile paralel sonuçlar ortaya koymuştur. Ortaya koyulan ampirik araştırmanın sonucunda, örneklemin yurtdışı ödemelerde ve yatırım kararlarında kripto varlıkları kullanma eğilimleri açısından en önemli etmenlerin "performans beklentisi" ve "sosyal etki" olduğu sonucuna ulaşılmıştır. The aim of the thesis study is to evaluate the use of crypto assets as a payment instrument within the scope of the components of foreign trade and to examine the factors affecting the attitudes of individuals in the context of the use of crypto assets in foreign payments and individual investments. For this purpose, first, it was evaluated that to what extent crypto assets are compatible with money functions and features. It was stated that stable priced crypto assets, which are equivalent to national currencies, are compatible with traditional and modern money functions. When considered in terms of money features, it was evaluated that all crypto assets are compatible with money features other than "acceptability" and "ordinariness". In addition, crypto assets were classified according to their monetary characteristics, and a classification was developed consisting of three categories: variable priced, stable priced and crypto assets linked to financial products. After the evaluations within the scope of money functions and features, the current and possible usage areas of crypto assets were examined specifically for the previously determined foreign trade components. The determined foreign trade components are international currencies, international banking, international logistics, foreign trade law and customs procedures. Evaluations for foreign trade components were based on the use of crypto assets as a payment instrument and arguments were formed for the categories of the crypto asset classification created within the scope of the study during the evaluation process. Within the scope of the study, an empirical research was carried out to examine individual attitudes towards crypto assets. A research model based on the UTAUT-2 model was formed and the factors affecting two different dependent structures, namely "intention to use in foreign payments" and "intention to invest", were examined. According to the value of the path coefficient (β), it was found that the structures that significantly affect the intention to use in foreign payments are the dimensions called "performance expectancy", "social impact" and "perceived risk", in order of importance. The components that significantly affect the intention to invest are "performance expectancy", "social impact", "awareness", and "perceived risk", respectively. Effect size (f²) and predictive relevance (q²) values were also calculated to examine the interaction between dependent and independent structures within the scope of the research. It was seen that the "perceived risk" dimension, which affects the dependent structures of the model significantly and negatively according to the path coefficient values, does not have a significant contribution in terms of f² value. In addition, according to the path coefficients, "performance expectancy" has the largest impact on the dependent structures, while the most important structure according to the effect size is "social impact". The predictive relevance (q²) values of the independent structures also showed similar results with the effect size (f²) values. As a result of the empirical research, it was concluded that the most significant factors in terms of the tendency of the participants to use crypto assets in foreign payments and investment decisions are "performance expectancy " and "social impact".
Tez N°771944

Uluslararası muhasebe standartları ile OHADA muhasebe sisteminin karşılaştırılması - Moussa Hisseine, Amine (Sakarya Üniversitesi, 2022)
Ekonomilerin küreselleşmesi ve piyasaların globalleşmesi karşısında, ortak bir dile sahip olma arzusu giderek daha fazla hissedilmektedir. Bu ihtiyacı hafifletmek için dünya çapında, birçok ülke, kalite ve karşılaştırılabilir bilgiler için UFRS standartlarını benimsemenin uygun olduğunu düşünmüştür. Bu momentumda, SYSCOHADA muhasebe sistemi aracılığıyla OHADA alanı, 2017 yılında standartlarını UFRS ile uyumlu hale getirmeye karar vermiştir. Bu çalışmanın amacı, Uluslararası Muhasebe Standartlarını (UMS/UFRS), on yedi ülkedeki tüm varlıklarının muhasebesini yöneten Afrika'da Ekonomi Hukuku'nun Uyumlaştırılması Örgütü'nün muhasebe sistemi (SYSCOHADA) ile karşılaştırmaktır. Bu karşılaştırmalı analizin amacı, yukarıdaki iki muhasebe sisteminin benzerliklerini ve farklılıklarını ortaya koymaktır. Bu analiz UMS 1 : Finansal Tabloların Sunuluşu, UMS 2: Stoklar, UMS 7: Nakit Akış Tablosu, UMS 8: Muhasebe Politikaları, Muhasebe Tahminlerinde Değişiklikler Ve Hatalar, UMS 10: Raporlama Döneminden Sonraki Olaylar, UMS 12 :Gelir Vergileri, UMS 16 :Maddi Duran Varlıklar, UMS 19 :Çalışanlara Sağlanan Faydalar, UMS 20 :Devlet Teşviklerinin Muhasebeleştirilmesi Ve Devlet Yardımlarının Açıklaması, UMS 21 :Kur Değişiminin Etkileri, UMS 23 Borçlanma Maliyetleri, UMS 37 Karşılıklar, Koşullu Borçlar ve Koşullu Varlıklar, UMS 38 Maddi Olmayan Duran Varlıklar açısından yapılan muamelelere odaklanacaktır. Çalışma, her iki muhasebe standardı hakkında da iyi bir anlayışa sahip olmayı sağlayacaktır. Bu nedenle, yatırımcılar ve diğer tüm kişiler, SYSCOHADA ve Uluslararası Muhasebe Standartları ile ilgilenenler, bu iki muhasebe standardının finansal tablolarının karşılaştırılabilirliğini kolaylaştırmak amacıyla muhasebe düzenlemeleri hakkında iyi bir anlayışa sahip olabileceklerdir. Çalışma sonucunda SYSCOHADA ile Uluslararası Muhasebe Standartları arasındaki karşılaştırma birçok benzerlik ve çok az farklılık ortaya koymaktadır. Kıta Avrupası muhasebe sistemi ve Anglo-Sakson sisteminden kaynaklanan SYSOHADA hükümleri, kaynaklarını Uluslararası Muhasebe Standartlarında bulmaktadır. Ancak, bu iki standarttaki en büyük fark, SYSCOHADA için tarihsel maliyet ölçüm yöntemi ile UFRS için gerçeğe uygun değer arasındadır. In the face of the globalization of economies and the globalization of markets, the desire to have a common language is increasingly felt. To alleviate this need, many countries around the world have considered it appropriate to adopt IFRS standards for quality and comparable information. At this momentum, the OHADA field, through the SYSCOHADA accounting system, has decided to harmonize its standards with IFRS in 2017. The purpose of this study is to compare the International Accounting Standards (IAS/IFRS) with the accounting system of the Organization for the Harmonization of Economic Law in Africa (SYSCOHADA), which manages the accounting of all its assets in seventeen countries. The purpose of this comparative analysis is to reveal the similarities and differences of the above two accounting systems. This analysis will focus on the treatment of IAS 1 : presentation of financial statements IAS 2: Inventories IAS 7-cash flows IAS 8 accounting policies, changes in accounting estimates and errors IAS 10: events after the reporting period IAS 12 income taxes IAS 16 :property, plant and equipment assets IAS 19 :employee benefits IAS 20 :accounting for government grants and government assistance, description of TMS 21 :the effects of changes in foreign exchange rates IAS 23 borrowing costs, IAS 37 Provisions, Contingent Liabilities and Contingent Assets, IAS 38 intangible assets . The study will allow to have a good understanding on both accounting standards. Therefore, investors and all others persons interested in the SYSCOHADA and International Accounting Standards will be able to have a good understanding on the accounting regulations in order to facilitate the comparability of the financial statements of these two accounting standards. As a result of the study, the comparison between the SYSCOHADA and international accounting standards reveals many similarities and few differences. Originating from the continental European accounting system and the Anglo-Saxon system, the provisions of the SYSOHADA find their sources in International Accounting Standards. However, the major difference in these two standards is between the historical cost measurement method for the SYSCOHADA and the fair value for IFRS.
Keywords: Accounting; Accounting standards; African countries; Afrika Ticaret Kanunu Uyum Örgütü; Afrika ülkeleri; Comparative analysis; Comparison; International Accounting Standards; International accounting; Karşılaştırma; Karşılaştırmalı analiz; Muhasebe; Muhasebe standartları; Organization for the Harmonization of African Business Law; Uluslararası Muhasebe Standartları; Uluslararası muhasebe

Anonim şirketin sosyal sorumluluğu - Okuyucu, Deniz (İstanbul Üniversitesi, 2022)
Kurumsal sosyal sorumluluk her ne kadar son yıllarda Türk iş dünyasının radarına girmiş olsa da, şirketler hukukunun doğuşundan beri var olan hem bir tartışma konusu hem de bir temennidir. İşbu tez kapsamında, üzerinde uzlaşmaya varılmış bir tanımı bulunmayan kurumsal sosyal sorumluk kavramının, yıllardır bağlayıcı olmayan hukuk enstrümanları ile düzenlenmesinin bir adım ilerisine geçmesi amaçlanmaktadır. Bu adımın da, kavramın şirketler hukuku mevzuatı çerçevesinde bağlayıcı hukuk kuralı hâline getirilmesi ile mümkün olacağı savunulmaktadır. Araştırma metodolojisinde, yürürlükte olan mevzuat hükümleri analizine yoğunlaşılmış olmasının yanı sıra kavramın tarihsel gelişimi gereği bağlayıcı olmayan hukuk (soft law) düzenlemelerine de yer verilmiştir. Şirketlerin pay sahibi dışında; işçiler, alacaklılar, çevre ve toplum gibi diğer menfaat sahiplerinin de çıkarlarını göz önünde bulunduracak şekilde varlığını devam ettirmesinin hâlihazırdaki Türk hukuk mevzuatı ve özellikle de Türk Ticaret Kanunu hükümleri kapsamında mümkün olmadığı görülmektedir. Bu doğrultuda şirketin kâr elde etme amacının yumuşatılması, diğer menfaat sahiplerinin şirket içindeki konumlarının güçlendirilmesi, yönetim kurulu yapısının değiştirilmesi ve yönetim kurulu üyelerinin özen ve bağlılık yükümlülüklerinin kapsamının yeniden düzenlenmesi ile kurumsal sosyal sorumluluğun şirketler hukuku kapsamında temellendirilebileceği öne sürülmektedir. Although corporate social responsibility has entered the radar of Turkish business world in recent years, it is both a topic of discussion and a wish that has existed since the birth of corporate law. Within the scope of this thesis, it is aimed to go one step further than mentioning the concept of corporate social responsibility, which has no agreed definition, in only non-binding legal instruments for years. It is argued that this step will be possible by making the concept a binding legal rule within the framework of company law legislation. In the research methodology, besides focusing on the analysis of the legislation provisions in force, non-binding law (soft law) regulations due to the historical development of the concept are also included. Within the scope of the current Turkish legislation, especially the provisions of the Turkish Commercial Code, it is seen that it is not possible for companies to continue their existence in a way that takes into account the interests of other stakeholders such as workers, creditors, environment and society other than the shareholders. In this direction, it is claimed that corporate social responsibility can be grounded within the scope of company law by, inter alia, softening the company's aim of making profit, strengthening the positions of other stakeholders within the company, changing the structure of the Board of Directors and reorganizing the scope of Board of Directors' duty of care.
Keywords: Anonim şirketler; CSR; Company law; Corporate Social Responsibility; Corporate sustainability; Joint stock company; Kurumsal sosyal sorumluluk; Kurumsal sürdürülebilirlik; Multi-stakeholderism; Social responsibility; Sosyal sorumluluk; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Çok paydaşlılık; Şirketler hukuku

Kara eşya taşıma sözleşmelerinde taşıyıcıya teslimin hukuki sonuçları - Sar, Mustafa Seyfullah (İstanbul Ticaret Üniversitesi, 2022)
Mesafe ve sınırların ortadan kalkmasıyla uluslararası ticarette pozitif yönde ivme kazanılmıştır. Bu yolda uluslararası ekonomik ilişkilerin geliştirilmesi amacıyla yapılan anlaşmalar, kurulan örgütler, sağlanan teşvikler ve kaldırılan ithalat vergileri sayesinde, farklı ülkelerdeki firmalar ve bireyler, birbirleriyle daha hızlı bir şekilde alışverişe girmeye başlamış ve bunun sonucunda ticari faaliyetler ülke sınırlarını aşarak küresel boyutlara ulaşmıştır. Bunun sağlanabilmesi için taşıma sektöründe kullanılan araçlar detaylandırılarak daha güçlü hale getirilmiştir. Böylelikle malların dağıtımı daha ekonomik, güvenli ve hızlı bir şekilde gerçekleştirilmektedir. Bunun sonucu olarak taşıma sözleşmelerinin uluslararası ticaretteki yeri de giderek önem kazanmıştır. Öyle ki hakların ve borçların teminatı için sözleşme kaçınılmaz yoldur. Yakın tarihte, uluslararası alanda ticaretin daha kolay ve hızlı hale getirilmesi için yeknesak bir sistem oluşturulması ihtiyacı ortaya çıkmış ve buna binaen ulusal düzenlememiz olan TTK'nın yanında, uluslararası karayolu taşımacılığında, koşulları standardize eden, taşıyıcının sorumluluklarını belirleyen CMR Konvansiyonu oluşturulmuştur. Düzenlenen kurallar doğrultusunda, taşıyıcı eşyayı teslim aldığı andan teslim edinceye kadar zarardan ve kayıptan sorumlu olacaktır. Taşıyıcı, ancak TTK ve CMR'de yer alan genel ve özel kurtuluş karinelerinin varlığının ispatı halinde sorumluluktan muaf olabilecektir. Aksi halde taşıyıcı, meydana gelen zarar veya zayiatın oranı doğrultusunda sorumlu olacak ve buna müteakiben tazminat miktarı belirlenecektir. TTK ve CMR pek çok noktada benzerlik gösterse de bazı yönleriyle keskin farklılıklar mevcuttur. Uluslararası ticaretin bekası için önem oluşturan bu nokta özellikle sorumluluk hususunda hukuki tartışmaları da beraberinde getirmiştir. With the obstacle of distances and borders disappearing, international trade has gained speed in a positive direction. Thanks to deals and agreements that were made, organisations that were built, incentives that were provided, and removal of import taxes in order to improve economic relations with this respect, companies and people in different countries have started to be able merchandise with each other more quickly; consequently, tradal actions have crossed borders of lands and reached global level. For this to happen, vehicles used in the sector of transportation have been developed, thus made stronger and more elaborate. As a result of this, the distribution of goods can be ensured in a more economic, safer, and faster way, and the role of vehicle contracts in international trade has gradually gained importance as contracts are inevitable to ensure and guarantee rights and debts. In recent history, a need to have a uniform system that would enable international trade to be easier and faster was born, and consequently, in addition to our regulations on TTK (Turkish Commercial Code), CMR Convention which standardized conditions and determined the responsibilities that transporters have in international land transportation. According to the regulations, the transporters are responsible for the safety of the goods in case of a damage and loss) from the moment they take them until they deliver them. The transporters can only be exempt from this responsibility in the case that general and specific presumptions of innocence that a place in the law (TTK) and the CMR can be proven. Otherwise, the transporter shall be responsible for compensating for the damage or the loss that occurred and the cost for the indemnity shall be determined. Although TTK and CMR Convention have similarities in many regards, in some ways they are distinctively different from one another. This point which has a critical role in the future of international trade has brought about many juridical discussions, especially ones related to responsibilities.
728226
Keywords: Contracts; Delivery; Eşya taşıma; Goods transportation; Highway Route with International Furniture Removal Agrement; Highway transportation; Kara yolu taşımacılığı; Karayolu ile Uluslararası Eşya Taşıma Sözleşmesi; Obligation to delivery; Sözleşmeler; Teslim borcu; Teslimat; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Anonim şirketlerde ilişkili taraf işlemleri - Şi̇mşek, Bahar (İstanbul Üniversitesi, 2022)
İlişkili taraf işlemlerine ilişkin özel düzenlemelerle şirketin varlıklarının ilişkili taraflara aktarılması ve şirketin ve şirketin bütün menfaat sahiplerinin hâkim pay sahipleri ve yöneticiler tarafından sömürülmesinin engellenmesi amaçlanır. Bu amaçla ilişkili taraf işlemleriyle ilgili Sermaye Piyasası Kanunu'nda etraflıca bir düzenleme getirilmiş ve önemli bazı işlemler için prosedür öngörülmüştür. Çalışmamız, esaslı düzenleme Sermaye Piyasası Kanunu'nda yer aldığı için bu düzenleme temel alınarak şekillendirilmiştir. Ancak sadece halka açık şirket değil; halka kapalı şirketler yönünden de konu incelenmiş, ilişkili taraf işlemi sayılabilecek Türk Ticaret Kanunu'nda ve diğer kanunlarda yer alan diğer düzenlemelere de yer verilmiştir. Tez dört bölümden oluşmaktadır. İlk bölümde ilişkili taraf işlemi kavramı genel olarak açıklanmış, ilişkili taraf işlemleriyle ilgili düzenlemelere neden ihtiyaç olduğu hususu ortaya koyulmaya çalışılmıştır. Bu kapsamda benzer kavramlarla karşılaştırılmış ve Avrupa Birliği ve çeşitli ülkelerde düzenlemeler incelenmiştir. Nihai olarak Türk hukukunda ilişkili taraf işlemlerinin tarihsel sürecine yer verilmiştir. İkinci bölümde yasal düzenlemelerdeki ilişkili taraf ve ilişkili taraf işlemi kavramı ele alınmıştır. Üçüncü bölümde ise ilişkili taraf işlemleriyle ilgili Sermaye Piyasası Kanunu, Türk Ticaret Kanunu ve bazı özel kanunlarda yer alan düzenlemeler incelenmiş, ilişkili taraf işlemleri için öngörülen prosedürel korumalar açıklanmıştır. Dördüncü bölümde ise hukuka aykırı ilişkili taraf işlemlerinin sonuçları incelenmiş ve ilgililerin sorumluluğuna yer verilmeye çalışılmıştır. Special regulations regarding related party transactions aim to prevent the transfer of the assets of the joint stock company to the related parties and thus prevent the exploitation of all the stakeholders of the company by the controlling shareholders and managers. For this purpose, a comprehensive regulation has been introduced in the Capital Markets Law regarding related party transactions and a procedure has been envisaged for some significant transactions. Since the main regulation is contained in the Capital Markets Law, our thesis has been shaped based on this regulation. However, this thesis has not examined the subject only for public companies; it has also examined it in terms of non-public companies, and other regulations in the Turkish Commercial Code and other laws, which can be considered as related party transactions. The thesis consists of four parts. In the first part, the concept of related party transactions is explained in general and the reason for the need for regulations regarding related party transactions is tried to be revealed. In this context, related party transactions have been compared with similar concepts and the regulations in the European Union and various countries have been examined. Finally, the historical process of related party transactions in Turkish law is examined. In the second chapter, the concept of related party and related party transactions as defined in legal regulations is discussed. In the third section, the regulations contained in the Capital Markets Law, the Turkish Commercial Code and some special laws related to related party transactions are examined and the procedural protections provided for related party transactions are explained. In the fourth chapter, the results of unlawful related party transactions are examined and the liability of the related parties is tried to be included.
Keywords: Anonim şirketler; Camouflage of earning distribution; Joint stock company; Société par actions; Turkish capital market; Turkish commercial law; Türk sermaye piyasası; Türk ticaret hukuku; Örtülü kazanç dağıtımı

Anonim ortaklıkta pay sahibinin bilgi alma ve inceleme hakkı - Sümer, Burak (Hacettepe Üniversitesi, 2022)
Anonim ortaklıkta her pay sahibi genel kurulda, yönetim kurulundan şirketin işleri; denetçilerden ise denetimin yapılma şekli ve sonuçları hakkında bilgi alma talebinde bulunma hakkına sahiptir. Ayrıca her pay sahibinin şirketin ticari defterlerini ve yazışmalarını, sorusunu ilgilendiren kısımları ile sınırlı olarak inceleyebilme hakkı bulunmakla birlikte, bunun için genel kurulun açık izni veya yönetim kurulunun bu hususta kararı gereklidir. Pay sahibinin bilgi alma ve inceleme hakkının reddi, talep edilen bilginin şirket sırlarının açıklanmasına veya korunması gereken diğer şirket menfaatlerinin tehlikeye girmesine neden olabilecek ise söz konusu olabilir. Bilgi alma ve inceleme talebinin cevapsız bırakılması, haksız olarak reddedilmesi, ertelenmesi veya pay sahibinin kanunda düzenlendiği şekilde bilgi alamaması halinde, hakkın açılacak bir dava ile mahkeme aracılığıyla kullanılması da mümkündür. Çalışmamız dört bölümden oluşmaktadır. İlk bölümde bilgi alma ve inceleme hakkının genel nitelikleri ile karşılaştırmalı hukuktaki düzenlenme şekli; ikinci bölümde hakkı etkileyen ilkeler ve hakkın düzenlenme amacı; üçüncü bölümde bilgi alma ve inceleme hakkının kullanılması ve hakkın sınırları; dördüncü ve son bölümde ise hakkın ihlalinin hukuki sonuçları ele alınmıştır. At the general meeting, any shareholder of a joint stock company is entitled to information from the board of directors on the affairs of the company and from the external auditors on the methods and results of their audit. Also the company ledgers and business correspondence, limited to the parts about the question may be inspected only with the express authorisation of the general meeting or by resolution of the board of directors. It may be refused where providing it would jeopardise the company's trade secrets or other interests warranting protection. If the request for information and examination is left unanswered, unfairly rejected, postponed or if the shareholder is unable to obtain information as regulated in the law, it is also possible to exercise the right through a lawsuit to be filed. Our study consists of four parts. In the first part, the general characteristics of the right to information and examination and the way it is regulated in comparative law; in the second part, the principles affecting the right and the purpose of regulation of the right; the exercise of the right to receive and review information and the limits of the right in the third part; In the fourth and last chapter, the legal consequences of the violation of the right are discussed.
Keywords: Anonim ortaklıklar; Bilgi alma ve inceleme hakkı; Company law; Incorporated companies; Pay sahipleri; Right to information and examination; Shareholders; Turkish commercial law; Türk ticaret hukuku; Şirketler hukuku

Halka açık anonim şirketler bakımından şirketler topluluğunda ortak nakit ve hizmet kullanımının hukuki sonuçları - Üzeler Demi̇rağ, Rabia Sanem (İhsan Doğramacı Bilkent Üniversitesi, 2022)
Bu çalışmanın temel amacı şirketler topluluğunda yer alan halka açık şirketlerin topluluk şirketleri ile ortak nakit ve hizmet kullanımına yönelik işlemlerinin sermaye piyasası mevzuatı açısından sınırlarının ve hukuki sonuçlarının tespit edilmesidir. Bu doğrultuda sermayenin oluşturulması ve malvarlığının korunması kuralları kapsamında ortak nakit kullanımı uygulamalarının sınırları, ilişkili taraf işlemlerine ilişkin düzenlemeler ve örtülü kazanç aktarımı yasağı çerçevesinde değerlendirilmiştir. İlaveten, şirketler topluluğunda maliyet tasarrufu sağlayan ve topluluğun ortak stratejiler çerçevesinde yönetilmesi bakımından gerekli olan ortak hizmetler nedeniyle yapılan ödemelerin tutarlarının belirlenmesine ilişkin esaslar örtülü kazanç aktarımı yasağı bağlamında ele alınmıştır. Son olarak, hukuka aykırılığa yol açan ortak nakit ve hizmet kullanımı uygulamalarına yönelik Sermaye Piyasası Kurulu'nun müdahale yetkileri ve şirketler topluluğunda hâkim şirketin bağlı şirketin kaybını denkleştirebilmesi olanağının halka açık şirketlerde uygulama alanı bulmasının hukuken hangi hâllerde gündeme gelebileceği irdelenmiş ve halka açık şirketlerin dâhil oldukları şirketler topluluklarında ortaya çıkan menfaat çatışmalarının dengelenmesine yönelik değerlendirme ve düzenleme önerilerinde bulunulmuştur. The main purpose of this study is to determine the legal limits and consequences of the shared use of cash and services within corporate groups for publicly held companies' in relation to capital markets legislation. In this respect, the legal limits of transactions which enables sharing cash among group companies with respect to rules on formation and protection of capital of publicly held companies is reviewed within the context of related party transactions and cases which may result in disguised profit distribution is evaluated. Additionally, the use of shared services in corporate groups which provides significant savings and is necessary for developing common strategies is examined in order to determine which principles must be adhered to while charging for these services with regard to the ban on disguised profit distribution. Furthermore, Capital Markets Boards' intervention powers regarding the shared use of cash and services which results in violation of the law is evaluated and the parent company's opportunity of balancing the disadvantages of the subsidiary is assessed for publicly held companies. Finally, legislative amendments have been proposed in order to balance the conflicts of interest which arises where a publicly held company is part of a corporate group.
Keywords: Anonim şirketler; Capital Market Board; Capital Market Law; Cash flow; Cash management; Cosourcing; Halka açık ortaklıklar; Joint stock company; Nakit akışı; Nakit yönetimi; Ortak kaynak kullanımı; Public held companies; Sermaye Piyasası Kanunu; Sermaye Piyasası Kurulu; Turkish commercial law; Türk ticaret hukuku

Geçmişe etkili sigorta - Yolal, Oğuz (Selçuk Üniversitesi, 2022)
Sigorta ettiren genellikle geleceğe etkili olarak sigorta korumasından yararlanmak üzere sigorta sözleşmesi yapmaktadır. Ancak sigorta ettiren, sözleşmenin kurulmasına ilişkin öneri ile sözleşmenin kurulması arasında veya sözleşmeye ilişkin önerinin yapıldığı tarihinden önce sigorta korumasından yararlanmak isteyebilir. Sigorta ettirenin sözleşmenin kurulmasından önce sigorta korumasından yararlanabilmesi, geçmişe etkili sigorta ile mümkün olmaktadır. Geçmişe etkili sigorta TTK m. 1458 hükmünde düzenlenmiştir. Geçmişe etkili sigorta sözleşmesinin kurulabilmesi için ikisi olumlu bir tanesi olumsuz şart olarak üç şartın bulunması gereklidir. Olumlu şartlar, sigorta sözleşmesine ilişkin mutabakatın bulunması ve sigorta sözleşmesinin kurulması; olumsuz şart ise, sigortacı, sigorta ettiren ve sözleşmeden haberdar olmak şartıyla sigortalının rizikoya ilişkin bilgi sahibi olmamasıdır. Bu şartların sağlanması hâlinde, geçmişe etkili sigorta sözleşmesi geçerli olacak ve böylelikle sigorta koruması, sigorta sözleşmesinin kurulduğu tarihten önce başlayacaktır. Geçmişe etkili sigorta gerçek ve gerçek olmayan geçmişe etkili sigorta olarak ikiye ayrılmaktadır. Gerçek geçmişe etkili sigorta, sigorta korumasının sözleşmenin kurulmasına ilişkin önerinin yapıldığı tarihten önce başladığı sigortadır. Gerçek ol-mayan geçmişe etkili sigorta ise, sigorta ettirenin sözleşmeye ilişkin öneride bulun-duğu tarih ile sözleşmenin şekli olarak kurulduğu tarih arasında sigorta korumasının sağlandığı sigorta olarak isimlendirilmektedir. Nitekim TTK m. 1458 düzenlemesinin ilk cümlesinde de, sigorta korumasının "sözleşmenin yapılmasından önceki bir tarihten itibaren" sağlanabileceği belirtilerek, gerçek veya gerçek olmayan geçmişe etkili sigortanın yapılmasının mümkün olduğu anlaşılmaktadır. The insured generally makes an insurance contract in order to benefit from insurance protection effectively for the future. However, the policyholder may wish to benefit from insurance protection between the proposal for the conclusion of the contract and the conclusion of the contract or before the date of the proposal regarding the contract. It is possible for the insurant to benefit from insurance protection before the conclusion of the contract, with retroactive insurance. Retroactive insurance TCC m. It was regulated in the 1458 provision. In order for a retroactive insurance contract to be established, three conditions must be present, two of which are positive and one is negative. Positive terms, agreement on the insurance contract and establishment of the insurance contract; The negative condition is that the insurer, the policyholder and the insured are not informed about the risk, provided that they are aware of the contract. If these conditions are met, the retroactive insurance contract will be valid and thus insurance protection will start before the insurance contract is established. Retroactive insurance is divided into two as real and unreal retroactive insurance. Actual retroactive insurance is insurance in which insurance protection begins before the date of the proposal for the establishment of the contract. Unreal, retroactive insurance, on the other hand, is called insurance in which insurance protection is provided between the date the policyholder makes a proposal regarding the contract and the date the contract is formally established. As a matter of fact, TTK art. In the first sentence of regulation 1458, it is understood that it is possible to make real or non-real retroactive insurance, by stating that insurance protection can be provided "from a date before the conclusion of the contract".
Keywords: Geçmişe etkili sigorta; Insurance; Insurance contracts; Insurance law; Insurance sector; Recroactive insurance; Sigorta; Sigorta hukuku; Sigorta sektörü; Sigorta sözleşmeleri; Turkish commercial law; Türk ticaret hukuku

Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması - Babayev, Ilgar (İstanbul Ticaret Üniversitesi, 2021)
Uluslararası ticaretin gelişimi ve artması dünyadaki bütün devletler tarafından hedeflenen bir amaçtır. Ancak devletlerin ulusal hukuk sistemleri arasındaki farklar bu gelişim için belirli engeller oluşturmaktadır. Bu engelleri aşmak için uluslararası ticaret hukukunun yeknesaklaştırılması, yani aynı uluslararası hukuki işleme uygulanacak iki veya daha çok ulusal hukuk sisteminin farklı kurallarının bir kuralla değiştirilmesi çare olarak görülmektedir. Bu amaçla şimdiye kadar bir çok çalışmalar yapılmış ve bir çok yeknesaklaştırma aracı ortaya konulmuştur. Uluslararası ticaret hukukunun bel kemiğini oluşturan uluslararası ticari sözleşmeler alanında hazırlanmış olan yeknesaklaştırma araçları ise bu bakımdan özellikle önem taşımaktadır. Hukukun yeknesaklaştırılması alanında çalışmalar sürdürülmekle birlikte bu konuya şüpheyle bakanlar ve yeknesaklaştırmanın kendi amacına ulaşamayacağını düşünenler de mevcuttur. Bu yeknesaklaştırma sürecinde ortaya çıkan bir takım sorunlarla ilgilidir. Ancak özellikle de uluslararası ticaret hukuku alanında yapılan yeknesaklaştırma çalışmalarında elde edilen başarılar umut vaat etmektedir. Uluslararası ticari sözleşmeler hukuku alanında yapılmış olan ayrı ayrı yeknesaklaştırma çalışmaları ile ilgili araştırmalar mevcut olsa da, konuyu daha kapsamlı bir şekilde ele alan ve meseleye daha geniş bir perspektiften bakan araştırmaların eksik olduğunu görmekteyiz. Özellikle de Türkiye'de bu tür araştırmalarda bir boşluğun mevcut olduğu hissedilmektedir. Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması amacıyla ortaya konulmuş çalışmaların ve hazırlanmış olan araçların daha kapsamlı bir şekilde araştırılması, onların sağladığı faydaları göstermek, bu alanda ortaya çıkan sorunları belirlemek ve gerekli çözüm önerileri sunmak açısından önem arz etmektedir. Bütün bunları dikkate alarak biz bu araştırmamızda uluslararası ticaret hukukunun yeknesaklaştırılması kavramını, onun önemini ve sağladığı avantajları, yeknesaklaştırmanın gerçekleştirilmesi yöntemlerini, uluslararası ticaret hukukunun yeknesaklaştırılması alanında çalışmalar yapan ve bu sürece katkıda bulunan uluslararası kurumları, uluslararası ticari sözleşmeler alanında yapılmış olan ve şu an yapılmakta olan çalışmaları, bu konuyla ilgili ortaya çıkan sorunları ve bu sorunların ortadan kaldırılması için sunulan çözüm önerilerini incelemeye çalıştık. [...] The development and growth of international trade is an aim targeted by all states in the world. However, the differences between the national legal systems of states pose certain obstacles to this development. To overcome these obstacles, the unification of the international commercial law is considered a remedy, that is, changing the different rules of two or more national legal systems to be applied to the same international legal process with one rule. For this purpose, so far many studies have been done and many unification instruments have been introduced. The unification instruments prepared in the field of the international commercial contracts, which form the backbone of international commercial law, are particularly important in this regard. Although studies on the unification of the law continues, there are also those who are skeptical about this issue and those who think that it cannot achieve its own goal. It concerns a number of problems that arise in the process of unification. However, the successes achieved in the unification studies especially in the field of international commercial law promise hope. Although there are researches on individual unification studies in the field of international commercial contracts law, we see that there is a lack of research that covers the issue more extensively and looks at the issue from a wider perspecitve. Especially, a vacancy in this kind of research is available in Turkey. It is important to investigate the studies and the instruments that have been prepared for the purpose of the unification of the international commercial contracts law, to show their benefits, to identify the problems that arise in this field and to offer necessary solutions. Considering all these, in this research, we tried to examine the concept of the unification of the international commercial law, its importance and advantages, the methods of realization of unification, the international institutions that work in the field of the unification of the international commercial law and contribute to this process, the problems that arise about this issue and the proposed solutions to eliminate these problems.
Keywords: Hukukun Yeknesaklaştırılması; International Commercial Contracts Law; International Commercial Law; International commercial contracts; Lex Mercatoria; Uluslararası Ticaret Hukuku; Uluslararası Ticari Sözleşmeler; Uluslararası Ticari Sözleşmeler Hukuku; Unification Instruments; Unification of Law; Yeknesaklaştırma Araçları

Yönetim kurulu krizleri ve çözüm yolları - Meti̇n, Umut (Kadir Has Üniversitesi, 2021)
YK farklı sorunlar veya uyuşmazlıklarla yüzyüze gelebilir. Sorunlar veya uyuşmazlıklar kriz halini alarak YK'nın işleyişine olumsuz etki edebilmektedir. Kriz derinleştikçe, YK işlevini yerine getirmekte zorlanabilir. Krizin bir adım ötesinde ise YK kilitlenebilmektedir. Pay sahipleri arasındaki menfaat çatışmaları, YK kriz ve/veya kilitlenmesinin en sık rastlanan temel nedenidir. Kilitlenme durumunda, YK toplantı yapamamakta veya karar alamamaktadır. Oysa ki, YK her daim çalışabilmesi gereken bir organdır. YK'nın kilitlenmesi, şirketin de kilitlenmesi sonucu doğurabilir. Bu durum öyle risklidir ki, şirketin feshi/tasfiyesi yakın bir ihtimal olabilmektedir. Bu aşamada kilidin olabildiğince hızlı açılması şirketten menfaati olan herkes için (pay sahipleri, YK üyeleri, çalışanlar, alacaklılar, kamu vb.) hayati önemdedir. Bu nedenle, şirket esas sözleşmesinde YK kriz ve kilitlenmelerine karşı önlemler planlanmalıdır. Tek kişiden ibaret YK modeli ve YK'ya danışma kurulu desteği kilitleme riskine karşı önerdiğimiz modeldir. Pay sahipleri sözleşmesi, aile şirketleri için aile anayasası gibi hukuki metinler kriz ve/veya kilitlenmeye ilişkin tedbirler içermelidir. Önlemlere, rağmen kilitlenme gerçekleşir ise, öncelikle YK içi ve şirket içi çözümler uygulamaya konulmalıdır. Bu tür yöntemler yeterli olmazsa, AUÇY'nin tatbiki, şirket dışından gelen çözümün ilk aşaması olarak kabul edilmelidir. Arabuluculuk ile YK kriz ve kilitlenmelerine karşı etkin, hızlı ve kalıcı çözümler sağlanabilmektedir. "Med-arb" veya "Arb-med" gibi yöntemlerden de faydalanılabilir. Tahkim de bir çözüm yoludur. Bu yolda "seri tahkim usulü" YK kilitlenmeleri için daha uygundur. Son çare olarak nitelediğimiz, dava yolu ise, bazı durumlarda içinde şirketin fesih ve tasfiye riskini barındırdığı için kilidi açmak ve hatta kilidi kırmak için uygulamaya konulabilir. Mahkemelerde, organ yokluğuna dayalı fesih davası ve özellikle haklı sebeple şirketin feshi davası çözüm sağlayabilecek dava tipleridir. Özellikle, haklı sebeple şirketin feshi davası, kriz ve kilitlenmelere daha uygun olup, stratejik sonuçlara da imkân vermektedir. Bunlar yanında, YK işleyişinde yapay zekâdan faydalanmanın mümkün olup olmadığı, yapay zekâya YK üyesi olarak kişi statüsü verilip verilemeyeceği, bu meselenin YK üyelerinin sorumluluğuna etkisi incelenmiştir. Board of Directors may face various disputes or disagreements. These disputes or disagreements may turn into crises which negatively affect the normal functioning of the board. As the crisis deepens, Board of Directors could have difficulties in fulfilling its function. Moreover, a step further from the crisis, Board of Directors might even be locked up. Conflicts of interest among shareholders are known as the most common cause of the board of directors crisis and/or deadlock. In event of a deadlock, Board of Directors, a body should always be able to function, cannot hold meetings or make decisions anymore. The deadlock of board of directors, may lead the entire company to be locked down whereas the company may encounter the possibility of dissolution and liquidation. At this point, unlocking the crisis as quickly as possible is vital for relevant competent persons of the company. Therefore, measures should be taken in the company's articles of association against Board of Director crisis and/or deadlock. One-person Board of Directors model and support of Advisory Board to Board of Directors is the model we recommend against the risk of locking. Legal texts such as shareholder agreements and family constitutions for family companies should include measures regarding deadlock. If a deadlock has occurred in spite of precautions, first of all, Board of Directors and internal remedies should be implemented. If such methods are not sufficient enough, Alternative Dispute Resolution (ADR) methods should be regarded as the first stage of external intervention. Effective and rapid solutions can be achieved against deadlocks via mediation. "Med-arb" or "Arb-med" could be also utilised. Arbitration is also a way and in this way; "expedited (fast-track) arbitration" procedure is more suitable for corporate deadlocks. Litigation, as the last possibility that we propose, could also be applied to unlock or even break the lock, since it contains the risk of dissolution and liquidation of company in some cases. In courts, termination action based on the absence of organs and especially termination of the company with a valid reason are the types of cases that may provide a solution. Especially termination of the company with a valid reason is more suitable for crisis and deadlocks, and also grants strategic results. In addition to these, it has been questioned in this study whether Board of directors possibly benefit from artificial intelligence in the operations and whether AI can be attributed a person-status as a member of Board of Directors. The effects of this issue on the responsibility of the members of Board of Directors have been analysed.
Keywords: Absence of body; Arabuluculuk; Arbitration; Artificial Intelligence; Board directors; Conseil d'administration; Crisis; Deadlock; Inteligência artificial; Intelligence Artificielle; Kilitlenme; Kriz; Mediation; Members of the board directors; Médiation; Organ yokluğu; Tahkim; Yapay zeka; Yönetim kurulu; Yönetim kurulu üyeleri

OHADA bölgesinde yabancı yatırımlara ilişkin hukuki sorunlar « Türk hukuku ile karşılaştırmalı olarak » - Useni, Ahmed Emedi (İstanbul Ticaret Üniversitesi, 2021)
OHADA bölgesindeki yabancı yatırımların yasal korunması bahassederken yasal mekanizmaların varlığı fikrine atıfta bulunur. Yabancı yatırımlarının korunmasının sağlanması Bu Örgüte üye olmayan ülkelerin vatandaşları. Mukayese arama sürecinde Türk hukuku ile anlayışlı olmalıdır. Bu yatırımlar için optimal yasal güvenlik modeli olmalidir çünkü OHADA yasa nispeten yeni ve yapım aşamasındadır. Talking about the legal protection of foreign investments in the OHADA zone inevitably refers to the idea of the existence of legal mechanisms capable of ensuring the protection of investments of economic operators who are nationals of non-member countries of this Organization. The comparison with Turkish law must to be understanding in the process of seeking the model of optimal legal security for these investments, because the OHADA law remains relatively new and under construction.
https://tez.yok.gov.tr/UlusalTezMerkezi/TezGoster?key=tqUiYt63sTQLTpozMJ92QppmfBTCxeWntSm8WuGV7UbfQesqsfYTJBeuQ5wKcBdH
Keywords: Company law; Comparative law; Foreign capital investments; Hukuksal korunma; Investissement étranger; Investments; Karşılaştırmalı hukuk; Legal protection; Organization for the Harmonization of African Business Law; Ticaret Kanunu Uyum Örgütü; Turkish law; Türk hukuku; Yabancı sermaye yatırımları; Şirketler hukuku

Medeni usul hukukunda inşai hüküm - Büyük, Elif Irmak (Marmara Üniversitesi, 2020)
ukuk davaları yaygın şekilde mahkemeden istenen hukuk himayeye göre bir sınıflandırılmaya tabi tutulmaktadır. Kişiler arasında geçerli olarak kurulan bir hukuki ilişkiyi bertaraf ederek yeni bir hukuki durum tesis eden davalar inşai davalar, bu davaların kabulü üzerine verilen mahkeme kararları ise inşai hükümler olarak adlandırılır. İnşai hükümler o zamana kadar var olmayan, ancak hükmün kesinleşmesiyle birlikte ortaya çıkan bir yeni bir hukuki durum yaratırlar. Kural olarak inşai hükümler herkese karşı etkilidir ve istenilen etkiyi doğurmak için icraya ya da herhangi bir aracıya ihtiyaç duymazlar. Özel hukuk alanında inşai davalar aile hukuku ve ticaret hukukunda yoğunlaşmakla birlikte, usul hukuk ve takip hukuk alanında inşai dava örnekleri de bulunmaktadır. Keza çekişmeli yargıda olduğu kadar çekişmesiz yargı işlerinde, geçici hukuki koruma tedbirleri görünümünde de inşai sonuç doğuran mahkeme kararlarına rastlanır. Bu tezde inşai hükümle ilgili temel kavramlar ele alındıktan sonra inşai hükmün özellikleri, türleri ve hükmün inşai etkisi başlıkları ayrıntılı bir şekilde ele alınacak; problemli gördüğümüz hususlarla ilgili kişisel önerilerde bulunulacaktır. Civil lawsuits are commonly subject to a classification according to the legal protection required from the court. Lawsuits which establish a new legal situation by eliminating a legal relationship established between individuals, are called constitutive lawsuits, and court verdicts made upon the acceptance of these lawsuits are called constitutive judgments. The constitutive judgments create a new legal situation that did not exist until then, but emerged with the finalization of the judgment. Likewise, as a rule, constitutive judgments are inter omnes effective against everyone and do not require execution or any means to produce the desired effect. In the field of private law, constitutive lawsuits are concentrated mostly in family law and commercial law, but there are also examples of constitutive lawsuits in the field of procedural law and law of execution. Moreover, in the area of non - contentious jurisdiction and temporary legal protections, constitutive court decisions are also exist. After considering the basic concepts related to the constitutive judgments, the features, the types and the titles of the constitutive judgments will be discussed in detail in our dissertation. Later on personal suggestions will be made on issues we consider problematic.
Keywords: Constitutive judgment; Constitutive lawsuits; Law of civil procedura; Medeni usul hukuku; İnşai davalar; İnşai hüküm

Şirketlerin insan hakları sorumluluğuna hak temelli bir yaklaşım: İnsan hakları due diligence'i (Human right due diligence) - Çimrin Ardiç, Çiğdem (İstanbul Bilgi Üniversitesi, 2020)
Çokuluslu şirketlerin etki alanı küresel olmakla birlikte, gerçekleştirdikleri faaliyetlerdeki menfaatleri özeldir ve nihai hedefleri de kârlılıklarını arttırmaktır. 1970'lerden itibaren çokuluslu şirketlerin dünyanın ekonomik kalkınmasına hizmet edebileceğine yönelik toplumsal beklentinin gerçekçi olmadığı ciddi insani ve çevresel maliyetleriyle birlikte anlaşılmıştır. Gerçekten de, neoliberal politikalar, ekonomik küreselleşme ve uluslararası yatırım antlaşmaları rejimiyle daha da güç ve nüfuz kazanan çokuluslu şirketlerin sebep olduğu siyasi, ekonomik, hukuki, çevresel ve sosyal sorunlar günümüzde belirgin bir hale gelmiştir. Toplumsal ve küresel eşitsizliklerin ve adaletsizliklerin daha da derinleşmesi kamuoyunda büyük endişe yaratmaktadır. Yaşanmakta olan bu süreç, insan haklarını koruma ve mağduriyetleri telafi mekanizmalarının yetersizliklerini gözler önüne sermektedir. Çokuluslu şirketlerin faaliyetlerini nasıl gerçekleştirdiğine veya güçlerini ne yönde kullandıklarına ilişkin hesap verilebilirliğin sağlanabilmesi için ortaya çıkan toplumsal beklentinin karşılanabilmesi amacıyla, 2011 yılında Birleşmiş Milletler İnsan Hakları Konseyi tarafından oybirliğiyle kabul edilen Rehber İlkeler çerçevesinde, devletlerin insan haklarını koruma ödevlerinin yanı sıra şirketlerin de insan haklarına saygı gösterme sorumluluğunun olduğu ve bu sorumluluğun gereklerini yerine getirmek için insan hakları etki incelemesi (HRDD) yapmaları gerektiği açık bir şekilde ifade edilmiştir. Şirketlere atfedilen bu insan hakları sorumluluğunun uluslararası hukukta ve uluslararası insan hakları hukukunda temellendirilmesi önem taşımaktadır. Zira, çokuluslu şirketlerin tedarik zincirlerindeki uygulamaları, uluslararası hukukun emredici kurallarının (jus cogens) ihlallerini de içeren birçok insan hakları ihlallerine sebebiyet vermektedir. Ancak, iç hukuk sistemlerinde çokuluslu şirketlerin örgütlenme biçimleri ve tüzel kişilik perdesinden kaynaklanan kısıtlar nedeniyle hesap verilebilirlikleri sağlanamamaktadır. Gerçekten de, iş dünyası ve insan hakları alanının esas tartışması ve sermayenin insan hakları ihlalleri kaynaklı yaşanan adaletsizliklerin esas nedeni, çokuluslu şirketlerin insan hakları sorumluluğunun sağlanabilmesine karşı en başta ticaret hukuku ve sözleşmeler hukuku olmak üzere iç hukukta yer alan yasal engeller, liberalizmin kalıplaşmış bakış açılarının aşılamaması ve çokuluslu sermayenin (yabancı yatırımın) ekonomik kalkınmayı ve toplumsal gönenci beraberinde getireceğine yönelik gerçekdışı beklentidir. Şirketlerin sahip olduğu insan hakları sorumluluğu uluslararası örf ve âdet hukuk normu olarak belirdikten sonra Rehber İlkeler kapsamında beyan edilmiş, HRDD de bu sorumluluğunun gereklerini ifa edilebilmesi için önemli ve gerekli bir risk tespit aracı olarak öngörülmüştür. Devletlerin insan haklarını koruma ödevleri gereği, şirketlerden hesap sorulabilirliğin ve hak mağdurlarının adalete erişimlerinin sağlanabilmesi için iç hukuk engellerini kaldırması ve/veya hesap sorulabilirliği kolaylaştırıcı iç hukuk düzenlemeleri yapması gerekmektedir. Son dönemde özellikle Avrupa Birliğinde ve Avrupa Birliğine üye olan devletlerde yaşanan yasal gelişmeler de bu gerekliliğin bir sonucudur. Even though the domain of multinational companies is global, their interests are private and their ultimate goal is to increase their profitability. Since 1970s, it has been understood that the social expectation that multinational companies can serve for the economic development of the world is not realistic and this understanding was gained with serious human and environmental costs. Indeed, the political, economic, legal, environmental and social problems caused by the mutinational companies, who have assumed more power and influence through widespread neoliberal policies, economic globalization and international investment treaties regime, have become more evident today. The intensification of social and global inequalities as well as injustice among societies raised great concern in the public opinion. This ongoing process reveals the shortcomings and inadequacies of human rights protection and remediation mechanisms. In order to meet the social expectation for ensuring legal accountability of multinational companies regarding their global activities, in 2011 the United Nations Human Rights Council unanimously adopted the 'Guiding Principles on Business and Human Rights', which explicity sets forth corporate responsibility to respect human rights in addition to already existing state duty to protect human rights. Guiding Principles also states that business actors should make human rights due diligence (HRDD) to fulfill the requirements and conditions of their human rights responsibility. It is important to establish legal basis of corporate responsibility to respect human rights within the scope of international law and international human rights law. Otherwise, such responsibility would not be legally enforceable and thus, one can easily argue that this responsibility exists in vacuum juris. However, we have been witnessing various practices and operations of multinational companies within their supply chains, which would constitute human rights violations - in fact, some of these violations are breaches of jus cogens. Nonetheless, it is not possible to ensure the legal accountability of multinational companies in the current national legal systems due to legal barriers arising from how multinational companies' organizations are structured and corporate veil doctrine stipulated in national laws. The main discussion in the field of business and human rights and the main reason for injustices due to human rights violations by corporate actors; legal barriers arising from domestic law – particularly, commercial and contractual law – for establishing human rights responsibility of multinational companies, inability to go beyond streotypical approach of liberalism, and the unrealistic expectation that multinational companies (as well as foreign investment) will bring economic development and social welfare. As a matter of fact, the corporate responsibility to respect human rights has been declared within the scope of the Guiding Principles after this responsibility was emerged as an international customary law norm. HRDD is also envisaged as an important and necessary risk assessment tool for the fulfillment of this responsibility's requirements. As precribed by the duty of states to protect human rights, in order to ensure legal accountability of corporate actors and to enable victims' access to justice, removing domestic legal barriers and enacting necessary regulations that would facilitate accountability are required. Recent legal developments, especially in the European Union and the member states of the European Union, are also a result of this necessity.
Keywords: Business world; Companies; Due diligence; Fundamental rights; Guiding principles; Human rights; Rehber ilkeler; Social rights; Sosyal haklar; Temel haklar; Özen yükümlülüğü; İnsan hakları; İş dünyası; Şirketler

Milletlerarası ticari tahkimde usule ilişkin konularda irade serbestisi - Takavut, İbrahim Doğan (İstanbul Üniversitesi, 2020)
Party autonomy is a well-accepted doctrine codified by national, international and supranational organizations that enables parties to be able to not only shape their contract but also their dispute resolution methods. It is believed that parties know their best interests; therefore, it is reasonable to give parties the freedom to decide whom they contract with and on what terms. This maximizes the autonomous freedom of the parties. Therefore, today it is well accepted that parties could waive their right to go to court and choose arbitration instead. However, through history, party autonomy has been seen as a direct threat to sovereign authority. States were always suspicious that arbitration hearings may not be as fair as court hearings since parties have the right to manipulate the arbitration processes. As a direct result of this, states regulated restrictions on party autonomy in international commercial arbitrations. Unfortunately, there is not an accepted definition of these restrictions and their effects on party autonomy have not been established or regulated internationally. Since party autonomy is the backbone of international commercial arbitration, it is important to crystalize the restrictions on party autonomy in procedural issues which directly affects the wellbeing of the arbitration process. Well accepted international regulations such as the New York Convention on Recognition and Enforcement of Foreign Arbitral Awards or UNCITRAL Model Law on International Commercial Arbitration helped to establish a unified system of restrictions on party autonomy but every state and state's courts interpret these restrictions differently. As procedural issues affect the result of international commercial arbitration, restrictions on party autonomy in procedural issues should be examined carefully. It is not an exaggeration that in international commercial arbitration the real and complicated questions most of the time originate from the issues of the boundaries of party autonomy. The tension between the party autonomy and efficiency of an arbitration process affects every decision which can be made by parties, arbitrators or courts. Therefore, this dissertation will investigate these problems in three parts by outlining; the source of party autonomy, the restrictions of party autonomy and the applications of these restrictions to party autonomy in procedural issues in international commercial arbitration. In the first part, the origin of party autonomy doctrine and how the doctrine developed throughout time will be examined. The law of arbitration, lex arbitri will be examined first. There are two accepted theories to determine lex arbitri. According to the territorialism theory, arbitration gets its power from the law of the place where the arbitration takes place. This theory suggests that the place where the arbitration takes place has control power over the procedure of arbitration. On the other hand, delocalization theory suggests that arbitral tribunals are detached from and not under the control of the law of the seat of arbitration. Although it looks like delocalization theory suits the needs of the international trade practice better because it assumes that arbitration is not in control of any law, it is still important to accept the power of the seat of arbitration since arbitration always needs a law to be controlled and get help. This section will also cover how different countries and international regulations determine lex arbitri and how it is determined in Turkish law according to the Turkish International Arbitration Law, Law no.4686. In the second part, restrictive measures of party autonomy will be examined. It will start with why party autonomy in procedural issues is needed to be restricted. Then the source of these restrictions will be mentioned. Afterwards, the common notions of the restrictions will be examined under the concepts of principles and rules. Under principles, the public policy and the common due process issues such as party equality, right to be heard, independence and impartiality of arbitrators will be examined in great detail. Then, mandatory rules which are based on these principles and their effect on party autonomy will be explained. The section will be closed with the examination of the circumstances where these principles and rules contradict each other. The main purpose of the second part is to look for commonly accepted problems of restrictions of party autonomy in procedural issues and how these common problems may evolve to a uniformed standard of the law, namely lex proceduralia. In the third part, the application of restrictions on party autonomy will be examined. The application of restrictions has different effects on parties, arbitrators and courts. Parties' autonomy is restricted while they are preparing their agreement on procedural issues, arbitrators are restricted during the arbitration processes and courts are restricted while helping the arbitration or controlling the awards. Before the arbitration process is initiated, parties' autonomy to shape their agreement looks like it is almost unlimited. However, parties' autonomy is always restricted by their choices. This situation is called the autonomy paradox. Therefore, the question of what parties can decide before the arbitrators join the processes is of the upmost importance. When the process starts and arbitrators start working, they balance the choice of parties and the restrictions of party autonomy. Since it is accepted that arbitrators are bound by the parties' choice and their power comes from the agreement of parties, it should be questioned whether they need to execute every choice of parties even if the choice is against mandatory provisions of lex arbitri or general accepted due process norms. Last but not least, courts' role on determining the party autonomy will be questioned. The power of courts to intervene in the arbitral process determine the practical limits of the autonomy of parties. During the arbitration process, the court may intervene in the process to help or control the arbitration; but real control power comes from when one of the parties asks courts to set aside or enforce the arbitral awards. While courts examine the arbitral awards, they also indirectly decide the limits of party autonomy. Therefore, this section will examine, which restrictions will affect the fate of the arbitral awards and how the courts should evaluate these restrictions. In conclusion, the dissertation will mainly investigate the topic of freedom of parties to determine the procedural issues in international commercial arbitration. It will aim to interpret and make use of the party autonomy doctrine as coherent as it can in the modern age. By illustrating the definition and limitations of the party autonomy in the procedural issues in international commercial arbitration, the dissertation will try to find a common international ground. This common ground may help to keep arbitration processes efficient while it provides fair hearings.
663179
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration boards; Commercial Arbitration; Commercial law; Free will; Hakem usulu; International Arbitiation Law; International Chamber of Commerce; Milletlerarası Tahkim Kanunu; Party autonomy; Procedural law; Tahkim; Tahkim kurulları; Ticaret hukuku; Uluslararası Ticaret Odası; Usul hukuku; Özgür istenç; İrade muhtariyeti

Anonim ortaklıklar hukukunda esas sözleşme özgürlüğü ve sınırları - Vezi̇roğlu, Cem (İstanbul Üniversitesi, 2020)
Bu doktora tezi, anonim ortaklıklar hukukunda esas sözleşme özgürlüğü ve bunun sınırlarının çeşitli açılardan incelenmesini konu almaktadır. Üç bölümden oluşan tezin ilk bölümü konunun kuramsal çerçevesini çizmeyi hedeflerken, ikinci ve üçüncü bölümler ise mevcut sorunlar karşısında dogmatik hukuk bakımından çözümler geliştirmeyi amaçlamaktadır. Bu kapsamda öncelikle özel hukukta ve ortaklıklar hukukunda sözleşme özgürlüğünün kavramsal, teorik, tarihsel, anayasal, ekonomik ve ahlaki zemini ortaya koyulmuştur. İkinci bölümde sözleşme özgürlüğünün anonim ortaklıklar hukukundaki görünümü ele alınmış ve bunu hayata geçiren en önemli işlem olan esas sözleşme çeşitli açılardan irdelenmiştir. Son bölümde ise esas sözleşme özgürlüğünün genel hükümler ve anonim ortaklıklar hukuku çerçevesindeki sınırları incelenmiştir. Bu bağlamda TK m. 340 hükmünde düzenlenen emredici hükümler ilkesine özel bir önem atfedilmiştir. Çalışmada disiplinler arası yöntemin esas alınması doğrultusunda ortaklık teorilerine ve hukukun ekonomik analizine başvurulmuştur. Anılan yöntemlerin katkısı hem pozitif hukuk hem de hukuk politikası açısından ortaya koyulmuştur. Ayrıca incelemede karşılaştırmalı hukuka ve tarihsel araştırmaya geniş yer ayrılmıştır. This doctoral thesis analyzes contractual freedom in articles of association and its limits in joint stock companies from various aspects. The thesis consists of three parts. While the first part aims to set the theoretical framework of the problem, the second and third parts intend to find solutions vis-à-vis existing problems in terms of positive law. Within this scope conceptual, theoretical, constitutional, economic and ethical aspects of contractual freedom in private law and corporate law are primarily examined. The second part deals with contractual freedom in corporate law and examines articles of association from various perspectives as it is the most important legal act that brings contractual freedom into being. The last part analyzes the limits of contractual freedom in articles of association pursuant to general provisions of civil law and joint stock company law. In this regard, the principle of mandatory norms stipulated in Turkish Commercial Code numbered 6102 Article 340 is attached a particular importance. Theories of the corporation and economic analysis of law are applied in accordance with the interdisciplinary methodological view adopted in this study. Contribution of the mentioned methods are set forth in terms of both positive law and legal policy. Moreover, comparative legal analysis and historical analysis are used extensively.
Ulusal Tez Merkezi
Keywords: Anonim ortaklıklar; Anonim şirketler; Commercial law; Company law; Contracts; Contractual freedom; Emredici norm; Incorporated companies; Joint stock company; Peremptory norms; Sözleşme özgürlüğü; Sözleşmeler; Ticaret hukuku; Şirketler hukuku

İşletme yöneticilerinin ticari belgelerin tanzim ve hukuki süreçlerine ilişkin bilgi ve algı düzeyleri üzerine bir araştırma - Yardimcioğlu, Melek (Gaziantep Üniversitesi, 2020)
"Bu tez çalışması ile işletme yöneticilerinin ticari belge tanzim ve hukuki süreçlerine ilişkin bilgi ve algı düzeyleri ortaya konmaya çalışılmıştır. İşletme yöneticileri içinde faaliyet gösterdikleri ülkenin hukuki kurallarına göre iş piyasası ve iş hayatında faaliyet gösterirler. Ve bu kurallar ticari hayat içinde onlar için en önemli bağlayıcı normlardır. Bu çalışma ilgi ticaret hukukunun iş hayatında en önemli faaliyet ve uygulama alanı bulan ticari belge tanzimi ve hukuki süreçlerinin yöneticiler tarafından ne seviyede algılandığının ortaya konması amaçlanmıştır. Tez çalışma dört bölümden oluşturulmuştur. İlk bölümümüz giriş bölümüdür. İkinci bölümde yönetim konuları, ticari belgeye ilişkin hukuki argümanlara yer verilmiştir. Üçüncü bölüm uygulama bölümüdür. Dördüncü bölümde ise sonuç ve yorumlara yer verilmiştir. With this thesis, the level of knowledge and perception of business executives regarding the issuance and legal processes of commercial documents has been tried to be revealed. Business executives operate in the labor market and business life according to the legal rules of the country in which they operate. And these rules are the most important binding norms for them in commercial life. With this study, it is aimed to reveal the level of perception of commercial document arrangement and legal processes, which find the most important field of activity and application in business life, by managers. The study is composed of four parts. Our first part is the introduction. In the second part, administrative issues and legal arguments related to the commercial document are included. The third part is the implementation part. In the fourth section, results and comments are given."
Keywords: Bilgi düzeyi; Business management; Commercial documents; Commercial law; Level of knowledge; Managers; Ticaret hukuku; Ticari belgeler; Yöneticiler; İşletme yönetimi

Finansal tabloların tutulması ve hukuksal sonuçları - Aksu Özkan, Raziye (Akdeniz Üniversitesi, 2019)
"Bu çalışmada finansal tabloların işlevleri, çeşitleri, düzenlenmesi ve tutulmasından kaynaklanan hukuksal sonuçlar incelenmiştir. Finansal tablolar, işletmenin finansal durumunun ve finansal performansının biçimlendirilmiş sunumudur. Bu tablolar aracılığıyla, şirketin finansal durumu hakkında bilgilendirme yapılmaktadır. Finansal tablolar, özellikle yabancı yatırımcının şirketlere güvenip yatırım kararı alması açısından önem arz etmektedir. Bu bağlamda, Türk Ticaret Kanunu'nun (TTK) genel gerekçesi beşinci paragrafında, uluslararası piyasaların bir parçası olmak hedefi ortaya konulmuştur. Hedefe ulaşmak için, finansal tabloların uluslararası standartlara göre düzenlenmesi gerekliliğine yer verilmiştir. Hedefe ulaşmada yeterli düzenleme yapılması konusunda Kamu Gözetimi, Muhasebe ve Denetim Standartları Kurumu görevlendirilmiştir. Kurum tarafından yapılan düzenlemeler, uluslararası muhasebe standartlarının çevirisinden ibaret olup, yeterli değildir. TTK ile muhasebe uygulaması arasında köprü kurulamamıştır. Ticaret ve vergi hukuku alanında yer alan düzenlemeler kapsamında iki ayrı uygulama yürütülmektedir. Finansal tabloların işletmenin finansal durumunu, finansal performansını ve nakit akışlarını gerçeğe uygun olarak sunması gereklidir. Kural olarak standartlara uygunluk, bilgilerin gerçeğe uygun şekilde açıklanması için yeterlidir; ancak bu uygunluk gerçek durumunu yansıtmıyorsa standartlar uygulanmayabilecektir. Finansal tablolar bilanço, döneme ait kar veya zarar ve diğer kapsamlı gelir tablosu, özkaynak değişim tablosu, nakit akış tablosu, önemli muhasebe politikalarını ve diğer açıklayıcı bilgileri içeren dipnotlardan oluşur. Bilanço, işletmenin hazırlandığı tarih itibariyle varlık, yükümlülük ve özkaynaklarını gösteren finansal tablodur. İşletmenin sahip olduğu her türlü malvarlığı unsuru veya katlandığı her sorumluluk bilançoda muhasebeleştirilemez. Bunun için standartlarda sayılan koşulları taşımaları gerekmektedir. Bilanço dışındaki diğer finansal tablolar, ya bilançonun hazırlanması açısından birer araçtır ya da bilançonun tamamlayıcısıdır. Tabloların içeriğinde yer alan bilgilerin birbiriyle ilişkisi, bunların bir bütün olarak değerlendirilmesi gerektiğini ortaya koymaktadır. Finansal tabloların tutulmasının yönetim kurulu, denetim ve genel kurul açısından hukuki sonuçları bulunmaktadır. Yönetim kurulu finansal tabloları hazırlar ve genel kurula sunar. Bununla birlikte, denetim finansal tablolar esas alınarak yapılacaktır. Buna bağlı olarak, denetçi şirket hakkında denetim raporunu oluşturacaktır. Genel kurul, denetimden geçmiş finansal tablolara dayanarak şirkete ve yönetim kuruluna ilişkin kararlar alacaktır. In this study, the legal results arising from the functions, types, regulation and retention of the financial statements are examined. Financial statements are a structured representation of the financial position and financial performance of an entity. These tables provide information on the financial position of the company. Financial statements are especially significant for foreign investors to trust companies and make investment decisions. In this context, the fifth paragraph of the general justification of the Turkish Commercial Code (TCC) aims to be a part of international markets. In order to reach the target, it is necessary to arrange the financial statements according to international standards. The Public Oversight, Accounting and Auditing Standards Authority has been appointed to ensure adequate regulation to reach the target. The regulations made by the institution consist of translation of international accounting standards and are not sufficient. No bridge could be established between the TCC and the accounting practice. Within the scope of the regulations in the field of trade and tax law, two different applications are carried out. Financial statements shall present fairly the financial position, financial performance and cash flows of an entity. As a rule, compliance with standards is sufficient for the information to be truthfully disclosed; however, if this compliance does not reflect the actual situation of the company, the standards may not apply. The financial statements comprises balance sheet, a statement of profit or loss and other comprehensive income for the period, a statement of changes in equity, a statement of cash flow, notes, comprising significant accounting policies and other explanatory information. The balance sheet is the financial statement showing the assets, liabilities and equity of the entity. Any asset that the entity owns or any liability that it endures cannot be recognized in the balance sheet. For this, they must meet the requirements listed in the standards. Other financial statements, other than the balance sheet, are either tools for the preparation of the balance sheet or complementary to the balance sheet. For this reason, the relationship between the information contained in the content of the tables suggests that they should be evaluated as a whole. The holding of the financial statements has legal consequences for the board of directors, auditing and general assembly. The Board of Directors shall prepare the financial statements and present them to the General Assembly. However, the audit will be performed on the basis of financial statements. Accordingly, the auditor will establish an audit report on the company. The General Assembly shall take decisions regarding the company and the board of directors on the basis of audited financial statements."
Keywords: Commercial law; Compliance with laws; Financial statements; Finansal tablolar; Hukuka uygunluk; Hukuksal esaslar; International Accounting Standards; Legal aspects; Standards; Standartlar; Ticaret hukuku; Turkish Accounting Standarts; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Türkiye Muhasebe Standartları; Uluslararası Muhasebe Standartları

Anonim şirketlerde yönetim kurulunda temsil edilme imtiyazı - Baltali, Candemir (İstanbul Bilgi Üniversitesi, 2019)
Bu çalışma İstanbul Bilgi Üniversitesi Hukuk Fakültesi Özel Hukuk Doktora Tezi olarak hazırlanmıştır. Tezin konusunu anonim şirketlerde yönetim kurulunda temsil edilme imtiyazı oluşturmaktadır. 6012 sayılı Türk Ticaret Kanunu ile imtiyazlara ilişkin yeni bir düzen getirilmiş, ayrıca yönetim kurulunda temsil edilme hakkı normatif düzenlemeye kavuşturulmuş ve belirli gruplar ile azlığa temsil edilme hakkı tanınabileceği hükme bağlanmıştır. Tez kapsamında ilk olarak imtiyaz kavramı ve imtiyazlara ilişkin temel ilkeler incelenmiştir. Takip eden bölümde yönetim kurulunda temsil edilme hakkı irdelenmiştir. Tezde en önemli amaç, temsil edilme hakkını etraflıca incelemek ve temsil edilme hakkıyla imtiyazlar arasında kurulan köprüyü tanıtmak olmuştur. Bu itibarla, bir imtiyaz olarak nitelendirilen temsil edilme hakkının, diğer imtiyazlardan ayrılan özellikleri üzerinde durulmuştur. Ayrıca temsil edilme hakkının tanınabileceği zümreler ile tanındığı her bir zümre özelinde hakkın hukuki niteliğine yönelik tespitlerde bulunulmuş ve öğretide pek tartışılmamış olan temsilci üyenin niteliği ele alınmıştır. Devamında temsil edilme hakkına dair yöntemler incelenmiş ve çeşitli esas sözleşme hükümleri yorumlanmıştır. Tezde karşılaşılan hukuki sorunların işlevsel bir menfaat hukukçuluğu çerçevesinde yanıtlanmasını hedefleyen bir yöntem benimsenmiştir. Yorum yapılırken amaçsal yorum metodu kullanılmış, saptanan hukuki sorunlar için de lege lata çözüm önerilerinde bulunmaya gayret edilmiştir. This paper is prepared as Istanbul Bilgi University Faculty of Law Private Law PH.D. Dissertation. Subject of the dissertation is the privilege to be represented in the board of directors of joint stock companies. Turkish Commercial Code numbered 6102 introduced a paradigm shift in relation to the privileges, regulated the right to be represented in the board of directors and set forth that such right may be granted to certain groups and minority. Firstly, privilege concept and principles surrounding the privileges have been examined in the dissertation. Following section focuses on the right to be represented in the board of directors. The substantial purpose of the dissertation is to introduce the right to be represented and the correlation between such right and privileges. Thus, the differences between the right to be represented which is a privilege and other privileges have been set forth. Further, determinations have been made on classes that may be granted with the right to be represented and legal qualifications of the right by taking into consideration each class that may be granted with such right, and characteristics of the representative, a subject so far that has not been examined in detail by doctrine, have been discussed. Methods of right to be represented are examined and miscellaneous articles of association provisions are interpreted in this regard. The method adopted in the dissertation aims to respond to the legal problems within the frame of taking into consideration the interests of the shareholders. The teleological interpretation methodology has been used for interpretations and proposals of de lege lata solutions to the legal problems have been endeavored.
581706
Keywords: Anonim şirketler; Board of directors; Concessions; Consumer right to representation; Joint stock company; Privileged share; Temsil edilme hakkı; Turkish Commercial Code; Turkish Commercial Law; Türk Ticaret Hukuku; Türk Ticaret Kanunu; Yönetim kurulu; İmtiyazlar; İmtiyazlı pay

Anonim şirketlerde yönetim kurulunun yönetim ve temsil yetkisinin devri ve sınırlandırılması - Büyükatak, Aytuğ (İstanbul Kültür Üniversitesi, 2019)
Anonim şirketin yönetim ve temsil yetkileri 6102 sayılı Türk Ticaret Kanunu'nda ayrı başlıklarda düzenlenmiştir. TTK'da, anonim şirketlerde yönetim yetkisinin devri için esas sözleşmede devre izin veren bir hükmün bulunması ve yönetim organizasyonuna ilişkin bir iç yönerge hazırlanması gerekmektedir. Bu hususlara uygun şekilde, yönetim kurulu alacağı bir karar ile yönetim yetkisinin tamamını veya bir kısmını kurul üyelerine ve/veya üçüncü kişilere devredebilecektir. Temsil yetkisinin devri ve sınırlandırılmasına ise TTK, kanuni ve iradi sınırlandırmaların yanısıra 371. maddenin 7. Fıkrasında yapılan ekleme ile sınırlı temsilci tayini hususunda yeni ve eleştirilen bir rejim getirmiştir. Bu bağlamda çalışmamızda, yönetim ve temsil yetkilerinin devir ve sınırlandırılmasının kapsamı, devir ve sınırlandırmalar için uyulması gereken şartlar, yönetim yetkisi ile temsil yetkinin devri arasındaki ilişki ve bu yetkilerin devredilebileceği kişiler inceleme konusu yapılmakta ve bu konulara ilişkin güncel tartışmalar ele alınmaktadır. Anahtar Kelimeler: Anonim Şirket, Yönetim Kurulu, Yönetim Yetkisi, Temsil Yetkisi, Yetki Devri, Örgüt Yönergesi, Sınırlı Yetkili, Sınırlı Temsilci, Sorumluluk. Management rights and representation rights in joint stock companies have been regulated under separate subjects in 6102 numbered Turkish Commercial Code. According to Turkish Commercial Code, joint stock companies that want to delegate the management rights should have a provision on their articles of association that allows such delegation and should prepare internal rules regarding the organization of management. According to such terms, the board of directors may delegate its management Powers fully or partially to one or more board members and/or third parties by issuing a decision on such matter. Regarding the delegation and limitation of representation rights, the addition of seventh paragraph to article 371. of Turkish Commercial Code, has introduced a new and highly criticized regime on such matter besides the legislative and voluntary limitations. In this context, our study will review the limits of delegation and limitation of management and representation right, requirements for such delegation and limitation, the relationship between right of management and right of representation, persons whom the powers may be delegated and the up-to-date discussions on such subjects. Keywords: Joint Stock Company, Board of Directors, Management Right, Representation Right, Delegation of Rights, Internal Rules, Limited Authority, Representative with Limited Power, Responsibility.
554902
Keywords: Anonim şirketler; Board of directors; Company management; Joint stock company; Representation; Representative authority; Subsidiarity; Succession; Temsil; Temsil yetkisi; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yetki devri; Yönetim devri; Yönetim kurulu; Şirket yönetimi

Bağlı şirketin borçlarından dolayı hakim şirketin sorumluluğu - Demi̇rtaş Nevzer, Sebla (Kocaeli Üniversitesi, 2019)
Birbirinden bağımsız birden fazla şirketin bir araya gelmek suretiyle bir organizasyon oluşturmalarına sıklıkla karşılaşılmakta, bu organizasyona ise şirketler topluluğu denilmektedir. Kuruluşların faaliyet alanlarını genişletmek istemeleri, bu yönde maliyetlerini en aza indirerek kârlılıklarını arttırmak için bir araya gelmeleri sonucunda ticari açıdan bir organizasyon oluşturmaları ülkemizde de sıklıkla görülmektedir. Ancak mevcut kanunlarımızda bu şekilde oluşan organizasyonlara yönelik herhangi bir özel düzenlemeye daha önce yer verilmemişti. Bu tür durumlarla farklı hukuk alanlarında da sıklıkla karşılaşılması, zamanla şirketler topluluğu açısından yasal düzenleme yapılması gereğini doğurmuş ve şirketler topluluğuna ilişkin düzenlemeler ilk olarak 6102 sayılı Türk Ticaret Kanunu ile yapılmıştır. Bu düzenlemeler, topluluk yapılanmasının, organizasyon şemasının kurulmasını, işleyişi ve ilgililerin sorumluluğunun belirlenmesini amaçlamaktadır. Ticaret Kanununda düzenlenen şirketler topluluğuna ilişkin hükümlerin önemli bir bölümü Alman Konzern Hukuku esaslıdır. Çalışmamızda kanundaki şirketler topluluğu düzenlemeleri incelenirken, Türk Hukuku esas alınmış ve konu diğer hukuk dalları ile birlikte çok yönlü bir şekilde ele alınarak şirketler topluluğu düzenlemelerinin uygulanabilirliğinin sağlanması hedeflenmiştir. Bağlı şirketin borçlarından dolayı hakim şirketin sorumluluğunu irdeleyen çalışmamızda, şirketler topluluğunun temel kavramları, şirketler topluluğunda sorumluluk halleri ile bağlı şirketin üçüncü kişilere karşı sorumluluğu konusu, özellikle fiili şirketler topluluğu kapsamında ve anonim şirket temelinde incelenmiştir. Ayrıca şirketler topluluğu düzenlemelerinin uygulama yelpazesinin genişletilmesine katkı sağlaması amacı ile diğer hukuk alanlarına da değinilmek suretiyle çok yönlü araştırma yapılmıştır. Anahtar Kelimeler: Şirketler Topluluğu, Sorumluluk, Hakim Şirket, Bağlı Şirket. It is frequently seen that multiple companies independent from each other come together to form an organization and this organization is called a group of companies. In our country, it is frequently observed that entities form a commercial organization by coming together around the desire of extending their field of activity and in order to reduce costs and increase profitability. However, existing laws lacked a specific regulation in connection with organizations that are formed as such. Encountering such cases in different fields of law has, in time, led to the requirement of a legislative regulation about group of companies and regulations have been introduced for the first time in connection with group of companies under Turkish Commercial Code No. 6102. These regulations are aimed at stipulating the structuring of the group of companies, forming the organizational chart, and determining operational aspects and responsibilities of the concerned persons. Substantial part of the provisions regarding group of companies regulated under Commercial Code is based on German Konzern Law. The present study is focused on group of companies regulations under the Law based on Turkish law and the subject matter is addressed in an in-depth approach based on other branches of the law in order to establish enforceability of the group of companies regulations. In the present study analysing liability of the Dominant Enterprise in connection with debts of an Affiliated Company, basic concepts related with group of companies, liabilities in a group of companies and liability of anAffiliated Company towards third persons are explained within the scope of actual group of companies and joint stock companies. In addition, an in-depth study has been conducted based on other fields of the law for the purpose of contributing to extension of the enforcement range of regulations on group of companies. Keywords: Group of companies, Liability, Dominant Enterprise, Affiliated Company.
566846
Keywords: Borçlar; Borçlu; Businesses; Company law; Debtor; Debts; Dette; Dominant position; Filiale; Hakim durum; Hukuki sorumluluk; Kanunlar 6102 sayılı; Laws 6102 numbered; Legal responsibility; Responsabilité; Responsibility; Société mère; Sorumluluk; Turkish Commercial Code; Turkish Commercial Law; Türk Ticaret Hukuku; Türk Ticaret Kanunu; İşletmeler; Şirketler hukuku

Orman karbonunun hukuksal yapısı ve karbon piyasası açısından değerlendirilmesi - Kiliç Hernandez, Hülya (İstanbul Üniversitesi-Cerrahpaşa, 2019)
Carbon emissions have increased steadily in the last quarter of the 20th century while countries have made more efficient actions to take international decisions within the United Nations. This has also had an impact on the signing of international agreements and on national law, making it necessary to prepare new legislation within the country. This is followed by significant legal arrangements in many countries. In Turkey, this issue is in its early stages and various regulations have started to be made in different institutions, but the regulations have not been in a level to meet the deficiencies in the legislation. Therefore, Turkey has made it a priority to put forth the legal structure of forest carbon rights and forest carbon markets. Turkey also continues to make changes to the legislation on forestry to solve this requirement. First, to form the legislation on forest carbon markets, it is necessary (1) to analyze the carbon element in terms of the law of property and (2) to put forth the carbon emissions and carbon sequestration capacity in Turkey utilizing available resources. In addition, the contribution of Turkey's clean energy projects carried out and planned to be carried out on clean energy must be taken into account. The findings, which will be obtained in this way, will reveal to what extent Turkey, General Directorate of Forestry in particular can benefit from the international carbon market. In our legislation, there are direct or indirect arrangements regarding environment, forest, nature protection, and carbon. Although there are no direct regulations on carbon at this level of law in Turkey, carbon emission or sequestration is mentioned in the environmental legislation with various approaches. These various provisions are not enough to represent position and situation, advantages and disadvantages of our country accurately in the carbon market. Therefore, it is clear that there is a need for legal regulations, which aims to solve the climate change problem, one of the most important problems of our time. In this context, the aim of the thesis is to determine the place of carbon in effective laws at the national level and to develop legal proposals for the creation of carbon markets. For this purpose, literature review was carried out as a priority. The current legislation on this issue was compiled and reviewed. In addition, by examining the jurisprudence of the judiciary, it was examined to determine what issues the current disputes are concentrated on and the direction of judicial practice. In the light of the findings obtained through these studies, it was revealed that there is a significant gap in the legal structure of forest carbon in Turkey. For example, in the case of the establishment of the carbon markets, it was determined that the legislation should be established first. It was also detected that there are different powers in different general directorates and there are not sufficient provisions in national legislation. The legislation on every stage of the process, from the production of carbon to the creation of the markets, has been dealt with within the framework of international conventions and national legislation, and the gaps in the legislation should be addressed. There are gaps in the definitons of the fields of forest carbon rights and property law, the nature of the carbon certificate, the trade law in order to be able to process carbon in the stock market, etc. and in the operation and authorization. . When it is necessary to sell forest carbon credit, it is important to certify and trade in the stock exchange. International certifications are applied for the certification. Turkey does not have a certification system. The EU, America, Germany, and New Zealand have established certification systems in their own countries and have made them open to international applications. Thus, encouraging the establishment of a certification system in Turkey and supporting the work that can be done in this direction is necessary. . This issue is also included in the thesis. The carbon retained in the forest (tree/soil, forest litter, dry body, branch, understorey, etc.) accumulation must be included in the concept of income as a sub-separation of the concept of production. The legal status of forest carbon should be evaluated separately according to the situation of either before or after leaving the original goods. As a result, there is a significant gap in the legislation related to forest carbon market in Turkey. This gap should be eliminated by establishing a department called "Department of Forest Carbon Management" within the General Directorate of Forestry of the Ministry of Agriculture and Forestry. Legal arrangements should be made including provisions to Article 169.4 of the Constitution, articles 1, 2, 4 and 26 of Law No. 6831, and the Articles 334 and 338 of Presidential Decree No.4, and the Environmental Law to support carbon projects. Keywords: Climate, climate change, carbon market, forest carbon right.
579020
Keywords: Ayni haklar; Easement; Forestry and Forest Engineering; Gas emission; Gaz emisyonu; Ormancılık ve Orman Mühendisliği; Real rights; İrtifak hakkı

Şirket birleşmelerinde ortakların dava yoluyla korunması - Sarikaya, Sinan (Marmara Üniversitesi, 2019)
Şirket birleşmelerinde ortakların korunması, belirlediği ilkeler ve tanıdığı dava hakları nazara alındığında, kanun koyucunun özel önem atfettiği hususlardan biridir. Devrolunan şirketin ortaklarının, mevcut pay ve haklarını karşılayacak değerde, devralan şirket pay ve haklarını iktisap etmesi esastır. Birleşmenin ortakların malvarlığı cephesinde yarattığı olumsuz sonuçlar, ortaklığın devamlılığı ilkesi çerçevesinde, denkleştirme davası ile denetlenmektedir (TTK m. 191). Bu davada ortaklar, pay ve haklarının gereğince korunmamış veya ayrılma akçesinin uygun belirlenmemiş olması gerekçesiyle, uygun bir denkleştirme isteyebilirler. Öte yandan, Kanun'un birleşmeye ilişkin hükümlerinin ihlali, yine ortakların açabileceği, özel iptal davası ile denetlenmektedir (TTK m. 192). Kanun koyucu, ilgili hükümlerin ihlaline iptal sonucunu bağlamakta; ancak eksikliklerin giderilmesi mekanizması ile bu ağır yaptırımla karşılaşılmaması için devralan şirkete olanak tanımaktadır. Son olarak, birleşme işlemlerine katılan bütün kişilerin, ortaklara karşı kusurları ile vermiş oldukları zararlardan sorumlu oldukları düzenlenerek, ortakların zararlarını tazmin edecek bir özel sorumluluk davası öngörülmektedir (TTK m. 193). Böylece birleşme karşısında ortaklar, üç farklı mekanizma ile koruma altına alınmış olmaktadır. Regarding the principles determined and the right to sue recognized, the protection of the shareholders in the mergers is one of the issues that the legislator attaches special importance to. It is essential that the shareholders of company being acquired attain the shares and rights in the acquiring company equivalent to those in the company being acquired. The negative results of merger on the assets of the shareholders are reviewed by an examination case within the framework of the continuity of the partnership principle (TCC Art. 191). In the present case, the shareholders may demand an appropriate compensation on the grounds that their share and rights are not properly protected or the amount of any cash payment is not determined appropriately. On the other hand, the violation of the provisions of the Law relating to the merger is controlled by a special nullification case, which could be filed by the shareholders (TCC Art. 192). The legislator has concluded the nullification of the violation of the relevant provisions; however, the elimination of deficiencies mechanism allows the acquiring company to avoid it. Finally, it is foreseen a liability case to compensate shareholders' damages that allows all persons participating in the merger transactions are liable for the damages they incurred against the them (TCC Art. 193). Thus, the partners are protected by three different mechanisms against the merger.
Keywords: Annulment action; Associés; Birleşmeler; Cases; Commercial law; Davalar; Denkleştirme; Equalization; Fusion d'entreprises; Liability case; Litige; Mergers; Ortaklar; Ortaklık; Partners; Partnership; Sorumluluk davası; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; İptal davası; Şirket birleşmeleri

Anonim şirket yönetim kurulu üyelerinin Rekabet Hukukundan kaynaklanan sorumluluğu - Seyman, Seda (Dokuz Eylül Üniversitesi, 2019)
Bu çalışmada anonim şirket yönetim kurulu üyelerinin Rekabet Hukukundan kaynaklanan sorumluluğu incelenmiştir. Anonim şirket kural olarak yönetim kurulu tarafından alınan kararlar ile faaliyetini sürdürür. Anonim şirkette yönetim kurulu üyesi olarak görev yapan kişiler birtakım haklara sahip oldukları gibi yükümlülük altına da girerler. Yönetim kurulu üyeleri kanunda kendileri için getirilen yükümlülüklerini ihlal ettikleri takdirde halinde yönetim kurulu üyelerinin hukuki ve cezai sorumluluğuna gidilir. Anonim şirket yönetim kurulunun hukuki sorumluluk sebepleri ve sorumluluğun şartları Türk Ticaret Kanunu'nda ayrıntılı olarak düzenlenmiştir. Yönetim kuruluna yaptırım uygulanabilecek düzenlemeler Türk Ticaret Kanunu'nda düzenleniyor olmakla birlikte, yönetim kurulu üyelerine yaptırım uygulanmasına imkan veren düzenlemeler mevcuttur. Bu düzenlemelerden biri de Rekabetin Korunması Hakkında Kanun'da yer almaktadır. Rekabetin Korunması Hakkında Kanun'un 16'ıncı maddesinde hem teşebbüs yahut teşebbüs birliklerine hem de teşebbüs ve teşebbüs birliğinin yönetici yahut çalışanına yaptırım uygulanmasına imkan veren düzenleme yer almaktadır. Söz konusu düzenleme uyarınca, , anonim şirket rekabeti sınırlayıcı anlaşma, uyumlu eylem ve kararlar, hakim durumun kötüye kullanılması yahut birleşme veya devralma sebebi ile idari para cezasına hükmedilmesi mümkündür. Maddede aynı zamanda Rekabet Kanunu'nun 16'ıncı maddesinin üçüncü fıkrası gereğince teşebbüs veya teşebbüs birliklerine üçüncü fıkrada belirtilen idarî para cezaları verilmesi halinde, ihlalde belirleyici etkisi saptanan teşebbüs veya teşebbüs birliği yöneticilerine ya da çalışanlarına teşebbüs veya teşebbüs birliğine verilen cezanın yüzde beşine kadar idarî para cezası verilebileceğine ilişkin düzenleme yer almaktadır. Çalışmanın birinci kısmında genel olarak Rekabet Hukukuna değinilecektir. İkinci kısmında ise Rekabet Kanunu'nun 16'ıncı maddesinin üçüncü fıkrası uyarınca teşebbüs ve teşebbüs birliklerine uygulanacak yaptırımın şartları ve yaptırımın uygulanması usulü incelenecektir. Çalışmanın son kısmında ise anonim şirket yönetici ve çalışanlarına uygulanacak yaptırımın koşulları ile yaptırımın uygulanması usulü ayrıntılı olacak incelenecektir. Anahtar Kelimeler: Anonim Şirket, Yönetim Kurulu, Rekabet Hukuku, Yönetim Kurulu Üyelerinin Sorumluluğu, Ticaret Hukuku, Rekabetin Korunması Hakkında Kanun. Liabilities of the members of board of directors in joint stock company under competition law is analysed in this study. As a rule, the joint stock company operates with the decisions taken by the board of directors. Persons who are members of the board of directors of a joint stock company have certain rights as well as obligations. If the members of the board of directors violate the obligations imposed on them by law, the members of the board of directors shall be subject to civil and criminal liability. The reasons for the legal responsibility of the joint stock company's board of directors and the conditions of the liability are regulated in detail in the Turkish Commercial Code. Although the regulations that may impose sanctions on the board of directors are regulated in the Turkish Commercial Code, there are regulations allowing sanctions to be imposed on the members of the board of directors. One of these regulations is included in The Act On The Protection Of Competition. Article 16 of The Act On The Protection Of Competition includes the regulation that allows sanctions to be applied to both the undertakings or associations of undertakings and the manager or employee of the association of undertakings and undertakings. According to article it is possible to impose an administrative fine on the basis of an agreement, concerted practices and decisions restricting competition, abuse of dominant position or merger or acquisition. According to article 16/3, in case administrative fines mentioned in paragraph three are imposed on undertakings or associations of undertakings, an administrative fine up to five percent of the penalty imposed on the undertaking or association of undertakings shall be imposed on managers or employees of the undertaking or association of undertakings who are found to have a decisive influence in the infringement. In the first part of the study, Competition Law will be discussed in general. In the second part, the conditions of the sanction to be applied to the undertakings and associations of undertakings and the method of enforcement of sanctions in accordance with the third paragraph of Article 16 of the Act On The Protection Of Competition will be examined. In the last part of the study, the conditions of sanction to be applied to the managers and employees of joint stock companies and the procedure of sanction will be examined in detail. Keywords: Joint Stock Company, Board Of Directors, Competition Law, Liabilities Of The Members Of Board Of Directors, Commercial Law, The Act On The Protection Of Competition.
573022
Keywords: Anonim şirketler; Board of directors; Competencia; Competition law; Concorrência; Concurrence; Joint stock company; Members of the board directors; Rekabet hukuku; Responsibility; Sorumluluk; Yönetim kurulu; Yönetim kurulu üyeleri

Anonim şirketlerde önemli miktarda malvarlığı üzerinde işlemler - Songur Hacigüzeller, Damla Gülseren (Ankara Üniversitesi, 2019)
"Anonim şirkette önemli miktarda malvarlığı üzerinde işlemler, anonim şirketin yapısı ve faaliyetlerini ve ayrıca pay sahiplerinin çıkarlarını etkileyen ciddi sonuçlar doğurur. Bu söz konusu işlemler, yabancı hukuk sistemlerinde uzun zamandır pay sahiplerinin korunması amacıyla genel kurulun yetkili olduğu özel usule tabidir. Türk hukukunda 6102 sayılı Türk Ticaret Kanunu öncesinde sadece tasfiye halindeki anonim şirket için düzenlenen genel kurulun bu yetkisi, Yargıtay kararlarında ve öğretide faaliyeti devam eden şirket için de kabul edilmekteydi. Bugün ise Yargıtay içtihatları ve yabancı hukuk sistemlerine uygun olarak önemli miktarda malvarlığı üzerindeki işlemler, faaliyeti devam eden şirketler açısından özel olarak düzenlenerek genel kurulun devredilemez görev ve yetkileri arasında sayılmış ve ayrıca halka açık şirketler için önemli nitelikte işlemlere özgü özel usule tabi kılınmıştır (TTK md. 408/2-f; SPK md. 23/1-b). Ancak Türk Ticaret Kanunu'na Adalet Komisyonu tarafından sonradan eklenen hüküm birçok yönden yoruma ve tartışmaya açıktır. Zira hükmün kapsamı ve uygulama alanı konusunda Türk Ticaret Kanunu bakımından usul ve esaslar yönünden söz konusu olan belirsizlikler, genel kurul ile yönetim kurulu arasında yetki çatışması yaratabileceği gibi, işlemin akıbeti ve dolayısıyla tarafların işlemle bağlılık durumu açısından da sorun doğurabilecek niteliktedir. Öte yandan halka açık şirketler bakımından Sermaye Piyasası mevzuatında önemli nitelikte işlemler için öngörülen usulün de önemli miktarda malvarlığı üzerindeki işlemler özelinde değerlendirilmesi gerekmektedir. Çalışmamızda yoruma ve tartışmaya muhtaç hususlara açıklık getirilmesi amacıyla, önemli miktarda malvarlığı üzerindeki işlemlerin gerçekleştirilmesine ilişkin hukuki bir çerçeve oluşturularak, bu işlemler düzenlenişi, kapsamı, tabi olduğu usul ve nihayet hüküm ve sonuçları yönünden incelenmiştir. From the legal and economic perspective, transactions regarding the substantial amount of assets of a joint stock company have serious consequences on its structure and activities, specifically affecting the interests of shareholders. That's why, in comparative law, within the scope of the protection of shareholders, such transactions are subjected to a special process in which the general assembly plays a crucial role in authorization of the aforementioned transactions. In Turkish law, before the enactment of Turkish Commercial Code nr. 6102, the general assembly had this authorization, but only in the liquidation process of a company. However, in various decisions of the Turkish High Court of Appeal and the legal scholarly work, in accordance with the comparative law, it was pointed out that the general assembly should have this authorization, even if the company is not in a liquidation process. Currently, such transactions of active companies are specifically regulated and are considered among the non-delegable authorizations of the general assembly. In addition, such transactions of publicly-held corporations are subjected to a special process (Art. 408/2-f of TCC; Art. 23/1-b of CML). However, the relevant article added by the Commission of Justice to the Turkish Commercial Code needs to be scrutinized and interpreted. There are many uncertainties regarding rules and procedures within the scope of this provision. This ambiguity might lead to authorization conflicts between the general assembly and the administrative board. Moreover, certain legal problems might arise from these transactions. Last, the special regulation in the Capital Market Law regarding the transactions embodying the substantial amount of assets needs detailed examination. This thesis aims to resolve the ambiguities of the aforementioned provisions and create a special legal basis for the regulations of these types of transactions."
Keywords: Anonim şirketler; Capital companies; Commercial Code; Commercial companies; Commercial law; Joint stock company; Malvarlığı; Multi partnership companies; Property; Sermaye şirketleri; Ticaret Kanunu; Ticaret hukuku; Ticari şirketler; Trade; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Çok ortaklı şirketler

Anonim ortaklıklarda şirket menfaati kavramı - Sulu, Muhammed (Marmara Üniversitesi, 2019)
Anonim ortaklıklarda şirket menfaati kavramı, şirket eksenli çatışan tüm menfaatlerin ortak paydasıdır. Pay sahibi, yönetici, çalışan, tedarikçi, alacaklı ve hatta toplumun menfaatinin sağlanması ile şirketin meşru menfaatinin sağlanması arasında doğru orantı vardır. Bir şemsiye kavram olan şirket menfaatinin sağlandığı durumlarda orta veya uzun vadede diğer grupların da menfaati sağlanmış olur. Bu kavram, şirket hayatının sürdürülebilirliği için en önemli enstrümandır. İlk bakışta soyut bir kavram olarak dikkat çeken şirket menfaati kavramına başta Türk Ticaret Kanunu olmak üzere mevzuatın pek çok yerinde bazen açıkça, bazen de örtülü olarak sıklıkla başvurulduğu gözlemlenmektedir. Çalışmada öncelikle şirket menfaati kavramı tanımlanmış, akabinde ise kavram ile ilgili olduğu düşünülen hukukî düzenlemeler mukayeseli hukuktan da yararlanılarak irdelenmiştir. The concept of company interest in joint-stock companies is the common denominator of all conflicting interests. There is a direct proportion between benefits of the shareholder, the manager, the employee, the supplier, the creditor, and even the community and the legitimate interest of the company. As an umbrella concept, if the company interest is provided, the benefit of other groups is ensured in the medium or long term. This concept is the most important instrument for the sustainability of the company life. The concept of the company interest which draws attention, prima facie, as an abstract concept, is frequently referred in many parts of the legislation especially Turkish Commercial Code both explicitly and implicitly. In the study, firstly the concept of company interest has been defined and then the legal regulations which are thought to be related to the concept have been examined by using comparative law.
536594
Keywords: Anonim şirketler; Commercial partnership; Common interest; Interest; Joint stock company; Menfaat; Ortak menfaat; Ticari ortaklık; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Adi ortaklıkta çıkma ve çıkarılma - Türkmen, Emre (Dokuz Eylül Üniversitesi, 2019)
Adi ortaklıkta çıkma ve çıkarılma ilk kez 6098 sayılı Türk Borçlar Kanunu ile pozitif hukukumuza kazandırılmıştır. Çıkma, bir ortağın tek taraflı ve diğer ortaklara varması gerekli bir irade beyanı ile ortaklıktan ayrılması şeklinde tanımlanabilir. Çıkma hakkı, diğer bir anlatımla, bir ortağın ortaklıktan kendi isteğiyle ayrılmasıdır. Çıkarma ise, ortağın kendi rızası ve isteği olmaksızın diğer ortaklar tarafından ortaklıktan uzaklaştırılması şeklinde tanımlanabilir. Her ikisi de ayrılma üst kavramının kapsamı içine girerler. Türk Borçlar Kanunu'nun sistemine göre, ortaklıktan çıkmak veya çıkarılmak için TBK m. 633'de sayılan sebeplerin gerçekleşmiş olması gerekir. Maddede belirtilen sebepler sınırlayıcı bir surette kaleme alınmadığından, çıkma ve çıkarma sebeplerinin ortaklık sözleşmesiyle genişletilmesi veya daraltılması olanaklıdır. Kanun koyucunun çıkma ve çıkarma sebeplerini düzenlerken İsviçre hukukundan yararlandığı (OR Art. 545) göze çarpmaktadır. Buna karşılık çıkma ve çıkarmanın hukuki sonuçları açısından ise Alman sisteminin (BGB 738- 740) esas alındığı görülmektedir. Çalışmamızın birinci bölümünde, ortaklık sıfatı, çıkma hakkı, çıkarma hakkına değinilmiştir. Bu bağlamda; haklı sebeple çıkma hakkına ve iki kişilik adi ortaklıkta çıkma- çıkarma haklarının gösterdiği özelliğe işaret edilmiştir. İkinci bölüm çıkma ve çıkarma nedenlerine, haklı sebeple çıkarmaya ve çıkma çıkarma prosedürüne ayrılmıştır. Haklı sebeple çıkarma kısmında, Alman hukuk öğretisinin zenginliğini ortaya koyması itibariyle, haklı sebep olmaksızın çıkarma sorunsalına yer verilmiştir. Çalışmanın üçüncü bölümünde ise çıkma ve çıkarılmanın hukuki sonuçları, özellikle; ortaklık sıfatının yitirilmesi, ayrılma payı, ayrılan ortağın tamamlanmamış işlerin sonucuna katılma hakkı, bilgi alma hakkı ile borçlardan kurtarılma talebi, ayrılan ortağın açığı kapama yükümü, ayrılan ortağa sözleşme ile yüklenen yükümlülükler ve ayrılan ortağın hukuki sorumluluğu konularının üzerinde durulmuştur. Anahtar Kelimeler: Ortaklık Sıfatı, Ayrılma, Çıkma, Çıkarılma, Haklı Sebep, Ayrılma Payı Withdrawal and exclusion in the ordinary partnership is gained positive Law with the Turkish Code of Oblligations number 6098 for the first time. Withdrawal can be defined as the separation of a partner from the partnership by a unilateral declaration of intention that must be reached by other partners. In other words, the right to withdrawal is the voluntary separation of a partner from the partnership. Exclusion can be defined as the removal of the partner by other partners without its consent. Both fall within content of the top consept of separation. According to the system of Turkish Code of Obligations, in order to wihtdraw and exclude from partnership, the reasons which listed in TCO 633 must be occured. As the reasons which stated in the article are not written in a limiting manner, it is possible to extend or narrow the reasons for withdrawal and exclusion with the partnership agreeement. It is noteworthy that the lawmaker has benefited from Swiss law (OR Art. 545) regulating the reasons for withdrawal and exclusion. On the other hand, it is seen that the German system (BGB 738- 740) is taken as the basis for he legal consequences of the withdrawal and exclusion. In the first part of our study, title of partnership, the right to withdrawal, the reasons for withdrawal and the right to exclusion are mentioned. In this context, the right to withdrawal for just cause and the property of the rights to withdrawal and exclusion in the two- person ordinary partnership is pointed out. The second part is reserved for the reasons of withdrawal and exclusion, exclusion for just cause and process of the withdrawal and exclusion. In section of exclusion for just cause, the problematic of exclusion without just cause is given as it manifests the richness of the German legal doctrine. In the third part of the study, the legal consequences of the withdrawal and exclusion, particularly; loss of the title of partnership, partnership buyout, the right of the separated partner to participate in the unfinished business, right to information, the request to be recovered from the debts, the obligation of the partner to cover the deficit, its contractial obligations and its legal liability were discussed. Keywords: title of partnership, separation, withdrawal, exclusion, just cause, partnership buyout
613698
Keywords: Adi şirket; Commercial Code; Commercial law; Dismissal from the partnership; Haklı neden; Just cause; Kanunlar 6098 sayılı; Laws 6098 numbered; Ordinary partnership; Ortaklıktan çıkarılma; Ortaklıktan çıkma; Ticaret Kanunu; Ticaret hukuku; Turkish Code of Obligations; Turkish law of obligations; Türk Borçlar Kanunu; Türk borçlar hukuku; Withdraw from a partnership

Ticari işletme kavramı ve korunması - Üstündağ, Mustafa Emi̇r (Hasan Kalyoncu Üniversitesi, 2019)
"Bu tez çalışması ile işletme yöneticilerinin ticari belge tanzim ve hukuki süreçlerine ilişkin bilgi ve algı düzeyleri ortaya konmaya çalışılmıştır. İşletme yöneticileri içinde faaliyet gösterdikleri ülkenin hukuki kurallarına göre iş piyasası ve iş hayatında faaliyet gösterirler. Ve bu kurallar ticari hayat içinde onlar için en önemli bağlayıcı normlardır. Bu çalışma ilgi ticaret hukukunun iş hayatında en önemli faaliyet ve uygulama alanı bulan ticari belge tanzimi ve hukuki süreçlerinin yöneticiler tarafından ne seviyede algılandığının ortaya konması amaçlanmıştır. Tez çalışma dört bölümden oluşturulmuştur. İlk bölümümüz giriş bölümüdür. İkinci bölümde yönetim konuları, ticari belgeye ilişkin hukuki argümanlara yer verilmiştir. Üçüncü bölüm uygulama bölümüdür. Dördüncü bölümde ise sonuç ve yorumlara yer verilmiştir. With this thesis, the level of knowledge and perception of business executives regarding the issuance and legal processes of commercial documents has been tried to be revealed. Business executives operate in the labor market and business life according to the legal rules of the country in which they operate. And these rules are the most important binding norms for them in commercial life. With this study, it is aimed to reveal the level of perception of commercial document arrangement and legal processes, which find the most important field of activity and application in business life, by managers. The study is composed of four parts. Our first part is the introduction. In the second part, administrative issues and legal arguments related to the commercial document are included. The third part is the implementation part. In the fourth section, results and comments are given."
Keywords: Bilgi düzeyi; Business management; Commercial documents; Commercial law; Level of knowledge; Managers; Ticaret hukuku; Ticari belgeler; Yöneticiler; İşletme yönetimi

Borçlar hukukunda zararın varlığı şartından bağımsız ödeme yaptırımları - Vuraloğlu, Mehmet Oğuz (Yeditepe Üniversitesi, 2019)
Türk sorumluluk hukukunda kural olarak tazminat talebinin kabul edilebilmesi için davacının zararının varlığını ispat etmesi gerekir. Ayrıca zararın miktarı, hükmolunacak tazminatın da üst sınırını oluşturur. Bununla birlikte mevzuatımızda zararın varlığı şartından bağımsız veya miktarı ile sınırlı olmadan talep edilebilecek birçok ödeme yaptırımı düzenlenmiştir. Bu doktora tezinde yalnızca borçlar hukuku alanındaki zararın varlığı şartından bağımsız ödeme yaptırımları incelenecek ve bunlarla ilgili olduğu tespit edilen, borçlar hukukunun ayrılmaz parçası olması itibariyle ticaret hukuku kapsamında öngörülen zararın varlığı şartından bağımsız ödeme yaptırımlarına temas edilecektir. Bu bağlamda temerrüt faizi ve zararın kanunen varsayıldığı diğer yaptırımlar, vâde farkı, götürü tazminat, sözleşme cezası, gerçek olmayan vekâletsiz iş görmede kazancın devri talebi, yeniden kiralama yasağına aykırı davranışın yaptırımı ve hizmet sözleşmesi hükümleri arasında yer verilen cezaî yaptırımlar, 6098 sayılı Türk Borçlar Kanunu ve 6102 sayılı Türk Ticaret Kanunu ile getirilen değişiklikler ve yeniliklerle birlikte ele alınacaktır. Ayrıca tezde, Alman hukukunda benimsenen normatif zarar teorisi ve Anglo-Amerikan hukuk sisteminde uygulanan cezalandırıcı tazminat (punitive damages) kavramlarının Türk hukukunda kabul görebilirliği araştırılacaktır. As a rule under Turkish law of liability, the claimant is required to prove the existence of damage suffered, in order to be granted compensation. Besides, the amount of loss constitutes the upper limit of indemnity to be entitled. Nevertheless, several payment sanctions that can be claimed either independently from the condition of the existence of damage or without limitation of its amount have been provided in Turkish legislation. In this dissertation, payment sanctions that are independent from the condition of the existence of damage in the field of law of obligations and, as inseperable part of it, their coherent sanctions in the area of commercial law will be analysed. In this context, default interest and other sanctions by which damage is presupposed by law, late charge, liquidated damages, penal clause, disgorgement of profits under non-genuine benevolent intervention, the sanction stipulated in case of breach of prohibition of re-renting and punitive sanctions set forth among provisions governing service contracts will be reviewed together with the alterations brought by the virtue of Turkish Code of Obligations numbered 6098 and Turkish Commercial Code numbered 6102. Moreover, the theory of normative damage adopted in German law and the concept of punitive damages applied in Anglo-American law will be researched in thesis, in the sense of their admissibility under Turkish law.
596760
Keywords: Borçlar hukuku; Cezai şart; Cezalandırıcı tazminat; Compensation; Damage; Default interest; Kazancın iadesi; Law of obligations; Maddi tazminat; Material compensation; Penal clause; Punitive damages; Return of gain; Sanctions; Tazminat; Temerrüt faizi; Yaptırımlar; Zarar

Milletlerarası Özel Hukukta arabuluculuk - Yarar, Güven (Akdeniz Üniversitesi, 2019)
Son yıllarda farklı hukuk düzenlerinde ve Türk hukukunda uyuşmazlıkların arabuluculuk yoluyla çözümü hususunda önemli gelişmeler kaydedilmesine rağmen bünyesinde yabancılık unsuru barındıran arabuluculuk faaliyetleri konusunda belirsizlik bulunmaktadır. Zira arabuluculuk faaliyetinin birden fazla hukuk düzeni ile irtibatlı olmasının arabuluculuk sürecine etkisine yönelik yasal düzenleme ve monografik çalışma eksikliği mevcuttur. Bu nedenle, arabuluculuk faaliyetinin yabancılık unsuru içermesi hâlinde meydana gelebilecek Kanunlar İhtilâfı ve Milletlerarası Usul Hukuku meselelerinin tespit edilip çözüm önerileri sunulması teorik ve pratik açıdan son derece önemlidir. Bu çalışma kapsamında ilk olarak, arabuluculuğa ilişkin genel bilgiler verilmiş ve arabuluculuğun hukuk sistemlerindeki yeri incelenmiştir. Akabinde arabuluculuğun Kanunlar İhtilâfı boyutu üzerinde durulmuş ve arabuluculuk faaliyeti kapsamında meydana gelebilecek Kanunlar İhtilâfı meselelerinin çözülebilmesi için terminoloji oluşturulması gereği anlaşılmıştır. Bu bağlamda, millî, milletlerarası ve milletlerarası ticarî arabuluculuğun çerçevesi genel hatlarıyla çizilmiştir. Ardından arabuluculuk faaliyetinin temel taşları niteliğinde olan arabuluculuk ve arabulucu sözleşmesine uygulanacak hukuka dair değerlendirme yapılmış, arabuluculuğa elverişliliğe ve arabulucunun hak ve yükümlülüğüne uygulanacak hukuka ilişkin muhtemel sorunlar tespit edilip çözüm önerilerinde bulunulmuştur. Arabuluculuğun Milletlerarası Usul Hukuku boyutu kapsamında ise arabuluculuk usulüne uygulanacak hukukun önemi ve bu hukukun tespitinde kullanılabilecek kriterlere yer verilmiştir. Daha sonra, birden fazla hukuk düzeni ile irtibatlı bulunan arabuluculuk faaliyetinin başarıyla sonuçlanmasıyla oluşan milletlerarası anlaşma belgesi ele alınmıştır. Bu bağlamda, milletlerarası anlaşma belgesinin mevcudiyeti için kabul edilebilecek koşullara yönelik değerlendirme yapılmıştır. Son olarak, milletlerarası anlaşma belgesinin tanınması ve tenfizine yönelik ihtiyaç tespit edilmiş, milletlerarası anlaşma belgesinin tanınması ve tenfizine ilişkin kabul edilebilecek ön ve aslî şartlar ile tanıma-tenfiz usulüne yer verilmiş ve sonuç ve değerlendirmelerde bulunularak çalışmamız tamamlanmıştır. Although significant progress has been achieved in different legal systems and Turkish law in terms of settlement of disputes through mediation for last years, there is uncertainty regarding mediation activities that include foreign elements. The reason is that there is not much legal regulation and monographic studies on the effect of mediation activity being linked to more than one legal order over mediation process. For this reason, it is very important theoretically and practically to identify the issues of Conflict of Laws and International Procedural Law that may occur in case of mediation activity involving foreign elements. In this study, first of all, general information concerning mediation is given and the legal aspect of mediation is examined in legal systems. Subsequently, the legal aspect of mediation in conflict of law was emphasized and it was understood that the terminology should be established in order to solve the Conflicts of Laws that may occur within the scope of mediation activity. In this context, the framework of national, international and international commercial mediation is outlined. Then, the assessment of the law to be applied to the mediation and mediation agreement which is the cornerstones of the mediation activity was made, possible problems related to the mediability and mediation of the mediator's rights and obligations were identified and solutions were proposed. Within the scope of mediation law aspect of International Procedural Law, the importance of the law to be applied to mediation procedure and the criteria that can be used in determining this law are included. Following this, the international agreement document which was formed by the successful completion of the mediation activity which is connected with more than one legal order was emphasized. In this context, an assessment was made on the conditions acceptable to the existence of the international convention. Finally, the need for the recognition and enforcement of the international agreement document was determined and our study was completed making results and evaluations by including the prerequisite and essential conditions for the recognition and enforcement of the international agreement document and the recognition-enforcement procedure.
578303
Keywords: Arabuluculuk; Droit international privé; International law; International private law; Mediation; Médiation; Uluslararası hukuk; Uluslararası özel hukuk

İmtiyazlı pay sahipleri özel kurulu - Aktaş, Betül (Galatasaray Üniversitesi, 2018)
Doktora tez konumuz olan imtiyazlı pay sahipleri özel kurulunun temel işlevi imtiyazların korunmasıdır. Bu doğrultuda, imtiyazlı pay sahiplerinin haklarını ihlal edebilecek nitelikte olan genel kurulun anasözleşme değişikliklerinde, yönetim kuruluna sermaye artırımı yetkisi verilmesi kararında ve kayıtlı sermaye sisteminde yönetim kurulunun yaptığı sermaye artırımında özel kurul onayı alınması gerekmektedir. Aksi takdirde alınan genel kurul veya yönetim kurulu kararı uygulanamaz. Özel kurul toplantısının yapılabilmesi bakımından aranan temel şartlardan biri, imtiyazlı pay sahiplerinin haklarını ihlal edebilecek nitelikte bir anasözleşme değişikliği veya yönetim kurulunun sermaye artırımı kararının alınmasıdır. Özel kurul kararının alınmadığı aşamada genel kurul kararı hukuken geçerli, fakat hukuki sonuçlarını doğurması özel kurul onayının varlığına bağlıdır. The basic function of the special committee of preference shareholders is to protect the preferences. In this respect, Art. 454 of the Turkish Commercial Code (TCC) regulates the approval of special committee for the amendments to the articles of association of the general assembly, which are in the nature of violating the rights of the preferred shareholders, authorization for capital increase for the board of directors and the capital increase in the registered capital system. Otherwise, the decision of the general assembly or board of directors cannot be applied. One of the basic conditions sought in order to be able to hold the special board meeting is to adopt an amendment in the articles of association or the capital increase decision of the board of directors. At the stage where the decision of the special board is not taken, the decision of the general assembly is legally valid but its legal consequences are subject to the approval of the special committee.
Keywords: Anonim şirketler; Commercial law; Joint stock company; Pay sahipleri; Privileged share; Shareholders; Special meeting; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Özel kurul; İmtiyazlı pay

Anonim ortaklıklar hukukunda özel denetim - Günay, Gözde Engin (Galatasaray Üniversitesi, 2018)
Anonim şirketlerde pay ve oy çoğunluğunu elinde bulunduranlar bir araya geldikleri zaman, hâkimiyeti elinde bulundurdukları için şirket yönetimini etkileyecek kararları alarak, kendi kararları doğrultusunda şirketi yönlendirebilirler. Çoğunluğu elinde tutanların gücü karşısında azlık ve münferit pay sahiplerinin korunması, onlara bazı bireysel haklar tanınması ile sağlanmaya çalışılmıştır. Çalışmamızın konusu Anonim Ortaklıklar Hukuku'nda Özel Denetim'dir. TTK'nin "pay sahibinin kişisel haklarıˮ ana başlığı ve V. numaralı özel denetim isteme hakkı alt başlığı altında TTK m.438 ve 444' da düzenlenen özel denetim isteme hakkı, anonim ortaklıkta önemli bir bireysel ortaklık ve azlık haklarından birisini oluşturmaktadır. Aydınlatıcı haklar olarak adlandırılan bilgi alma ve inceleme hakkı ile özel denetim isteme hakları; şirketin faaliyetleri, işlemleri, ekonomik durumu hakkında yeterli bilgiye sahip olmayan pay sahiplerinin, bu haklarını kullanarak daha bilinçli olmalarını sağlarlar. Bu iki hak, hem önleyici hem de telafi edici niteliktedir. According to Article 438, CO Art.697a, any shareholder may introduce a motion at the general meeting of shareholders calling for certain facts to be subject to a special examination by a special and independent searcher. The special examination has to be necessary for the exercising of the shareholders' rights. If the shareholders' meeting approves the motion, the judge (called upon by the Company or by shareholder) appoints the special searcher. If the general meeting does not approve the motion calling for the appointment of the appointment of the special searcher, shareholders who represent at least ten percent of the share capital or who represent shares with par value of one million Turkish Lira may request the judge to appoint a special searcher. The shareholders are legally entitled to the appointment of a special searcher if they credibly establish that corporate bodies have violated the law or the articles of incorporation and have thereby damaged company or shareholders. Special examination has a pre-condition for requesting, as per article TTK m.438, in order for a shareholder to request a special examination, that shareholder or any shareholder of the company should have duly consumed its right to information and examination. This is pre- condition for requesting the special examination
635031
Keywords: Anonim ortaklıklar; Anonim şirketler; Control; Denetim; Incorporated companies; Joint stock company; Private auditor; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Özel denetçi

Acentenin ücret hakkı - Teki̇n, Ufuk (Ankara Üniversitesi, 2018)
Ücret hakkı acentenin en temel hakkı olup Türk Ticaret Kanunu'nun 113 ila 116. maddeleri arasında düzenlenmiştir. Hangi işlemlerin acenteye ücret hakkı kazandıracağı 113. maddede yer almaktadır. Bu hükme göre acente doğrudan kendi katkısıyla kurulan işlemler sebebiyle ücrete hak kazanabileceği gibi, müvekkile daha önce kazandırdığı müşterilerle sonradan kurulan aynı nitelikteki işlemler sebebiyle de ücrete hak kazanabileceği ifade edilmiştir. Söz konusu hükme göre ayrıca acente, kendisine belirli bir bölge veya müşteri çevresi bırakıldığı takdirde, bu bölgede veya müşteri çevresiyle kendi katkısı olmadan kurulan işlemler sebebiyle de ücrete hak kazanabilecektir. Yine aynı hükme göre acente, bazı şartların varlığı halinde acentelik sözleşmesinin bitiminden sonra kurulan işlemler sebebiyle de ücrete hak kazanmaktadır. Acentenin ücrete hak kazanabilmesi için Türk Ticaret Kanunu m. 113'e göre ücrete hak kazandıran bir işlemin varlığına ek olarak, m. 114'te ifade edildiği üzere kurulan işlemin ifası da gerekir. İşlemin ifasıyla doğan ücret hakkı, doğumu tarihinden itibaren en geç üç ay içinde ve her halde sözleşmenin sona erdiği tarihte muaccel olur (m. 116). Acentenin, ücret istemi, muacceliyeti ve hesaplanması bakımından önemli olan bütün konular hakkında kontrol hakkı bulunmaktadır. Bu hak, onun bilgi alma, müvekkilin defter kayıtlarının suretlerinin gönderilmesini talep ve inceleme hakkı olmak üzere üç haktan oluşmaktadır. Çalışmamızın birinci bölümünde Türk ve karşılaştırmalı hukukta konunun düzenlenişi ile kavramsal çerçeve üzerinde durulacak; ikinci bölümünde ücrete hak kazanılmasının şartları ele alındıktan sonra üçüncü bölümünde ücretin belirlenmesi, hesaplanması ile ödenmesi ve ücrete ilişkin kontrol hakkı açıklanmaya çalışılacaktır. The right of remuneration, which regulated between the Articles 113 to 116 of the Turkish Commercial Code, is the most fundamental right of commercial agent. According to Article 113, it is stated that the commercial agent has the right of remuneration due to the transactions established by its own contribution. Commercial agent has the right of remuneration also for same quality of transactions, which established later with the former customer. According to same Article, the commercial agent may also be entitled to remuneration, whether it is left in a certain area or customer environment, due to the transactions established in this area or the customer environment even without its own contribution. It is pointed in the same Article that, commercial agent also has the right of remuneration due to transactions established after the end of the commercial agency contract in the presence of certain conditions. As indicated in the Article 114, it is also necessary to perform the transaction, which gives the commercial agent the right of remuneration. The remuneration arising from the performance of the transaction shall be due within three months at the latest from the date of birth and in any circumstances at the date on which the contract is concluded (Article 116). The commercial agent has the right to control all matters that are important in terms of remuneration, accural and calculation. That right includes, the right to demand information, copies of the commercial book records of the client and examination. In the first part of our work we will focus on the regulations and conceptual framework of Turkish and comparative law. After considering the conditions of the acquisition of the remuneration in the second part, it is aimed to explain the determination and the calculation of the remuneration, payment and the control right of commercial agent about the right of remuneration in the final section.
Keywords: Acenteler; Agents; Commercial law; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Wage; Wage account; Wage fixing; Ücret; Ücret belirleme; Ücret hesaplama

Viyana satım sözleşmesi uyarınca teslim borcu - Davarci, Atakan Âdem (İstanbul Ticaret Üniversitesi, 2017)
CISG, yeknesak satım hukuku oluşturma çabasının bir sonucu olarak karşımıza çıkmaktadır. CISG'in temelini satım sözleşmesi oluşturur. Satım sözleşmesi insanların mal alımını sağlayarak ihtiyaçlarını karşılamasını sağlayan bir sözleşmedir. Satım hukukunun temelini satım sözleşmesi oluşturmaktadır. Satım sözleşmeleri tarafların mal ve satım bedeli üzerinde anlaşmaları ile kurulur. Satım sözleşmesinde satıcının asıl borcu ise sözleşmeye konu malın teslimidir. Malın doğru yer ve zamanda teslim edilmesi ve teslim edilen malın sözleşmeye uygun olması konuları teslimin en önemli unsurlarıdır. Malın sözleşmeye uygun olmaması veya sözleşmeye uygun yer ve zamanda teslim edilmemesi satıcının sözleşmeye aykırı davrandığını gösterir. Sözleşmeye aykırılığın tespiti, aykırılığın derecesine göre alıcıya bazı haklar tanımaktadır. Bu çalışma, hem teslim borcunun içeriğini hem de teslim borcu açısından sözleşmeye aykırılığı ayrıntılı olarak ele almaktadır. CISG emerges as a result of the effort to create a uniform selling law. The basis of the CISG is the contract of sale. The sale contract is a contract that allows people to buy goods and meet their needs. The sales contract constitutes the foundation of the law of sale. Sale contracts are established with the parties agreeing on the goods and sales price. The actual debt of the seller on the sales contract is the delivery of the goods subject to the contract. The fact that delivery at the right place and time and the delivered goods conform to the contract are the most important elements of delivery. The fact that the merchandise is incompatible with the contract or not delivered at the proper time and place indicates that the seller is breaching the contract. The determination of breach of contract gives the buyer some rights according to the degree of breach. This study elaborates on the contradiction to the contract in terms of both the content of the delivery debt and the delivery debt.
Tez N°478791
Keywords: CISG; Commercial law; Contracts; Milletlerarası Mal Satımlarına İlişkin Birleşmiş Milletler Antlaşması; Obligation to delivery; Sözleşmeler; Teslim borcu; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku; Vienna Sales Convention; Viyana Satım Sözleşmesi

Örtülü kazanç aktarımı - Günay, Ece Deniz (Galatasaray Üniversitesi, 2017)
Sermaye Piyasası Kanunu'nun amacı, sermaye piyasasının işleyişinin güvenli bir biçimde sağlanmasına ve yatırımcıların hak ve menfaatlerinin korunmasıdır. Bu amaçla yatırımcıların(halka açık anonim ortaklık pay senedi sahiplerinin); yatırımlarını gerçekleştirirken kararlarını doğru bilgilere dayanarak vermelerini sağlamak, şirketin kontrolüne sahip olan şahısların kişisel menfaatlerinden bağımsız olarak sadece şirketin menfaatleri doğrultusunda hareket etmelerini temin etmek üzere SerPK kendi içinde düzenlemeler barındırmaktadır. Bunlardan biri de SerPK madde 21 hükmüdür ve SerPK'nın amaçları doğrultusunda bir özel hüküm niteliği taşımaktadır. Söz konusu hükmün ratio legis'inin, halka açık anonim ortaklığın; ilişkili kişiler ile yapılan işlerde emsallere, piyasa teamüllerine uygun, ticari hayatın basiret ve dürüstlük ilkelerine uygun işlemler gerçekleştirmesini sağlamak suretiyle, ortaklık pay sahiplerinin menfaatlerinin korunması olduğu anlaşılmaktadır. SerPK madde 21'de sayılan yapılan işlem sonucu; halka açık ortaklığın, kolektif yatırım kuruluşunun, bunların iştirak ve bağlı ortaklıklarının; kârlarını azaltmak, malvarlıklarını azaltmak, kârlarının artmasını engellemek, malvarlıklarının artmasını engellemek, kârlarını korumak veya artırmak için yapmaları beklenen faaliyetleri yapmamak, malvarlıklarını korumak veya artırmak için yapmaları beklenen faaliyetleri yapmamak suretiyle ilişkili oldukları kişilerin kârlarının ya da malvarlıklarının artmasını sağlamak şeklinde aktif veya pasif davranışlarla kazanç aktarımında bulunmaları yasaklanmıştır. Konunun vergi hukukunda, Kurumlar Vergisi Kanunu m. 13'te transfer fiyatlandırması yoluyla örtülü kazanç dağıtımı adıyla düzenlenmekte olduğu görülmektedir. Şüphesiz vergi hukukunda gözetilen amaçlarla sermaye piyasası hukukunun izlediği amaçlar arasındaki farklılık, maddi unsurları benzeyen bu iki düzenlemeyi birbirinden ayırmaktadır. Konunun vergi hukuku ve maliye boyutu bağlamında eserler mevcuttur. Buna mukabil bu tez ile SerPK düzenlemesinin ardından konunun özel hukuktaki yeri ve sonuçları ile spesifik olarak konunun Borçlar Hukuku, Ortaklıklar Hukuku ve Sermaye Piyasası Hukuku yönlerinden araştırılması hedeflenmektedir. [...] Related-party transactions include the routine forms of abusive insider behavior that have come to be dubbed tunneling in the economic literature a category that includes all forms of misappropriation of value by corporate insiders. Prohibited related party transactions are the ones which contain transfer prices that contradict the arm's length principle. SerPK article 21/4 say that parties which have received an income transfer are obliged to return the transferred amount with its legal interest within the period to be determined by the Board. Sweeping prohibitions of related-party transactions were once common in company law. Apart from bans on loans, prohibitions tend to focus on transactions between managers and third parties that are thought to divert the value of information that the law assigns, implicitly or otherwise, to the company or its shareholders. It is forbidden that publicly- held corporations and collective investment schemes and their subsidiaries and associates to transfer income to real persons or legal entities with whom they have a direct or indirect relationship in terms of management, audit or capital by decreasing their profits or their assets or by preventing the increase of their profits or their assets via performing transactions such as making contracts or commercial practices containing different prices, fees, costs or conditions producing a trading volume in violation of the conformity with market practices and comparability to similar transactions prudence and honesty principles of commercial life.
475523
Keywords: Borçlar hukuku; Camouflage of earning distribution; Camouflaged capital; Capital Market Law; Commercial law; Kar aktarımı; Law of obligations; Profit shifting; Sermaye Piyasası Kanunu; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku; Örtülü kazanç dağıtımı; Örtülü sermaye

Rekabet Hukukunda ekonomik bütünlük kavramı ve hukuki sonuçları - Hüseyi̇n, Tamer (Marmara Üniversitesi, 2017)
4054 Sayılı Rekabetin Korunması Hakkında Kanun'un uygulanması bakımından teşebbüs kavramının merkezi önemi haiz olması, ilk olarak teşebbüsün tespit edilmesini gerektirmektedir. Ancak kendiliğinden gelişmiş birtakım fiili durumlar ve yasal düzenlemeler, teşebbüsün tespit edilmesini giderek zorlaştırmaktadır. Teşebbüsün sınırlarını belirleme amacı taşıyan bu tespit rekabet hukukunda "ekonomik bütünlük" kavramıyla ifade edilmektedir. Fiili durumlar ve yasal düzenlemelerin sebep olduğu karmaşa dolayısıyla teşebbüsün tespit edilmesinde merkezi öneme sahip ekonomik bütünlük kavramının belirlenebilmesi noktasında uygulamada çeşitli zorluklar ile karşılaşıldığını söylemek mümkündür. RKHK bağlamında rekabet ihlaline yönelik işlemlere taraf teşkil eden unsurlar teşebbüsler olduğundan ilgili teşebbüslerin ve dolayısıyla bu teşebbüslerin sınırlarının belirlenmesi gerektiğinden, ekonomik bütünlük burada büyük öneme sahip bir kavram olarak karşımıza çıkmaktadır. Bu nedenle çalışmanın amacı ekonomik bütünlüğün ne şekilde tespit edileceği sorununun ele alınması ve çözüme yönelik öneriler sunulmasına yöneliktir. For the implementation of the Code on the Protection of Competition No. 4054, the fact that the concept of enterprise has a central importance requires that the enterprise be determined first. However, some spontaneously developed actual situations and legal regulations make it increasingly difficult to identify the enterprise. This determination, which aims to determine the boundaries of the enterprise, is expressed in the concept of "economic entity" in competition law. It is possible to say that various difficulties have been encountered in the practice of determining the concept of economic entity with the central presumption when the enterprise is identified due to the actual situation and the complexity caused by the legal regulations. In the context of the Code on the Protection of Competition No. 4054, the economic entity is a concept with great precaution here, since the elements that are the parties to the competition breach are enterprises, and the boundaries of the related undertakings and therefore of these undertakings must be specified. For this reason, the aim of the study is to examine the problem of how economic entity will be determined and to propose suggestions for solution.
476857
Keywords: Commercial law; Competencia; Competition law; Concorrência; Concurrence; Economic entity; Ekonomik bütünlük; Hukuki sonuç; Judicial conclusion; Law on Protection of Competition; Rekabet; Rekabet hukuku; Rekabetin Korunması Hakkında Kanun; Ticaret hukuku

Sınır aşan şirket birleşmelerine uygulanacak hukuk - Kavlak, Bengül (Dokuz Eylül Üniversitesi, 2017)
Son yıllarda, uluslararası ticaret hukukundaki gelişmelerle birlikte sınır aşan şirket birleşmeleri de giderek önem kazanmıştır. Şirketler bakımından yabancı bir şirketle birleşmenin getirdiği pek çok avantaj yanında, çeşitli zorluklar da mevcuttur. Bu zorluklardan en önemlilerinden bir tanesini de sınır aşan birleşmelere uygulanacak hukukun tespiti oluşturmaktadır. AB hukukunda, sınır aşan şirket birleşmelerine ilişkin düzenlemeler öngörülerek üye devletler arasındaki uygulamanın yeknesaklaştırılması adına 2005/56/EC sayılı Direktif kabul edilmiştir. Türk hukuku bakımından ise, sınır aşan şirket birleşmelerinin önemine vurgu yapılmakla birlikte bu hususta henüz bir düzenleme getirilmiş değildir. Çalışmada, AB hukukunda bu hususta öngörülen düzenlemeler de değerlendirilmek suretiyle, Türk hukukunda sınır aşan şirket birleşmelerine uygulanacak hukukun tespiti üzerinde durulmuştur. Sınır aşan şirket birleşmelerine uygulanacak hukuka ilişkin görüşler de değerlendirilerek, AB hukuku ile de uyum sağlamak adına, Türk hukukunda her bir birleşme işlemi için uygulanacak hukuk değerlendirilmiş ve sınır aşan şirket birleşmelerine uygulanacak hukuka ilişkin düzenleme önerisinde bulunulmuştur. Anahtar Kelimeler: Sınır aşan birleşme, uygulanacak hukuk, şirket birleşmeleri, 2005/56/EC, AB hukuku. With the recent developments in international commercial law, cross-border mergers have been developed during the last few decades. Besides the advantages of merging with a company from a different country, there are also some difficulties especially about determining the applicable law. In European Union, Directive 2005/56/EC of the European Parliament and of the Council of 26 October 2005 on cross-border mergers of limited liability companies has been accepted to regulate this issue and harmonise the rules of substantive law of the member states. In Turkish law, despite the emphasize on the significance of the cross-border mergers at the preamble of Turkish Commercial Code, currently there is no codification about cross-border mergers. This study attempts to make a discussion about the applicable law to cross-border mergers from the perspective of Turkish law and a comparison between the regulations of European Union law and Turkish law. Yet, taking into consideration the EU-Turkey relations and the developments about the adaption of Turkish law to European Union law, the harmonization of rules about cross-border mergers must be inevitable. As the applicable law to cross-border mergers is topical and important subject for Turkish law, the study will also deal with the legislation proposal in accordance with European Union law. Key Words: merger, cross-border merger, applicable law, 2005/56/EC, EU law.
460545
Keywords: Avrupa Birliği hukuku; Birleşmeler; European Union law; Fusion d'entreprises; Intenational strategical mergers; International Law; International enterprises; International integrations; Mergers; Uluslararası Hukuk; Uluslararası bütünleşmeler; Uluslararası işletmeler; Uluslararası stratejik birleşmeler; Şirket birleşmeleri

Dönüştürücü arabuluculuk ve problem çözücü arabuluculuk ile uyumlaştırılması - Kiyak, Emre (Atatürk Üniversitesi, 2017)
Nüfus artışı, uyuşmazlıkların karmaşık boyutlara ulaşması, ekonomik kısıtlar, yeni uyuşmazlık çözümü anlayışları gibi nedenlerle modern medeni usul hukuku, sübjektif hakların korunması ve maddi gerçeğe ulaşma gibi klasik hedeflerin dışında, yeni hedeflerin başarımına odaklanmaktadır. Adalete erişimini zorlaştıran kısıtları ortadan kaldırmak noktasında, alternatif uyuşmazlık çözüm yöntemlerine işlerlik kazandırılması modern yargılama reformlarının olmazsa olmaz bir parçası haline gelmiştir. Kısaca tarafsız üçüncü kişi yardımıyla yürütülen müzakere şeklinde tanımlanabilecek arabuluculuk yöntemi de, bu şekilde gerçekleştirilen reform hareketlerinde yaygın olarak benimsenen ve üzerinde en çok çalışılan alternatif uyuşmazlık çözüm yöntemi olarak gündeme gelmektedir. Arabuluculuk, en yalın haliyle yukarıdaki şekilde bir tanıma sahip olsa da bugün, söz konusu yöntem ile ilgili literatür oldukça derin boyutlara ulaşmıştır. Arabuluculuk sürecinin modellenmesine ilişkin çalışmaların, artık klasik kolaylaştırıcı – değerlendirici bloğundan sıyrılarak taraflar arasındaki sorunlara ilişkisel boyuttan yaklaşan yeni modellerin oluşturulmasına odaklanması bunun göstergelerinden sadece biridir. Bu çalışmanın konusu, Robert A. Baruch Bush ile Joseph P. Folger tarafından 1994 yılında kaleme alınan The Promise of Mediaton: Responding to Conflict through Empowerment and Recognition isimli eserde temelleri oluşturulan ve aynı yazarların 2005 yılında yayınladıkları The Promise of Mediation: The Transformative Approach to Conflict isimli eser ile günümüzdeki halini alan dönüştürücü arabuluculuk yaklaşımının, problem çözücü yaklaşım ile entegrasyonunun sağlanmasının mümkün olmadığına yönelik argümanına karşı, bu yaklaşımın problem çözücü yaklaşımla uyumlaştırılmasının mümkün olduğu temel argümanından yola çıkarak uygulamaya yönelik heterojen bir arabuluculuk yaklaşımı oluşturmaktır. Bu doğrultuda çalışmanın birinci bölümünde arabuluculuk yöntemi genel hatlarıyla ele alınacak, ikinci bölümde temel müzakere modelleri içindeki konumundan başlanarak dönüştürücü yaklaşımın arabuluculuk alanındaki konumu saptanacak ve bu yöntemde benimsenen temel taktik ve stratejilere değinilecektir. Çalışmanın üçüncü bölümünde ise, dönüştürücü arabuluculuğa getirilen eleştiriler genel olarak ele alındıktan sonra, söz konusu arabuluculuk yaklaşımını problem çözücü yaklaşımla aynı arabuluculuk sürecinde bir araya getirebilecek heterojen, modüler ve dinamik bir arabuluculuk modeli oluşturulmaya çalışılacaktır. Son bölümde ayrıca, uyumlaştırılmış yaklaşım adı verilen bu yaklaşımın çatışma dönüşümüne odaklanan bir yaklaşımın uygulama alanını genişletme ve mahkeme bağlantılı uyumlaştırılmış arabuluculuk yapısını oluşturma şeklinde tezahür eden iki temel fayda odağına vurgu yapılacaktır. Sonuç bölümünde ise, çalışmanın tezine yönelik değerlendirmeler bir bütün halinde sunulacaktır. Due to reasons like population growth, conflicts reaching complex dimensions, economic constraints, new dispute resolution approaches, modern civil procedure law focuses on the achievement of new goals, beyond the classical goals of protecting subjective rights and achieving material truth. At the point of eliminating the constraints that make it difficult to access to justice, the introduction of alternative dispute resolution methods has become an indispensable part of modern judicial reforms. In short, mediation method that can be defined as a negotiation conducted with the assistance of a neutral third party is also the most commonly used alternative dispute resolution method that is widely adopted in these reform movements carried out in this way. Although mediation has the above definition in its simplest form, today the literature on this method has become quite extensive. The fact that studies on modeling the mediation process are now focused on creating new models approaching the problems between the parties from a relational dimension rather than the classical facilitator - evaluator block is simply one of the indicators of this. The subject of this study is to build a heterogeneous mediation approach for implementation, based on the basic argument that it is possible to harmonize transformative mediation approach with the problem solver approach, against the argument that it is not possible to achieve integration of the transformative mediation approach, which was established in the work The Promise of Mediation: Responding to Conflict through Empowerment and Recognition, written by Robert A. Baruch Bush and Joseph P. Folger in 1994 and taken its current form in the work published by the same authors in 2005, The Promise of Mediation: The Transformative Approach to Conflict, with the problem solving approach. In the first part of the study, the mediation method will be discussed in its general terms, and in the second part, starting from its position in the basic negotiation models, the position of the transformative approach in the field of mediation will be determined and the basic tactics and strategies adopted in this method will be mentioned. Finally, in the third part of the study, after the criticisms of the transformative mediation approach are discussed in general terms, a heterogeneous, modular, and dynamic model of mediation will be developed that brings this approach together with the problem solving approach in the same process. In addition, in the final section, two fundamental focuses of benefit of this approach, which is called the harmonized approach, that manifests themselves as expanding the scope of application of an approach that focuses on conflict transformation and creating court-connected harmonized mediation structure, shall be emphasized. In the conclusion section, evaluations of the thesis of the study will be presented as a whole.
479453
Keywords: Arabuluculuk; Conflict; Conflict resolution; Harmonization; Incompatibility; Labour disagrement; Mediation; Problem solving; Problem çözme; Transformative mediation; Uyumlaştırma; Uyuşmazlık; Çatışma; Çatışma çözme; Önüştürücü arabuluculuk; İş uyuşmazlıkları

Kurumsal yönetim ilkeleri bakımından halka açık anonim şirketlerde icrada görevli olmayan yönetim kurulu üyeleri - Küçükgüngör, Makbule Asli (Ankara Üniversitesi, 2017)
In publicly held companies where the shareholdership is differentiated from the control and the management of the company, the dispersed shareholding structure prevents the active involvement of the shareholders in the company management while the directors have the opportunity to act in their personal interests. The aforementioned conflict of interest between the shareholders and the directors in the management of the publicly held companies which has been identified as "Principle-Agent Problem" in economic literature has had substantial effect in modern company law. Accordingly, considerable work in the company law has been dedicated to the legal strategies developed to decrease the cost of monitoring directors for shareholders. One of the main corporate governance strategies that is developed to deal with the "Principle-Agent Problem" focuses on increasing the number and the effectiveness of the directors who are not involved in the managing activities of the company. The main principle of this legal strategy is the designing the structure of the board of directors on the basis of team spirit and mutual accountability. In that sense, non-management directors conduct their duties as directors without having management tasks in the company. As these directors work on a part time basis they are not fully depended to the company and in principle they receive symbolic amounts of remuneration. Under this incentive strategy it is accepted that the esteem and reputation that the non-management directors preserve in eye of the public are the main incentives that motivate them to monitor the managing directors. The corporate governance principles are designed as alternative to the rule based regulation approach in company law. The non-management directorship which is introduced as a corporate governance concept for solving the problem of conflict of interest between the shareholders and the directors is the focus area of this thesis. The thesis consists of five parts. In the first part of this study, the concept of corporate governance which is the source of non-management director concept and the conflict of intererest problem between the shareholders and the directors regarding the management of the publicly held companies have been introduced. In this regard, "Centralised Management" and "Principle-Agent Problem" are explained. Finally, based on the "Principle-Agent Problem" the legal theories that are developed to increase the effectiveness of the board of directors, the categorisation of those strategies that has been introduced and place of the non-management directors among those strategies are clarified. In the second part the emergence of the concept of non-management directorship system and the development of the mechanisms for increasing director independence are described and different forms of non-management directors in one-tier board structures are analysed. On this subject the legal designing of the concepts of independent and disinterested directorship which is developed in American law and non-executive directorship which is introduced in the British Law is analysed. In the third part, the concept of the supervisory directorship which corresponds to the non-management directorship in two-tier board system is examined. Forth part of the thesis focuses on the comparison of one-tier and two-tier board structures in application of the non-management directorship concept. Within this scope, it has been analysed whether there is a convergence in the functions of non-management directors in terms of supervision, strategy development and networking in the two types of board systems. Related to this analysis, the effectiveness of the non-management directors in one-tier and two-tier board systems and the role of the institutional investor regarding this effectiveness is evaluated. In recent years, depending on the inclination of convergence in different law systems, there has been an alignment effort in the European Union to have a single set of rules regarding the non-management directors. In this respect as a final focus point, in this part, the regulations of the European Union regarding the non-management directors are examined. The fifth part is dedicated to legal design of the independent directorship which is regulated under the non-management directorship concept in the Turkish law. Turkish Commercial Code is the general code that regulates all joint stock corporations including the publicly held ones. Therefore in order to explain the effects of Anglo-American approach on the administrative organ, the approach of the Turkish Commercial Code regarding the structure and functioning of the board of directors which are based on corporate governance principles are explained. Following that general introduction, the system change regarding the corporate governance principles in Turkey which consists of application of mandatory rules rather than "Comply or Explain" approach that is applicable to independent directors is explained. After that the independence criteria which are set for the independent directors under the capital market regulations for publicly held joint stock corporations and the role of independent directors in decision making mechanism are analysed. Finally, the structure and functioning of the board committees are evaluated by examining the functions of the independent board members.
482045
Keywords: Bağımsız idari otoriteler; Commercial law; Corporate governance; Halka açık ortaklıklar; Independent administrative authority; Kurumsal yönetim; Management; Members of the board directors; Principle; Public held companies; Representation; Ticaret hukuku; Vekalet; Yönetim; Yönetim kurulu üyeleri; İlke

Özel Hukuk sözleşmelerinin Vergi Hukukunda geçerliliği - Kurtulmaz, Nihan (Marmara Üniversitesi, 2017)
Vergi hukuku kurum ve işlemlerini iktisadi hayatın işleyişi üzerine kurmuştur. İktisadi hayat ise ticaret hukuku, borçlar hukuku ve medeni hukuk gibi özel hukuk kurallarının denetimindedir. Bu durumun doğal bir sonucu olarak da vergi hukuku vergiyi doğuran olayları tanımlarken özel hukukun kurum ve kavramlarından faydalanmaktadır. Hukuki işlemlerin en önemlilerinden biri olan özel hukuk sözleşmeleri de vergilendirmenin sebep unsurunu oluşturabilmektedir. Çalışmamızda vergi hukukunun özel hukuk ile ilişkisi açıklanmış ve özel hukuk sözleşmelerinin vergi hukukundaki geçerlilikleri literatürdeki farklı görüşlere, yargı kararlarına ve İdare'nin görüşlerine yer verilerek araştırılmıştır. Özel hukuk sözleşmeleri ile ortaya çıkartılabilen sayısız durumda her iki hukuk dalının aynı olaya farklı bakış açıları mükellefler ve İdare'nin sıklıkla karşı karşıya gelmesine sebep olmaktadır. Vergiyi doğuran olayın sözleşmelerle ortaya çıkması halinde adil bir vergilendirme bu sözleşmelerin hukuki nitelendirmelerinin doğru yapılmasıyla mümkün olmaktadır. Ayrıca vergi hukukunun özel hukuk kavramlarına atfettiği anlamlar verginin yasallığı ilkesi çerçevesinde kanunlarla şekillenmelidir. Anahtar Kelimeler : Vergi Hukuku, Özel Hukuk Sözleşmeleri, Verginin Yasallığı. Tax law establishes its institutes and procedures as based on the operation of the financial life. Financial life is under the control of the rules of the private laws such as trade law, obligations law and civil law. As a natural consequence of this, when tax law defines the events that give rise to tax, it also benefits from the institutions and concepts of the private law. Private law contracts, which are among the most important legal procedures, may also result in taxation. In our study, the relation of the tax law with private law is explained and the validity of the private law contracts in tax law is examined by inclusion of different opinions in the literature, judicial decisions and the opinions of the Administration. The different points of views of both branches of law about the same event in countless number of cases, which occur as a result of private law contracts, cause the tax payers come up against the Administration frequently. If the event giving rise to taxation is a result of the contracts, then a fair taxation is possible through correct legal identification of such contracts. Moreover, the meanings referred by the tax law to the private law concepts should be shaped by the laws within the frame of the principle of the legality of tax Keywords : Tax Law, Private Law Contracts, Legality of Tax
464385
Keywords: Compliance with laws; Contracts; Droit fiscal; Fiscal law; Geçerlik; Hukuka uygunluk; Kanunilik; Legality; Mali hukuk; Private law; Sözleşmeler; Tax law; Validity; Vergi hukuku; Özel hukuk

Şirketler topluluğunda hakimiyetin hukuka aykırı kullanılması - Özcanli, Fatma Beril (İstanbul Üniversitesi, 2017)
Şirketler Topluluğunda Hakimiyetin Hukuka Aykırı Kullanılması başlıklı çalışmamız ile 6102 sayılı TTK ile ilk defa pozitif düzenlemeye kavuşturulan şirketler topluluğu sorumluluk hukuku incelenmiştir. Kanun koyucu TTK m. 202 hükmü ile alelade hakimiyet bakımından, TTK m. 203 vd. hükümleri ile de tam hakimiyet bakımından hakimiyetin hukuka aykırı kullanılması ve sonuçlarını düzenlemiştir. TTK'nın şirketler topluluğuna ilişkin hükümlerinin önemli bir kısmı AktG sistematiği örnek alınarak oluşturulmuştur. Bu doğrultuda şirketler topluluğuna ilişkin TTK sistematiği incelenirken Alman doktrinine de sıklıkla başvurulmuştur. Çalışmamız kapsamında TTK m. 195 hükmünde düzenlenen kontrol araçları ve hakimiyet kavramı; yönlendirme, talimat ve yapısal karar alınması yoluyla hakimiyetin hukuka aykırı kullanılması; kayıp-denkleştirme sistemi; hakimiyetin hukuka aykırı kullanılmasından kaynaklanan sorumluluk, unsurları ve öngörülen talep hakları ayrıntılı olarak incelenmiştir. The new Turkish Commercial Code (TCC) Nr. 6102 has introduced the notion of "groups of companies" to the Turkish Commercial Law; hereby the "groups of companies" concept was spelled out for the first time in Turkish law. This thesis examines corporate group law in Turkey and demonstrates the intragroup responsibility regime in comparison with the German system. TCC Art. 202 foresee the consequences of unlawful exercise of control in basic dominance/control. Whereas TCC Art. 203-206 regulate the responsibility regime regarding the unlawful exercise of control with regards to full-control. Turkish corporate group law has been enacted under the big influence of the German AktG-System. Although our thesis focuses on the analysis regarding corporate group provisions of the TCC, the research on German law also covers a significant part of our thesis. This thesis examines in detail the control instruments stipulated in TCC Art. 195, the concept of control, the unlawful exercise of control by means of TCC Art. 202/1, TCC Art. 203 and TCC Art. 202/2, the concept of disadvantage and adjustment, the different liability regimes with regards to the category of the unlawful exercise of control and the rights of action.
483051
Keywords: Business union; Company law; Dominant position; Hakim durum; Hukuka aykırılık; Multicorporate enterprises; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Unlawful; İşletmeler topluluğu; Şirket toplulukları; Şirketler hukuku

Anonim ortaklık genel kurul toplantılarında pay sahibinin temsili - Tekten, Emel (Erciyes Üniversitesi, 2017)
Pay sahipleri genel kurula katılma maliyetlerinin fazla gelmesi, buna ayıracak zamanlarının olmaması veya sağlık sorunları gibi sebeplerle dolayı genel kurula katılmak istemeyebilir. Bunun sonucunda pay sahiplerinin şirketin işleyişine ve genel kurul kararlarına etki etme olasılıkları zayıfladığından; genel kurullarda, etkin ve iyi organize olmuş pay sahipleri gerçekte çoğunluk olmasalar da istedikleri kararların alınmasını sağlayabilmektedirler. Bu durum genel kurulda güç boşluğu sorununun doğmasına neden olmaktadır. Bu kapsamda anonim şirket genel kurulunda pay sahibinin temsilinin bu konudaki sorunları giderme de önemli bir rolü vardır. İşte tezimizin konusu, TTK ve SerPK çerçevesinde anonim şirket genel kurulunda pay sahibinin temsilidir. Bilindiği üzere 6102 sayılı TTK bir bütün olarak 01.07.2012 tarihinde yürürlüğe girmiş ve böylece elli yılı aşkın bir süredir uygulanan 6762 sayılı eTTK'yı yürürlükten kaldırmıştır. Yine 6362 sayılı SerPK 30.12.2012 tarihinde yürürlüğe girerek 2499 sayılı SerPK'yı yürürlükten kaldırmıştır. Bu yeni kanunlarda tez konumuzla ilgili olarak bir dizi değişiklikler yapılmış ve yenilikler getirilmiştir. Tez konusunun seçilmesindeki amaç, pay sahibinin temsiliyle ilgili olarak TTK ve SerPK mevzuatlarında getirilen yeni düzenlemelerin Yargıtay kararları, öğretideki görüşler ve mukayeseli hukuk ışığında değerlendirerek olası problemler karşısında çözüm önerileri getirip Türk Hukukuna katkı sağlamaktır. Bu tez çalışmasının ortaya konulması sırasında özellikle konuya kaynaklık eden İsviçre Hukuku ve literatüründen faydalanılmıştır. Konu, Türk Hukuku bakımından incelenirken İsviçre Hukukundan farklılıkları ve benzerlikleri ortaya konulmaya çalışılmıştır. Bunun dışında konumuzla ilgili olarak Alman, Amerikan, İngiliz ve Avrupa Birliği Hukuklarından da yararlanılmıştır. Yapılan değerlendirmeler sonucunda birçok sonuçlar elde edilmiştir. Ancak özellikle şunu belirtmeliyiz ki; halka açık anonim ortaklıklar düşünülerek getirilen TTK m. 428'de ifade edilen toplu temsilciler ile ilgili düzenleme, SerPK m. 30/4'te ve SPK II-30.1 sayılı Tebliğ m. 5/3 düzenlemeleri sebebiyle uygulanmayacaktır. Üstelik bu hükümler nedeniyle Türk Ticaret Kanunu ile Bazı Kanun ve Kanun Hükmünde Kararnamelerde Değişiklik Yapılmasına Dair Kanun Tasarısı Taslağı m. 12'de TTK m. 428, 430 ve 431 hükümlerinin yürürlükten kaldırılması öngörülmektedir. Getiriliş amacı geniş kitlelerin temsilini sağlamak olan bu hükümleri yürürlükten kaldırmak yerine, SerpK'nın ilgili hükümleri ile gerekli koordinasyon sağlanarak, bunların tüm ortaklıklar yönünden uygulanmasının yolu açılmalıdır. Anahtar Kelimeler: Anonim Ortaklık; Genel Kurul; Pay Sahibi; Temsil. Shareholders may refrain to join general assembly meetings due to the reasons like participation costs, lack of time and health issues. Since the possibility of the shareholders to have an impact on the functioning of the company and its general assembly gets weakened as a result of non-attendance, active and well-organized shareholder groups-despite the fact that they do not constitute the majority of the shareholders- may achieve their desired general assembly decisions. This particular issue causes an occurrence of a power gap in general assemblies. In this context, representation of the shareholders in the general assembly of the joint stock companies plays a role of utmost importance in eradicating such problems. Hence, the topic of my thesis is the representation of the shareholders in the general assembly of the joint stock companies within the legal framework of Turkish Commercial Code and Turkish Capital Market Code. As known, Turkish Commercial Code No. 6102 came into force in 01.07.2012, repealing former Turkish Commercial Code No. 6762 which was in force for more than fifty years. Also, Turkish Capital Market Code no. 6362 came into force in 30.12.2012, repealing former Turkish Capital Market Code no. 2449. There has been a series of amendments performed on those two codes concerning my thesis topic. My main goal on choosing this topic is to contribute to Turkish Law through assessing those amendments in the light of supreme court orders, scientific opinions and comparative law and to provide solutions to the existing and prospective problems. In preparation of this work, apart from Turkish Law, Swiss Law is highly referenced as it constitutes the main source of the issue. Therefore, while assessing the point, similarities and differences between Turkish and Swiss law is asserted. Besides, German Law, European Union Law, American Law and English law are also referenced for the sake of the proper assessment of the topic. As a consequence of made analyzes, a lot of conclusions are drawn. However, it is to be pointed out particularly that the regulations in Turkish Commercial Code No. 6102 article 428 which were provided considering open joint stock companies will not be applied because of Turkish Capital Market Code No. 2449 article 30/4 and the regulation of Turkish Capital Market Board no. II-30.1 article 5/3. Moreover, because of those provisions, repealing of the articles no. 428,430,431 of Turkish Commercial Code no. 6102 is at stake. Instead of repealing those provisions of Turkish Commercial Code no. 6102 -which aim at representation in a broader sense- establishing the coordination between those provision and related Turkish Capital Market Code provisions and enabling the application of those provisions on all sort of companies must be done. Keywords: Joint Stock Company, General Assembly, Shareholder, Representation
480444
Keywords: Actionnaires; Anonim ortaklıklar; Assemblée générale; Consumer right to representation; Genel kurul; Genel kurul kararları; General assembly; General assembly resdutions; Incorporated companies; Meetings; Pay sahipleri; Representation; Représentation; Shareholders; Temsil; Temsil edilme hakkı; Toplantılar; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Açık kambiyo senetleri - Tüzemen Ati̇k, Ebru (Selçuk Üniversitesi, 2017)
"Açık Kambiyo Senetleri" başlıklı bu çalışmada, 6102 sayılı Türk Ticaret Kanunu'nun 680. maddesinde yer alan düzenlemeden hareketle Türk hukukunda açık kambiyo senetleri; yani açık bono, açık poliçe ve açık çek ele alınmıştır. Açık kambiyo senetleri, senedi verenin, ileride unsurları tamamlanarak geçerli bir kambiyo senedi şeklinde ortaya çıkmak üzere, karşı tarafa bir doldurma yetkisi ile birlikte vermiş olduğu, imza dışındaki unsurlarının tamamı ya da bir kısmı boş bırakılmış olan, unsurları tam kambiyo senetlerinin ön aşaması niteliğindeki senetlerdir. Açık kambiyo senetlerinde imza sahibi, senedin anlaşmaya aykırı doldurulması rizikosunu üstlenmektedir. Bu nedenle ortaya çıkan hukuki görünüşe güvenerek senedi devralan kötüniyeti veya ağır kusuru bulunmayan hamil iktisabında korunur. TTK'nın 680. maddesinde açık kambiyo senetleri yalnız def'i yönünden ele alınmıştır. Oysa konuya ilişkin olarak üzerinde durulması meseleler bundan ibaret değildir. Bu nedenle üç ana bölümden oluşan bu çalışmanın birinci bölümünde açık kambiyo senetlerine ilişkin genel açıklamalara; ikinci bölümünde açık kambiyo senetlerinde doldurma hakkı, devri ve sona ermesine; üçüncü bölümünde ise açık kambiyo senetlerinin anlaşmaya aykırı doldurulmasının taraflar arası ilişkilerde ileri sürülmesi, ispatı ve cezai sonuçları konularına yer verilmiştir. In this study titled "The Blank Bills of Exchange", starting from Regulation in Article 680 of the Turkish Commercial Code no 6102, The Blank Bills of Exchanges; namely, blank bills, blank notes, and the blank cheques have been evaluated in Turkish law. The Blank Bills of Exchange are the preliminary notes of the full bill of exchange that the singer gave it to the opposing party with a filling entitlement to be revealed in the form of a valid bill of exchange in the future; all or some of the elements outside the signature are left blank. In the Blank Bills of Exchange, the owner of the signature undertakes the risk of filling the notes contrary to the agreement. For this reason, the person takes over the bill of exchange relying on the revealed legal appearance is protected as holder without bad faith or gross negligence. In the 680th article of the Turkish Commercial Code, the blank bills of exchange are dealt with only in terms of exceptions. However, this is not the only issue to focus on. For this reason, in the first part of this study, which consists of three main parts, general explanations about the Blank Bills of Exchange are given while the right to fill, turnover and termination in exchange notes are discussed in the second part. In the last chapter, the submission, prove and criminal consequences of the fulfilment of the Blank Bills of Exchange contrary to the agreement at the inter-party relations are introduced.
492164
Keywords: Bill of exchange; Bills; Exchange; Kambiyo; Kambiyo senetleri; Kanunlar 6102 sayılı; Laws 6102 numbered; Senetler; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Pay sahipleri sözleşmesinden doğan birlikte satma hakkı ve birlikte satışa zorlama hakkı - Yilmaz, Gülşah (Dokuz Eylül Üniversitesi, 2017)
Birlikte satma hakkı ve birlikte satışa zorlama hakkı pay sahipleri sözleşmesinde yer alan iki haktır. Bu hakların kaynağı Amerikan hukukudur. Bu haklar ülkemizde anonim şirket esas sözleşmelerinde sıklıkla yer almaktadır. Bu çalışmada Amerikan hukukundan gelen bu haklar Türk Ticaret Hukuku kuralları açısından incelenmiştir. İnceleme yöntemi ilk olarak hakların tanıtılması ikinci olarak ortaya çıkardığı hukukî ilişkinin niteliğinin tespiti ve son olarak hukukumuza ait yasal düzenlemeler karşısında ne derece geçerli kabul edilebileceğinin belirlenmesi şeklindedir. Çalışmada, hakların karşılaştırmalı hukuktaki yeri incelenmiştir. Bu kapsamda yabancı mahkeme kararları ve yasal düzenlemeler hakkında bilgi verilmiştir. Akabinde hakların hukukî niteliği ve haklardan doğan borçlar incelenmiştir. Son olarak hakların anonim ve limited şirket sözleşmelerinde yer alması durumunda meydana gelebilecek hukukî sorunlar tartışılmıştır. Bu kapsamda hakların yarattığı pay devir sınırlandırmasının anonim şirketler hukukunda yer alan kurallar karşısındaki durumu incelenmiştir. Ayrıca hakların limited şirketlerde pay devri ile ilgili düzenlemeler açısından geçerliliği tartışılmıştır. Anahtar Kelimeler: Birlikte Satma Hakkı, Birlikte Satışa Zorlama Hakkı, Pay Devrinin Sınırlandırılması, Pay Sahipleri Sözleşmesi, Anonim Şirket Esas Sözleşmesi. Tag along right and drag along right are two rights in shareholders' agreement. The source of these rights is American Law. These rights are frequently found in the articles of association of the joint stock company in our country. In this study, these rights coming from American law were examined in the terms of Turkish Commercial Law. The examination method is firstly the identification of the rights, secondly the determination of the nature of the legal relationship that emerges from the rights and finally the determination of the extent to which they can be regarded as valid under the legal regulations of our law. In the study, the position of the rights in comparative law were examined. In this context, information is given about the foreign court decisions and legal regulations. Then the legal nature of the rights and the obligations arising from the rights were examined. Finally, the legal issues that may arise in case of the rights are included in joint stock company and limited company contracts are discussed. In this context, the situation of the share transfer restrictions created by the rights against the rules in the corporation law has been examined. Furthermore, the validity of the rights in terms of the share transfer regulations in limited companies has been discussed. Keywords: Tag Along Right, Drag Along Right, Share Transfer Restriction, Shareholders' Agreement, Article Of Association.
486520
Keywords: Actionnaires; Anonim şirketler; Birlikte satma hakkı; Birlikte satışa zorlama hakkı; Birlikte vekalet; Drag along righ; Joint agency; Joint stock company; Pay devri; Pay sahipleri; Sale; Sales contracts; Sales methods; Satış; Satış sözleşmeleri; Satış yöntemleri; Shareholders; Tag along righ; Transfer of shares; Vente conjointe; Vente forcée

Elektronik ortamda gerçekleşen alım satım işlemlerinin İslam Hukuku açısından değerlendirilmesi (İslam Hukuku açısından e-ticaret) - Bayraktar, Ahmet (Ankara Üniversitesi, 2016)
Araştırmamız bugüne kadar ülkemizde İslam hukukçularınca doktora düzeyinde girilmemiş ve değerlendirilmemiş bir mesele olan İslam hukuku açısından elektronik ticareti konu edinmiştir. Bu manada ilk bölümde İslam hukuku açısından ticaret hukuku kavramlarına kısa bir değini yapılmış ve bununla ilgili çok temel bilgiler verilmiştir. İkinci bölümde İslam hukuku açısından e-ticaret incelenmiş, E-ticaretin İslam hukuk kavramlarıyla nasıl anlaşılabileceğine ve anlatılabileceğine dair görüş ve tespitlerimiz sunulmuştur. Elektronik ortamda akitleşme, irade beyanı gibi yeni durumların analizi yapılmıştır. Üçüncü bölümde ise fıkhî hükümleri açısından e-ticaret incelenmiştir. Bu bölümde de e-ticarette yeni ortaya çıkan durumlar, kavramlar ve olgular incelenmiştir. Fıkhî açıdan hangi kavramlarla açıklanacağı hususunda kanaatlerimiz sunulmuştur. İkinci bölüm değerlendirme ve analiz ağırlıklı iken üçüncü bölümde daha çok pratik sonuçları açısından durum incelenmiş, bu hususta literatüre girmesi gerektiğini düşündüğümüz yeni kavramlar ve tasnifler de zikredilmiştir. Son olarak da mevcut modern yasalarda e-ticaretin nasıl ele alındığı gösterilmiş, İslam hukuku açısından nasıl değerlendirilebileceğine dair görüşlerimiz arz edilmiştir. This work is about electronic commerce in İslamic law which has not been studied or evaluated by anyone with such a scale until now. In this sense, at the first section, the concepts of commerce law have been mentioned briefly by the view of Islamic law, and has been given basic knowledge. At the second section, E-commerce regarding to concepts of Islamic law has been examined. Our opinions and detections about it like how this is must be understood with the notions of Islamic law have been presented. The conceptual analysis of new situations such as contracting, declaration of intention, on the İnternet has been done. At the last section, e-commerce regarding rules of Islamic law has been examined. In this section, new situations and concepts that just emerged have been examined. Our opinions have been presented. As the second section weighted with assessment and analysis, at the third section, the case has been examined rather practically. New concepts and categorizations that must be added to the literature have been mentioned.
Keywords: E-commerce; Electronic commerce; Elektronik ticaret; Islamic Law; İslam Hukuku

İş Hukuku açısından ticaret şirketlerinde yapısal değişiklikler - Kayik Aydinalp, Aslıhan (Erciyes Üniversitesi, 2016)
Doktora tezi olarak hazırlanan bu çalışmanın konusunu esas olarak Türk Ticaret Kanununun 178. maddesi oluşturmaktadır. İşyerlerinde meydana gelen birleşme, bölünme ve tür değiştirmeyi de kapsamına alan işyeri devirleri, çeşitli Avrupa Birliği Yönergelerine konu olmuştur. Ticaret hayatında meydana gelen gelişmeler neticesinde ve uluslararası müktesebata uyum sağlamak amacıyla 2011 tarih ve 6102 sayılı Türk Ticaret Kanunu kabul edilmiştir. Birleşme, bölünme ve tür değiştirme, Ticaret Hukukuna ilişkin kavramlar olmakla birlikte, işyeri devrine sebebiyet verdiği ve iş ilişkilerini ilgilendirdiği ölçüde çalışmamıza konu edilmiştir. İş ilişkisinin devrine sebep olan işyeri devirleri 4857 sayılı İş Kanununun 6. maddesinde düzenlenmekle birlikte, birleşme, bölünme ve tür değiştirme yapısal değişiklikleri için özel nitelikteki Türk Ticaret Kanunun iş ilişkilerinin geçmesi" başlıklı 178. maddesi getirilmiştir. Dolayısıyla İş Hukuku açısından 6102 sayılı Türk Ticaret Kanunu, işyeri ve işyeri devirleri konusunda önem arz etmektedir. Çalışmamızda, ticaret şirketlerinde meydana gelen birleşme, bölünme ve tür değiştirme yapısal değişikliklerinde, işyerinde çalışan işçilerin iş ilişkilerinin akıbeti, işçilerin itiraz hakkı ve bu hakkı kullanmaları için gerekli olan bilgilendirme yükümlülüğü ile işçilik alacaklarından sorumluluk ve teminat konuları işlenmiştir. Anahtar Kelimeler: İşyeri devri, yapısal değişiklik, birleşme bölünme ve tür değiştirme, bilgilendirme yükümlülüğü, itiraz hakkı, teminat hakkı, işçilik alacaklarından sorumluluk. Article 178 of Turkish Commercial Code constitutes mainly the subject of this study prepared as a doctoral thesis. Business transfers including fusion, demerger and change of form occurred in works of business, have become a subject for various European Union Directives. Turkish Commercial Code dated 2011 and numbered 6012 has been accepted as a result of developments occurred in commercial life and for the purpose of complying with international acquis. As well as fusion, demerger and change of form are concepts related to Commercial Law; they are mentioned in our study to the degree that they give cause for business transfers and concern employment relations. While business transfers causing transfer of employment relations are regulated in the 6th article of Labor Law numbered 4857; it is brought the 178th article titled as "transition of employment relations" of Turkish Commercial Code special for fusion, demerger and change of form. Thus, Turkish Commercial Code numbered 6102 has importance for business and transfers of business in terms of Business Law. In our study, it is discussed the matters of the responsibility from labor dues, and warranty, and informing liability which is necessary for consequence of business relations of employees working in this business, their rights of objection and using these rights in transformation of fusion, demerger and change of form occurred in trading companies. Keywords: Business transfer, transformation of trading companies, fusion, demerger and change of form, informing liability, right of objection, warrant, responsibility from labor dues.
447853
Keywords: Commercial companies; Division of company; Labour law; Labour relations; Mergers; Structural change; Ticari şirketler; Turkish Commercial Code; Turkish labor law; Türk Ticaret Kanunu; Türk iş hukuku; Workers; Workplace transferring; Yapısal değişme; İş hukuku; İş ilişkileri; İşyeri devri; İşçiler; Şirket birleşmeleri; Şirket bölünmesi

Milletlerarası ticari tahkime ilişkin UNCITRAL model kanununda yargılama yetkisi kavramı ve tahkim mahkemesinin yargılama yetkisinin sınırları - Ki̇tapçi, Hakan (Selçuk Üniversitesi, 2016)
447977
Keywords: Arbitration; Authority; International Arbitiation Law; Judgement; Milletlerarası Tahkim Kanunu; Tahkim; UNCITRAL Model Kanunu; UNCITRAL Model Law; Yargılama; Yetki

Hakim şirketin azınlığın paylarını satın alma hakkı - Tütüncü, Muharrem (İstanbul Kültür Üniversitesi, 2016)
Anonim ortaklıklar hukuku prensipleri çerçevesinde sermaye koyma taahhüdünü yerine getiren pay sahiplerinin ortaklıktan çıkarılmalarını sağlamak kural olarak mümkün değildir. 6102 sayılı TTK ile söz konusu prensibe iki önemli istisna getirilmiştir. Bunlardan ilki birleşme yoluyla ortaklıktan çıkarma (TTK md.141/2), diğeri ise hâkim şirketin azınlığın paylarını satın alma hakkıdır (TTK md.208). Satın alma hakkına ilişkin TTK md.208 hükmünün kaleme alınmasında, mukayeseli hukuktaki düzenlemelerden etkilendiği görülen yasa koyucu tarafından, Türk şirketler hukuku doktrini ve uygulamasının özellik arz eden yönlerini de dikkate alınmış ve neticede kendine özgü bir satın alma hakkı düzenlemesi ortaya çıkarılmıştır. Under the principles of the law of joint stock companies, it is not, at least in principle, possible to squeeze out the shareholders who had fulfilled their capital subcription. However, Turkish Commercial Code nr.6102 (TTK) contains two significant exceptions to this principle. These exceptions are: squeeze-out merger (TTK article 141/2) and the squeeze-out right of the controlling company (TTK article 208). Turkish legislator, considering the important aspects of the doctrine and practice of Turkish companies law and under the influence of the regulations in the comparative law, made a sui generis regulation of squeeze-out right in the article 208 of the Turkish Commercial Code.
422918
Keywords: Anonim ortaklıklar; Dominant position; Hakim durum; Incorporated companies; Satın alma hakkı; Squeeze-out right; Turkish Commercial Code; Turkish commercial law; Turkish law; Türk Ticaret Kanunu; Türk hukuku; Türk ticaret hukuku

İslam ticaret hukukunda cehalet ve güncel akitlere etkisi - Aslan, Bedri (Dicle Üniversitesi, 2015)
Türk Hukuku'nda navlun (deniz yolu ile eşya taşıma) sözleşmeleri; yolculuk çarteri sözleşmesi ve kırkambar sözleşmesi olmak üzere iki ana gruba ayrılmıştır. Bunlardan çarter sözleşmeleri arızi deniz taşımacılığında, kırkambar sözleşmesi ise genellikle düzenli hat taşımacılığında kullanılır. Günümüzde deniz taşımacılığında yaşanan gelişmelerin sonucu olarak düzenli hat taşımacılığının ve kırkambar sözleşmesinin önemi artmaktadır.Bu tezde; Türk Hukuku'nda kırkambar sözleşmesi kavramı, sözleşmenin asli unsurları, özellikleri, benzer sözleşmelerle karşılaştırılması, sözleşmeye uygulanacak hükümlerin tespiti gibi konuların yanında sözleşmenin tarafları, ilgili kişileri, sözleşmenin ifasında yer alan yardımcı kişileri, tarafların hak ve yükümlülükleri ve sözleşmenin sona ermesine değinilmiş Türk Ticaret Kanunu ve diğer mevzuat hükümlerinden, ilgili uluslararası andlaşmalardan, ticari örf-adet kurallarından, yüksek mahkeme kararlarından, öğretiden, uygulamada kullanılan tip sözleşme ve konişmento örneklerinden yararlanılmıştır. In Turkish Law, contracts of affreightment are divided into two main cathegories which are; voyage charter and contract of common carriage of goods. While the former is being used in tramp shipping, the latter is being used in liner shipping. As a result of recent developements in carriage of goods by sea, the importance of liner shipping and contract of common carriage of goods has been rising.This thesis is based on; Turkish Commercial Code, other related national regulations and international agreements, customs, decisions of high courts, doctrine, mostly used standard contract and bill of lading forms. In this thesis; the chracteristics, parties, differences from other contracts, rights and obligations of the parties and termination of contract of common carriage of goods have been analysed.
Tez N°429811
Keywords: Affreightments; Commercial law; Contract of Common Carriage of Goods by Sea; Contract of carriage; Deniz hukuku; Deniz ticareti; Deniz yolu taşımacılığı; Kırkambar Sözleşmesi; Law of the sea; Navlun sözleşmeleri; Sea trade; Sea transportation; Taşıma sözleşmesi; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku

Anonim şirketlerde pay devrinin sınırlandırılması (Bağlam) - Bozkurt, Tamer (Ankara Üniversitesi, 2015)
Anonim şirkette geçerli temel ilkelerden birisi, pay devrinin serbestliği ilkesidir. Anonim şirkette üyeliği temsil eden paylar, serbestçe devredilebilir ve miras yoluyla geçişe konu olabilir. Yeni dönemde, İsviçre Hukuku'nu takip eden TTK, pay devri sınırlamalarını "borsaya kote edilmiş" ve "borsaya kote edilmemiş" paylar üzerinden kurgulamıştır. Borsaya kote edilmemiş paylarda bağlam, gerçek bir devir sınırlamasıdır ve şirket devre onay vermeden, işlem geçerlilik kazanamaz. Ayrıca onay olmadan, payı devralan müktesibe, hiçbir hak geçmez. Kanun şirkete üç red nedeni vermiştir. Birincisi, şirket sözleşmesine yazılacak "önemli nedenler," ikincisi esas sözleşmede bir devir sınırlaması iradesi olmak kaydıyla, uluslararası literatürde "kaçınma klozu" olarak geçen "Escape-Clause" ve inançlı iktisaba karşı korunmadır. Borsaya kote edilmiş paylarda ise TTK ve SPKn. devrededir. TTK'da, borsaya kote edilmiş paylarda sadece "yüzdelik sınırlama"ya izin verilmekte ve payın geçişi ile birlikte (borsa dışı iktisapta bildirim), katılım hakları hariç, diğer haklar müktesibe intikal etmektedir. Bu paylar, yasal yolla intikal ettiğinde ise (miras, miras paylaşımı, cebri icra veya eşler arası mal rejimleri hükümleri), şirket müktesibi tanımak zorunda kalmaktadır. Buna karşılık, SPKn.'nın 137/3. maddesi gereğince şirket, borsada gerçekleşen işlemler sonucu payı edinen kişiyi, pay defterine kayıttan kaçınamaz. Bu tercih tartışmalar getirebilecektir. Özellikle borsa şirketlerinin kendini bağlamla koruyamayacak olmaları ile borsanın yapısına uygun olarak "mutlak devredilebilirlik" arasındaki çatışmanın sonuçlarını ilerleyen yıllar gösterecektir. Bağlam, anonim şirket düzeni ile temelde çatışan bir kurumdur. Ancak şirketin yabancılaşmaya karşı veya kendine özgü niteliklerinin korunması bakımından yararlıdır. Ancak bağlamın yasadaki düzenleniş şekli, devrin fiilen (de facto) engellenmesi şekline bürünmemelidir. Buna rağmen şirket düzeni ile temelde çelişki yaratan bir kurum olan "bağlam" ile ilgili tartışmalar, hiçbir zaman bitmeyecektir. One of the main respected principles in stock companies is the principle of transferability of shares. Shares representing membership in a stock corporation shall be freely transferred and inheritted. According to this principle each shareholder may depart from the stock company by transferring his/her share/shares principally whenever he wants. The Turkish Commercial Code based on Swiss Law regulated restriction of transferability as "Listed registered shares" and "Not listed registered shares". Restriction on transferability in "Not listed registered shares" is an exact restriction. Because where the consent required for transfer of shares is not given, the ownership of the shares and all attendant rights remain with the alienator (Turkish Commercial Code, Art. 494/1). Listed registered shares are regulated in both The Turkish Commercial Code and the Capital Market Law. In the case of listed registered shares, the company may refuse to accept the acquier as a shareholder only where the articles of association envisage a percentage limit on the registered shares for which an acquirer must be recognised as shareholder and such a limit is exceeded. But according to the art. 137/3 of Capital Market Law a stock corporation can not refrain from registering a shareholder who acquired listed registered shares to share register. Especially is protection of a stock corporation itself against hostile take-over by means of "restrictions on transferibility" important or absolute transferibility which is appropriate for the structure of stock-exchange? The results of the art. 137/3 of Capital Market Law will occur in the future.
Tez N° 425406
Keywords: Anonim ortaklıklar; Anonim şirketler; Commercial law; Incorporated companies; Joint stock company; Pay devri; Restrictive provisions; Sınırlayıcı hükümler; Ticaret hukuku; Transfer of shares; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Kayıtlı sermaye sistemi - Cenkci̇, Esra (Akdeniz Üniversitesi, 2015)
Sermayenin yönetim kurulu kararıyla artırılması esasına dayanan kayıtlı sermaye sistemi, daha hızlı ve daha az masrafla ortaklığın sermayesinin artırılmasını amaçlar. 2499 sa. SerPK' den bu yana halka açık anonim ortaklıklara özgü bir kurum olarak Türk hukukunda uygulanmakta olan sistem, TTK ile birlikte halka açık olmayan anonim ortaklıklar için de uygulanabilir hale gelmiştir. Aynı esaslara dayandığı ve aynı amaca hizmet ettiği için kurumun, TTK ve SerPK' de ayrı ayrı düzenlenmesine lüzum yoktur. Sistem, yönetim kurulunun usulüne uygun olarak sermayenin artırılması konusunda yetkilendirilmesi suretiyle ortaklık açısından uygulanabilir hale gelir. Yetkilendirme işlemleri esas sözleşme değişikliğini gerektirir. Yönetim kurulunun sermayeyi artırma yetkisi, esas sözleşmede gösterilen kayıtlı sermaye ve yetki süresiyle sınırlıdır. Bu sınırlara ulaşılmışsa ve esas sözleşmeyle yeni yetki sınırları tespit edilmemişse, yönetim kurulu sermaye artırım kararı alamaz. Öte yandan, bu yetkilendirmede yönetim kuruluna, sermaye artırım yetkisi yanında sermayenin artırılmasıyla bağlantılı olup kanunda izin verilen konularda da yetki tanınabilir. TTK ve SerPK' deki ilgili hükümler incelendiğinde, kayıtlı sermaye sisteminde sermaye artırım kararının, esas sermaye sisteminde olduğu gibi, esas sözleşme değişikliği olarak kabul edildiği görülmektedir. Bu düzenlemeler, sadece genel kurulun toplanıp karar alması işlemleri için gerekli olan zamandan ve masraftan tasarruf edilmesini sağlar. Kayıtlı sermaye sisteminin daha etkin bir kurum olarak kullanılması, esas sözleşme değişikliğine ilişkin işlemlerin de bertaraf edilmesini gerekli kılar. Anahtar Kelimeler: Sermaye, Kayıtlı Sermaye, Sermaye Artırımı, Yönetim Kurulu, Anonim Ortaklık. The registered capital system is based on increasing the capital with decision of board aims to increase the company's capital faster and less costly. System that is applied in Turkish Law as an institution special to public companies since CMC no: 2499, becomes applicable for non-public companies with TCC. As based on the same principles and serves the same purpose, there is no need to regulate the institution in TCC and CMC separately. System becomes applicable in terms of company, by duly authorization the board concerning capital increase. Authorization procedures require amendment of company's article. Authority of capital increase of board is limited with the registered capital and authority period that are shown in company's article. When it reached this limits and determined any new authority limits with the company's article, board can not take a decision on capital increase. On the other hand, in this authorization, board also can be authorized on the issues that are in connection with capital increase and permitted by act, in addition to the capital increase authority. When analyzed the related provisions in TCC and CMC, it is seen that the capital increase in registered capital system, as in ordinary capital system, is accepted as company's article amendment. These regulations provide to save only from time and cost that are required for procedures to take decision of general assembly. Using the registered capital system as more effective institution requires to eliminate the procedures related to amendment of company's article. Keywords: Capital, Registered Capital, Capital Increase, Board of Directors, Joint Stock Corporation.
Keywords: Anonim ortaklıklar; Board of directors; Capital increase; Capital social; Incorporated companies; Kayıtlı sermaye sistemi; Registered capital system; Sermaye artırımı; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yönetim kurulu

Anonim ortaklıkta ayni sermaye - Çonkar, Mustafa Halil (İstanbul Üniversitesi, 2015)
Tez N°451645
Keywords: Anonim ortaklıklar; Anonim şirketler; Ayni haklar; Capital; Capital companies; Commercial companies; Commercial law; Incorporated companies; Joint stock company; Real rights; Sermaye; Sermaye şirketleri; Ticaret hukuku; Ticari şirketler; Turkish commercial law; Türk ticaret hukuku

Limited ortaklıklarda ortakların ek ödeme ve yan edim yükümlülükleri - Di̇nç, Serhan (Gazi Üniversitesi, 2015)
Bu çalışmanın amacı, 6102 sayılı Türk Ticaret Kanunu sistemi ile limited ortaklıklar hukukuna getirilen iki yeni müessesenin incelenmesidir. Ek ödeme ve yan edim yükümlülükleri incelenmiştir. Ortak, ortaklık, pay senedi, limited ortaklık sözleşmesi, esas sermaye, esas sermaye payı, bilânço, bilânço açığı, zarar, zararın kapatılması, edim, yükümlülük, ek finansman araçları, ortaklıktan çıkma ve çıkarılma kavramları ışığında ek ödeme ve yan edim yükümlülüklerinin bu kavramlarla irtibatı açıklanmıştır. Bu incelemeler sonucunda ek ödeme ve yan edim yükümlülüklerinin ülkemizde limited ortaklıkların ticaret hayatında yer edinebilmelerini ve gelişmesini temin edecek faydalı hukuki müesseseler olduğu tespit edilmiştir. Anahtar Sözcükler 1. Limited Ortaklıklar 2. 6102 sayılı Türk Ticaret Kanunu 3. Yükümlülük 4. Ek Ödeme Yükümlülüğü 5. Yan Edim Yükümlülüğü. The main purpose of this thesis is to research the new two concepts which were ordered by the system of new Turkish Commercial Code numbered 6102. In this thesis, the concepts of supplementary obligation of subscription and obligation of fulfilment were researched. The relationships between the concepts of supplementary obligation of subscription and obligation of fulfilment and the shareholder, limited company, certification of share, contract of limited company, capital, balance, deficit of balance, damage, annihilation of damage, fulfilment, obligation, departation and taking off were explained. The results of these research shows us that the concepts of supplementary obligation of subscription and obligation of additional fulfilment are beneficial concepts which are useful and necessary for surviving and developing materials for limited companies in Turkish business life. Key Words 1. Limited Companies 2. Turkish Commercial Code numbered 6102 3. Obligation 4. Supplementary Obligation of Subscription 5. Obligation of Additional Fulfilment
405733
Keywords: Ek ödeme sistemi; Limited company; Limited şirketler; Obligation; Obligation of additional fulfilment; Ortaklar; Ortaklık; Ortaklık hakkı; Partners; Partnership; Partnership right; Supplementory payment system; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yan edim yükümlülüğü; Yükümlülük

Sermaye şirketlerinde azınlık hakları Türk ve OHADA hukuklarının karşılaştırılması - Emedi̇ Useni̇, Ahmed (İstanbul Ticaret Üniversitesi, 2015)
Tüm sermaye şirketlerinde, "sermaye" niteleyicisinin de belirttiği üzere, hissedarların şirket borçlarına karşı sorumluluğu, hissedarların şirkete hisse katılım değerleriyle sınırlı olduğu prensibi kabul edilir. Aynı şekilde, hissedarların ticari kararlardaki ağırlığı aynı sınırlama prensibine bağlı olarak belirlenir. Ticari şirketler hakkındaki Türk yasalarında ve Afrika Ticaret Kanunu Uyum Örgütünün (Organisation pour l'harmonisation en Afrique des droits des affaires, OHADA) yasalarında, sermaye şirketlerinde, "hissedarların sorumluluk ve ağırlığı prensiplerinin" sıkı bir şekilde korunduğunu gözlemleriz. Hissedarların genel olağan ve olağanüstü kurulları, genellikle, şirketin günlük yönetimini aşan kararları alma yetkisine sahiptir. Bu kararlar kesin belirlenmiş bir çoğunluğa göre alınır. Sermaye şirketlerinin günlük yönetimi alanında kalan bütün kararlar, bahsi geçen şirketlerin ticari katılım oranlarına göre – aslında hissedarlardakileri gelen – şirketlerin yönetim organlarının yetkilerinden kaynaklanır. Sermaye şirketlerinde, genel kurullar veya yönetim organları tarafından alınan, tüm kararlar, bu şirket hissedarları bahse geçen kurullara veya organlara katılmalarsalar bile, tüm şirket hissedarları için geçerli, uygulanabilir veya muhalefet edilebilirlerdir. Bu durum göz önüne alındığında şöyle bir çıkarımda bulunabiliriz: bu tür şirketlerde, hisselerin çoğunluğunu elinde bulunduran hissedarlar, bu şirketleri idare etme yetkisini de aynı zamanda elinde bulundurmaktadırlar. Birçok aynı durumda, çoğunluk hissedarları ve azınlık hissedarları arasındaki menfaat çatışmalarını gözlemleyebiliriz. Oybirliği veya nitelikli çoğunluk gerektiren kararlar dışında, çoğunluk hissedarları, olağan ve olağanüstü kurallarda tüm yetkiyi ellerinde bulundurmaktadır. Aynı şekilde, sermaye şirketlerinin yönetim organlarında, çoğunluk hissedarları her zaman yöneticileri tayin etmektedir. Bu koşullarda, kararların alınmasında, çoğunluğun azınlığın menfaatlerinin göz önüne aldığı durumlarla karşılaşmak pek olanaklı değildir. Bu nedenle, çoğunluğun karşılıklı menfaatleri ve azınlığın menfaatleri arasındaki denge sorunu, genellikle çoğunluğa karşı azınlığın haklarının ve menfaatlerinin korunması sorunuyla bir tutulmayı hak etmektedir. Özellikle, çoğunluğu kontrol etmek yoluyla suiistimalleri önlemek veya hissedarlar arasındaki çatışmaları azaltmak için, azınlığa bazı haklar ve yetkiler vermek suretiyle azınlığı korumak esastır. Ancak, bu hak ve yetkilerin kapsamı "çoğunluk tarafından yönetim prensibi" ile sınırlandırılmalıdır. Bu çalışma kapsamında, OHADA ve Türkiye Cumhuriyeti'nin ticaret hukukunda yer aldığı şekliyle, sermaye şirketlerinde azınlığın korunması hakkındaki uygulanan yolları analiz ettik. Bununla beraber, azınlık hissedarlarının korunması hakkında statü düzenlemelerini analiz edebilmek için, OHADA ve Türk hukukundaki, bazı sermaye şirketlerinin esas sözleşmelerini örnek olarak aldık. Hissedarlar, bu sözleşmelerde, yasalarda öngörülen düzenlemelerden daha iyi düzenlemeleri öngörme olasılığına sahip olmaktadırlar. Bu çalışmanın sonuçlarının, Afrikalı ve Türk hukukçular için olduğu kadar OHADA'ya üye ülkelerden Türkiye Cumhuriyeti'ne yatırım yapmak isteyen herkes için yararlı olacağı inancındayız. Dans les sociétés commerciales des capitaux, il existe le principe de délimitation des responsabilités des actionnaires par rapport aux dettes sociales et aux prises de décisions sociales. En lisant attentivement la législation turque sur les sociétés commerciales et la législation de l'Organisation pour l'harmonisation en Afrique des droits des affaires « Ohada» en sigle, nous observons également l'existence de ce principe de délimitation des responsabilités et de poids des actionnaires dans les sociétés commerciales des capitaux prévues dans toutes les deux législations. En Droit de l'Ohada tout comme en Droit Turc des sociétés commerciales, les assemblées générales des actionnaires dans les sociétés des capitaux, disposent de la compétence de prendre les décisions sur la politique générale et qui dépassent la gestion quotidienne des sociétés. Les décisions des assemblées générales sont prises, selon la majorité bien déterminée au cas par cas. Tandis que, les organes de gestion de ces sociétés, disposent des compétences pour décider sur la gestion quotidienne desdites sociétés. Toutes les décisions prises tant par les assemblées générales des actionnaires que par les organes de gestion des sociétés commerciales des capitaux, demeurent valables et opposables à tous les actionnaires sociaux; même à l'égard des actionnaires qui n'y ont pas participé. Au regard de cette observation, il nous est logique d'affirmer que dans les sociétés des capitaux, ce sont les actionnaires majoritaires qui disposent logiquement tous les pouvoirs de décider sur les sorts sociaux. Dans pareilles conditions, nous pouvons observer que les conflits d'intérêts entre les actionnaires majoritaires et ceux minoritaires, sont inévitables. Sauf pour les décisions qui nécessitent l'unanimité ou celles qui requièrent une majorité qualifiée, les actionnaires majoritaires détiennent tous les pouvoirs des décisions dans les assemblées et même dans les organes de gestion car, ce sont toujours les actionnaires majoritaires qui désignent les dirigeants de ces sociétés en fonctions de leurs poids sociaux. Il est ainsi peu probable que la majorité prenne en considération les intérêts de la minorité dans la prise des décisions. Pour cette raison, la question d'établir l'équilibre entre les intérêts respectifs des actionnaires majoritaires et ceux des minoritaires, mérite d'être assimilée en général à la question de la protection des droits et intérêts de la minorité contre la majorité. Plus précisément, il est indispensable de protéger la minorité en lui accordant certains droits et pouvoirs pour qu'elle puisse contrôler la majorité aux fins de prévenir les abus ou de limiter les conflits entre les actionnaires. Cependant, l'étendue de ces droits et de ces pouvoirs mérite d'être limitée par le principe de la gestion sociale par la majorité. Dans le cadre de cette étude, nous avons analysé la manière dont les actionnaires minoritaires sont protégés dans les législations de l'Ohada et turque. En plus, nous avons approfondi notre étude avec les analyses des dispositions statutaires y relatives d'une dizaine des sociétés commerciales des capitaux de deux Droits concernés car, les actionnaires disposent légalement le pouvoir d'en prévoir meilleur que ce qui était prévu par les législateurs. Nous sommes convaincus que les résultats de cette étude, seront théoriquement bénéfiques pour les juristes qui s'intéressent aux Droits turc et de l'Ohada et pratiquement importants pour toute personne qui souhaite investir tant dans la République de Turquie que dans l'un des dix-sept (17) pays membres de l'Ohada.
Keywords: Afrika Ticaret Kanunu Uyum Örgütü; Azınlık hakları; Capital companies; Companies; Company law; Minority rights; Organization for the Harmonization of African Business Law; Sermaye şirketleri; Turkish Law; Türk Hukuku; Şirketler; Şirketler hukuku

Anonim şirketin haklı sebeple feshi - İlbasmiş Hizlisoy, Özlem (Ankara Üniversitesi, 2015)
413801
Keywords: Anonim ortaklıklar; Anonim şirketler; Azınlık hakları; Cancellation; Cancellation right; Fesih; Fesih hakkı; Haklı neden; Incorporated companies; Joint stock company; Just cause; Minority rights; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Anonim şirketlerde örtülü kâr dağıtımı - Karslioğlu, Hasan (Gazi Üniversitesi, 2015)
Anonim şirket pay sahiplerinin temel amacı, şirkete koydukları sermaye karışlığında kâr elde etmek ve bu elde ettikleri kârı artırmaktır. Kâr dağıtımı ve şartları genel olarak Türk Ticaret Kanunu'nda düzenlenmiş olup, uygulamada da kâr dağıtımı bu düzenlemelere göre yapılmaktadır. Ancak vergi kanunlarında ve uygulamasında, Ticaret Kanunu'ndaki bu düzenlemeler dışındaki bazı ödemeler için de "örtülü kâr" nitelendirmesi yapılmıştır. Örtülü kâr dağıtımı konusu, genellikle vergi hukukçuları tarafından ele alınan bir konu olup, bu konu şimdiye kadar kâr payının temel unsurlarının düzenlendiği ticaret hukuku açısından detaylı olarak ele alınmamıştır. Bu nedenle hem vergi kanunları, hem de Türk Ticaret Kanunu kapsamında kâr dağıtımının, hangi hallerde örtülü olduğunun ele alınması gerekmektedir. Bunun yanında Sermaye Piyasası Kanunu'nda örtülü kâr dağıtımına benzer uygulamaların olup olmadığı ve halka açık anonim şirketler açısından konunun öneminin de ortaya konulması, meselenin daha net ele alınmasını sağlayacaktır. Çalışmamızda bu amaca yönelik tespitler yapılmış olup, konu tüm yönleri ile ele alınmıştır. İncelemelerimiz sonucunda; vergi kanunlarında "örtülü kâr" olarak nitelendirilen haksız menfaat ödemelerinin, Ticaret Kanunu'ndaki "kâr payı" düzenlemeleri ile açıkça çeliştiğini değerlendirmekteyiz. Bu nedenle vergi güvenliği amacıyla yapılmış da olsa "örtülü kâr dağıtımı" nitelendirmesinin ticaret hukuku genel ilkeleri ile çeliştiği tespitinde bulunduk. Çalışmamızda bu değerlendirmenin gerekçelerini ortaya koymaya gayret ettik. The principal purpose of the shareholders in a joint-stock company is to get profit in consideration of the capital provided and to increase the level of such profit. The profit distribution and the relevant conditions are defined in the Turkish Commercial Law in general and the profit distribution in practice is performed according to these stipulations. However, there is the term i.e. "concealed profit" for some payments in the tax laws and practice apart from these stipulations in the Commercial Law. The concealed profit distribution is a subject that is generally handled by the tax jurists and this subject has not been studied in detail so far in terms of trade law where the main factors of the dividend are defined. For this reason, it is necessary to study on the cases where the profit distribution is deemed ad "concealed" within the scope of both tax laws and Turkish Commercial Law. Besides, whether there are similar practices to the concealed profit distribution in the Capital Markets Law and putting forward the importance of this subject in terms of the public joint-stock companies will enable to handle the subject more clearly. The determinations for this purpose are provided in our study and this subject is handled in all aspects. As a result of our analysis, we have revealed that the unjust interest payments characterized as "concealed profit" in the tax laws are clearly in conflict with the stipulations of "dividend" in the Commercial Law, and therefore, "concealed profit distribution" conflicts with the general principles of trade law even though it is performed for tax safety. We have tried to put forward the justifications of this evaluation in our study.
Tez N°384579
Keywords: Anonim şirketler; Camouflage of earning distribution; Dağıtım; Distribution; Droit des sociétés commerciales; Joint stock company; Kar dağıtımı; Profit distribution; Örtülü kazanç dağıtımı

Milletlerarası ticari tahkimde hakemlerin bağımsızlığı ve tarafsızlığı - Kayali, Di̇dem (Ankara Üniversitesi, 2015)
Milletlerarası ticarî sözleşmelerden kaynaklanan uyuşmazlıklar söz konusu olduğunda akla ilk gelen çözüm yöntemi tahkimdir. Zira milletlerarası ticarî tahkimin devlet yargılamasına göre önemli avantajları bulunmakta, hakemlerin bağımsızlığı ve tarafsızlığı ise bu avantajların en önemlilerinden biri olarak karşımıza çıkmaktadır. Bu çerçevede, tahkim süreci başlarken hakemlerin bağımsız ve tarafsız olmaları ile süreç tamamlanana kadar bu şekilde kalmaları gerektiği hususu milletlerarası ticarî tahkimin en temel ilkesi olarak genel kabul görmüş; millî kanunlarda, milletlerarası metinlerde ve milletlerarası tahkim kurumlarının düzenlemelerinde doğrudan ya da dolaylı bir şekilde yerini almıştır. Bu çalışmada da bağımsızlık ve tarafsızlık kavramlarından ne anlaşılması gerektiği, bu kavramların uygulamada nasıl yorumlandığı, tahkim yargılamasındaki önemi ve nasıl korunduğu, yukarıda bahsedilen düzenlemeler ile millî mahkemeler ve milletlerarası tahkim kurumlarının kararları ışığında incelenmiştir. When disputes emerging from international commercial contracts are in question, arbitration is the first resolution method that comes to mind. This is because international commercial arbitration has significant advantages compared to the state jurisdiction where impartiality and independence of arbitrators is considered to be one of the most important ones of those advantages. In this framework, the necessity that arbitrators ought to be impartial and independent from the very start till the end of the arbitration process has gained general acceptance as the basic principle of international commercial arbitration and directly or indirectly has taken its place in national laws, international texts and regulations of international arbitration institutions. In this study, the meaning of independence and impartiality, how they are interpreted in practice, the importance of these concepts in international commercial arbitration and how they are protected are examined in the framework of above mentioned regulations and decisions of national courts and international arbitration institutions.
393376
Keywords: Arbitrage; Arbitration; Arbitrators; Arbitre; Bağımsızlık; Hakemler; Impartiality; Impartialité; Independence; International Arbitiation Law; International Trade; International disputes; Milletlerarası Tahkim Kanunu; Tahkim; Tarafsızlık; Uluslararası ticaret; Uluslararası uyuşmazlıklar

Acentenin ücret hakkı - Kizilay, Aygül (Kocaeli Üniversitesi, 2015)
6102 sayılı TTK acentelik alanında önemli yenilikler getirmiştir. Yeni kanun 6762 sayılı Kanunda yer almayan bazı kurumlara yer vermiş, eski kanun döneminde uygulamada sorunlara yol açan bazı hükümler ise gözden geçirilmiştir. Acentelik sözleşmesi tam iki tarafa borç yükleyen sözleşme olduğundan, acentenin gördüğü iş için her zaman bir ücret talep etme hakkı bulunmaktadır. Acentenin en önemli hakkı olan ücret hakkı, müvekkilin karşı edimi olarak kendisini gösterir. Ücret hakkını düzenleyen hükümler arasında ücrete hak kazandıran işlemler ve ücrete hak kazanma zamanı ile ilgili hükümler yeniden ele alınmıştır. Bunlarla birlikte ücret hakkıyla ilgili olarak acenteye çok geniş bir bilgi alma ve defter kayıtlarını isteme ve inceleme hakkı tanınmıştır. Çalışma "Giriş" ve "Sonuç" bölümleri haricinde üç bölümden oluşmaktadır. Birinci bölümde acente kavramı ve bu kavramı oluşturan unsurlar incelenmiştir. Ayrıca acentenin hak ve borçlarına değinilmiştir.Çalışmanın ikinci bölümünde, acentenin en temel hakkı olan ücret hakkı incelenmiş olup; üçüncü bölümde ise, 6102 sayılı TTK ile getirilen düzenlemeler ve değişiklikler, 6762 sayılı TTK ile karşılaştırmalı olarak ele alınmıştır. Ücret hakkına ilişkin bu değişiklikler, acentelik sözleşmesi sona erdikten sonra acentenin ücret talep edebileceği haller; ücrete hak kazanma anındaki ve ücretin muaccel olacağı andaki değişiklikler; ücret hakkında acentenin belge ve bilgi isteme hakkının emredici olarak düzenlenmesi olarak özetlenebilir. Law no. 6102 Turkısh Commercial Code brings advances at provisions about agency .The new Code brings new provions comparing with Law no. 6762 Turkısh Commercial Code. Furthermore, it resolves some issues existing in the period of 6762 Turkısh Commercial Code. Agency contract is a bilateral contract. Therefore the rights of the agent, constitutes theobligations of the principal. The commission right is also obligation of the principal. The provisions about commission right are reargued out, including transactions which bearing commission and time of entitlement of commission This thesis is consist of three chapters excluding the "introduction" and the "conclusion" parts. In first chapter, the notion of the agent and the elements of this notion are discussed. Moreover, rights and obligations of agent are examined. In chapter two, the principal right of agent, commission right is discussed. In chapter three, commission right is examined comparing with the provisions of Law no. 6102 Turkısh Commercial Code and Law no. 6762 Turkısh Commercial Code. Amendments about commission right are time of entitlement of commission , time of commission becoming payable. Furthermore , in some cases, an agent shall be entitled to commission on commercial transactions concluded after the agency contract has terminated. Lastly, an agent shall be entitled to demand that he be provided with all the information, and in particular an extract from the books, which is available to his principal and which he needs in order to check the amount of the commission due to him. Provision about demanding information is statutory.
433640
Keywords: Acenteler; Agents; Commissions; Kanunlar 6762 sayılı; Komisyonlar; Laws 6762 numbered; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Wage policies; Wage systems; Ücret politikaları; Ücret sistemleri

İnternete erişim yasakları ve hukuka aykırılıklar - Taşkin, Şaban Cankat (Kocaeli Üniversitesi, 2015)
İnternet, bünyesi gereği pek çok temel hak ve özgürlükle bağlantılıdır. Bu da İnternet'i pek çok açıdan incelemeyi gerektirmektedir. Bu yönüyle de İnternet'e erişim hakkının kendine özgü (sui generis) niteliğe sahip olduğu söylenebilir. Çalışmamızda, İnternet'e erişim yasakları temel hak ve özgürlükler ışığında incelenirken, hakkın kendine özgü yapısı Anayasa'daki düşünceyi ifade, bilim ve sanat, basın, bilgi edinme ve bilgiye ulaşma, haberleşme ve eğitim özgürlükleri açısından konuya ilişkin AİHM, ABD-YM, AYM, Yargıtay kararları da analiz edilerek, İnternet sitelerinin nitelik farkları da gözetilerek, ceza, anayasa, idare hukuku; MK 24 ve 25'teki kişiliğin korunması, 5651 Sayılı Kanun, ihtiyati tedbirler, Ticaret Hukuku boyutlarıyla ve devletin genel kuramı ışığında, istatistiki veriler ve karşılaştırmalı hukuk düzenlemeleriyle bilrikte detaylıca incelenmiştir. Çalışmada ayrıca İnternet üzerinde denetim ve yaptırım yetkisi olan Telekominikasyon İletişim Başkanlığı (TİB), Erişim Sağlayıcıları Birliği (ESB) de karşılaştırmalı hukuktaki örnekleriyle kıyaslamalı olarak incelenmiştir. Anahtar Sözcükler: 5651 Sayılı Kanun, erişim yasakları, erişim yasağı, TİB, ESB. Due to the structure of the internet, is related to many basic rights and freedoms. In many ways the internet requires this review. In this respect, the distinctive right of access to the internet (sui generis), it can be said that the character has. In our study, the prohibition of access to the internet is examined in the light of fundamental rights and freedoms, while the peculiar expression of the right in the Constitution, structure, science and art, press, information, and access to information, in terms of freedom of communication and education on the issue, the court in U.S.-YM, the Constitutional Court, the decisions of the Supreme Court by analyzing the quality of the internet site considering the differences, criminal, constitutional, and administrative law; MK 24 and 25 on protection of personality, Law No. 5651, the precautionary measures, in the light of general theory of law and state commercial, statistical data have been studied in detail and Comparative Law in conjunction with the Regulations. The study also who has the authority to control and sanction over the Internet, the telecommunication communication presidency (TIB), Access providers Association (ESB) was investigated also in comparison with the examples in Comparative Law. Keywords : Law No. 5651, access bans, ban access, TIB, ESB
Keywords: Access; Blocking access; Erişim; Erişim engelleme; Hukuka aykırılık; Illegal; Internet; Kanuna aykırılık; Kanunlar 5651 sayılı; Laws 5651 numbered; Prohibitions; Telecommunication Communication Presidency; Telekomünikasyon İletişim Başkanlığı; Unlawful; Yasaklar; İnternet

Anonim ortaklıkta şirkete borçlanma yasağı - Toraman Çolgar, Emek (İstanbul Üniversitesi, 2015)
Çalışmamız, 6102 sayılı Türk Ticaret Kanunu'nda ilk kez düzenlenen anonim ortaklıkta şirkete borçlanma yasağını konu edinmektedir. Anılan yasak, pay sahipleri için TTK m. 358'de, pay sahibi olmayan yönetim kurulu üyeleri içinse TTK m. 395'te düzenlenmiştir. Her iki hüküm de Türk hukukuna özgüdür ve Kanun'da yalnızca ana hatları ile düzenlenmiştir. Bu nedenle çalışmada, düzenlemelerin kapsamı, istisnaların sınırı ve yasağa aykırılığın sonuçları incelenmiş ve değerlendirilmiştir. The subject matter of this thesis is the prohibition to be indebted to the company in the form of a joint stock partnership, which has been regulated in the Turkish Commercial Code for the first time. Said prohibition is regulated in the article 358 of TCC for shareholders and in the article 395 for the board of directors who are not a shareholder. Both provisions are unique to Turkish law and introduced with their essential points only. Therefore in this thesis, the scope, limitation of exceptions and the consequences of the breach of the prohibition are analysed and assessed.
422225
Keywords: Anonim şirketler; Borrowing; Borçlanma; Borçlanma yönetimi; Company law; Debt management; Joint stock company; Kanunlar 6102 sayılı; Laws 6102 numbered; Prohibitions; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yasaklar; Şirketler hukuku

Hukuki açıdan forfaiting - Aşik, Pinar (Ankara Üniversitesi, 2014)
Forfaiting, yatırım malları ve hizmet ihracından doğan alacakların satıcı-ihracatçıya rücu edilmeksizin satışı olarak tanımlanmaktadır. Farklı biçimleri bulunmasına karşılık, bu finansman yönteminin temel konusu poliçe ve bonodan doğan alacaklardır. Poliçe forfaiting'inde poliçe, ihracatçı tarafından ithalatçı üzerine çekilmekte ve onun tarafından kabul edilmektedir. Bu durumda ihracatçı keşideci, forfaiter ise lehdar ya da ciranta konumunda bulunmaktadır. Fakat bu durum bazı problemlere yol açmaktadır. Zira bu finansman yönteminin temel ve ayırıcı özelliği rücu edilmezlik klozudur. Bu kloz, kıymetli evrak hukuku bakımından ihracatçının, ciroya "rücu edilmez" kaydı eklemek suretiyle kendisini poliçenin ödenmemesi sorumluluğundan kurtarmasını ve forfaiter'ın ticari riski üstlenmesini gerekli kılar. Fakat bir poliçenin keşidecisi, poliçenin kabul edilmesini ve ödenmesini garanti etmektedir. Onun kendisini poliçenin kabul edilmemesi sorumluluğundan kurtarması mümkün iken, ödenmemesi sorumluluğundan kurtarması mümkün değildir. Zira keşidecinin poliçenin ödenmemesinden sorumluluğunu kaldıran kayıtlar yazılmamış sayılır. Bu durum ise forfaiting'in özüne aykırıdır. Bahsi geçen bu problem bonolar bakımından söz konusu olmaz; çünkü bono forfaiting'inde ithalatçı, asıl borçlu olarak düzenleyen, ihracatçı ise lehdar konumundadır ve onun kendisini ciranta olarak ödememeden sorumsuz kılması mümkündür. Bu farklılık nedeniyle forfaiting işleminde bir çok ihracatçı tarafından bonolar, poliçelere nazaran tercih edilmektedir. Forfaiting is defined as the purchase, without recourse to any previos holder of receivables due to mature in the future and arising from export of capital goods and services. Although there are several forms of forfaiting, main subject of this form of finance is receivables arising from bills of exchange and promissory notes. In bill of exchange forfaiting, the bill of exchange is drawn on the importer (drawee) by exporter (drawer) and accepted by importer. The forfaiter is payee (beneficiary) or indorser. But this cause several problems . Because the main characteristic and distinctive speciality of this financing method is "without recourse clause". This clause requires exporter to free himself from any responsibilities by using of "without recourse, sans recourse stipulation" in the indorsement and requires forfaiter to assume commercial risks in terms of law of negotiable instrument. But the drawer of a bill of exchange guarantees both aceptance and payment. He may release himself from the liability of non acceptance but any stipulation by which he releases himself from the liability of non payment is deemed to be not written. Thus, the drawer of a bill of exchange, the exporter, may not be liable as it is indorser but will always be liable as it is drawer. This situation conflicts with the esense of forfaiting. But the problem as stated above is not seemed in promissory notes because in promissory note forfaiting, the importer is maker as main obligor and the exporter is (payee) beneficiary. And he has the legal right to free himself of any liability as an indorser by using without recourse stipulation. Because of this difference promissory notes are prefered to bill of exchange by many exporters.
Keywords: Alacağın temliki; Commercial law; Export; Forfaiting; Ticaret hukuku; Transfer of the credits; İhracat

Ticari işlerde kefilin sorumluluğu - Özkul, Burcu (Süleyman Demirel Üniversitesi, 2013)
Ticari hayatta sıklıkla karşılaşılan hukuki işlemler ve özellikle sözleşmeler dolayısıyla borç ilişkileri ortaya çıkmaktadır. Borç ilişkisi ise sözleşmenin taraflarını alacaklı veya borçlu konuma getirmektedir. Ticari hayatın baş aktörlerinden olan tacir; borç ilişkisinde alacaklı tarafta yer aldığında, alacağını elde edememe kaygısını taşıyabilir. Bu kaygıyı minimize etmek amacıyla borçludan bir güvence istemesi tabidir. Bu bağlamda tacir, ipotek veya rehin ile alacağını güvence altına almaya çalışabilir. Ancak gerek ipotek ve rehin tesis edilebilecek unsurların sınırlı olması gerekse bu işlemlerin fazla masraflı olması nedeniyle tacir ayni teminatlardan daha çok şahsi teminatlara yönelmektedir. Kefalet sözleşmesi ise en sık başvurulan şahsi teminatlardan biridir. Çünkü genellikle dostane ilişkilere dayanmaktadır. Dolayısıyla kefalet sözleşmesi ticari hayatın vazgeçilmez unsurlarındandır. 01.07.2012 tarihinde yürürlüğe giren 6098 sayılı Türk Borçlar Kanunu ile borçlar hukuku alanında, yine aynı tarihte yürürlüğe giren 6102 sayılı Türk Ticaret Kanunu ile de ticaret hukuku alanında reform sayılabilecek değişimler yaşanmıştır. Her iki Kanundaki değişimler gerek ticari iş, ticari işletme, ticaret ortaklıkları ve dolayısıyla tacire ilişkin hükümleri ve gerekse kefalet sözleşmesi başta olmak üzere teminat sözleşmelerini yeni bir yapılanmaya götürmüştür. Bu çerçevede çalışmada; Türk Ticaret Kanunu ve Türk Borçlar Kanunu'nda yapılan reform değişiklikler harmanının ticari işlerde kefalet sözleşmesine ve kefile yansımaları ele alınmıştır. Konu, gerçek kişi tacir-tüzel kişi tacir ayrımı doğrultusunda incelenip ticari işlerde kefalet sözleşmesi düzenlendiğinde, sözleşmenin durumu ve tacirlerin sorumlulukları değerlendirilmiştir. Değerlendirme yapılırken, tüzel kişi tacir sıfatına sahip olan ticaret ortaklıkları, ticari işletme işleten dernekler ve vakıflar, ticari şekilde işletilmek üzere kurulan kamu tüzel kişileri ve ayrıca bankaların kefalet sözleşmesindeki konumu, durumu ve sorumluluğu yenilenen hükümler ışığında irdelenmiştir. Anahtar Kelimeler: Kefalet Sözleşmesi, Kefil, Sorumluluk, Tacir, Ticari İş. Relations of loan rise due to legal transactions and especially contracts which are frequently experienced in business life. Relations of loan put contracting parties either debtor or creditor positions. When trader, who is one of the main actors of business life, is on creditor side; might have concern about not collecting the debt. And it is quite natural that he can ask for security to minimize this concern. In this regard, trader could secure his claim by hypothec and pleadings. However, trader heads for personal guarantee rather than real security as both the components which can establish hypothec and pleading are limited and these transactions are too costly. Suretyship contract is one of the most chosen personal guarantees. Because, it relies on amicable terms. So, suretyship contract is one of the indispensable components of business life. Turkish Code of Obligations, Law Number 6098 which came into force on 01.07.2012 and Turkish Commercial Code, Law Number 6102 which entered in force on the same date are the changes which can be called as reforms. With changes in both laws, not only commercial affair, business organization, business partnership and accordingly the terms as to trader, but also contract of guarantees, particularly suretyship contracts were re-structured. Within this scope in this study, changes in Turkish Commercial Code and Turkish Code of Obligations and their influence on surety and suretyship contracts in business affairs are interpreted. Subject is assessed in line with difference between real person trader and legal person trader and when suretyship contract is drawn up in business affairs, condition of contract and responsibilities of traders are handled. The business partnerships which have legal person trader title, associations and foundations which run business organizations, the public entities established to be operated commercially, and position, condition and responsibility of banks in suretyship contracts are addressed in the light of renewed terms.
Keywords: Commercial Affair; Kefalet sözleşmesi; Responsibility; Sorumluluk; Surety; Suretyship contract; Trader

Sözleşmelerde cezai şart - Pekdemi̇r, Şevket (Ondokuz Mayıs Üniversitesi, 2013)
Tarafların sözleşmeden kaynaklanan sorumluluklarını kararlaştırılan zamanda ifa etmemeleri birtakım sorunlara sebep olmaktadır. Özellikle davaların kısa sürede sonuçlandırılamaması, zarar ve kusurun ispatı gibi güçlükler alacaklıyı borcun ifasını sağlayacak arayışlara sevk etmektedir. Cezai şart günümüzde borçlar hukukunda, ticaret hukukunda, iş hukukunda ve medeni hukukta geniş uygulama alanına sahiptir. Tarafların kolay bir şekilde ve kendi iradeleriyle istedikleri gibi kararlaştırabilmeleri cezai şartın sıklıkla başvurulan hukuki işlem olmasının en önemli nedenlerindendir. Borçluyu ifaya zorlama, zararın tazmin edilmesi ve alacağın teminat altına alınması gibi birçok temel işlevi olan cezai şart borçlunun, asıl borcunu ilerde hiç veya gereği gibi ifa etmemesi ya da geç ifa etmesi durumunda, alacaklıya ödemeyi önceden taahhüt ettiği edimdir. Cezâî şart anlaşmasından doğan borç, asıl borca bağlı feri bir borçtur. Bu bakımdan asıl borç yoksa cezai şartın varlığından bahsedilemez. Ancak ifa zamanından sonra cezai şart, niteliği veya miktarı bakımından bağımsız bir edim haline dönüşür. ?Sözleşmelerde Cezai Şart? konulu çalışmamız, üç bölümden oluşmaktadır. Giriş kısmında çalışmanın önemi, amacı, yöntemi, kaynakları ve değerlendirme metodu hakkında bilgi verilmiştir. Birinci bölümde hem modern hukuk hem de İslam hukukuna göre sözleşme, şart ve cezai şart kavramları incelenmiş, cezai şartın konusu, amacı, benzer kavramlarla ilişkisi ve çeşitleri araştırılmış, hukuki niteliği, unsurları ve muaccel olmasının şartları tespit edilmiş, İslâm hukukuna göre para borçlarında ve diğer borçlarda cezai şartın hükmü tahlil edilmiştir. İkinci bölümde amacı bakımından sınıflandırılan sözleşmelere cezai şartın etkisi araştırılmıştır. Bu bağlamda sözleşme çeşidi hakkında kısa bilgi verilmiş İslâm hukukçularının görüşleri delilleriyle birlikte tespit edilmiştir. Üçüncü bölümde cezai şartın tadili, iptali ve sona ermesi başlığı altında, modern hukukla mukayeseli olarak cezai şart miktarının indirilmesinin veya artırılmasının kriterleri tespit edilmiş, cezâî şartın iptali ve sona ermesi konusu araştırılmıştır. Sonuç kısmında ise `Sözleşmelerde Cezai Şart? konulu çalışmadan elde ettiğimiz neticeler ifade edilmiştir. Anahtar Kelimeler: İslâm Hukuku, Cezai şart, Borç, Faiz, Zarar. Not performing the responsibilities of two partners on a stated time causes some problems. Especially not ending of the lawsuits in short time and difficulties such as proving of damage and negligence lead to searching to provide executing of debt. Penal clause has a large practice field in law of obligations, trade law, labour law and civil law. Deciding of the partners easily and with their own freedom is one of the most important causes commonly applied process of penal clause. Penal clause having many functions such as forcing to excuting, reimbursing of damage and ensuring the credit is an action that commits to pay to the creditor in case of not performing of the borrower at all in the future. The debt from penal clause contract is a secondary one belonging to the principal debt. So, in the absence of original debt, it is not a case to talk about penal clause. But after the time of execution, penal clause transforms into an independant action. The study titled 'The Penal clause in Contracts' consists of three sections. In the introductory section In the introductory chapter the information has been presented about the goal, the method, resources evaulation method of the study. In the first section, the conditions of the contract and the concept of penal clause have been searched according to both modern law and islamic law and also the subject of penal clause has been examined in terms of its goal and relations with similar concepts and types and also judicial qualification and conditios for being executory and the provision of penal clause with currency debtsand another type of debts according islamic law. In the second section the effects of penal clause to the contracts classified in the respect of the goals have been researched. In this sense a short information has been given about the types of contract and the thoughts of islamic lawyers have been examined. In the third section under the title of remodelling and ending of penal clause, the criteria of the decrease or increase of the quantitity of penal clause in contrast with modern law have been examined and the issue of cancellation and ending of penal clause has been searched. In the conclusion part of the study , the results obtained by the study titled penal clause in contracts have been stated. Key Words: Islamic Law, Penal Clause, Loan, Interest, Los
Keywords: Clause pénale; Contract; Contrat; Interest; Loan; Penal clause

Markanın hükümsüzlüğü ve hukuki sonuçları - Sekmen, Orhan (İstanbul Kültür Üniversitesi, 2013)
"Bu çalışma, markanın hükümsüzlüğü ve hükümsüzlüğün hukuki sonuçlarını mukayeseli hukukla karşılaştırmak suretiyle incelemeyi amaçlar. İnceleme 3 bölüm-den oluşmaktadır. Marka kavramı ve benzer kavramlarla karşılaştırılması başlıklı birinci bölümde: Markanın tarihçesi ve marka hakkındaki hukuki gelişmeler, teori-ler, markanın iktisabına ilişkin sistemler, markanın tanımı, türler, işlevi ve sınıfları ile markanın benzer kavramlarla karşılaştırılması konuları; markanın Hükümsüz-lük Halleri başlıklı ikinci bölümde: Hükümsüzlük ve iptal kavramları, mutlak ret nedenleri, nispi ret nedenleri ve markanın tescil edilmesinden sonra ortaya çıkan di-ğer hükümsüzlük nedenleri ile KHK da öngörülmemesine rağmen, Tasarıda düzen-lenen ve bizce de hükümsüzlük nedeni olarak kabul edilmesi gereken bazı haller; Hükümsüzlük davası ve hükümsüzlüğün hukuki sonuçları başlıklı üçüncü bölümde ise: hükümsüzlük davasının niteliği ve özellikleri, tarafları, deliller ve değerlendiril-mesi ile resen araştırma sorunu ve hükümsüzlük kararının etkileri ayrıntılı olarak incelenmiş ve gerekli değerlendirmeler yapılmıştır. This study aims at examining the invalidity of trademark and legal conse-quences of invalidity through comparative law. The study is divided into three chapters. The first chapter with the heading of Trademark Concept and It’s Comparison with Similar Concepts reviews the history of trademark and legal evolution of trademark, theories, trademark acquisition systems, definition of trademark, types of trademark, functions and classifications and comparison of trademark with similar concepts; then, the second chapter with the heading of Reasons of Invalidity of Trademark reviews the concepts of invalidity and annulment, absolute refusal reasons, relative refusal reasons and other reasons that can appear after registration of trademark and many reasons, in our opinion, that should be accepted as reasons for invalidity despite those are not foreseen in Decree Law, many further reasons for annullment that are stated in Draft Law as we also share the same opinion; while, finally, the third chapter with the heading of Suit of Invalidity and Legal Consequences of Invalidity reviews in detail, the nature of suit of invalidity and its properties, the parties, proofs and its as-sessment, courts duty of ex-officio assessment, and effects of court verdict for invalidity. Then, necessary evaluations were made at the end of the study."
Tez N°333258
Keywords: Brand; Commercial law; Hukuki işlemler; Hukuki sonuç; Hukuksal korunma; Hükümsüzlük; Intellectual property; Judicial conclusion; Legal processes; Legal protection; Marka; Marka tescili; Nullity; Propriété intellectuelle; Regitration of trademark; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku

Cari hesap sözleşmesi - Durgut, Ramazan (İstanbul Üniversitesi, 2012)
Keywords: Banka hukuku; Banking law; Cari hesap sözleşmesi; Commercial law; Current account agreement; Faiz; Interest; Ticaret hukuku

Milletlerarası unsurlu acente ilişkilerinden doğan kanunlar ihtilafı - Güner, Cemil (Selçuk Üniversitesi, 2012)
Milletlerarası ticarette, acenteler aracılığıyla yapılan ticarî işlemlerin önemli bir yeri vardır. Acenteler, tacirler ad ve hesabına sözleşme akdettikleri için, doğrudan temsil hükümleri doğmaktadır. Milletlerarası unsurlu acente ilişkisine uygulanacak hukuk ve bu statünün uygulama alanına giren meselelerin tespiti, kanunlar ihtilâfı hukukunda tartışmalı konulardan biridir. Bu çerçevede, acente ilişkisine uygulanacak hukuk, acente iç ve dış ilişkisi dikkate alınarak tespit edilmektedir. Acente iç ilişkisine uygulanacak hukuk, karşılaştırmalı hukukta ve Türk hukukunda akit statüsüne tâbi tutulmaktadır. Buna göre, acente ve temsil olunan, iç ilişkiye uygulanacak hukuku açıkça ya da zımnen serbestçe seçebilirler. Hukuk seçimi anlaşmasının yokluğunda ise, sözleşmeyle sıkı ilişkili hukuk esas alınır. Sözleşmeyle sıkı ilişkili hukukun tespitinde ise genellikle acentenin işyeri tercih edilmektedir.Acente dış ilişkisine uygulanacak hukuk ise, temsil statüsü olarak anılmaktadır. Buna göre, acente ilişkisinde temsil yetkisine uygulanacak hukuk bakımından, karşılaştırmalı hukukta ve Türk hukukunda, irade muhtariyeti reddedilmektedir. Ancak Avusturya hukuku, İspanyol hukuku ve La Haye Temsil Konvansiyonu'nda sınırlı hukuk seçimine imkân tanıyan düzenlemeler vardır. Milletlerarası acente ilişkisinin gereklerine uygun olarak, temsil olunanın seçtiği hukukun üçüncü kişi tarafından açıkça kabulü şartıyla böyle bir hukuk seçimi geçerli kabul edilebilmelidir. Acente dış ilişkisine uygulanacak hukukun, objektif kriterlere göre tespitinde ise, genellikle acentenin işyeri hukuku tercih edilmektedir. Ancak acentenin işyerinin olmaması ya da üçüncü kişinin bu işyerini bilmemesi hâllerinde, acentenin işyeri hukuku yerine temsil yetkisinin kullanıldığı yer hukukunun bu çerçevede ortaya çıkan ihtilâflara uygulanması kabul edilmektedir. The business transactions are made through agents have important role in the international trade. The direct agency relationship occurs through the agent. Because the agent serves with continuing authority to conclude contract on behalf of and in the name of its? principal. The law applicable to agency relationship with foreign element and finding of it?s application area?s topics are controversial in conflict of laws. In this context, the law applicable to agency relationship is determined according to internal side and external side of this relationship. The internal agency relationship is normally founded on the agency contract and, as such, is governed by the general principles of private international law applying to the contracts in comparative law and Turkish law. According to this, principal and agent may choose expressly or impliedly the law applicable to the internal agency relationship between them. If principal and agent have failed to indicate the law governing, it becomes necessary to determine the law with which the agency contract is most closely connected. In general, this maybe the law of the country in which the agent has his place of business.The law applicable to external agency relationship is known as the agency statute. According to this, the party autonomy has not been adopted as regards the agency statute in comparative law and Turkish law. But there are some exceptional regulations which adopt the resticted party autonomy. For example, Austrian law, Spanish law and, The 1978 Hague Convention on The Law Applicable to Agency allow party autonomy which is resticted. So, the law applicable to external agency relationship may be chosen in accordance with international agency relationship as long as third party expressly adoptes the law principal choices. While the law applicable to external agency relationship is determined in respect of objective criterias, in general, the agent?s place of business is prefered in comparative law like Turkish law. Nonetheless if there is no agent?s place of business or, the third party couldn?t know this place, this matter is governed by the law of place in which the agent act.
Keywords: Acenteler; Agents; Commercial law; Contracts; Hukuki uyuşmazlıklar; Incompatibility; International Law; International disputes; Labour disagrement; Legal disputes; Sözleşmeler; Ticaret; Ticaret hukuku; Trade; Uluslararası Hukuk; Uluslararası uyuşmazlıklar; Uyuşmazlık; İş uyuşmazlıkları

Sermaye azaltımı ve vergisel sonuçlarının analizi - Öztürki, İlham (Gazi Üniversitesi, 2012)
Ekonomi, finans ve hukuk bilimleri açısından farklı anlamlara gelen sermaye, başta pay sahipleri ve ortaklık alacaklıları olmak üzere, ileride pay sahibi olması muhtemel kişileri, ortaklıkla ilişki halinde olan diğer gerçek ve tüzel kişileri ve şirketlerin vergi mükellefi olması nedeniyle de devleti yakından ilgilendiren bir kavramdır. İktisadi faaliyetlerin yürütülmesinde hayati önemi haiz sermayenin çeşitli ekonomik nedenlerle ihtiyari ya da sermaye kaybında olduğu gibi zorunlu nedenlerle azaltılması mümkündür.Sermaye azaltımı müessesesi Türk Ticaret Kanunu'nun (TTK) 473, 474 ve 475'inci maddelerinde düzenlenmiştir. Sermayenin şirket alacaklıları için güvence oluşturma fonksiyonu dikkate alınarak, özü itibariyle bir esas sözleşme değişikliği mahiyetinde olan sermaye azaltımı diğer esas sözleşme değişikliklerinden farklı birtakım düzenlemelere ve sıkı kurallara tabi tutulmuştur.Ülkemizde uzun yıllar süren enflasyonist etkiler ve ağır işleyen maliyetli bir süreç gerektirmesi nedeniyle yaygınlık kazanamayan yapının; enflasyon oranlarındaki düşme eğilimine ve sermaye azaltımı sonucunu doğurabilecek şirket bölünmelerinin TTK ile yasal alt yapıya kavuşturulmasına paralel olarak eskiye oranla daha sık kullanılması beklenmektedir. Bu itibarla sermaye azaltımı müessesesinin, uygulamada yaygınlık kazanması öncesinde vergisel sonuçlarıyla birlikte ele alınması, irdelenmesi, tereddüt ve belirsizliklerden arındırılmış daha etkin işleyen esnek bir yapıya kavuşturulması önem arz etmektedir.Vergi kanunlarımızda sermaye azaltımının vergilendirilmesi hususunda açık bir hüküm bulunmamasına rağmen, uygulamada sermaye azaltımı neticesinde ortaklara yapılan ödemelerin kâr payı olarak nitelendirilmesinin ve kâr paylarının tabi olduğu vergilendirme rejimi kapsamında vergilendirilmesinin anayasal bir ilke olan vergilerin kanuniliği ilkesine uygunluğu tartışmalıdır.Bu çalışmada, ticaret hukuku, sermaye piyasası hukuku ve vergi hukuku bileşenleri dikkate alınarak eski ve yeni ticaret kanunu, vergi kanunları ve vergilendirme ilkeleri, sermaye piyasası mevzuatı, konuya ilişkin yargı kararları, vergi uygulamaları bir arada değerlendirilerek sermaye azaltımı müessesesi ve bunun vergilendirilmesi incelenmiş, başta sermaye azaltımının vergilendirilmesine ilişkin açık bir kanun hükmünün bulunmamasından kaynaklananlar olmak üzere uygulamada karşılaşılan sorunlara değinilerek bunların çözümüne yönelik öneriler geliştirilmiştir. Capital is defined differently in economics, finance and law and it is a subject of interest to various natural and legal persons such as shareholders, creditors, possible future shareholders and other stakeholders of the firm. Firms being tax payers, firms? capital is also a subject of interest to the state. Capital can be reduced voluntarily due to various economic reasons, or as a mandatory process in case of a loss of capital.In the Turkish legislation, capital reduction is regulated in Articles 473, 474, and 475 of the Turkish Commercial Code (TCC). Taking into consideration the protective role of capital for the creditors, capital reduction, which is in essence, a change in the Articles of Incorporation, is regulated with stricter rules than other changes to the Articles of Incorporation.Capital reduction has not been widely used in Turkey, due to the long lasting high inflation periods, and the process being slow and costly. Currently, with substantially lowered inflation rates, and the newly introduced changes to the TCC, setting the rules for corporate spin offs, which might result in capital reductions, the process is expected to be used much more frequently than before. Consequently, before it becomes widely used, it is important to analyze the process of capital reduction together with its tax impacts, and to suggest any revisions to the existing process, for eliminating any uncertainties and making the process more effective.Although there is no explicit provision in our tax laws related to the taxation of capital reduction, in practice, when there is a payment to the shareholders due to capital reduction, for tax purposes this payment is treated as dividend and taxed accordingly. However, it is debatable that this practice is in line with the constitutional principle that taxes can only be levied through laws.This study analyses capital reduction and issues related to its taxation, taking into consideration their relevance to commercial law and capital market law. Thus, the analysis collectively evaluates the provisions in the old and the new Commercial Codes, Tax Codes, Capital Market Legislation, related court decisions and taxation practices, identifies and suggests solutions to the problems encountered in practice, which mainly arise due to the fact that there is no explicit provision in the tax laws for taxation of capital reduction.
Keywords: Capital decrease; Dividend; Kar dağıtımı; Kar payı; Profit distribution; Sermaye azaltma; Tax responsibility; Tax system; Taxation; Vergi sistemi; Vergi sorumluluğu; Vergilendirme

Uluslararası Ticaret Hukukunda vesaik mukabili ödeme - Atalay, Ersan (Yeditepe Üniversitesi, 2011)
Uluslararası ticaretle ilgili alım satım sözleşmelerinde temel olan edimlerden birisi de ödeme dir. Türk hukuk sisteminde kullanıldığı şekli ile Vesaik mukabili ödeme uluslararası ticaretin önemli ödeme araçlarından birisidir.Uluslararası ticaret hukukunda bu konu hakkında tüm ülkeler açısından geçerli olan bir yasal düzenleme yoktur. Bu yüzden bazı örgütler, bu boşluğu doldurmayı amaçlamışlardır. Bu örgütlerden biri Uluslararası Ticaret Odası dır. Uluslararası Ticaret Odası, uluslar arası ticaretin yeknesak kurallara bağlanmasını amaç edinmiştir. Bunun için bazı broşürler yayınlamaktadır. Vesaik Mukabili Ödeme' ye ilişkin olarak, URC 522 kısaltmasıyla anılan, Tahsiller İçin Yeknesak Kurallar broşürünü yayınlamıştır. En son gözden geçirme çalışmaları 1995 yılında yapılmıştır. Bu yayının amacı, ortak dil ve anlayış birliğini sağlamak ve uluslar arası ticaretin daha hızlı, basit ve güvenli şekilde yürütülmesini gerçekleştirmektir.Türk hukuk sisteminde bu konuyu özel olarak düzenleyen bir yasa mevcut değildir. O yüzden uluslar arası ticaretle uğraşan kişilerin, vesaik mukabili ödeme yöntemini kullanarak ithalat-ihracat yapmak istediklerinde başvurabilecekleri kurallar URC 522 yayınıdır. Uluslararası ticarette taraflar URC 522 adıyla anılan yeknesak kuralların, kendi sözleşmelerine uygulanmasını sağlayabileceklerdir. Aksi durumda, yeknesak kurallar uygulanamayacaktır. Bu durumda, devletler özel hukuku kurallarına göre, söz konusu sözleşmeye uygulanacak hukukun tespiti gereklidir. Bu durumda ülkelerin milli hukuklarının, uluslar arası ticarete etkileri söz konusu olmaktadır. Yeknesak kuralların, kendiliğinden uygulanması söz konusu değildir.Uluslararası ticarette yeknesak kuralların varlığı olası problemleri en aza indirgemek açısından önemli ve gereklidir. One of the basic performances in international sale contract is payment. There are different types of payment methods in international trade law. Besides Letter of Credit Documents against payment? has an important place not only in Turkish export trade law but also in international business area.There is no current law arrangement about this payment method for all nations in international trade law. Therefore some organization have aimed to fill this legal loophole. One of this organizations is International Chamber of Commerce. This organization has aimed international trade to be tied with uniform rules. Therefore it has published some brochures. It has prepared and published Uniform Rules for Collections shortly called as URC 522 related documentary collections. Last revision was done in 1995. This brochure?s aim is to ensure common understanding and common language, and to be conducted more faster, guaranteed and easier of international trade.There are no special legal arrangement about this subject in Turkish legal system. Therefore, the actors who want to make export-import is mostly use the documents published in the brochure no URC 522.Parties of international trade can ensure application of the uniform rules called as URC 522 to their sales contracts. At the contrary case, uniform rules for collections is not applied. About this case, applicable law rules of Private International Law has to be determined to according contract. In such case, nations law regulations appear to effect in international trade. Uniform rules does not applicable per se.Existance of uniform rules in international trade is important and necessary for reducing possible problems.
Keywords: Akreditif; Alım-satım; Cash against documents; Commerce international; Commercial law; Contracts; International Chamber of Commerce; International Trade; International law; Letter of credit; Payment systems; Payments; Sale and purchase; Sözleşmeler; Terms of payment; Ticaret hukuku; Uluslararası Ticaret Odası; Uluslararası hukuk; Uluslararası ticaret; Vesaik mukabili ödeme; Ödeme sistemleri; Ödeme şekilleri; Ödemeler

Hukuk sosyolojisi açısından vahiy döneminde ticari hayat - Baysa, Hüseyin (Ondokuz Mayıs Üniversitesi, 2011)
Modern dönemde ticarî hayatta ortaya çıkan mübadele yöntemlerini İslâm ticaret hukuku açısından değerlendirebilmek ve İslâm'ın ticarî alandaki temel ilkelerine aykırı işlemlere alternatif yöntemler üretebilmek için öncelikle vahiy dönemindeki ticaret hukukunu tespit etmek gerekmektedir. Vahiy dönemindeki ticaret hukukunun sağlıklı bir şekilde anlaşılabilmesi ise dönemin ticarî kurallarının sosyolojik açıdan incelenmesini zorunlu kılmaktadır. Bu amaçla yapılan bu araştırmada ulaşılan sonuçları kısaca şu şekilde ifade etmek mümkündür:Cahiliye döneminde Hicaz bölgesinde sosyal hayat, bölgenin coğrafî yapısı ile dönemin siyasî ve dinî şartları etkisi altında sürdürülmüştür. Yeni bir yaşam biçiminin hedeflendiği vahiy döneminde toplumsal hayatın bütün ünitelerinde değişikliğe gidilmiş, Hicazlılar'ın iktisadî tecrübe ve ihtiyaçları göz önünde bulundurularak yeni bir ticaret hukuku oluşturulmuştur. Mekke devrinde, Hz. Peygamber kanun koyup uygulayacak siyasî güce sahip olmadığı için, hayatın diğer alanlarında olduğu gibi ticaret hukuku alanında da temel ahlâkî değerler müslüman tebaaya benimsetilmeye çalışılmakla yetinilmiştir. Hicretten sonra Medine'de siyasî ve askerî bakımdan yeterli güce kavuşulunca ekonomik sisteme müdahale edilmeye başlanmıştır. Bir önceki dönemden devralınan ticarî kurum ve işlemler adalet eksenli yeni hukukî ve ahlâkî kurallara göre değerlendirilmeye tabi tutulmuştur. Ticaret hayatında yapılan değişiklikler içtimaî kurallara uygun bir şekilde gerçekleştirilmiştir. Yeni hukukî düzenlemelerin kargaşaya meydan vermemesi için gerekli görülen konularda tedricî yöntem uygulanmış ve alternatif uygulamalar devreye sokulmuştur. Öte yandan toplumsal yapıyı oluşturan diğer kurumlarda gerçekleştirilen değişiklikler de yeni ticaret hukukunun kolaylıkla topluma mal edilmesinde oldukça etkili olmuştur. Occurring in the commercial life of modern methods of exchange, to assess in terms of commercial law of Islam, and contrary to the fundamental principles of commercial transactions in the field of Islam in order to produce alternative methods, primarily trade law to determine the required period of revelation. Revelation during the period of commercial law in a healthy way to understand the rules of trade requires a review of the sociological perspective. For this purpose, the results achieved in this study, it is possible to briefly stated as follows:The period of ignorance of social life in the Hijaz, the region's geographical structure and the period continued under the influence of political and religious conditions. Revelation in a new way of life, social life aimed to change all the units were made, considering the economic needs of the people of Hijaz experience and created a new trade law. Mecca during the reign of the Prophet put the law does not have the power to implement the political, as in other areas of life in the field of commercial law to teach basic moral values were muslims. After the migration, the strength is reached Medina, the political and military respects, the economic system started to intervene. Commercial institutions and processes inherited from the previous period, according to the rules of justice-oriented evaluation has been subject to new legal and moral. Changes to trade in his life was carried out in accordance with social rules. New legal challenge to prevent confusion in the arrangements, gradual method is applied to matters deemed necessary and alternative practices were introduced. On the other hand, changes in social structure in the new trade law is easily performed by other institutions in society to be the goods have been quite effective.
Keywords: Cahiliye Dönemi; Commercial law; Commercial life; Hedjaz; Hicaz; Hukuk sosyolojisi; Islam; Jahiliyye Period; Law sociology; Socio-cultural structure; Socio-economic life; Sosyoekonomik hayat; Sosyokültürel yapı; Ticaret; Ticaret hukuku; Ticari hayat; Trade; İslamiyet

Vergi Hukukunda birleşme, bölünme ve hisse değişimi işlemleri - Göktuna, Hamdi Deniz Ege (Marmara Üniversitesi, 2011)
Kurumların birleşme, bölünme, kısmi bölünme ve hisse değişimi yoluyla yeniden yapılandırılma işlemleri başta ticaret hukuku olmak üzere, rekabet hukuku, sermaye piyasası hukuku ve vergi hukuku gibi birçok hukuk dalını ilgilendiren çok disiplinli bir alandır. Ticaret hukuku, genel olarak yeniden yapılandırma işlemlerinde şirket alacaklarının ve ortaklarının haklarının korunmasını amaçlamaktayken, vergi hukuku söz konusu işlemler sonucunda ortaya çıkan kâr ile ilgilenmektedir. Yeniden yapılanma işlemlerin vergisel maliyeti, bunların önündeki en önemli engeli teşkil etmektedir. Bu sebeple, tüm hukuk sistemlerinde vergisel açıdan tarafsızlığı sağlayıcı hükümler yer almaktadır.Çalışmamızda, özellikle, üye devletler arasındaki ekonomik ilişkilerin artırılarak, ekonomik gelişmenin ve refahın sağlanması yoluyla güçlü bir topluluk yaratma amacı taşıyan Avrupa Birliği Hukuku ve Türk Hukukunda yeniden yapılandırma işlemlerinin vergisel boyutu incelenmiştir. Avrupa Birliği Mevzuatına uyum sağlama çalışmaları çerçevesinde dolaysız vergiler alanında yapılması gereken düzenlemelerden birisi de vergi kanunlarında şirketlerin bölünmesini ve hisse değişimini kolaylaştırıcı, kalıcı mahiyette hükümler getirmek olmuştur. Dolayısıyla Avrupa Birliği Birleşme mevzuatı, tam üyelik sürecindeki ülkemiz açısından önem arz etmektedir.Çalışmamızın birinci bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerinin kavramsal esasları, Kurumlar Vergisi Kanunu, Türk Ticaret Kanunu ve Yeni Türk Ticaret Kanunu ile ilgili Avrupa Birliği mevzuatı çerçevesinde ortaya konulmaya çalışılacaktır. İkinci bölümde, birleşme, bölünme, kısmi bölünme, aktif transferi ve hisse değişimine ilişkin temel Avrupa Birliği düzenlemesi olan Birleşme Direktifi, Avrupa Birliği Adalet Divanı kararları çerçevesinde incelenecektir. Son bölümde ise Türk vergi mevzuatındaki, birleşme, bölünme ve hisse değişimine ilişkin hükümler tereddütlü noktalara da değinilmek suretiyle ele alınacaktır. Sonuç bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerine ilişkin değerlendirmelerimize yer verilmiştir. Transactions concerning the restructuring of companies through mergers, divisions, partial divisions and exchanges of shares relate to a multi disciplinary domain, including commercial law, competition law, capital markets law and tax law. While commercial law generally aims at the protection of rights of company's creditors and shareholders, tax law is mostly interested with the profit generated through these transactions. The tax cost of restructuring transactions, constitutes the main obstacle for those. For this reason, all legal systems include provisions providing tax neutrality regarding these transactions.In this study, we have analysed the tax law dimension of restructuring transactions especially in Turkish Law and Law of European Union which aims at the creation of a strong community through the development of economic relations between member states. Within the context of harmonisation to the European Union Legislation, one of the necessary regulations concerning direct taxes has been the enactment of tax law provisions enabling the division of companies and exchanges of shares thereof. Consequently, EU Merger Legislation is of utmost importance for Turkey as a candidate state.The first chapter of this study presents the conceptual basis of the transactions in question within the context of Corporate Tax Law, Commercial Law and the New Commercial Law and EU Legislation. The second chapter examines the Merger Directive within the framework of jurisprudences of European Court of Justice. The last chapter deals with problematic issues in Turkish Tax and Commercial laws. We conclude by presenting our evaluations based on previous chapters.
Tez N° 291505
Keywords: Avrupa Birliği hukuku; Avrupa Topluluğu hukuku; Birleşmeler; Change; Corporate Tax Law; Değişim; Division of company; European Community law; European Union law; Hisse senedi devri; Hisse senetleri; Kurumlar Vergisi Kanunu; Mergers; Stock transfer; Stocks; Tax harmonisation; Tax law; Vergi hukuku; Vergi uyumlaştırması; Şirket birleşmeleri; Şirket bölünmesi

Haksız Rekabet Hukukunun amacı ve koruduğu menfaatler - Güven, Şirin (Ankara Üniversitesi, 2011)
Haksız rekabet hukuku, ticarî hayatın gerektirdiği dürüstlüğü sağlamak ve rekabet etme serbestîsini bu yönden sınırlamak amacıyla ortaya çıkmıştır. İlk olarak, haksız rekabet eyleminden zarar gören rakiplerin menfaatleri(ekonomik kişilikleri) korunmuştur. Daha sonra, rakibin kişiliği ile doğrudan bağlantısı bulunmayan ve hattâ rakip olmayanların menfaatlerinin de(müşteri, tüketici) zarar görebildiği farklı haksız rekabet eylemlerinin ortaya çıkması neticesinde, dürüst rekabetin temin edilmesinde, sadece rakiplerin değil; toplumun(tüketici dahil) da menfaatinin bulunduğu kabul edilmiştir. Bu yaklaşım, haksız rekabet hukuku ile korunan menfaat çevresinin genişlemesine zemin oluşturmuştur.Kartel kanunlarının etkisiyle, haksız rekabet hukukunun da tıpkı rekabetin korunması hukuku gibi, rekabet serbestisini ve rekabeti kurum olarak koruduğu, bu sebeple, ekonomik düzenin gerçekleşmesine katkıda bulunduğu ve ekonomi politikaları ile ilgisinin olduğu ileri sürülmüş ve uygulama alanının genişletilmesi önerilmişse de, bu görüşler kalıcı olamamıştır.Haksız rekabet ile ilgili düzenlemelerin(1986 tarihli İsviçre Haksız Rekabete Karşı Kanunu, 2004 tarihli Alman Haksız Rekabet Kanunu ve Temmuz 2012'de yürürlüğe girecek olan 6102 sayılı Türk Ticaret Kanunu'nun haksız rekabetle ilgili hükümleri) amacı, tüm ilgililerin lehine dürüst ve bozulmamış rekabeti temin etmektir. "Bozulmamış rekabet" kavramından, piyasa ekonomisi kurumu olarak rekabetin bozulması anlaşılmamalıdır. Haksız rekabet hukuku, dürüstlük kurallarına aykırı davranışın, ilgili mal ya da hizmetin tedavülü ile bağlantısı olan çevrelerin pazar davranışını ve böylelikle pazara katılanlar arasındaki ilişkileri etkileyip etkilemediği ile ilgilenir. Davranışın ya da kullanılan yöntemin, salt aldatıcı nitelikte olmasından hareketle haksız rekabet teşkil ettiği söylenemez. Bu nedenle, haksız rekabetle ilgili düzenlemelerin amacının, pazara katılanlar bakımından dürüst ve bozulmamış rekabetin temini olarak yorumlanması gerektiğini düşünüyoruz.Öte yandan, belli bir pazar gücüne sahip teşebbüslerin, piyasa yapısı üzerinde, rekabeti bütünüyle ya da önemli ölçüde ortadan kaldırabilecek düzeydeki uygulamaları, haksız rekabet hukukunun uygulama alanı içerisinde değerlendirilemez. Pazar gücünün denetimi ve piyasa yapısının korunması, münhasıran rekabetin korunması hukukunun konularıdır. Dolayısıyla, haksız rekabet hukuku ve rekabetin korunması hukuku, farklı açılardan rekabet kurumunun korunmasına hizmet etmektedir. Unfair competition law aims at assuring fairness in commercial affairs and restricting the freedom of competition from this respect. Firstly, the interests(the economic personality) of competitors who were damaged by the unfair competition act were protected. Next, as a result of different unfair competition acts which are not directly related to the personality of the competitor and even by which the interests of non-competitors might be damaged(client, consumer), it has been accepted that not only the competitors, but, also the public(including consumer) has an interest on the assurance of fair competition. This approach has established a basis for the enlargement of the scope of protected interests.Under the influence of cartel laws, it has been claimed that, like competition law, unfair competition law protects the freedom of competition and the competition itself as an institution and therefore, unfair competition law contributes to the settlement of economic order and has a relation with economy policies and its scope of application should be extended. Nonetheless, this idea did not remain.The aim of the unfair competition rules(Swiss Code Against Unfair Competition, German Act Against Unfair Competition and the provisions on unfair competition of Turkish Commercial Code which shall enter into force by July 2012) is in favour of all concerned parties, to assure fair and undistorted competition. By the concept of "undistorted competition", it should not be understood the distortion of competition as an institution of market economy. Unfair competition law is concerned with whether the unfair conduct influences or not the market behaviour of the milieu, which is related to the exchange of the concerned good or service, and eventually the relations between market participants. The conduct or the applied method could not be qualified as unfair competition, solely by its deceptive nature. For this reason, the aim of the unfair competition rules should be interpreted as the assurance of fair and undistorted competition with respect to the market participants.However, the practices of enterprises with certain market power, which could annihilate, completely or to a considerable extent, the competition in the market could not be treated in scope of unfair competition law. The control of market power and the protection of market structure are exclusively the matters of competition law. Therefore, unfair competition law and competition law serve to the protection of competition as an institution from different aspects.
Keywords: Commercial law; Competencia; Competition; Competition law; Concorrência; Concurrence; Haksız rekabet; Law on Protection of Competition; Protection of competition; Rekabet; Rekabet hukuku; Rekabetin Korunması Hakkında Kanun; Rekabetin korunması; Ticaret hukuku; Unfair competition

Anonim ortaklıklarda anasözleşme değişikliği - Hamamcioğlu, Esra (Ankara Üniversitesi, 2011)
Tezimizin amacı, ortaklığın anayasası niteliğinde sayılan anasözleşmedeki değişikliklerin, hangi temel esaslar dahilinde yapılabileceğini ortaya koymak, değişikliğin şekli, kapsamı, usulü, sınırları ve sonuçları konusundaki mevzuat hükümlerini, doktrin görüşleri ve uygulama sorunları ile birlikte incelemektir. Çalışmamızda, ayrı birer tez konusu yapılmış veya yapılabilecek ayrıntılar içeren, esas sermaye artırımı, sermaye azaltımı gibi özel anasözleşme değişiklikleri tek tek incelenmek yerine, tüm anasözleşme değişikliklerinde geçerli olan temel esaslar incelenmeye çalışılmış, esas sermaye artırımı ve azaltımına özgü ve genel değişikliklerden farklı olan özel düzenlemeler kapsam dışı bırakılmıştır. 1 Temmuz 2012 tarihinde yürürlüğe girecek olan Yeni Türk Ticaret Kanununun konumuzla ilgili hükümleri de 6762 Sayılı Türk Ticaret Kanunu hükümleri ile karşılaştırmalı olarak tezimizde incelenmiştir. Üç ana bölümden oluşan tezimizin ilk bölümünde anasözleşme kavramı ve hukuki niteliği üzerinde durulmuş ve Alman, İsviçre, Türk öğretisindeki görüşler doğrultusunda anasözleşmenin hukuki niteliği konusunda bir sonuca varılmaya çalışılmıştır. Anasözleşme değişikliği konusunda çıkış noktamız olan anasözleşme içeriği de yine bu bölümde TTK ve YTTK hükümleri karşılaştırmalı olarak ele alınarak incelenmiştir. İkinci bölümde, öncelikle değişiklik kavramı üzerinde durulmuş ve hangi tür değişikliklerin anasözleşme değişikliği kapsamında değerlendirilmesi gerektiği tespit edilmeye çalışılmıştır. Değişiklik usul ve şartları konusu ise, değişiklik metninin hazırlanması, gerekiyorsa Sanayi ve Ticaret Bakanlığından izin alınması, değişikliğin genel kurulda karara bağlanması, imtiyazlı paysahiplerinin onayı ile ticaret siciline tescil ve ilan alt başlıkları çerçevesinde ele alınmıştır. Çalışmamızın son bölümü anasözleşme değişikliğinin sınırları ve denetimine ayrılmıştır. Bu kapsamda özellikle vazgeçilmez ve müktesep haklarla, imtiyazlı paylardan doğan hakların anasözleşme değişikliklerine çizmiş oldukları sınırlar kanun hükümleri kapsamında tespit edilmeye çalışılmıştır. Aynı bölümde, anasözleşme değişikliğinin hükümsüzlüğü ve denetimi başlığı altında, yokluk, butlan, iptal edilebilirlik ve askıda hükümsüzlük halleri üzerinde genel hatlarıyla durulmuştur. The purpose of this thesis is to put forward the main principles through which the amendments in the main contract, considered to be the constitution of partnership, could be made and to analyze provisions of the legislation together with doctrinal views and implementation issues regarding the form, scope, procedures (mode), limits and results of amendment.In this study, rather than focusing on specific main contract amendments with details that have been or could be the subject of a separate thesis such as the increase or reduction in authorized capital, the basic principles that apply to all main contract amendments were analyzed and the arrangements specific to increase and reduction in authorized capital and special arrangements, which are different from general amendments, were left out of the scope of the study.The relevant provisions of the new Turkish Commercial Code, which will come into force on 1 July 2012, are examined in this thesis in comparison with the provisions of the Turkish Commercial Law No. 6762. This thesis is consists of three main parts. In the first part, the emphasis is on the concept of main contract and its legal attributes; and in accordance with the legal opinions stemming from the German, Swiss and Turkish doctrines the first part tries to reach a conclusion regarding the legal attributes of the main contract.The content of the main contract, which is the point of departure regarding the main contract amendment, is also analyzed in this part by means of discussing the provisions of the TCL in comparison with that of the NTCC. The second part primarily focused on the concept of amendment and sought to determine what kind of amendments should be evaluated within the scope of main contract amendment.The issue of procedures and conditions for the amendment is elaborated under the subheadings: the preparation of the text of amendment, (if necessary) the authorization from the Ministry of Industry and Commerce, the decree for the amendment in the general assembly, registration at the trade registry and promulgation with the approval of the privileged shareholders.The last part of the thesis is on the limits and supervision of main contract amendment. Within this context, this part tried to determine the limits stipulated for the main contract amendments under the provisions of the law particularly by indispensable and vested rights as well as the rights incurred from concessional shares. Within the same part, under the heading/title of invalidity of the main contract amendment the cases of absence, voidness, revocation and pending invalidity have been analyzed in general terms.
Keywords: Anonim ortaklıklar; Change; Companies; Contracts; Değişim; Incorporated companies; Sözleşmeler; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Şirketler

Uluslararası Ticari Tahkim ve geçici hukuki koruma tedbirleri - Balkar, Süheyla (Galatasaray Üniversitesi, 2010)
Yargılama sürecinin yaratabileceği olumsuzluklardan hak arayan kişileri korumaya ve onlara hukuki güven ortamı sağlamaya yarayan geçici hukuki koruma tedbirleri tüm hukuk sistemleri açısından yargılamanın etkinliğinin teminatıdır. Devlet yargısında olduğu gibi, özellikle ticari uyuşmazlıklar açısından büyük önem taşıyan tahkim yargılamasında da bu tür tedbirlerin varlığına ihtiyaç gün geçtikçe artmaktadır. Çalışmamızda, uluslararası ticari tahkime konu olan uyuşmazlıklarda geçici koruma tedbirlerine hükmedebilme yetkisi, bu yetkinin sınırları ve bu tür tedbir kararlarının icrası meseleleri gerek mahkemeler gerekse hakemler açısından incelenmiştir. Interim relief or provisional measures may be as important as an award on the merits of any arbitration case. If the subject matter of the arbitration is not preserved, a long and costly arbitration procedure may just end up in learning at the time of execution of the award, that there is no substance right to enforce anymore. Consequently, the topic of provisional measures, in the understanding that they maintain the status quo of the arbitration, becomes of great relevance to all who may be involved in the arbitration world. Nonetheless, the topic of provisional measures, the powers to enforce them and even, the degree of court cooperation/intervention in such matters, varies from one country to another. Unfortunately, provisional measures in arbitration face several problems related to the lack of actual enforceability of the arbitrators? resolutions as well as to the good will of the parties to arbitrate and to grant the other parties enough securities that the subject matter of the arbitration will be executable.
279315
Keywords: Arbitration; Geçici hukuki korumalar; Hukuksal korunma; Incompatibility; Koruma tedbirleri; Legal protection; Protection measures; Tahkim; Temporary legal protection; Uyuşmazlık

Kırkambar Sözleşmesi - Cumalioğlu, Emre (Dokuz Eylül Üniversitesi, 2010)
Türk Hukuku'nda navlun (deniz yolu ile eşya taşıma) sözleşmeleri; yolculuk çarteri sözleşmesi ve kırkambar sözleşmesi olmak üzere iki ana gruba ayrılmıştır. Bunlardan çarter sözleşmeleri arızi deniz taşımacılığında, kırkambar sözleşmesi ise genellikle düzenli hat taşımacılığında kullanılır. Günümüzde deniz taşımacılığında yaşanan gelişmelerin sonucu olarak düzenli hat taşımacılığının ve kırkambar sözleşmesinin önemi artmaktadır.Bu tezde; Türk Hukuku'nda kırkambar sözleşmesi kavramı, sözleşmenin asli unsurları, özellikleri, benzer sözleşmelerle karşılaştırılması, sözleşmeye uygulanacak hükümlerin tespiti gibi konuların yanında sözleşmenin tarafları, ilgili kişileri, sözleşmenin ifasında yer alan yardımcı kişileri, tarafların hak ve yükümlülükleri ve sözleşmenin sona ermesine değinilmiş Türk Ticaret Kanunu ve diğer mevzuat hükümlerinden, ilgili uluslararası andlaşmalardan, ticari örf-adet kurallarından, yüksek mahkeme kararlarından, öğretiden, uygulamada kullanılan tip sözleşme ve konişmento örneklerinden yararlanılmıştır. In Turkish Law, contracts of affreightment are divided into two main cathegories which are; voyage charter and contract of common carriage of goods. While the former is being used in tramp shipping, the latter is being used in liner shipping. As a result of recent developements in carriage of goods by sea, the importance of liner shipping and contract of common carriage of goods has been rising.This thesis is based on; Turkish Commercial Code, other related national regulations and international agreements, customs, decisions of high courts, doctrine, mostly used standard contract and bill of lading forms. In this thesis; the chracteristics, parties, differences from other contracts, rights and obligations of the parties and termination of contract of common carriage of goods have been analysed.
Tez N° 263985
Keywords: Affreightments; Carriage of Goods; Commercial law; Contract of carriage; Deniz hukuku; Deniz ticareti; Deniz yolu taşımacılığı; Kırkambar Sözleşmesi; Law of the sea; Navlun sözleşmeleri; Sea trade; Sea transportation; Taşıma sözleşmesi; Ticaret hukuku; Turkish commercial law; Türk ticaret hukuku

Kurtarma yardımda sigortacının sorumluluğu - Ci̇vi̇r Engi̇n, Mehtap (Marmara Üniversitesi, 2009)
Denizciliğin kendine özgü ihtiyaç ve sorunlarından ortaya çıkmış bir kurum olan kurtarmayardım, TTK. m. 1222-1234'de düzenlenmiş olup köken itibariyle Alman hukukundanalınmıştır. Alman Hukukunun bu konudaki kaynağı ise Türkiye'nin de taraf bulunduğu 1910tarihli Brüksel Konvansiyonu'dur. 1910 tarihli konvansiyona 1967 yılında eklenen protokoleTürkiye taraf olmamıştır. 1989 Londra Konvansiyonuna taraf olma ise gereklidir. Zira 1989konvansiyonu gelişen ve değişen kurtarma teknikleri ve sorunlarını hukuki açıdan çözmekiçin uluslararası alanda düzenlenmiş en son konvansiyondur.Kurtarma yardım ücretinde sorunlardan biri, ücretin nasıl hesaplanacağıdır. Bu husus, 1910Brüksel Konvansiyonu hükümleri ve bu konvansiyona eklenen özel tazminat ve çevre zararınıönleme kriterlerini düzenleyen 1989 Londra Konvansiyonu hükümleri ile düzenlenmiştir.Kurtarma yardım ücreti hesaplanırken mahkeme bu kriterlerin ışığında hakkaniyete uygun birücret belirleyecektir.Kurtarma yardım ücretinin ödenmesi meselesinde önemli bir konu da bu ücretten denizsigortalarının teminat kapsamı doğrultusunda sigortacının sorumluluğu hususudur. Birkurtarma yardım hizmeti gerçekleştirildiğinde öncelikle uygun bir kurtarma yardım ücretibelirlenir. Bu kurtarma yardım ücreti olayın şartlarına göre müşterek avarya teşkil ettiğitakdirde kurtarma ücreti dispeçte alacaklı masasına kaydedilir ve müşterek avaryapaylaşımında yerini alır. Bu paylaşımda sigortacının tazminat sorumluluğu TTK hükümleri,genel şartlar ve İngiliz Hukuku özel şartları (Klozlar) ile York Anvers kuralları ışığındabelirlenir.Kurtarma yardım teşkil etmediği halde ise paylaşıma girmeden kurtarılan değerinsigortacısının kurtarma ücreti ve zararlarından sorumluluğu TTK hükümleri, genel şartlar veİngiliz Hukuku özel şartları (Klozlar) ile belirlenir. Emerged from own specific needs and problems of maritime Salvage, legislated in TTK.m.1222-1234, which has been originated from the German law. The source of German law inthis subject is the Convention dated 1910 in which Turkey is also a party. Turkey has not beenparty of the protocol in 1967 added to Convention dated 1910. Being a party to LondonConvention 1989 is necessary. Because Convention 1989 is the last convention to solvedeveloping and changing salvage techniques and problems from a legal perspective atinternational level.One of the problems of salvage payments is about how to calculate. This issue has beenregulated by provisions of Brussels 1910 Convention and London 1989 Convention whichregulates special compensation and prevention criteria of environmental damage. Whencalculating salvage payment, the court will determine a fair cost in the light of these criteria.An important subject matter of the payment of Salvage is the liability of insurer oriented withthe scope of maritime insurance assurance. When the salvage operation was done paymentwas determined primarily. When general average was established according to thecircumstances of this case this payment is recorded to creditor table at adjustment and takesplace in general average. This shared responsibility in the insurer's indemnity provisions aredetermined in light of the TTK provisions, general terms and specific terms of English Lawand York Antwerp Rules.In the case of without salvage, insurer liability of rescued value from salvage cost and lossesis determined by TTK, general terms and specific terms of English Law without sharing.
Keywords: Deniz araçları; Gemiler; Insurance; Kurtarma; Liability insurance; Naval vessels; Rescue; Responsibility; Ships; Sigorta; Sorumluluk; Sorumluluk sigortası; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

İslam Deniz Ticaret Hukukunda hukukî sorumluluk - Karaaslan, Muhammet Abdülmecit (Süleyman Demirel Üniversitesi, 2009)
İslam Deniz ticaret hukukunda hukuki sorumluluk? adlı çalısmamızdadeniz ticaret hukuku ile ilgili olarak, İslam hukuku eserlerinde çesitli bölümlerde dağınıkhalde bulunan ?Daman? konusu üzerinde durmaya çalıstık.Konuyu ele alırken giriste özellikle önce, deniz hukuku ile deniz ticaret hukukarasındaki ayrıma dikkat çekerek deniz hukuku ile ilgili konuları dısarıda tuttuk. Daha sonra?İslam deniz ticaret hukuku? kavramını irdeledik. Ardından hukuk-fıkıh arasındaki güncelayrıma göre ?slam hukuku eserlerindeki ibadetlerle ilgili konuları ele almamamız gerektiğinibelirttik. Daha da özele inerek tezimizde; konunun cezai sorumlulukla ilgisini dısarıdatutmak gerektiğinin gerekçelerini sıralamaya çalıstık ve kaynakları nasıl ele alacağımızı izahettikArastırmamızda, birinci bölümde genel olarak ?slam hukuku ve günümüzhukuklarında sorumluluk üzerinde durduk. Sorumluluk fikriyle ilgili ayet ve hadislerden vefıkıh eserlerindeki ilgili tanımları ve sınıflandırmalara dikkat çektik. İslam deniz ticarethukukunun kısa tarihçesini vererek, Rodos deniz Kuralları gibi Roma hukukundan alıntıolduğu iddiasına cevap vermeye çalıstıkİkinci bölümde sözlesmeden doğan hukuki sorumlulukla ilgili olarak, İslamhukukçularının daha ilk yüzyıllardan beri denizde yük/esya ve yolcu tasıma ile ilgili olarak,gemiyi tümden kiralama ve sözlesme yaparak bir bölümünü kiralama veya bizatihi yüktasımayı esas alan kiralama sözlesmelerini farklarıyla birlikte bildiklerini gördük. İslamhukukçuların özellikle sözlesmelerde; geminin adı, varma limanı, yolculuğun süresi, yüksahibinin adı, navlun ücreti ve onun ne zaman ne sekilde ödeneceği vb. hukuki ayrımlarınyük tasıma sözlesmelerinde sözlü veya yazılı olarak olarak ayrıntılı bir sekilde yer almasınısart kostuklarını belirttik.Bilhassa Maliki hukukçuların bu alanda çalısmalarının diğerlerine göre daha fazlaolduğunu gördük. Malikiliğin yaygın olduğu Endülüs İspanyasında ortaya çıkan Consolatedel Mare'da Maliki emir ve hukukçuların büyük etkisi olduğunu karsılastırmalı olarakgöstermeye çalıstık.Üçüncü bölümde haksız fiilden doğan sorumlulukta İslam hukuku eserlerinde?ta'addî ve ifrât? kavramının olduğunu, deniz kazaları, avarya gibi yükün ve gemininkorunması ile ilgili meydana gelen masrafların iki taraf arasında kusurlu olup olmamadurumuna göre bölüsülmesi gerektiğine dikkat çektik. Fırtına, rüzgâr gibi beklenmeyendurumların sebebiyet verdiği kazalarda kusur bulunmasa da sorumlu olunduğunu vemasrafların iki taraf arasında paylasıldığını gördük. Müstakil bir bölüm teskil edecek ölçüdepek yeterli örnekler olmamakla birlikte, son bölümde sebepsiz zenginlesmeden kaynaklananhukuki sorumlulukla ilgili bazı tespitlere yer verdik. We tried to study “Liability Law in the Islamic Maritime Law” in the our exploration. There is a concept called “Daman” that means liability in the islamic maritime law. “Daman” is the same as the compensation of the damage because of the damages given. There are several sections called “Kitabu’d-Daman” in the some Islamic law books. We come across plenty of examples concerned liability that is not only an independent section in the most of Islamic law books but also caused on the contract and unjust action mostly. Some of these examples is concerned about liability in the islamic maritime law. As today in the past as well in the islamic laws the incidents of the maritime law were explained with a comparison with the ones on the land. They paid attention to many principles as well. Fob instance when ships crash each other, they added “unexcpected state”. They also asked like the position of the riders and horse carts bumped into each other on the land at these times horses were under trouble had failure accidents. In addition to this, the sea and ship sourced with the actions they mentioned this in their contract effect. Again, islamic law lecturers, finally with several improvments that were clear in the nineenth and twentieth centuries supplied the ship wholly leased with a contract one section or based on the goods earried as leasing contracts showed law distinctions significantly. Moreover, storing, not suitable to the sea average, shipwreck, goods found under the sea, they paid attention to both sides responsibility when there was an accident. Especially during the reigns of Endulus Spain there was a widespread religious flow called “Malikite” and the Maliki law lecturers stood more than as usual. Muslim judges and others in Katolanya region on the coast of Pacific Ocean of Spain issued rules called “Consolate de’l Mare” today’s maritime laws Like Mediterranean Geography several mixed a widespread culture in such a converted sitiuation maritime law affected under Rhodes rules was rumoured that e neutral investigation put into practice Islamic law people freely their own laws. When Muslims ruled the Mediteranean Area the law of Rome lost control over the region. To some extent there was an influential sitiuation; in other words that was naturally a result.
Keywords: Avarage; Avarya; Beklenmeyen Durum; Consolate Del Mare; Consolate De’l Mare; Contracts; Daman; Daman; Sözlesme; DenizKazaları; Haksız Fiil; Islamic Maritime Law; Kusur-Zarar; Leasing Of Ship; Liability Law; Malikite Law; Sea Accident; Sorumluluk Hukuku; Unexcpected State; Unjust Action; İslam Deniz Ticaret Hukuku

Anonim şirketlerin ehliyeti (özellikle ultra vires doktrini ile sınırlandırılması) - Serder, Selen (Ankara Üniversitesi, 2009)
Türk Ticaret Kanunu'nda, ultra vires doktrininin etkisiyle, ticaret şirketlerinin ehliyetlerinin işletme konusuyla sınırlandırılması ölçütüne yer verilmiştir. Buna göre TTK.'nun 137. maddesinde ticaret şirketlerinin ehliyetinin işletme konusu çevresiyle sınırlı olduğu kabul edilmiştir. Anonim şirketlerin ehliyeti de TTK. m. 137 kapsamında işletme konusu çevresiyle sınırlandırılmıştır.İşletme konusu, ana sözleşmede yer alan ve şirketin faaliyet göstereceği iş alanlarını somut olarak ortaya koyan bir kavramdır. Sınırlı ehliyet ilkesinin sakıncalarını gidermek amacıyla işletme konusu kavramını geniş yorumlamak ve işletme konusu kapsamındaki faaliyetleri kolaylaştırmak adına yapılan işlem ve faaliyetleri işletme konusundan saymak gerekmektedir.Anonim şirketlerin ehliyetlerinin kapsam ve sınırları, anonim şirket temsilcilerinin yetkilerinin kapsam ve sınırlarını belirlemesi bakımından da önem taşımaktadır. Anonim şirketin ehliyetinin ve buna bağlı olarak temsilcilerinin yetkilerinin kapsam ve sınırlarının belirlenmesi, anonim şirket ortaklarının, alacaklılarının ve kamu menfaatinin korunması amacına da hizmet etmektedir.Ticaret şirketlerinin ve buna bağlı olarak anonim şirketlerin ehliyet dışı işlemleri, öğretide yer alan baskın görüşe göre yok hükmündedir. Ehliyet dışı yapılan işlemin yok hükmünde kabul edilmesi, bu işlemin hiç doğmadığı ve sonradan onay vermekle bu işleme geçerlilik kazandırılamayacağı anlamındadır.Ticaret şirketlerinin ve dolayısıyla anonim şirketlerin ehliyetinin işletme konusu çevresi ile sınırlandırılması ultra vires doktrini olarak ifade edilmektedir. Ultra vires doktrini İngiliz hukuku kaynaklı olup, şirketler hukuku bakımından şirketlerin hukuki ehliyetinin ana sözleşmelerinde yazılı olan konularıyla sınırlandırılması temeline dayanmaktadır. Günümüzde ultra vires doktrini terk edilmiştir. Nitekim Türk Ticaret Kanunu Tasarısı'nın ticaret şirketlerinin ehliyetini düzenleyen 125. maddesinde ultra vires doktrininin yansıması olan işletme konusu çevresiyle sınırlı ehliyet ilkesine yer verilmemiş olup ultra vires doktrininin yarattığı sakıncaları önlemek adına olumlu bir adım atılmıştır. The rule of limited capacity of companies in the frame of the objects clause, was given a place in the Turkish Commercial Code with effect of ultra vires doctrine. According to this, Article 137 of the Turkish Commercial Code stipulates that capacity of companies are limited in frame of the objects clause of the companies. Capacity of incorporated companies are also limited in frame of the objects clause according to Article 137 of the Turkish Commercial Code.Objects clause is a concept which takes place in the memorandum and which shows scope of the company. In order to remove inconveniences of principle of limited capacity, the transactions and activities made for widely interpreting the concept of objects clause and facilitating the activities in the cover of objects clause, are assumed in the frame of objects clause.Contents and limits of capacity of incorporated companies are significant with regard to defining contents and limits of power of directors of incorporated companies. Defining contents and limits of capacity of incorporated companies and whereupon defining content and limits of power of directors also serve the purpose of protecting share holders and creditors of incorporated companies and public interest Companies? transactions and whereupon incorporated companies? transactions, which are out of capacity are nul and void according to the dominant idea in the doctrine. Assuming the transactions that exceed the capacity of company as nul and void means that this transactions were never made and that further approving such transaction would not make it valid. Limited capacity of companies and whereupon of incorporated companies in frame of objects clause is called ultra vires doctrine. Ultra vires doctrine is of English Law origin and based on the limitation of capacity of the companies by the objects clause of the memorandum, with regard to the law of companies. Today, ultra vires doctrine is relinquished. As a matter of fact, Article 125 of the Scheme of Turkish Commercial Code regulating capacity of the companies did not give place the limited capacity principle which is a reflection of the ultra vires doctrine and took an important step in order to avoid the drawbacks of ultra vires doctrine.
Keywords: Anonim ortaklıklar; Capacity; Commercial law; Ehliyet; Incorporated companies; Ticaret hukuku; Turkish Commercial Code; Türk Ticaret Kanunu; Ultra-vires

Menkul kıymetleştirme ve varlığa dayalı menkul kıymetler - Turan, Gökçen (Ankara Üniversitesi, 2009)
Menkul kıymetleştirme düzenli nakit akışı sağlayan alacakların likit hale getirilmesi esasına dayanan bir finansman yöntemidir. Bu yöntemde, finansman ihtiyacı içinde olan şirket, düzenli nakit akışı sağlayan alacaklarını özel amaçlı kuruluşa devreder. Alacakları devralan özel amaçlı kuruluş, bu alacakları karşılık göstererek menkul kıymet ihraç eder. Menkul kıymeti satın alan yatırımcılara, vadesi geldiğinde anapara ve faiz ödemeleri, havuzdaki alacaklardan sağlanan gelirlerle yapılır. Böylece, alacakların ilk sahibi olan kaynak şirket, alacaklarının vadesini beklemeden nakit ihtiyacını gidermiş olurken, ihraç edilen menkul kıymeti satın alan yatırımcılar da, güvenilirliği yüksek ve şirketin risklerinden arındırılmış bir alacaklar topluluğunun güvencesi altında sağlam bir yatırım yapmış olurlar.5582 sayılı Kanunun temelinde de, menkul kıymetleştirme yöntemi kullanılarak, konut finansmanı sisteminin ikincil piyasa ayağını oluşturma düşüncesi vardır. Bu kapsamda, ipotekli konut kredilerinin menkul kıymetleştirilmesi sonucunda ihraç edilecek ipotek teminatlı menkul kıymetler ve ipoteğe dayalı menkul kıymetler düzenlenmiştir. İpotek teminatlı menkul kıymetler bir bilanço içi menkul kıymetleştirme özelliği gösterirken, ipoteğe dayalı menkul kıymetler bilanço dışı menkul kıymetleştirme niteliğine sahiptir. Her iki menkul kıymet türünde de, menkul kıymet sahiplerinin korunmasına azami şekilde özen gösterilmiş ve her durumda menkul kıymet sahiplerinin alacaklarını almalarına öncelik verilmiştir. İflasın teminat varlıklara menfi bir etkisinin olması her iki menkul kıymet türünde kanun hükmüyle engellenmiş, gerek teminat havuzu gerek fon portföyü dokunulmaz bir statüye kavuşturulmuştur.Aynı Kanunda, varlık teminatlı menkul kıymetler ve varlığa dayalı menkul kıymetler yoluyla, ipotekli konut kredileri dışındaki alacak çeşitlerinin de menkul kıymetleştirilmesi kabul edilmiştir.Sonuç olarak, menkul kıymetleştirme günümüzün vazgeçilmez finansman metotlarından biridir. Ancak menkul kıymetleştirmeden beklenen faydaların sağlanabilmesi, ana prensiplerine riayet edilerek uygulanmasına bağlıdır. Securitization is a method based on liquidation of receivables enabling regular cash flow. In this method, the company in need of financing transfers such receivables to special purpose vehicle. The special purpose vehicle which take over the receivables issues securities by assuring them. On due the capital and interest payments to the investors purchasing securities are made by the income acquired from the receivables in pool. Therefore, while the company, the originator of receivables, solve the problem of liquidity without waiting for the receivables?s due, the investors make a safe invesment under the assurance of a community of receivables that is highly secure and free of credit risk.On the basis of the Law 5582, there?s also the idea of forming the secondary part of housing finance system by using securitization method. Within this framework, mortgage covered bonds and mortgage backed securities have been regulated, both of which are issued as a result of securitization of residential mortgage loans. Mortgage covered bonds display a characteristic of on-balance sheet, while mortgage backed securities have off-balance sheet property.In both types of securities, utmost great pains to protect securities owners is taken and that securities owners are satisfied under any circumstances is of high priority. Bankruptcy?s negative effect on cover assets is impeded with a law article, thus both cover pool and fund portfolio acquire an immune statute.In the same Law, other types of receivables except residential mortgage loans might be securitised is acknowledged through asset covered bonds and asset backed securities.Consequently, today, securitization is one of indispensible way of financing. However, that expected benefits from securitization can be obtained is possible provided that it is performed with respect to main principles.
Keywords: Asset backed bonds; Asset-backed securitization; Commercial law; Financing; Financing methods; Finansman; Finansman yöntemleri; Menkul kıymetleştirme; Ticaret hukuku; Turkish Law; Türk Hukuku; Varlığa dayalı menkul kıymetler

Milletlerarası Özel Hukukta kambiyo senetleri - Aygün, Mesut (Anadolu Üniversitesi, 2008)
Milletlerarası Özel Hukukta Kambiyo Senetleri başlığını taşıyan çalışmamız, üç bölümden oluşmaktadır. Bu konuyu seçmemizin başlıca nedeni, kambiyo senetleri alanında yapılan (veya yapılacak olan) yeknesaklaştırma çalışmalarının milletlerarası özel hukuk alanına etkilerini ortaya çıkarmaktır.Tezimizin Birinci Bölümünde, kambiyo senetleri (ticarî senetler) başlığı altında, öncelikle kanunlar ihtilâfı hukuku açısından önem arz eden kıymetli evrak ve kambiyo senetlerinin bazı konuları üzerinde genel hatlarıyla durulmuştur. Daha sonra, yabancılık unsuru, vasıflandırma, atıf, bağlama noktaları gibi kambiyo senetlerine ilişkin olarak ortaya çıkan kanunlar ihtilâfı hukukunun genel problemleri incelenmiştir. Son olarak, kambiyo senetlerine uygulanacak hukuka ilişkin olarak Cenevre Konvansiyonları sistemi ile Anglo-sakson hukuk sistemi genel olarak incelenmiştir.Tezimizin İkinci Bölümünde, milletlerarası özel hukuk düzenlemelerinde kambiyo senetleri başlığı altında, öncelikle kambiyo senetlerine ilişkin uyuşmazlıklarda milletlerarası yetki üzerinde durulmuştur. Bu konuya ilişkin olarak, Brüksel Konvansiyonu, Brüksel I Tüzüğü ve La Haye Konvansiyon taslağı gibi milletlerarası sözleşmeler incelenmiştir. Sonra, uygulanacak hukukun tespitinde faydalanılan taahhütlerin birliği ve taahhütlerin bağımsızlığı esasları ele alınmıştır. Anglo-sakson hukuk sisteminde kambiyo senetlerine ilişkin düzenlemeler incelendikten sonra, diğer sistem içinde kalan Cenevre konvansiyonları üzerinde durulmuştur.Tezimizin Üçüncü Bölümünde, Türk milletlerarası özel hukukunda kambiyo senetleri başlığı altında, yine öncelikle milletlerarası yetki konusu ele alınmıştır. Uygulanacak hukuk kısmında vasıflandırma üzerinde durulduktan sonra, önce poliçe ve bonolara uygulanacak hukuk, daha sonra çeke uygulanacak hukuk inceleme konusu yapılmıştır. Uygulanacak hukuka ilişkin incelemelerimizde önce ehliyet, şekil gibi kambiyo senedinin geçerlik şartlarına ilişkin konuları, sonra sırasıyla kambiyo taahhüdünün hükümlerine ve kambiyo taahhüdünün icrasına uygulanacak hukuk ile ilgili konular ele alınmıştır. Our study, under the title of Commercial Papers in Private International Law comprises three chapters. The main reason in choosing this subject is that reveal effects of unification works in the commercial papers on the field of private international law.In the first chapter of the thesis, under the title of commercial papers, first some subjects of negotiable instruments law and commercial papers which critically important for conflict of laws have been mentioned. Next, general matters of conflict of laws such as foreign element, classification, renvoi and connecting factors have been examined respectively. Lastly the system of Geneva Conventions and Anglo-sakson law system have been examined generally relating to applicable law.In the second chapter of the thesis, under the title of commercial papers in arrangements of private international law, first international jurisdiction dealing with the conflicts of commercial papers have been dwelled upon. International conventions such as Brussel Convention, Council Regulation (EC) No. 44/2001 and Draft of Hague Convention on Jurisdiction and Foreign Judgments in Civil and Commercial Matters regarding this subject have been examined. Next, the principle of combination of stipulations and the principle of independency of stipulations are used in determination of law applicable have been handled. After the arrangements of Anglo-sakson law were examined, the other system, Geneva Conventions? rules have been dwelled upon.In the third chapter of the thesis, under the title of commercial papers in Turkish private international law, first international jurisdiction has been handled. First the classification, then applicable law to bills of exchange and promissory note and applicable law to cheque has been examined. In this part, terms of validity of commercial papers such as capacity, form, applicable law to obligations arising out of a commercial paper and applicable law to subjects regarding discharge of a commercial paper have been handled respectively.
Keywords: Bill of exchange; Commercial law; Devletler özel hukuku; International adjective law; International private law; Kambiyo senetleri; Kanunlar ihtilafı; Kıymetli evrak; Laws conflict; Milletlerarası usul hukuku; Private international law; Ticaret hukuku; Uluslararası özel hukuk; Valuable paper

İcra ve İflas Hukuku açısından malvarlığı veya ticari işletmenin devri - Durman, Okay (İstanbul Üniversitesi, 2008)
Borçluların alacaklılarına zarar vermek kastıyla malvarlığını veya işletmesini devretmesi ile mücadeleye yönelik icra hukuku hükümlerinin incelendiği bu çalışmada üç ana bölüm yer almaktadır. İlk bölümde konunun kapsamını oluşturan malvarlığı, özel malvarlığı, işletme ve ticari işletme kavramları detaylı olarak tarif edilmektedir.İkinci bölümde maddi hukuk açısından, üçüncü bölümde değinilen İcra Hukuku hükümlerinin uygulanmasında önem taşıyan malvarlığı veya işletmenin devrinde devreden ve devralanın sorumluluğu açısından düzenleme getiren BK m. 179 hükmü, kaynak İsviçre ve Alman Hukukları'ndaki hükümler ile birlikte değerlendirilmektedir.Malvarlığı veya işletmesini alacaklılarına zarar vermek kastıyla devreden borçlularla mücadele olanaklarına sadece İcra Hukuku hükümlerinde yer verilmiş olması nedeniyle çalışmamızın asıl konusunu oluşturan üçüncü bölümde ise, İİK m. 280/III ve m. 44 uygulamasının olumlu ve olumsuz yanları, yargı kararları eşliğinde belirtilmektedir. There are three chapters in this work which deals with the regulations related to combating with the debtors who transfer their assets or businesses in order to harm their creditors. In the first chapter the asset, separate property, enterprise and businesses that are forming the scope of work are defined in details.In the second chapter, the Turkish Obligation Code Art. 179 that regulates the obligation of the debtors transfering their assets or businesses in order to harm their lenders is considered in light of the source law of Swiss and German regulations.For the reason that the only regulations for combating with the debtors who transfer their assets and businesses in order to harm their creditors are arranged within the Turkish Execution and Insolvency Code, in the third and the main chapter, the related articles of 280/III and 44 are considered in light of the Supreme Court decisions with their positive and negative effects.
261768
Keywords: Bankruptcy law; Businesses; Commercial institutes; Contract of transfering; Devir sözleşmesi; Enforcement law; Malvarlığı; Property; Ticari işletmeler; Workplace transferring; İcra hukuku; İflas hukuku; İşletmeler; İşyeri devri

Bağımsız denetim sözleşmesi - Köksal, Aytaç (Ankara Üniversitesi, 2008)
Bağımsız denetim sözleşmesi, bağımsız denetçiler ile denetime tabi müşteriler arasında yapılan bir sözleşmedir. Bağımsız denetim sözleşmesi, düzenlemelerde belirtilen unsurları içermelidir. Bağımsız denetçi ile denetim müşterisi, sözleşmenin unsurları üzerinde anlaşmalıdırlar. Bir bağımsız denetim sözleşmesi yapıldığında, bağımsız denetçiler ile denetim müşterileri karşılıklı borç altına girerler.Bağımsız denetçi, denetim müşterisinin finansal tablolarını denetleme ve finansal tabloların, finansal raporlama standartları ile düzenlemelere uygunluğu konusunda bir görüş açıklama borcu altındadır. Bağımsız denetçi, denetimi yürütürken, uluslararası denetim standartlarını, etik standartları ve düzenlemeleri dikkate almalıdır. Bağımsız denetçiler, bağımsız denetim faaliyetinde her zaman mesleki özeni göstermek zorundadırlar. Eğer, denetim raporu gerçeği yansıtmaz ise, bundan zarar gören denetim müşterisi ile üçüncü kişilerin uğradıkları zararlardan, bağımsız denetçiler sorumlu olurlar. Bağımsız denetçi, ayrıca, bağımsız denetim raporunu zamanında denetim müşterisine teslim etmelidir. Bunun yanında, bağımsız denetçi, düzenlemelerde belirtilen süre içerisinde çalışma kâğıtlarını saklamalılar ve bu süre sona ermeden, çalışma kâğıtlarını yok etmemeli veya atmamalıdırlar. Bağımsız denetçi, denetim müşterisine ait sırları açıklamamalı, kendisinin veya bir diğer kişinin yararına kullanmamalıdır.Denetim müşterisi, bağımsız denetçilere, denetim ücretini ödemeli ve ayrıca, denetim ile ilgili kayıt, belge ve diğer bilgileri bağımsız denetçiye vermelidir. The independent audit agreement is made between independent auditors and the clients who are dependent on audit. The agreement should include terms which are showed by regulations. The auditors and the audit clients must agree on the terms of the agreements. When to be acted the agreement, the auditors and the client? have mutually liablity.The auditors are liable to audit the clients? financial statements and to express an opinion on if the financial statements are suitable the financial reporting standards and the regulations. While performing audit, the auditors should observe in international auditing standards, the ethical standards and regulations. The auditors should always have a duty to provide professional care when performing audit. If the auditors prepare a misleading audit reports, they will liable to the clients and third parties because of their loss was incurred. Also, the auditors should deliver the audit report to the client on time which they agree on. Besides, the auditors should save the audit documentation some time which is showed by regalitations and shouldn?t the delete and discard audit documentation before the end of that time. The auditors also shouldn?t disclose confidential information of the clients? or not use this information for the personal or the other persons? advantage.The audit clients? pay the audit fee and also give the records, documentation and other information requested in connection to with the audit to the independent auditors. Finally, when the auditors deliver the audit report to, the audit clients should accept it.
Keywords: Audit reports; Auditing standards; Banka hukuku; Banking law; Bağımsız denetim; Bağımsız denetim kuruluşları; Bağımsız dış denetim; Capital Market Law; Commercial Code; Commercial law; Denetim raporları; Denetim standartları; Independent audit; Independent auditing companies; Independent external auditing; Responsibility; Sermaye Piyasası Kanunu; Sorumluluk; Ticaret Kanunu; Ticaret hukuku

Uluslararası ticari sözleşmelere uygulanacak hukuk olarak UNIDROIT (özel hukukun yeknesaklaştırılması için uluslararası enstitü) prensipleri - Süral, Bahar Ceyda (Dokuz Eylül Üniversitesi, 2008)
Global ticaret hayatı her geçen gün genişlemekte ve global ekonomik pazarlar tarafından şekillendirilen global bir hukuk kültürü gelişmektedir. Bu yeni hukuk kültürünün bir parçası da, uluslararası ticaret hukuku alanında maddi hukukun yeknesaklaştırılmasıdır. Değişik uluslararası (a-nasyonal) hukuk kaynakları milletlerarası alanda faaliyet gösteren tacirlerin kullanımına sunulmuştur.Bu uluslararası hukuk kaynaklarına en güzel örneklerden biri Unidroit Prensipleri'dir. Uluslararası ticaret söz konusu olduğunda, farklı hukuk sistemlerinin uyuşmazlık halinde uygulanması belirsizliğe ve süprizlere yol açabilmektedir. Unidroit Prensipleri gibi yeknesak ve önceden belirlenen bir düzenlemenin uyuşmazlığın çözümünde uygulanması bu olumsuzluğu ortadan kaldırabilecek; tarafsız bir hukukun uygulanmasına imkan tanıyacaktır.Çalışma, üç bölümden oluşmaktadır. İlk bölümde, ?uluslararası ticari sözleşme? kavramı ve bunlara uygulanacak hukukun yeknesaklaştırılması çabaları bazı örnekler ile incelenmiştir.İkinci bölümde Unidroit Prensipleri'nin içeriği genel olarak açıklanmıştır. Unidroit Prensipleri'ne ilişkin açıklamalarımız, Prensipler'in düzenlediği hususlarla sınırlı kalmıştır.Üçüncü bölümde, tarafların Unidroit Prensipleri'ni uygulanacak hukuk olarak belirlemiş olmaları hali, Unidroit Prensipleri'nde yer alan tüm ya da bazı hükümleri sözleşmelerine almış olmaları hali, uygulanacak hukuk olarak lex mercatoria ya da hukukun genel prensiplerinin seçilmiş olması hali ve tarafların herhangi bir hukuk seçimi yapmamış olmaları halinde Unidroit Prensipleri'nin sözleşmeye uygulanma ihtimali ele alınmıştır. Bu meseleler, mahkeme ve tahkim yargılamaları bakımından ayrı ayrı incelenmiştir. Prensipler, uluslararası ticaret alanında ve özellikle uluslararası tahkim uygulamasında kullanılmakta ve yabancı doktrinde kullanılmasının yaygınlaşmasını savunanların sayısı artmaktadır. Bu gelişmelerin gerisinde kalmamak ve Türk ticaret ve hukuk alanında da bunları tanıtmak bu çalışmanın ana amacını oluşturmaktadır. Bu çalışmada, Prensipler'in Türk hukuku bakımından sözleşmeye uygulanacak hukuk olarak uygulanabilirliği ele alınmış ve Prensipler'in uluslararası ticari uyuşmazlıkların çözümünde yaygınlaşması desteklenmiştir. The global commercial activity expands and a new global law culture shaped by the global economic markets develops. A part of this new law culture is the unification of substantial law in the field of international commercial law. Various international (a-national) sources of law are presented to the usage of the international merchants.One of the best examples of these unified international sources of law is the Unidroit Principles. The application of different laws to the international commercial disputes causes uncertainty and suprises for the parties. The application of a unified and pre-determined rules such as the Unidroit Principles prevents such disadvantage and a neutral law may be applied to the resolution of the disputes.This study comprises of three chapters. The concept of ?international commercial contract? has been explained and some examples to the efforts of unification of substantial law have been outlined in the first chapter.The content of the Unidroit Principles has been explained in general in the second chapter. These general explanations are limited with the issues provided by the Principles.In the third chapter, the application of the Unidroit Principles to the disputes arising out of international commercial contracts in the cases of choice of Unidroit Principles as the applicable law to their contract by the parties, the inclusion of Unidroit Principles to the contracts by way of incorporation, choice of lex mercatoria or the general principles of law as the applicable law to their contract by the parties and the case when there is no choice of law by the parties have been explained. These explanations are separate for international arbitration and domestic courts.The Principles are being used in international commercial law, especially in the field of international arbitration, and the opponents of expansion of its usage are increasing in the international doctrine. The main objective of this study is not to fall beyond these developments and to introduce the Unidroit Principles to Turkish merchants and lawyers. The application of the Principles as the law applicable to contracts in Turkish law has been reviewed in this study and widening of their application in the resolution of international commercial disputes has been supported.
Keywords: International Trade; International disputes; International law; Uluslararası hukuk; Uluslararası ticaret; Uluslararası uyuşmazlıklar

Kambiyo senetlerinde sebepsiz zenginleşme - Yasan, Mustafa (Marmara Üniversitesi, 2007)
Tezimizin konusu ?Kambiyo Senetlerinde Sebepsiz Zenginleşme?dir. Kambiyo senetlerinde sebepsiz zenginleşme müessesesi TTK m.644'te düzenlenmiştir. TTK m.644'e göre keşideci ve kabul etmiş muhatap, hamilin poliçedeki hakkını zamanaşımı ya da poliçedeki hakkı koruyucu işlemleri kaybetmesi sebebiyle poliçedeki borcu ödemek yükümlülüklerinden kurtulmuş olsa dahi sebepsiz zenginleşme hükümleri ile takip edilebilirler. TTK m.644'te düzenlenmiş olan kambiyo senetlerinde sebepsiz zenginleşme müessesesi kambiyo senedindeki asıl alacak ile genel hükümlerde yer alan sebepsiz zenginleşme talebinden bağımsız kendine özgü bir talebi içermektedir. TTK m.644 TTK m.730 gereği çekler hakkında da uygulanır. TTK m.690'da açık bir atıf olmamasına rağmen bonolara da uygulanabilmelidir. TTK m.644'ün uygulanabilmesi için hamilin zarara uğraması şarttır. Hamilin zararı iki sebebe dayanmalıdır. Bunlar, zamanaşımı ve hamilin poliçedeki hakkı koruyucu işlemlerin yerine getirilmemesidir. Zamanaşımı süreleri kambiyo senetlerinin türlerine ve kambiyo senetlerindeki alacaklı ve borçluların kimliklerine göre değişik süreler olarak TTK'da tespit edilmiştir. Hamilin poliçeyi muhataba kabul için arz etmemesi, ödenmek üzere ibraz etmemesi ya da gerektiğinde protesto keşidesinin gerçekleştirilmemesi poliçedeki hakkın kaybına yol açan hakkı koruyucu işlemler olarak kabul edilmektedir. Hamilin poliçedeki hakkını kaybetmesi neticesinde borçtan kurtulan borçlular zenginleşmiş olarak kabul edilirler. Kambiyo senetlerinde sebepsiz zenginleşme talebine dayanan dava mutlak ticari davadır. Görevli ve yetkili mahkeme Ticaret Hukuku, Borçlar Hukuku Usul Hukuku prensipleri birlikte değerlendirilerek tespit edilmelidir. Ve bu davaya uygulanacak zamanaşımı süresi hakkında doktrinde ve mahkeme kararlarındaki ihtilaf bu konudaki boşluğun kanun koyucu tarafından doldurularak giderilmelidir. [...] Tezimizin konusu ?Kambiyo Senetlerinde Sebepsiz Zenginleşme?dir. Kambiyo senetlerinde sebepsiz zenginleşme müessesesi TTK m.644'te düzenlenmiştir. TTK m.644'e göre keşideci ve kabul etmiş muhatap, hamilin poliçedeki hakkını zamanaşımı ya da poliçedeki hakkı koruyucu işlemleri kaybetmesi sebebiyle poliçedeki borcu ödemek yükümlülüklerinden kurtulmuş olsa dahi sebepsiz zenginleşme hükümleri ile takip edilebilirler. TTK m.644'te düzenlenmiş olan kambiyo senetlerinde sebepsiz zenginleşme müessesesi kambiyo senedindeki asıl alacak ile genel hükümlerde yer alan sebepsiz zenginleşme talebinden bağımsız kendine özgü bir talebi içermektedir. TTK m.644 TTK m.730 gereği çekler hakkında da uygulanır. TTK m.690'da açık bir atıf olmamasına rağmen bonolara da uygulanabilmelidir. TTK m.644'ün uygulanabilmesi için hamilin zarara uğraması şarttır. Hamilin zararı iki sebebe dayanmalıdır. Bunlar, zamanaşımı ve hamilin poliçedeki hakkı koruyucu işlemlerin yerine getirilmemesidir. Zamanaşımı süreleri kambiyo senetlerinin türlerine ve kambiyo senetlerindeki alacaklı ve borçluların kimliklerine göre değişik süreler olarak TTK'da tespit edilmiştir. Hamilin poliçeyi muhataba kabul için arz etmemesi, ödenmek üzere ibraz etmemesi ya da gerektiğinde protesto keşidesinin gerçekleştirilmemesi poliçedeki hakkın kaybına yol açan hakkı koruyucu işlemler olarak kabul edilmektedir. Hamilin poliçedeki hakkını kaybetmesi neticesinde borçtan kurtulan borçlular zenginleşmiş olarak kabul edilirler. Kambiyo senetlerinde sebepsiz zenginleşme talebine dayanan dava mutlak ticari davadır. Görevli ve yetkili mahkeme Ticaret Hukuku, Borçlar Hukuku Usul Hukuku prensipleri birlikte değerlendirilerek tespit edilmelidir. Ve bu davaya uygulanacak zamanaşımı süresi hakkında doktrinde ve mahkeme kararlarındaki ihtilaf bu konudaki boşluğun kanun koyucu tarafından doldurularak giderilmelidir. The title of this thesies is "Unjustified Enrichment in Commercial Papers". The concept of Unjustified Enrichment in Commercial Papers was regulated in TTK (Code of Turkish Commerce) article 644. According to TTK article 644, drawer and drawee who accepted the bill of exchange, can be fallowed by unjustified enrichment regulations even the holder looses the rights in commercial papers because of prescription and negligence for saving the rights in commercial papers. The concept of unjustified enrichment which was regulated in TTK article 644 consists of independent, exceptional, and sui generis demand against the general regulations in Code of Obligations and basic relations in the commercial papers. TTK article 644 can be applied for the cheques because of the special rule in TTK article 730. TTK article 644 should be able to be applied for the promissory notes eventhough there is not any special rule in TTK article 690. For TTK article 644?s ability to apply holder should have a damage. And this damage must have one of two limited reasons. These are prescription and the negligence for saving the rights in commercial papers. Prescription timings were determinated according to the changing of the commercial papers? kinds and the the holders? and debtors? identities in the Turkish Commercial Code. If holder does not supply the bills of exchange to the drawee for acceptance or if holder does not supply the commercial paper for payment or if required, protesting is not cared by the holder, the debt gets lost. The result of the holder?s loss of the rights in commercial papers is the enrichment of the debtors. The case which is related to unjustified enrichment is the perfect commercial case. Authorized and charged court should be determinated by focusing the principles in Commercial Law, Obligation Law and Procedure Law. And the conflict for the prescription timings in scientific and courting decisions should be solved by the law maker.

Milletlerarası 'ticari' tahkimde nihai karardan önce mahkemelerin yardım ve denetimi - Yeşi̇lova, Bi̇lgehan (Dokuz Eylül Üniversitesi, 2007)
Tahkim anlasması ile taraflar, aralarındaki uyusmazlığın tahkim yoluyla çözüleceği konusunda anlasmıslardır. Böyle bir seçim, aynı zamanda yine taraflarar asındaki hukuki uyusmazlıklar yönünden devlet mahkemelerinin artık herhangi bir yargı yetkisine sahip olmadığı anlamına da gelmektedir. ?rade serbestîsinin yaygın kabulü, mahkemelerin tahkime müdahalesini, her geçen zaman daha da azaltmıstır. Bugün artık hâkim eğilim, devlet mahkemelerinin müdahalesinin ya tahkime yardım edilmesi ya da kamu düzeninin korunması amacıyla sınırlandırılmasıdır. Kural olarak, tahkim anlasmasının geçerliliğinin tespiti ile birlikte mahkemeler, tarafları, genis anlamda tahkime yönlendirecekler; uyusmazlığın esasıyla ilgili ol arakherhangi bir yargılama yapmayacaklardır. Ancak bazen, tahkimle ilgili konularda mahkemelerin yardımı ve desteği hatta kimi hâllerde denetimi, kaçınılmazdır. Hakem heyetinin seçimi, delillerin toplanması, hep bu kapsamdadır. Hakemlerce verilen nihai kararın cebren icrası gerektiğinde, mahkemelerin hem yardım hem de denetim islevi, gündeme gelmektedir. Hakemin reddinde olduğu gibi yargısal temel hakların korunması gerektiğinde, yine mahkemelerin rolü kaçınılmaz olmaktadır. Geçen zaman içinde mahkemelerin tahkime karsı olan yoğun süpheleri; tahkim anlasmaları ile hakem kararlarını sıkça geçersiz sayarak tahkime olumsuz anlamda müdahale etmek seklindeki alıskanlıkları, artık neredeyse tümüyle değismis ve ortadan kalkmıstır. Denetime yönelik mahkeme müdahalesinin geçmiste çoğu zaman taraf iradelerinin hiç sayılması anlamına geldiği, bilinmektedir. Oysa bugün, özellikle de UNCITRAL Model Kanunu'nun 5. maddesiyle yaygınlık kazanan anlayıs, taraflara ve hakem heyetlerine, basta yargı yetkisi olmak üzere pek çok alanda, genis yetkiler tanımak; denetime yönelik mahkeme müdahalesinin en son anda ve son derece kısıtlı nedenlerle gerçeklesmesini temin etmektir. Tahkim anlasmasının geçerliliği, mahkemelerin tahkimde sıkça rol oynadığı alanlardan biridir. Fransız hukukunda, bu konuda ilk sözün hakemlere bırakıldığı; mahkemelerin ise ancak nihai karar sonrası dönemde etkin oldukları bilinmektedir. Hakem heyetinin seçimi, delillerin tespiti, geçici hukuki koruma tedbirlerine hükmedilmesi, tahkim yargılaması öncesi, mahkemelerin yardımını gerektiren konulardır. Geçici hukuki koruma tedbirlerine hükmedilmesi veya hükmedilenlerin icrasına karar verilmesi ile tahkimdeki sürenin uzatılması, tahkim yargılaması sırasında, mahkemelerin yardımını gerektiren meselelerdir. By entering into an arbitration agreement parties express their intention that all disputes between them be referred to and settled by arbitration. This choice at the same time manifests a decision against the competence of the state courts. By accepting the party autonomy the level of the court intervention has significantly diminished over the past years. The general trend is towards limiting court intervention to the cases where it is either necessary to support the arbitration process or required by public policy considerations. By finding the arbitration agreement between the parties valid, no court proceedings on the merits of the disputes can be brougt before the courts and all disputes covered by that agreement are referred to arbitration. There are, however, some situations where court intervention and assistance is needed. Courts may be asked to assist with the appointment of arbitrators, and the collective of evidence. They may also be asked to order protective measures where the arbitrators lack coercive power. Courts may also intervene to guarantee that the minimum requirements of precedural fairness by removing an arbitrator for his lack of impartiality. Courts have moved from strong scepticism resulting in extensive judicial intervention in the arbitration precess or the non-enforcement of arbitration agreement to a position in favor of arbitration giving priority to party autonomy and eschewing intervention. Supervisiory court intervention has the potential of disrupting the arbitration process and impeding the parties? quest for a speedy dispute resolution. It is a common feature of recent arbitration legislation to limit the scope for court intervention after the UNCITRAL Model Law Art. 5. The effect has been that the parties and the tribunals are given wider powers especially about the jurisdiction issues. The authority of the courts has been limited in some cases that could be used at the final stage under the listed the reasons. To what extent the courts can at the pre-award stage review the existance of a valid arbitration agreement is one of the main fields that the courts play role. In French law, the arbitrator has a right of first decision and any court review is deferred to the post-award stage. Establishing the arbitral tribunal, ordering protective measures are the topics need the assistance of the courts. Ordering protective measures or helping for their execution and the extending the time-limt of the arbitral jurisdiction are the issues met during the arbitral procedure.
207755

İpotekli sermaye piyasası araçları - Adigüzel, Burak (Marmara Üniversitesi, 2006)
"Inceleme konumuz olan Ipotekli Sermaye Piyasası Araçları; Konut Finansmanı Sistemine Iliskin Çesitli Kanunlarda Degisiklik Yapılması Hakkında Kanun Tasarısı i l e hukukumuza girecek, uzun vadeli ipotege dayalı krediler veya konusu konut olan finansal kiralama sözlesmelerinden dogan alacakların menkul kıymetlestirilmeleri sonucu ortaya çıkan ipotekli sermaye piyasası araçlarıdır. Incelememizin birinci bölümünde, esas olarak ipotekli sermaye piyasası araçlarının tarihçesini ve bununla alakalı ipotekli konut finansman sistemi ile agırlıgı uzun vadeli ipotekli krediler olan kaynakların yabancı hukuklardaki geçmisten bugüne gelisimine baktık. Daha sonra ipotekli sermaye piyasası araçlarının, yine yabancı hukuklardaki yerlerine degindik. Gelisme çizgisi içinde geleneksellesen ve Avrupa ile ABD'de farklılasan ipotekli sermaye piyasası araçlarını karsılastırmalı olarak inceledik ve ABD ve Avrupa ülkelerinde ipotekli kredi verme sistemlerine de genel bir bakıs yapmayı uygun gördük. Bu bölümde, inceledigimiz diger bir konu ise, tezimizin konusunu olusturan ipotekli sermaye piyasası araçları hakkında, kanunlastırmayla mevzuatımıza girecek olan tasarıya ait hükümlerdir. Bu hükümler içinde sadece ipotekli sermaye piyasası araçlarına iliskin SerPK'da yapılan degisikliklere degil, konut finansman sistemine iliskin degisikliklerin hepsine, bütün sistemi anlamak açısından deginilmistir. Ikinci bölümde, ipotekli sermaye piyasası aracı kavramı, tasarıdaki ipotekli sermaye piyasası araçları ve hukuki nitelik yönünden de ipotekli kredilerin menkul kıymetlestirilmesi sonucu ihraç edilecek bu sermaye piyasası araçlarının, ticaret hukukuna göre kıymetli evrak niteligi ve sermaye piyasası hukuku açısından da menkul kıymet nitelikleri incelenmistir. Burada, ABD ile Avrupa'da ikinci ipotek piyasalarındaki sermaye piyasası araçlarının hukuki niteliklerine de göz atılmıstır. Bu bölümde, SerPK'ya yeni tasarı ile getirilen hükümler ile ortaya konulan, her türlü alacak seklindeki varlık menkul kıymetlestirmesine yönelik, bilhassa konumuz bakımından önemli olan konut hariç olmak üzere diger gayrımenkullere yönelik alacakların menkul kıymetlestirilmesinde kullanılacak varlık teminatlı menkul kıymetler ve varlık finansman fonlarından da söz edilmistir. Üçüncü bölümde ise, ipotekli sermaye piyasası araçlarının, ihraç edilebilmesi için hem Sermeye Piyasası Kurulu dısında hem de nezdinde izlenecek yöntem ipotekli sermaye piyasası araçlarına göre ayrıntılı olarak incelenmistir. Son bölümde ise, ipotekli sermaye piyasası araçlarına iliskin, bu araçlar ihraç edildikten sonra hukuki anlamda her bir menkul kıymet tipi için ihraçcılar ve yatırımcıların hak borçları ile bu borçların sona ererek ipotekli sermaye piyasası araçlarının ortadan kalkması incelenmeye çalısılmıstır. This study that name Mortgage Securities includes mortgage securitisation with mortgage credit and leasing for homes. When Konut Finansmanı Sistemine Iliskin Çesitli Kanunlarda Degisiklik Yapılması Hakkında Kanun Tasarısı will effect soon mortgage securities will run regularly in capital market. The study consists four main chapters : First chapter explanations history of mortgage secuirites with mortgage credits evolvement in compare laws. Next to mortgage securities reveal in foreign laws nowadays. Diversifield mortgage secutities which MBS (Mortgage Backed Securites) in USA and Covered Bonds in Europe are revisaled as compare. Additional subject also is which provisions with mortgage securities from law draft in this chapter. This explanation provisions not only concerned mortgage securites, but also they are relevant all home mortgage financings system. This provisions is intented IIK, FKK, THKHK and some tax laws. Mortgage securities conception, mortgage securities legal characteristics which as capital market instrument and negotiable instrument observations in the second chapter. And USA Mortgage Backed Securities, Europe Covered Bonds legal respects maintained in this chapter. As a last subject asset backed securites and asset bonds in law draft whom pursuanced for other property (etc. commercial or another property have settling licence) as a mortgage purses elucidated in this chapter. Third chapter consists mortgage secuiritisation process both inside and outside Capital Market Board. This process explanations both MBS issued in Mortgage Finance Fonds and Covered Bond. Rights and obligation on issued mortgage securities are showed i n fourth chapter. As a last outcame this rights and obligation in his mortgage securities and how are annuled this mortgage securities."

İnternet üzerinden kurulan sözleşmeler - İnal, Emrehan (İstanbul Üniversitesi, 2004)
Bu çalışmada, internet teknolojisindeki gelişmelerin özel hukuk alanındaki en önemli yansımalarından biri olan, sözleşmelerin internet üzerinden kurulması konusu işlenmiştir. Çalışmanın birinci bölümünde internet ve elektronik ticaret kavramları ve uygulamaları kısaca açıklanmıştır. İkinci bölümde ise, gerek internet üzerinden sözleşmelerin kurulması konusundaki bazı sorunlara ışık tutması, gerekse Türk hukukuyla karşılaştırma yapmaya imkan tanıyarak Türk hukukundaki eksikliklerin görülmesini sağlaması açısından, elektronik ticaret hukukuna ilişkin belli başlı düzenlemeler incelenmiştir. Bu çalışma, sözleşmelerin kurulması konusundaki tüm hukuki sorunlara cevap arama iddiasında değildir. Ancak bu sorunlara bütünüyle kayıtsız da kalınmamıştır. İşte üçüncü bölümde esas itibariyle yazar, sözleşmelerin kurulmasına ilişkin genel prensiplerin ışığında, sözleşmelerin internet aracılığı ile kurulmasının yarattığı sorunları incelemeye gayret sarfetmiştir. Son olarak, gerek uygulamadaki gerekse son zamanlarda gerçekleşen hukuki düzenlemelerdeki yeri bakımından önem arz eden, internet üzerinden kurulan sözleşmelerde tüketicinin korunması konusu ana hatlarıyla ele alınmıştır. The subject of this study is the formation of contracts via the Internet, which is one of the most significant outcomes of the development of Internet technologies in the field of private law. IllSection I seeks to define "Internet" and "electronic commerce". In section II, major electronic commerce legislations are examined, (i.e. EU directives, UNCITRAL Model Laws and the E-Sign Act of the US), in order to make it possible for a comparison with Turkish Law and to highlight some of the problems relating to the formation of contracts via the Internet. The purpose of this study is not an in-depth coverage of the formation of contracts in general. But the important legal questions and problems of general contract law are not entirely overlooked. With section III, the essential aim of the author has been to examine the problems which are generated by the use of Internet communication for the purpose of contract formation. Finally, because of its importance both in practice and legislation, consumer protection issues in distance contracts are also surveyed. IV
Keywords: Consumer protection; Contracts; Electronic commerce; Elektronik ticaret; Internet; Sözleşmeler; Ticaret; Trade; Tüketicinin korunması; Özel hukuk; İnternet

Elektronik sözleşmeler - Sağlam Atabarut, İpek (Marmara Üniversitesi, 2003)
Keywords: Avrupa Birliği; Commercial law; Contracts; Electronic signature; Electronics; Elektronik; Elektronik imza; European Union; International conventions; Internet; Signature; Sözleşmeler; Ticaret hukuku; Uluslararası sözleşmeler; İmza

Genel işlem şartları ve içerik sınırları - Oğuz, Cemal (Ankara Üniversitesi, 1993)
AGB sind vor ihrer Einbeziehung in Einzelvertrâge rechtlich irrelevant. Unser geltendes Recht kennt keine Befugnis zur überindividuellen Gestaltung von Vertragsbedingungen. Man kann die AGB weder Quasi Normen noch iiberindividuelle Besttimungen gualifiziert werden. Im Verhaltnis zu den Individuellvereinbarungen sind sie zweitrangig. Wir haben auch festgestellt dass, die Geltung der AGB für einzelne Vertragsverhâltnisse auf rechtsgeschâftlicher Grundlage beruht und durch das Prinzip der Vertrags freiheit gedeckt wird. Indessen setzt Einbeziehung von AGB in Individialvertrâge eine Einbeziehungsvereinbarung vor. İm Vierten Teil der These haben wir dargestellt dass, die Einbezilhungsvereinbarung inhaltnich auf die Ausgestaltung der Individualabreden beschrânkt. Nur diejenigen Klauseln werden von der Einbeziehungsvereinbarung erfasst, die im Einklang mit den Individuelabreden Stehen. In AGB euthaltene Schriftformklauseln können den mündlichen getroffen Vereinbarung der Parteien die Rechtswirksamkeit nicht nehmen. Werden einzelne Klauseln nicht zum Inhalt von den Parteien abgeschlossenen Individualvertrages, ergibt sich dies aus einer Auslegung der Einbeziehungsvereibarung. Das Problem der Teilnichtigkeit stellt sich nicht. - Lâsst eine Klauseln bei Vernünftiğer Auslegung mindestens zwei Deutungen zu, liegt eine Objektive Unklarheit der AGB vor. Der artige Unklarheiten gehen zu Lasten desjenigen, der die Einführung der AGB in125 den vertrag veranlasst hat. Man muss die dem Kunden günstigere Auslegung wahlen. - İm letzten Abschnitt, endscheidet wir uns dazu, dass Der Problembereich der Inhaltsgrenzen gehört zum Problem der Vertragsauslegung Eine Kompetz der Gerichte zur Korrektur der unter Einbeziehung von AGB geschlossenen Vertrâge ist abzulehnen. Eine Auslegungsgrundsatz, die Auslegung von AGB habe ohne Berücksichtigung derUmstânde ist abzulehnen.
Keywords: Commercial law; Consumer protection; Contracts; Genel işlem şartları; General transaction conditions; Sözleşmeler; Ticaret hukuku; Tüketicinin korunması